Partnering with communities to co-design humanitarian health strategies: A SeeChange CommunityFirst Framework for implementation in MSF projects - Chapela Trillo, Violeta; Farber, Jessica (MSF, 2034)
The CommunityFirst Framework is intended to be implemented by field teams at MSF. The theoretical aspects and evidence presented on the importance of community engagement are intended for all MSF staff seeking to learn more about why and how to shift the way we work with communities as humanitarians. We believe this guideline, and other tools like it (including OCA’s Person-Centred Approach Guidance07, and MSF Vienna Evaluation Unit’s Guidance for Involving Communities08), to be an important contribution to the growing movement of communities and humanitarian actors who are pushing for changes in the humanitarian system that translate to dignity, health, justice, equity and self-determination for communities around the world. Specifically, the CommunityFirst Framework is intended to guide MSF teams to co-design health strategies with communities, throughout all stages of the project cycle, for exploratory missions, projects that are just opening, projects that have been running for some time, or those that are closing. At the time of publication, the CommunityFirst Framework has been tested in pilot projects in: (1) Madre de Dios, Peru (MSF OCP, August 2022), (2) Tonkolili, Sierra Leone (MSF OCA, November 2022) and (3) Anzoátegui, Venezuela (MSF OCB, February 2023) The experiences from these pilots (feedback from teams, implementation results, adaptations to each context, etc.) have informed the adaptation of the Framework. CommunityFirst builds on existing community engagement work inside MSF and contributes a practical framework for co-designing health initiatives with communities. To avoid duplicating efforts and resources around community engagement inside MSF, the appendices in this guideline largely refer to already existing MSF resources.09 This guideline is meant to be a living document that can evolve and be adapted given the experience of MSF staff and community members and diverse community contexts. This guide can be used by anyone in MSF who is interested in partnering with communities to improve the responsiveness and impact of their humanitarian programs. This is the first iteration of the document. Subsequent iterations will be published based on additional testing during future phases of the CommunityFirst TIC project.

A Manifesto for the Platform Organization - Cicero, Simone; Quintarelli, Emanuele; Ruggeri, Luca (Boundaryless, 2024)
Discover the future of organizational structure with the Platform Organization Manifesto. Our guiding principles provide a blueprint for dynamic, adaptable businesses designed to thrive in a constantly changing marketplace. Harness the power of entrepreneurial spirit, cooperation, innovation, and key design principles to empower corporate evolution.

The Radical How - Greenway, Andrew; Loosemore, Tom (Nesta and Public Digital, 2024)
Any mission-focused government should be well equipped to define, from day one, what outcomes it wants to bring about. But radically changing what the government does is only part of the challenge. We also need to change how government does things. The usual methods, we argue in this paper, are too prone to failure and delay. There’s a different approach to public service organisation, one based on multidisciplinary teams, starting with citizen needs, and scaling iteratively by testing assumptions. We’ve been arguing in favour of it for years now, and the more it gets used, the more we see success and timely delivery. We think taking a new approach makes it possible to shift government from an organisation of programmes and projects, to one of missions and services. It offers even constrained administrations an opportunity to improve their chances of delivering outcomes, reducing risk, saving money, and rebuilding public trust. The Radical How in a nutshell The struggles and shortcomings of delivering in government are well rehearsed. Many of the root causes that make it tough have been restated several times over several decades. But what to do? We believe the government can and should change how it delivers, by: organising around multidisciplinary teams embracing incremental, feedback-driven iteration focusing more on outcomes. The Radical How is a change of mindset as much as a change in organisation. It promotes methods and processes that have been shown to work, multiple times, at scale. They are the default ways of working for many of the world’s most successful companies. However, the occasions where they have been deployed are rare in government. These occasions have come about thanks to exceptional leaders, exceptional circumstances, or both. We think they’d make a big difference if they became the norm, rather than the exception. We also think that without them, mission oriented government will not become a reality. New policy ideas will remain just that, rather than translating into profound improvements to society. Central to this approach is the widespread adoption of internet-era ways of working. This paper explains both those and our thinking in more detail, with reference to real examples.

Doing weeknotes - What weeknotes are, how weeknotes work, and how to start writing weeknotes of your own - Turnbull, Giles (Use the Human Voice, 2024)
Doing weeknotes brings together various things I’ve written about weeknotes in different places. This text expands on things I wrote in The agile comms handbook, as well as various blog posts. Quite a lot of it is brand new. - Weeknotes for beginners - Why write weeknotes - The weeknotes rules - Weeknotes within the corporate environment - What weeknotes can bring about - Examples of good weeknotes - How to write weeknotes - Weeknotes tips and tricks - Further reading

Social Accountability 3.0: Engaging Citizens to Increase Systemic Responsiveness. Background Paper - Guerzovich, Florencia; Aston, Tom (Grupo Politeia, ESAG, UDESC and act4delivery, 2024)
Social accountability has become increasingly important to development programming since the 2004 World Development Report spearheaded its first generation of programming. In 2016, Thomas Carothers synthesized global experts’ perspectives on what became known as the second generation. With an evolving global context, new research and evaluations and tacit knowledge on how those assumptions played out in practice, the time is ripe for asking what the evidence since 2004 can tell us about what the social accountability’s next generation might look like? This meta-analysis takes stock of that knowledge through a systems lens and presents a possible “social accountability 3.0.” It draws on a database of 157 cases of initiatives implemented by different civil society organizations around the world and the lived experience of practitioners. Scholarly debates present practitioners’ options in binary terms, contrasting 1.0 minimalist and 2.0 maximalist options. The review finds that this binary is inaccurate and misleading; it masks practitioners’ diverse interpretations of 2.0 and range of feasibility considerations. Instead, work in the last decade looks more like a mosaic. By opening the analysis to the broader range of evidence, and reflecting more critically on scholars’ assumptions, a more adaptable middle path for social accountability 3.0 emerges. Its key outcomes include contributing to systemic responsiveness and an operational mechanism to rework the social contract.

Practicing what we preach — our experience rethinking M&E in complex settings - Bina, Andrea; Vester, Søren (UNDP Strategic Innovation, 2023)
The UNDP has been exploring new approaches to M&E to better understand and address complex systems challenges. Traditional linear project-based planning and evaluation methods are insufficient for dealing with the unpredictable nature of such systems. The UNDP’s new Strategic Plan calls for a shift in M&E practices to align with the complexity of today’s global challenges. Key points from the blog post include: Learning and Adapting: There’s a need for continuous learning and adaptation in M&E practices to effectively address complex problems like transitioning to a circular economy. Longer Time Horizons: Substantive change takes time, and it’s often unclear what the results will look like, making it difficult to track progress. Aggregate Impact: Evaluating interconnected interventions as a portfolio is crucial because they cannot be assessed in isolation. Contribution vs. Attribution: Focusing on the contribution to broader change processes is more important than attributing specific outcomes to individual actions. The UNDP has initiated the M&E Sandbox to experiment with and learn from innovative M&E practices. This collaborative space has attracted participants from over 180 organizations, highlighting a shared interest in evolving M&E to better understand change in contexts of uncertainty. A partnership with the Bill and Melinda Gates Foundation has also been formed to focus on M&E in food systems. The blog post emphasizes the importance of embracing uncertainty, experimenting, and collaborating to contribute to positive change in complex settings1.

Insights for Influence: Understanding Impact Pathways in Crisis Response - Clark, Louise; Carpenter, Jo; Taylor, Joe (Institute of Development Studies, 2023)
The Covid-19 Responses for Equity (CORE) programme was a three-year initiative funded by the Canadian International Development Research Centre (IDRC) that brought together 20 projects from across the global South to understand the socioeconomic impacts of the Covid-19 pandemic, improve existing responses, and generate better policy options for recovery. The research covered 42 countries across Africa, Asia, Latin America, and the Middle East to understand the ways in which the pandemic affected the most vulnerable people and regions, and deepened existing vulnerabilities. Research projects covered a broad range of themes, including macroeconomic policies for support and recovery; supporting essential economic activity and protecting informal businesses, small producers, and women workers; and promoting democratic governance to strengthen accountability, social inclusion, and civil engagement. The Institute of Development Studies (IDS) provided knowledge translation (KT) support to CORE research partners to maximise the learning generated across the research portfolio and deepen engagement with governments, civil society, and the scientific community. As part of this support, the IDS KT team worked with CORE project teams to reconstruct and reflect on their impact pathways to facilitate South-South knowledge exchange on effective strategies for research impact, and share learning on how the CORE cohort has influenced policy and delivered change. This report presents an overview of these impact pathways and the lessons learnt from a selection of the projects chosen to represent the diversity of approaches to engage policymakers, civil society, and the media to generate and share evidence of the effect of the pandemic on diverse vulnerable groups.
Accepted: 2023-11-10T12:56:06Z Publisher: Institute of Development Studies

How AI Fits into Lean Six Sigma - Holweg, Matthias; Davenport, Thomas H.; Snyder, Ken (Harvard Business Review, 2023)
AI already is being used in some areas of process improvement, and the usage of this technology — including generative AI — promises to grow. That’s because it can perform tasks faster and much less expensively than humans alone. But it will never fully replace people — and that poses management challenges.
Section: Operations and supply chain management

Challenge-led Innovation Workbook. Organising for Systems Innovation at Scale - Burkett, Ingrid (Griffith Centre for Systems Innovation, 2023)
Organising for Systems Innovation at Scale Our team at Griffith Centre for Systems Innovation have been experimenting with and evolving a Challenge-led Innovation Approach (based on Mission-oriented approaches developed by Mariana Mazzucato at UCL IIPP and others internationally). We are using this approach to guide the way we work internally and engage with our systems innovation partners. We’ve facilitated intensive Re:Treats, worked with government bodies, businesses and civic organisations, and engaged deeply with others exploring this work. We have a bias for developing and testing HOW such approaches could be applied to respond to both local and global challenges rather than getting too caught up in the what and why of such approaches. We decided to openly share our learnings and thinking to date in this workbook, to spark conversations and innovation in both practice and thinking amongst those exploring how we work, and to learn together to address complex systems and challenges. We see this booklet as a first step in a longer learning journey. In it we share an overview of: the principles and processes that sparked our evolution to a Challenge-led Innovation framework (from Mission-oriented). examples of our learnings from other system innovators who are experimenting. an adaptable process to help guide the learning journey. learning tools and canvases to catalyse thinking, practice, and further adaptations. Part One sets out some foundations we’ve identified as important to Challenge-led Innovation. If you want to jump straight into the mapping process, we suggest you skip to Part Two. The final section, Part Three, focuses on what we have learnt about the conditions needed and how to get started on a Challenge-led initiative.

Hidden Potential: The Science of Achieving Greater Things - Grant, Adam (WH Allen, 2023)
#1 New York Times bestseller "This brilliant book will shatter your assumptions about what it takes to improve and succeed. I wish I could go back in time and gift it to my younger self. It would've helped me find a more joyful path to progress."-Serena Williams, 23-time Grand Slam singles tennis championThe #1 New York Times bestselling author of Think Again illuminates how we can elevate ourselves and others to unexpected heights.We live in a world that’s obsessed with talent. We celebrate gifted students in school, natural athletes in sports, and child prodigies in music. But admiring people who start out with innate advantages leads us to overlook the distances we ourselves can travel. We can all improve at improving. And when opportunity doesn’t knock, there are ways to build a door.Hidden Potential offers a new framework for raising aspirations and exceeding expectations. Adam Grant weaves together groundbreaking evidence, surprising insights, and vivid storytelling that takes us from the classroom to the boardroom, the playground to the Olympics, and underground to outer space. He shows that progress depends less on how hard you work than how well you learn. Growth is not about the genius you possess – it’s about the character you develop. Grant explores how to build the character skills and motivational structures to realize our own potential, and how to design systems that create opportunities for those who have been underrated and overlooked.This book reveals how anyone can rise to achieve greater things. The true measure of your potential is not the height of the peak you’ve reached, but how far you’ve climbed to get there.

Anatomy of Social Accountability 3.0: A working framework for moving forward - Guerzovich, Florencia; Aston, Tom (Florianopolis, SC, Brazil: Grupo Politeia, ESAG, University of the State of Santa Catarina and act4delivery, 2023)
This note presents the key components of a potential next generation of social accountability programming. The key aspects outlined emerge from a review of over 150 cases as well as tacit knowledge from dozens of practitioners (Guerzovich and Aston, 2023).The main thread of social accountability 3.0 and what distinguishes it from previous generations is a focus on its contribution towards more responsive systems and accountable social contracts. In particular, social accountability should be considered as an operational means to rework social contracts.Over the last two decades, the field has been defined by a supposed dichotomy between minimalist (i.e., “widget” based) approach or a maximalist (“go big or go home”) approaches. Yet, most practice sits somewhere between these extremes. The paper presents various options derived from practice; practitioners should choose whichever best fits their own particular circumstances.Those hoping to improve and expand their practice with a systems-lens may benefit from considering how they approach the key elements of social accountability 3.0.
Keywords: accountability; development; responsiveness; social accountability; social contract; systems

How adaptive M&E from the peace sector can help demonstrate the value of aid - Kratzer, Sebastian (2023)
Over the last decade, the peace sector has been developing and adapting Monitoring and Evaluation (M&E) systems and tools to fit their contexts and ways of working. This evolution may hold some insights for the aid community in how to go beyond more traditional, backwards-looking M&E to navigate today’s volatile, interest-based world of politics and aid.

Foreign Aid and Its Unintended Consequences - Koch, Dirk-Jan (Routledge, 2023)
Foreign aid and international development frequently bring with it a range of unintended consequences, both negative and positive. This book delves into these consequences, providing a fresh and comprehensive guide to understanding and addressing them. The book starts by laying out a theoretical framework based on complexity thinking, before going on to explore the ten most prevalent kinds of unintended effects of foreign aid: backlash effects, conflict effects, migration and resettlement effects, price effects, marginalization effects, behavioural effects, negative spillover effects, governance effects, environmental effects, and ripple effects. Each chapter revolves around a set of concrete case studies, analysing the mechanisms underpinning the unintended effects and proposing ways in which policymakers, practitioners, and evaluators can tackle negative side effects and maximize positive side effects. The book also includes personal testimonies, a succinct overview of unintended effects, and suggestions for further reading. Providing a clear overview of what side effects to anticipate when planning, executing, and evaluating aid, this book will be an important resource for students, development practitioners, and policymakers alike.

Is the problem driven iterative adaptation approach (PDIA) a panacea for public financial management reform? Evidence from six African countries - Lawson, Andrew; Harris, Jamelia (World Development Perspectives, 2023)
This article assesses the application of the problem driven iterative adaptation (PDIA) approach to public financial management reform in six African countries. It draws on primary data collected using a mix of interviews, overt participation observations and a short survey. PDIA responds to shortcomings in orthodox approaches to reform and technical assistance in developing countries. It stresses local solutions to local problems, achieved through experimentation and adaptation. The principles of PDIA are appealing, but its empirical assessment is in its infancy. This study aims to fill part of this gap. Findings show that PDIA delivers results in the short-term, particularly in cases where there is an influential authorising agent and dedicated team. Progress was less forthcoming for reforms that required high level political buy-in from senior officials. The approach does exceptionally well to develop staff capability, transferable skills, and local empowerment to solve local problems, thus potentially benefitting future reforms.

Fractal approaches to scaling transformations to sustainability - O’Brien, Karen; Carmona, Rosario; Gram-Hanssen, Irmelin; Hochachka, Gail; Sygna, Linda; Rosenberg, Milda (Ambio, 2023)
Responses to sustainability challenges are not delivering results at the scale and speed called for by science, international agreements, and concerned citizens. Yet there is a tendency to underestimate the large-scale impacts of small-scale, local, and contextualized actions, and particularly the role of individuals in scaling transformations. Here, we explore a fractal approach to scaling sustainability transformations based on “universal values.” Universal values are proposed as intrinsic characteristics that connect humans and nature in a coherent, acausal way. Drawing on the Three Spheres of Transformation framework, we consider how enacting universal values can generate fractal-like patterns of sustainability that repeat recursively across scales. Fractal approaches shift the focus from scaling through “things” (e.g., technologies, behaviors, projects) to scaling through a quality of agency based on values that apply to all. We discuss practical steps involved in fractal approaches to scaling transformations to sustainability, provide examples, and conclude with questions for future research.
Keywords: Agency; Fractals; Relational paradigms; Scaling; Three Spheres of Transformation; Universal values

Gestión de la complejidad para el impacto sistémico: respuestas a entornos VUCA y BANI - Peña-López, Ismael (SociedadRed, 2023)
Research on the Information Society, the Digital Divide and Information and Communication Technologies for development

From mouthset to mindset shifts in co-creating systems change - Blomkamp, Emma; Snow, Thea; Burkett, Ingrid (Griffith Centre for Systems Innovation, 2023)

Lasting Roots: Naatal Mbay and the Integrated Finance Model in Senegal - Fowler, Ben; Courbois, Laura (USAID, 2023)
This report addresses the well-recognized evidence gap1 on the longer-term impacts created by marketdriven programming; specifically, programming influenced by market systems development (MSD) principles. It does so by presenting the findings of an ex-post study conducted three and a half years after the close of USAID’s Feed the Future Senegal Naatal Mbay Activity (hereafter Naatal Mbay) in 2019. It examines the scale and sustainability of changes resulting from Naatal Mbay’s introduction of an integrated finance model (IFM) – described in Error! Reference source not found. below – in the domestic rice sector. This study is one in a series of ex-post evaluations that are being conducted between 2023-2026 on USAID-funded MSD interventions around the world. This study focused on four questions, noted below in Figure 1. These were addressed using a mix of desk research, 122 key informant interviews with market actors and other stakeholders remotely and in Senegal, focus group discussions with 26 rice producers networks in Senegal, and a validation workshop with USAID/Senegal, implementing partner staff and market actors. Findings were analyzed leveraging the Disrupting System Dynamics (DSD) framework (see Figure 4 in the body of the report) as an analytical tool for understanding systems change.

Agile on steroids through the RenDanHeYi - Quintarelli, Emanuele (Boundaryless, 2023)
This article offers initial insights into the overlap, positioning, shared values, and convergences between RenDanHeYi compared to agile practices.

Fast Forwarding to Systems Maps of Corruption: Getting to Usable Analysis More Quickly - Woodrow, Peter (CJL, 2023)
For AC practitioners, systems mapping is essential but also difficult. To lessen obstacles, Peter Woodrow proposes a scaffolded approach. An Experiment in “Fast Forwarding” Drawing upon our near-decade work on corruption, we recently decided to try an experiment: we would present “common patterns” of corruption as tentative models to adapt and add to—rather than try to teach people to do systems mapping from scratch. In this teaching experiment, each common pattern would function as a kind of “scaffolding” or framework that participants can build on to generate a cogent systems map as the basis for identifying possible points of intervention and subsequent program planning.

Practitioners Guidance to Assessing Systems Change: Co-Authors Preview - Gover, Dun; Nasution, Zulka; Okutu, David; Bolder, Meghan; Henao, Lina (USAID, 2023)
Check out this video to see what’s inside our new resource: Practitioners' Guidance to Assessing Systems Change, developed by MEL Managers for MEL Managers. (Check out the Guidance here https://bit.ly/MSPMELClinics.) Hear from the authors about which parts they love the most and how this guide challenges MEL managers to assess systems change as an ongoing aspect of implementation, generating feedback that teams need to better understand and catalyze change, for more impact.

Applying Adaptive Management in a Fragile Context – Case Study - Lonsdale, Jane; Green, Duncan; Robertson, Kelly (DT Global, 2023)
DT Global is proud to introduce our new Guidance Note: Practical Introduction to Adaptive Management There is a growing consensus around adaptive management as an effective (even necessary) approach when programs are tackling complex development problems. While there is no standard definition of adaptive management, there is general agreement that such programs need to routinely engage with and respond to program context; constantly test what works in that context; and adjust approaches, plans, and activities based on continuous learning. However, there remains a more limited body of evidence about what this looks like in practice—the enabling conditions, systems, resourcing, skills, and attitudes to effectively operationalise adaptive management. There is also limited guidance around when adaptive management is required, and to what extent—both critical and often overlooked considerations when planning for successful adaptive management. This Guidance Note draws together lessons and good practice in adaptive management from across DT Global’s diverse portfolio of donor-funded programs. It outlines our conceptual framework for adaptive management, with practical guidance on how it can be applied by our program teams. It is also designed to help our teams distinguish adaptive management from good (non adaptive) project management, consider when adaptive management is most useful on a program, and how adaptive a program (or part of a program) should be.

Applied political economy analysis for human rights programs and campaigns: A guide for practitioners (second edition) - Pact (Pact, 2023)
This updated guide provides practical guidance to practitioners in the human rights sector and beyond on how to integrate Applied Political Economy Analysis

Knowledge Retention and Transfer (KRT) - Model overview presentation - USAID (USAID, 2023)
What problem is the KRT model trying to solve? For workforces that experience continuous staff turnover, the lack of systematic knowledge transfer can often lead to: - Loss of programmatic momentum, - Duplication of efforts and frustration, and - Wasted time and resources. The Knowledge Retention and Transfer (KRT) model provides tools, processes, and practices to individuals, teams, offices, and organizations to improve knowledge handover, which in turn improves efficiency and programmatic and operational learning.

Evaluative reasoning in complexity - King, Julian (Evaluation and Value for Investment, 2023)

When Complex is as Simple as it Gets: Guide for Recasting Policy and Management in the Anthropocene - Roe, Emery (Institute for Development Studies, 2023)
Many readers recognise and understand that complex is about as simple as it gets for major policy and management. This guide is for those unwilling in the Anthropocene to shrink back into the older platitudes about ‘keep it simple’ and ‘not to worry, we’ll scale up the analysis later on’. This guide offers key concepts, methods, counternarratives, and analogies that recast major policy and management issues in ways that do not deny their complexity but help render them more tractable for action.
Accepted: 2023-06-06T09:51:20Z ISSN: 2040-0209

How to Build Movements with Cyclical Patterns in Mind - Non Profit News | Nonprofit Quarterly - Algoso, Dave; Guerzovich, Florencia; Gattoni, Soledad (Nonprofit Quarterly, 2023)
The world changes too much for anyone who is invested in social change work to imagine that this work is linear and predictable. Opportunities come and go, whether caused by a pandemic or political shifts. This much most social movement leaders and activists intuitively understand. But what can be done with this realization? How might movement groups better prepare for moments of opportunity? We want to explore how we can create the changes we want to see by responding to the changes that are outside our control.

Participation for Humanitarian Innovation - Background Paper - Smith, Amy; Thompson, Martha; Saida Benhayoune; Crespo Cardona, Omar (Elrha, 2023)
A resource designed to help organisations, teams and individuals manage innovation journeys responsibly and successfully. We have partnered with MIT D-Lab to develop a new resource to drive greater diversity and inclusion within project design and implementation. The Participation for Humanitarian Innovation (PfHI) toolkit sets out a robust approach to setting expectations for and monitoring the degree of participation within research and innovation projects for, with, and by people affected by crisis. The PfHI toolkit is composed of five tools: Opportunity Adviser: Identify and prioritise the desired benefits of participation while weighing the potential barriers. Participation Matrix: Agree on the precise degree of participation to target at a given project stage. Resource Navigator: Select tools and processes to address the needs of stakeholders, the project objectives and context. Quality Guidance: Ensure engagements are delivered to the highest standard. Assessment Matrix: Collectively evaluate the degree of participation achieved during an activity or project phase, learn and adapt. By applying these tools before, during and after a research and/or innovation project, implementors can ensure that stakeholders/end-users are included and participating at the highest possible degree. We encourage users of the PfHI toolkit to consider how else to integrate the tools into existing practices. For instance, the Evaluation Matrix could be used to supplement existing MEAL activities to: Establish baselines to measure changes in participation over time. Track the degree of participation/engagement of stakeholders. Regularly assess the degree of participation. Seek feedback from participants about the degree of their participation. Monitor the progress of activities related to stakeholder engagement. Our Participation for Humanitarian Innovation toolkit represents our ongoing commitment to responsible research and innovation across our portfolio of grants and for the humanitarian sector more broadly. We hope you will consider downloading and using the toolkit on your next project.

Participation for Humanitarian Innovation - Toolkit - Smith, Amy; Thompson, Martha; Saida Benhayoune; Crespo Cardona, Omar (Elrha, 2023)
A resource designed to help organisations, teams and individuals manage innovation journeys responsibly and successfully. We have partnered with MIT D-Lab to develop a new resource to drive greater diversity and inclusion within project design and implementation. The Participation for Humanitarian Innovation (PfHI) toolkit sets out a robust approach to setting expectations for and monitoring the degree of participation within research and innovation projects for, with, and by people affected by crisis. The PfHI toolkit is composed of five tools: Opportunity Adviser: Identify and prioritise the desired benefits of participation while weighing the potential barriers. Participation Matrix: Agree on the precise degree of participation to target at a given project stage. Resource Navigator: Select tools and processes to address the needs of stakeholders, the project objectives and context. Quality Guidance: Ensure engagements are delivered to the highest standard. Assessment Matrix: Collectively evaluate the degree of participation achieved during an activity or project phase, learn and adapt. By applying these tools before, during and after a research and/or innovation project, implementors can ensure that stakeholders/end-users are included and participating at the highest possible degree. We encourage users of the PfHI toolkit to consider how else to integrate the tools into existing practices. For instance, the Evaluation Matrix could be used to supplement existing MEAL activities to: Establish baselines to measure changes in participation over time. Track the degree of participation/engagement of stakeholders. Regularly assess the degree of participation. Seek feedback from participants about the degree of their participation. Monitor the progress of activities related to stakeholder engagement. Our Participation for Humanitarian Innovation toolkit represents our ongoing commitment to responsible research and innovation across our portfolio of grants and for the humanitarian sector more broadly. We hope you will consider downloading and using the toolkit on your next project.

The adoption of innovation in international development organisations: lessons for development co-operation - Kumpf, Benjamin; Jhunjhunwala, Parnika (OECD Publishing, 2023)
Addressing 21st century development challenges requires investments in innovation, including the use of new approaches and technologies. Currently, many development organisations prioritise investments in isolated innovation pilots that leverage a specific approach or technology rather than pursuing a strategic approach to expand the organisation’s toolbox with innovations that have proven their comparative advantage over what is currently used. This Working Paper addresses this challenge of adopting innovations. How can development organisations institutionalise a new way of working, bringing what was once novel to the core of how business is done? Analysing successful adoption efforts across five DAC agencies, the paper lays out a proposed process for the adoption of innovations. The paper features five case-studies and concludes with a set of lessons and recommendations for policy makers on innovation management generally, and adoption of innovation in particular.

Participatory action research - Cornish, Flora; Breton, Nancy; Moreno-Tabarez, Ulises; Delgado, Jenna; Rua, Mohi; de-Graft Aikins, Ama; Hodgetts, Darrin (Nature Reviews Methods Primers, 2023)
Participatory action research (PAR) is an approach to research that prioritizes the value of experiential knowledge for tackling problems caused by unequal and harmful social systems, and for envisioning and implementing alternatives. PAR involves the participation and leadership of those people experiencing issues, who take action to produce emancipatory social change, through conducting systematic research to generate new knowledge. This Primer sets out key considerations for the design of a PAR project. The core of the Primer introduces six building blocks for PAR project design: building relationships; establishing working practices; establishing a common understanding of the issue; observing, gathering and generating materials; collaborative analysis; and planning and taking action. We discuss key challenges faced by PAR projects, namely, mismatches with institutional research infrastructure; risks of co-option; power inequalities; and the decentralizing of control. To counter such challenges, PAR researchers may build PAR-friendly networks of people and infrastructures; cultivate a critical community to hold them to account; use critical reflexivity; redistribute powers; and learn to trust the process. PAR’s societal contribution and methodological development, we argue, can best be advanced by engaging with contemporary social movements that demand the redressingl of inequities and the recognition of situated expertise.
Number: 1 Publisher: Nature Publishing Group

A new pathway: how can funders support meaningful monitoring, evaluation, and learning practice in the field? - Blog post on Better Evaluation - Acevedo, Andrea; Colnar, Megan (2023)
How can donors and grantees work together to create effective monitoring, evaluation, and learning (MEL) practices that drive field-wide transformation?

How are Research for Development Programmes Implementing and Evaluating Equitable Partnerships to Address Power Asymmetries? - Snijder, Mieke; Steege, Rosie; Callander, Michelle; Wahome, Michel; Rahman, M. Feisal; Apgar, Marina; Theobald, Sally; Bracken, Louise J.; Dean, Laura; Mansaray, Bintu; Saligram, Prasanna; Garimella, Surekha; et al. (The European Journal of Development Research, 2023)
The complexity of issues addressed by research for development (R4D) requires collaborations between partners from a range of disciplines and cultural contexts. Power asymmetries within such partnerships may obstruct the fair distribution of resources, responsibilities and benefits across all partners. This paper presents a cross-case analysis of five R4D partnership evaluations, their methods and how they unearthed and addressed power asymmetries. It contributes to the field of R4D partnership evaluations by detailing approaches and methods employed to evaluate these partnerships. Theory-based evaluations deepened understandings of how equitable partnerships contribute to R4D generating impact and centring the relational side of R4D. Participatory approaches that involved all partners in developing and evaluating partnership principles ensured contextually appropriate definitions and a focus on what partners value.

Berkana Two Loop Model: A quick introduction to an accessible model for systems change - Proud, Emma (LinkedIn - Emma Proud, 2023)
A model I've been using a lot recently, to bring systems thinking to life, is the Berkana Two Loop model. It doesn't describe complexity or systems thinking. But it does describe systems change in a way that's simple and oriented to action.

The Secret Sauce of Development Professionals: Tools for Assessing TOR Potential to Source Scalable Learning Interventions - Barton, Adam (Research on Improving Systems of Education (RISE), 2023)
Terms of reference (TORs) play an outsized role in driving scalable educational programming. These procurement documents shape, constrain, and signal programme priorities and possibilities. Successful funders and implementers across the globe hold rich processual knowledge about this documentation, which they use to draft and assess TORs. This project explores such best-practice knowledge around TOR review, seeking to support the design and implementation of educational programmes that can improve learning at scale in developing contexts.

Reflections on Ten Years of USAID’s Experience with Political Economy Analysis and Thinking and Working Politically - Brinkerhoff, Derick; Cassidy, Marc (TWP CoP, 2023)
The global Thinking and Working Politically (TWP) Community of Practice (CoP), the Washington DC TWP CoP, and USAID organised a webinar on 5 December 2022 to take stock of how USAID and its partners have used PEA to inform programme strategy, design and implementation, and support TWP. This paper synthesises the key points arising from the webinar, including observations on the impacts, opportunities, challenges, and prospects for PEA/TWP to become more deeply adopted and sustained as a development methodology and approach across sectors. It starts by defining key concepts. It then highlights insights from the discussions of the impact of the application of PEA and TWP principles across sectors. The paper concludes by looking at progress achieved to date, as well as constraints and opportunities to increase the uptake of both thinking and working politically in USAID-sponsored programming.

Adaptive Evaluation: A Complexity-based approach to Systematic Learning for Innovation and Scaling in Development - Gokhale, Siddhant; Walton, Michael (Center for International Development, Harvard University, 2023)
Nearly all challenges in international development tend to be complex because they depend on constantly evolving human behaviour, systems, and contexts, involving multiple actors, entities, and processes. As a result, both the discovery and scaling of innovations to address challenges in development often involve changes in system behaviour or even system-level transformation. This is rarely a linear process over time and can result in unexpected outcomes. Existing evaluation techniques commonly used in international development, including Randomized Control Trials (RCT) and quasi-experimental methods, are good at assessing specific effects of interventions but are not designed for the change processes inherent to innovation and scaling within a system. There is a need to reconstruct how we use existing measurement tools, techniques, and methodologies so that they capture the complexity of the environment in which an intervention or change occurs. We introduce Adaptive Evaluation, designed to learn at various levels of complexity while supporting the transformation needed to foster sustainable change. An Adaptive Evaluation uses three main approaches to work with complex questions—systems diagnosis, theorybased assessment of change processes, and iterative designs. An Adaptive Evaluation typically builds hypotheses from field-based interactions, emphasizes learning over testing, advocates open-mindedness with techniques, and appreciates the value of dialogue and participation in navigating complex processes. It can use RCT or similar techniques to analyse specific processes within a system or a development cycle, but these are embedded in a broader approach to assessment and interpretation. It is designed to be flexible and adjust to shifting contexts. Finally, an Adaptive Evaluation can be applied at any stage in a complex intervention's lifecycle, from the interpretation of the system and change processes to rapid experimentation, prototyping, and testing of select interventions, and then adaptation to different settings for impact at scale. This paper provides the theoretical basis for an Adaptive Evaluation—the main approaches, core ideology, process, and applications.

The Big Con: How the Consulting Industry Weakens our Businesses, Infantilizes our Governments and Warps our Economies - Mazzucato, Mariana; Collington, Rosie (Allen Lane, 2023)
There is an entrenched relationship between the consulting industry and the way business and government are managed today which must change.Mariana Mazzucato and Rosie Collington show that our economies' reliance on companies such as McKinsey, Boston Consulting Group, Bain & Company, PwC, Deloitte, KPMG and EY stunts innovation, obfuscates corporate and political accountability and impedes our collective mission of halting climate breakdown.The 'Big Con' describes the confidence trick the consulting industry performs in contracts with hollowed-out and risk-averse governments and shareholder value-maximizing firms. It grew from the 1980s and 1990s in the wake of reforms by both the neoliberal right and Third Way progressives, and it thrives on the ills of modern capitalism, from financialization and privatization to the climate crisis. It is possible because of the unique power that big consultancies wield through extensive contracts and networks - as advisors, legitimators and outsourcers - and the illusion that they are objective sources of expertise and capacity. To make matters worse, our best and brightest graduates are often redirected away from public service into consulting. In all these ways, the Big Con weakens our businesses, infantilizes our governments and warps our economies.Mazzucato and Collington expertly debunk the myth that consultancies always add value to the economy. With a wealth of original research, they argue brilliantly for investment and collective intelligence within all organizations and communities, and for a new system in which public and private sectors work innovatively for the common good. We must recalibrate the role of consultants and rebuild economies and governments that are fit for purpose.

How Big Things Get Done: The Surprising Factors Behind Every Successful Project, from Home Renovations to Space Exploration - Flyvbjerg, Bent; Gardner, Dan (Macmillan, 2023)
World expert Bent Flyvbjerg and bestselling author Dan Gardner reveal the secrets to successfully planning and delivering ambitious projects on any scale.Nothing is more inspiring than a big vision that becomes a triumphant new reality. Think of how Apple’s iPod went from a project with a single employee to an enormously successful product launch in eleven months. But such successes are the exception. Consider how London’s Crossrail project delivered five years late and billions over budget. More modest endeavours, whether launching a small business, organizing a conference, or just finishing a work project on time, also commonly fail. Why?Understanding what distinguishes the triumphs from the failures has been the life’s work of Oxford professor Bent Flyvbjerg. In How Big Things Get Done, he identifies the errors that lead projects to fail, and the research-based principles that will make yours succeed:- Understand your odds. If you don’t know them, you won’t win.- Plan slow, act fast. Getting to the action quick feels right. But it’s wrong.- Think right to left. Start with your goal, then identify the steps to get there.- Find your Lego. Big is best built from small.- Master the unknown unknowns. Most think they can’t, so they fail. Flyvbjerg shows how you can.Full of vivid examples ranging from the building of the Sydney Opera House to the making of the latest Pixar blockbusters, How Big Things Get Done reveals how to get any ambitious project done – on time and on budget.

Don't Lead Alone: Think Like a System, Act Like a Network, Lead Like a Movement! - Justis, Cleveland; Student, Daniel (Fast Company Press, 2023)
Think. Act. Lead.It seems simple enough. But understanding your desired impact and how it fits into a larger picture, connecting your work to others and finding new collaborators, and bringing those collaborators together and moving them in a unified direction is never easy.Governments, businesses, and nonprofits all have unique approaches and ideas that many of us learn through our work. Yet, we rarely consider the skills needed to create and maintain the partnerships between them. Most of us learn those skills through trial, error, and often, failure. Worse, we typically stay in our self-reinforcing silos, sharing perspectives and frustrations with like-minded people, limiting our vision of what our work can become. By partnering with other sectors, we combine and adapt approaches to solve complex problems, and leaders in any industry can create large-scale change.Cleveland Justis and Daniel Student share a road map for effective partnerships that increase impact and profitability. Using real-life examples and practice exercises, the authors teach how to acquire and use skills to solve complex problems and propel your organization forward by combining a multitude of perspectives, split into three sections:Think Like a SystemAct Like a NetworkLead Like a MovementIt’s time to get out of our silos. Don’t lead alone.

Celebrating Adaptive Delivery: A View from the Frontline in Myanmar - Barnes, Katrina; Lonsdale, Jane (IDS, 2023)
The conversation on adaptive management has grown fast amongst development actors. These conversations often focus on designing, commissioning, and managing large-scale development programmes. Exactly how this impacts the frontline, the implementers, and day-to-day project delivery is still being debated. Yet, perspectives drawn directly from practice are often largely missing within these debates. This paper is written by two development practitioners. Through this paper, we reflect on the difference between adaptive management and adaptive delivery, and how this interacts with risk and aid accountability, particularly in contexts of fragility. Drawing on examples of Oxfam in Myanmar work and our personal insights in relation to delivering programming across humanitarian, peace-building, and development, we suggest that in complex, conflict-affected, and highly political environments adaptive delivery already happens far more regularly than is currently recognised, as a necessity to get activities delivered. However, it happens despite the system, not because of it, and is therefore often hidden and carried out ‘under the radar’ rather than celebrated as a success in difficult environments. This paper was written in 2019, before the military seized control of Myanmar in February 2021. Whilst it draws on examples from pre-2021 Myanmar to illustrate real life cases, it is a contribution to a broader global debate on adaptive management in practice, specifically in fragile contexts. This is not specifically aimed at practitioners working in Myanmar at present, who are now working in a protracted crisis. This paper makes tangible recommendations on steps that donors, international non-governmental organisations, local staff, and partners could take to promote a system of encouraging and celebrating adaptability in programme delivery in fragile contexts.
Accepted: 2023-02-02T14:48:03Z Publisher: Institute of Development Studies

Two Loops Guide - Colchester, Joss (Si Network, 2023)
The Two Loop model is a nonlinear theory of change based upon the ideas of living systems created by Margaret Wheatley & Deborah Frieze. It provides us with insight into the simultaneous growth and decline process that are underway within a system during a transition period. In this way, it provides a heuristic for us to better try and recognize and connect the past to the future during a change process. It likewise gives us the possibility to try and come to some consensus about where we might be as a group in this process of change and the best actions to take at different stages. This guide will be of relevance for anyone involved in a complex organizational change process.

Understanding Political Economy Analysis and Thinking and Working Politically - Whaites, Alan; Piron, Laure-Hélène; Menocal, Alina Rocha; Teskey, Graham (FCDO and TWP CoP, 2023)
This guide is adapted from work by the UK Foreign, Commonwealth and Development Office (FCDO) with inputs from members of the Thinking and Working Politically Community of Practice (TWP CoP). It outlines how to understand and use a set of analytical tools that are collectively known as Political Economy Analysis (PEA). The guide aims to equip practitioners to act in an informed manner, given that development objectives are invariably politically complex, and entail engaging with counterparts’ political incentives and preferences. The guide summarises different types of tools – from very light-touch to more in-depth approaches – and provides advice on how development professionals can decide what is most appropriate in a given context, with illustrations based on the experiences of teams working on these issues. This guide will help development professionals and others to make use of PEA and to apply it to their own specific needs. The first part of the guide offers a general picture of the approach. The second part provides more specific guidance for those who are tasked with deploying a PEA. Contents –> Main audience What is PEA, its role and purpose (Section 2) –> General information for all readers The main elements of PEA (Section 3) Thinking and Working Politically (Section 4) –> Core information for teams planning and using PEA How to ensure quality (Section 5) –> Essential reading for those directly responsible for a PEA Important concepts and terminology (Annex) –> General information for all readers

Innovative M&E from the Sandbox and beyond - Vester, Søren; Tran, Samuel (Medium, 2023)
In this blog we are sharing a digest of some of the many useful and innovative monitoring, evaluation and learning resources and efforts that have come through the M&E Sandbox in 2022. A lot of these resources have been shared by our community in response to the overwhelmingly positive feedback from the launch of the Sandbox (please keep them coming!). We hope you find it useful. We have grouped these efforts and resources under six broad questions: - How do we measure systems transformation? - How do we know if we are on track? - How do we rethink complexity and independence in evaluation? - Why, how and for whom do we measure? - How do we generate insights and learn? - How do we make decisions and adapt?

A Better Approach to After-Action Reviews - Fletcher, Angus; Cline, Preston B.; Hoffman, Matthew (Harvard Business Review, 2023)
In the decades since the Army created the After Action Review (AAR), businesses have embraced the practice as a way of learning from both failure and success. But all too often the practice gets reduced to nothing more than a pro forma exercise. The authors of this article describe the history and philosophy of the original AAR, debunk three myths about the practice that impede its proper use, and finally suggest three improvements that can help business leaders make the most of it.
Section: Collaboration and teams
Keywords: Collaboration and teams; Crisis management; Project management

Introducing the CLA Maturity Tool for Implementing Partners - Salib, Monalisa; Ziegler, Jessica (Social Impact, 2023)
On December 13, 2022, Social Impact hosted a webinar in our Evidence for Impact series, "Strengthen Your Team's CLA Practices: Introducing the CLA Maturity Tool for USAID Implementers." Through the session, we shared more about the origin and history of the USAID tool upon which this version is based, why and how we updated
Section: Uncategorized

Holistic Flexibility for Deploying Systems Thinking as a Cognitive Skill - Chowdhury, Rajneesh (Systemic Practice and Action Research, 2023)
Considering Systems Thinking (ST) as a cognitive skill can create greater acceptability of and openness to the discipline from practitioners and researchers outside operations research and management science. Rather than associating ST with frameworks and methodologies, ST as a cognitive skill can help popularize and democratize the discipline. This paper highlights how the conceptual lens of Holistic Flexibility can help practitioners deploy ST as a cognitive skill without the application of any traditional systems methodology. Holistic Flexibility is defined as the dynamic interplay between a state of mind that has the ability to absorb systemic complexity and a state of practice that has the ability to embrace flexibility, both in intent and in form. Through two case-studies, discussions in this paper highlight how Holistic Flexibility can serve as a conceptual lens for systems practitioners. The case-studies demonstrate the importance of a practitioner’s ability to seamlessly manage and work with multiple variables, stakeholders, and factors to deliver responsible outcomes with the aid of learning loops. The main contribution of this paper lies in the case-studies and analyses presented that provide use cases for Holistic Flexibility in ST, which will help address recent calls in the discipline for ST to be considered as a cognitive skill.

Strengthen Your Team’s CLA Practices: Introducing the CLA Maturity Tool for USAID Implementers - Social Impact , Inc (2023)
The Collaborating, Learning & Adapting (CLA) Maturity Tool has been used by USAID operating units since 2015. The tool enables staff to self-assess their current CLA practice and plan ways to improve their internal and external collaboration, organizational learning efforts, and adaptive management practices. Recently, SI built on this resource to create the CLA Maturity Tool for implementing partners (IPs) to provide a version that speaks more directly to the experience of international and local organizations. Learn more here.

MSD Competency Framework - BEAM Exchange (BEAM Exchange, 2023)
MSD Competency Framework A catalogue of the full range of knowledge, skills and aptitudes found in high-performing teams that use the market systems approach. Useful for: Practitioners - identify personal training needs and continue your professional development Trainers - diversify your courses and refine your training / capacity-building offers Managers - strengthen your recruitment and induction processes MSD competencies Competency is a mix of knowledge, skills and attitudes demonstrated through concrete behaviours. This section explores the 17 competencies used by high-performing MSD teams. Arranged in three groups they relate to how we understand the world, make decisions and interact with others. Each competency is defined and has links to useful resources that explain or illustrate the knowledge or skills that feed it. Where available, sources of teaching and learning for that competency are included. Teaching and learning modes An exploration of the most common modes of teaching and learning that support practitioners to acquire knowledge, skills and attitudes. Some modes of learning are more relevant to certain types of competency - as indicated by the box colours. Each page has a summary of the teaching mode, guidance for team leaders and trainers, and examples of how to use this mode for developing specific competencies. Assessment modes Assessing competency is important for recruitment, performance appraisal and continued professional development These pages describe distinct approaches to evaluating individuals. They include a summary of the evaluation mode, guidance for assessors, and examples tailored to specific competencies.

Si Guides on System Innovation - Colchester, Joss; Si Network (Si Network, 2023)
So you have just hear about systems thinking and systems innovation and are keen to know more, Ok sparky let's get started.We have structured all the content into four main areas that we think you ...

Designing & Facilitating Collaborative Learning Networks. A toolkit - Folsom, Amanda (Results for Development, 2023)
Collaborative Learning — an approach which brings together people who face common challenges to share knowledge and jointly problem-solve — is a powerful way to support locally-led development and achieve impact. It provides a structured process in which change agents determine priorities, set the learning agenda, work together to identify strategies to address complex challenges, and provide ongoing implementation support to one another. Collaborative Learning — unlike traditional approaches to technical assistance — centers the expertise of local change agents and captures the valuable tacit knowledge of practitioners to advance systems change. This toolkit synthesizes lessons, tips, and tools accumulated from more than a decade of experience designing and facilitating over 20 Collaborative Learning Networks. The lead author was Amanda Folsom, Senior Program Director and Collaborative Learning Practice Lead, Results for Development (R4D). The toolkit benefited from the contributions of many R4D colleagues, including Katie Bowman, Cheryl Cashin, Tanya Jones, Gina Lagomarsino, Agnes Munyua, Maria Jose Pastor, and Abeba Taddese. R4D has not done this alone. The lessons and examples are drawn from our work with many network partners from the Joint Learning Network for Universal Health Coverage (JLN), Linked Immunisation Action Network (Linked), Health Systems Strengthening Accelerator, Strategic Purchasing Africa Resource Center (SPARC), the Primary Health Care Performance Initiative (PHCPI), the Partnership for Evidence and Equity in Responsive Social Systems (PEERSS), and the School Action Learning Exchange (SALEX), to name a few. We are grateful for the thought partnership and support of our partners and funders, including the Bill & Melinda Gates Foundation, Gavi, Hewlett Foundation, Jacobs Foundation, Rockefeller Foundation, USAID, and World Bank.

The Art of Scaling Deep - Research in Summary - Fraser, Tatiana (The Systems Sanctuary, 2023)
Over the last 15 years the concept of scale has become a foundational part of the apparatus of the social and environmental change sector. A business mindset of growth has been seamlessly transferred to the social and environmental problems we are collectively trying to shift in the world. Scaling up, (influencing policy) has been considered the strategic pathway to systems change. Scaling out (spreading new models) is seen as a pathway to success. The allure of these scaling theories lies, in part, in their tangibility, and the easy way in which they can be measured. However this focus on growth has shifted our attention away from a series of messy truths. Sometimes bigger isn't better. Endless growth is not sustainable and our urgency to try to fix the problem and seek solutions may be part of the crisis we are in. One unintended consequence of this has been that another type of scale has been devalued and as a result, under-resourced. It’s a scale that values the slow steady work of deepening relationships. It recognizes the significance of context, building connections that bridge diverse communities and it prioritizes inner work and healing as integral components of the scaling process. We call this type of scale ‘Scaling Deep’ and we believe that adequately supporting it, and funding it, holds the greatest potential for long lasting systemic change. The purpose of this research has been to delve deeper into the art and craft of Scaling Deep. Ultimately, our goal is for it to become firmly ingrained within the recognized realm of social change, alongside the well-established concepts of scaling up and scaling out. We want practitioners who are Scaling Deep to be able to harness the wisdom and power of this work and to talk about it openly, with confidence and credibility. We want understanding of this approach to flourish and evolve and for it to be appropriately celebrated and supported. We want decision-makers to be informed and inspired by the principles and practices of scaling deep. For it to be embedded in theories of change as an essential component of decision-making processes within the wider change discourse. Importantly we want leaders who are Scaling Deep to have access to sufficient resources and to receive the care from the field that they need to thrive. We would like to see organisations that have the power to invest, to align their efforts with the profound impact that scaling deep aspires to cultivate in the world. Before we begin, let us be crystal clear. We are not opposed to scaling up and out as strategies for change. Innovation and scaling what is working is part of how we evolve as humanity. As social entrepreneurs ourselves, we have both done this twice over. We value it and we know it’s important. We recognize these are strategies for creating widespread impact and effecting positive change. Our intention here is not to dismiss or undermine the value of scaling up and out, but rather to encourage a broader and more holistic perspective that includes other dimensions of scale. There is a need to understand how the different scaling approaches can work together, rather than seeing them as hierarchical and disconnected. Our ultimate goal is to equip the change sector with a more inclusive, expansive, and powerful approach to tackling the myriad challenges we face, by exploring the potential of Scaling Deep as a transformational strategy for systems change.

Building a team culture for Adaptive Management in MSD: 5 Strategies MEL Managers Say Work - Gover, Dun; Nasution, Zulka; Okutu, David; Bolder, Meghan; Henao, Lina (USAID, 2023)
Keywords: Bolder Meghan; Gover Dun; Henao Lina; Nasution Zulka; Okutu David

Enhancing partner and system-level learning: 8 Tips from MEL Managers - Gover, Dun; Nasution, Zulka; Okutu, David; Bolder, Meghan; Henao, Lina (USAID, 2023)
Effective learning is a key driver of market systems change, with the potential to enhance system competitiveness, resilience, and inclusiveness. Shifting the Locus of Learning: Catalyzing Private Sector Learning to Drive Systemic Change recently outlined a rationale for enhancing the scale and quality of learning in a system and identifying 10 strategies programs can contextualize to catalyze learning. These strategies are also backed with robust examples from 13 programs doing this work across 11 countries. To deepen insights on what MSD Monitoring, Evaluation and Learning (MEL) Managers have experienced in putting several of those strategies into practice, the Feed the Future Market Systems and Partnerships (MSP) Activity convened a series of peer discussions as part of a larger initiative (see Figure 1). This brief shares the collective learning and experience on this topic of three senior MEL Managers who were interested in and had experience with this topic. The group represented full-time, program-based MEL Leads working on MSD programs funded by USAID and DFAT, based in Fiji, Albania, and Kosovo working for Adam Smith International, SwissContact, and DT Global, respectively. From those discussions, this paper synthesizes eight tips from MEL Managers for practically enhancing partner and system-level learning: 1. Identify the right decision-maker(s) at potential partners. 2. Use a co-creation process to identify learning opportunities. 3. Use diagnostics and assessments to strengthen partner and system capacity for actionable learning. 4. Use a phased capacity strengthening process tied to behavior change. 5. Measure partners’ continued investment in and use of learning—not the continuation of specific learning activities. 6. Work with sector-level institutions for scale but be aware of risks. 7. Leverage informal communities of practice to share learning. 8. Use the right terminology to talk about partner and system-focused learning.

Practioners Guide to Assessing Systems Change - Gover, Dun; Nasution, Zulka; Okutu, David; Bolder, Meghan; Henao, Lina (USAID, 2023)

The Dynamics of Team Learning: Harmony and Rhythm in Teamwork Arrangements for Innovation - Harvey, Jean-François; Cromwell, Johnathan R.; Johnson, Kevin J.; Edmondson, Amy C. (Administrative Science Quarterly, 2023)
Innovation teams must navigate inherent tensions between different learning activities to produce high levels of performance. Yet, we know little about how teams combine these activities—notably reflexive, experimental, vicarious, and contextual learning—most effectively over time. In this article, we integrate research on teamwork episodes with insights from music theory to develop a new theoretical perspective on team dynamics, which explains how team activities can produce harmony, dissonance, or rhythm in teamwork arrangements that lead to either positive or negative effects on overall performance. We first tested our theory in a field study using longitudinal data from 102 innovation teams at a Fortune Global 500 company; then, we replicated and elaborated our theory in a study of 61 MBA project teams at an elite North American university. Results show that some learning activities can occur within the same teamwork episode to have harmonious positive effects on team performance, while other activities combine to have dissonant negative effects when occurring in the same episode. We argue that dissonant activities must be spread across teamwork episodes to help teams achieve a positive rhythm of team learning over time. Our findings contribute to theory on team dynamics, team learning, and ambidexterity.

Adaptive Programming and going with the grain: IMAGINE's new water governance model in Goma, DRC - Kirk, Tom; Green, Duncan; Stys, Patrycja; Mosquera, Tom (Development Policy Review, 2023)
Motivation This paper explores adaptive approaches to development programmes that aim at improving service provision in underperforming sectors in fragile and conflict affected states (FCAS). It does this through a case study of the Integrated Maji Infrastructure and Governance Initiative for eastern Democratic Republic of the Congo's (IMAGINE) public-private partnership model for water provision. Purpose The processes and decisions that culminated in IMAGINE's model emphasize the need for programming that is culturally and politically aware, responsive to events, learns in real-time, is entrepreneurial, and works with the grain of local institutions to support change. Detailed case studies of such ways of working are crucial for programmes that seek to challenge and reform the status quo in FCAS. Methods and approach The paper is based on 42 semi-structured interviews conducted in the summers of 2019 and 2020. They reflect the broad spectrum of actors – individuals, public authorities, and organisations – involved in IMAGINE's evolution. Findings The narrative focuses on IMAGINE's attempts to professionalise and commercialise Goma's water sector. It shows how as IMAGINE repeatedly adapted to ground realities, it took on the characteristics of a public authority, thereby, engendering backlashes that threated its longer-term goals. However, by revisiting its initial values and logics it was able to get things done and achieve it aims. Policy implications IMAGINE's story suggests that adaptive programmes should put politically savvy local development professionals in key positions and enable them to carefully construct coalitions of allies across the systems they aim to disrupt. This may also require them to revisit and adapt their initial ideas, guiding principles and values as greater understandings of development problems are gained. A pubic authorities lens, attuned to the logics programmes seek to address and introduce to FCAS, may help analysts to foreground the implications of such adaptations.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/dpr.12691

On the Right Tack: Reflections on Coalition-Building Initiatives across The Asia Foundation - Nixon, Nicola; Yates, Peter; Saluja, Sumaya; Yi, Su Lae; Lucas, Miranda; Bain, Katherine (The Asia Foundation, 2023)
Coalitions—groups of organizations and individuals that work together to pursue a common policy goal or reform—are crucial to development. Some of The Asia Foundation’s longest-standing and most successful development programs and portfolios have used coalition-building as an implementation modality. This paper examines successful initiatives in Bangladesh, Nepal, Philippines, Sri Lanka, Thailand, and Timor-Leste. By delving into each of these, we shed light on this coalition-building modality, sharing insights about how externally supported coalitions emerge and function and contributing ideas about how such support can be adapted to other contexts. We hope that this paper and these case studies contribute to innovations in contemporary development theory and help practitioners use and move beyond some formulaic and technocratic modalities, such as traditional capacity development, knowledge transfer, and technical assistance. People, relationships, and working partnerships can then take center stage, and sustained cooperation will gain primacy over short-term outputs and deliverables.

Developing a Systems Thinking Lens for Collective Leadership - O’Donnell, Joan (Collective Leadership for Scotland, 2023)
Systems thinking approaches are gaining traction as an effective way of understanding and working with increasing complexity. They are being put forward by the Organisation for Economic Co-operation and Development as well as the World Health Organisation as a way to tackle the complex and unpredictable environments we now operate in. As the world has become increasingly interconnected, national or local boundaries cannot isolate and control social problems. The climate emergency, war and political instability have become everyday realities that accompany an ever-widening gap between those who have and control resources, and those who do not have enough to meet basic needs. The usual responses are becoming more and more ineffective; all interventions have unseen consequences or emergent properties that cannot be predicted using an inputoutput outcomes model. Designing interventions therefore requires a fresh lens to manage our way through turbulence and uncertainty. Most complex situations benefit from a complementary mix of a systematic (linear) decisive intervention as much as a systemic (whole-view) understanding of a proposed intervention. In this sense, adopting a systems thinking approach requires both framing the situation using a systems lens, as well as a commitment to take action and learn forward in realtime. When utilised in this way, a systems thinking lens complements rather than replaces traditional management tools. It draws on well-tested concepts and tools and relies on the systems leader to develop their practice, which includes the art of knowing what is needed and when. It is about threading traditional planning methods together with an understanding of the interrelationships, multiple perspectives and boundary judgements that influence the framing of a situation. It is becoming increasingly clear that effective leadership is embedded and invested: objective management science has no place in a world bound by interconnectedness and unintended consequences. Leaders are, as we shall see, an inherent part of both the problem and the proposed intervention. The purpose of this paper is to share some concepts informed by systems thinking to support you, as leaders in your organisations, to bring a systems-informed lens to your work. It puts you as a practitioner-leader at the centre of your own practice and encourages you to reflect critically on your positionality, as well as the lens you use to understand and intervene in complex issues. This paper has been developed on foot of training piloted with public service leaders in Scotland in the summer of 2022, and acts as an introduction to developing your systems literacy skills. While we are all born with a systems sensibility, many of us lose that sense of connectedness and interdependence with the world as we grow up. This paper acts as a prompt to bring a complexity informed approach to your work practice. It also contains some pointers for further resources and tools that may support your learning.

Re-institute website - RE!NSTITUTE (Re!nstitute, 2023)
We are a dynamic non-profit organization with a unique approach to managing change and catalyzing innovation to support global systems transformation. We know that to achieve equal, just, and safe communities, we must collectively challenge and change the systems that people rely on — especially those most vulnerable. Together, we must RE!BUILD a system's resilience and capacity to take on our biggest generational challenges. Justice, housing, health, and other systems in every country are often struggling to come together, across institutions and organizations, to unite under a common vision for change, and implement those changes in effective and innovative ways. Our work and methodology — the 100-Day Challenge — are designed to support these systems to achieve extraordinary results. Our approach is rooted in the philosophy that frontline staff, supported by leadership, can unleash innovation and achieve incredible results by creating new relationships, experimenting with fresh ideas from across their system, and building authentic engagement with those with lived experience.

Propel - Strhive (2023)
Learn from experience. Together. In the complex landscape of international development, organisations need a way to learn from their experiences and build on what works. Propel is the software solution that revolutionises the way organisations capture, access, and reuse learnings to adapt, innovate, and create lasting change on a global scale. Let's stop reinventing the wheel and build on what works, together.

How Political Contexts Influence Education Systems: Patterns, Constraints, Entry Points - Levy, Brian (Research on Improving Systems of Education (RISE), 2022)
This paper synthesises the findings of a set of country studies commissioned by the RISE Programme to explore the influence of politics and power on education sector policymaking and implementation. The synthesis groups the countries into three political-institutional contexts: - Dominant contexts, where power is centred around a political leader and a hierarchical governance structure. As the Vietnam case details, top-down leadership potentially can provide a robust platform for improving learning outcomes. However, as the case studies of Ethiopia, Indonesia, Nigeria, and Tanzania illustrate, all-too-often dominant leaders’ goals vis-à-vis the education sector can veer in other directions. - In impersonal competitive contexts, a combination of strong formal institutions and effective processes of resolving disagreements can, on occasion, result in a shared commitment among powerful interests to improve learning outcomes—but in none of the case studies is this outcome evident. In Peru, substantial learning gains have been achieved despite messy top-level politics. But the Chilean, Indian, and South African case studies suggest that the all-too-common result of rule-boundedness plus unresolved political contestation over the education sector’s goals is some combination of exaggerated rule compliance and/or performative isomorphic mimicry. - Personalised competitive contexts (Bangladesh, Ghana, and Kenya for example) lack the seeming strengths of either their dominant or their impersonal competitive contexts; there are multiple politically-influential groups and multiple, competing goals—but no credible framework of rules to bring coherence either to political competition or to the education bureaucracy. The case studies show that political and institutional constraints can render ineffective many specialised sectoral interventions intended to improve learning outcomes. But they also point to the possibility that ‘soft governance’ entry points might open up some context-aligned opportunities for improving learning outcomes. In dominant contexts, the focus might usefully be on trying to influence the goals and strategies of top-level leadership. In impersonal competitive contexts, it might be on strengthening alliances between mission-oriented public officials and other developmentally-oriented stakeholders. In personalised competitive contexts, gains are more likely to come from the bottom-up—via a combination of local-level initiatives plus a broader effort to inculcate a shared sense among a country’s citizenry of ‘all for education’.

How and Why Practitioners Think and Work Politically - Evidence from Chemonics Programming Across Sectors - Kantelberg, Renee; Swift-Morgan, Jennifer; Watson, Bryce (Chemonics International, 2022)
Most development practitioners have long recognized that deep contextual knowledge is crucial to understanding how projects interact with their local systems and, in turn, to navigating these systems. Moreover, this knowledge must complement projects' technical solutions, or they will fall flat and may even undercut project objectives as they clatter down. What, then, explains practitioners' particular interest in TWP as an explicit strategy and more than just "doing good development"? This report responds to that question and to the many calls for a more comprehensive picture of TWP by presenting new evidence of the various forms that TWP may take in practice. The evidence comes from a 2022 study that Chemonics undertook to foster more robust learning about TWP. Specifically, we closely examined Chemonics implemented projects that used or are using various forms of TWP in nine countries: Bangladesh, Iraq, Mozambique, the Philippines, Pakistan, Syria, Timor-Leste, and Tunisia. In conducting the study, we interviewed multiple staff from these projects. We complemented what we learned from these projects with a review of eight additional Chemonics- implemented projects applying TWP that had received dedicated support from Chemonics’ Center for Politically Informed Programming (the Center). We consider these findings alongside those of the recent (2022) USAID-Chemonics study on political economy analysis (PEA) usage to identify and articulate what is different and more effective about PEA processes and TWP practices that have received more support.

Transforming M&E for Uncertain and Complex Contexts: The UNDP’s Innovation Sandbox Approach - Fraser, Dugan; Haldrup, Søren (Powered by Evidence Podcast, 2022)
How can we transform monitoring and evaluation (M&E) into a more adaptive, emergent process to address uncertainty and complexity in todays’ world? How do we move from compliance and accountability to learning – to support better, more timely, decisions? Join GEI Program Manager, Dugan Fraser, as he discusses these questions and others with Special Guest, Søren Haldrup, from UNDP's Strategic Innovation Unit where he manages UNDP's innovation facility and leads a new initiative called the M&E Sandbox.

Everyday patterns for shifting systems - GCSI (GCSI, 2022)

Everyday patterns for shifting systems - Right scaling - GCSI (GCSI, 2022)

The Art and Craft of Bricolage in Evaluation - Aston, Thomas; Apgar, Marina (Institute for Development Studies, 2022)
This CDI Practice Paper by Tom Aston and Marina Apgar makes the case for ‘bricolage’ in complexity-aware and qualitative evaluation methods. It provides a framework based on a review of 33 methods to support evaluators to be more intentional about bricolage and to combine the component parts of relevant methods more effectively. It discusses two cases from practice to illustrate the value added of taking a more intentional approach. It further argues that navigating different forms of power is a critical skill for bricolage, and that doing so can help to ensure rigour.
Accepted: 2022-10-14T10:56:39Z Publisher: Institute of Development Studies

UNDP Digital Leadership Learning Modules - UNDP (United Nations Development Programme, 2022)
In order to support the digital transformation of government operations Digital Learning Modules for Civil Servants are available, an off-the-shelf package of capacity development in form of replicable training modules to empower public servants at both the local and central government level to be leaders of digital transformation for delivering better public services. The modules cover a multitude of fundamental areas: comprehending digital government and services, human-centered design for inclusivity and agile learning cycles; feature the importance of security and privacy, the value of data and how to manage data and technology related risks; spotlight the key role of supportive leadership and offer practical tools for assessing and overcoming main barriers to ensure a successful digital transformation journey.

Thinking and Working Politically in the Land Sector in Mekong Region - Burns, Tony; Ingalls, Micah; Rickersey, Kate (2022)
In recent decades, the World Bank and many bilateral development partners have provided funding to support land administration reform. Traditional land administration reform projects focus on the economic and technical design of interventions based on a library of best practice, commonly avoiding the “messy politics” typically involved in land governance. Experience and lessons from land administration reform initiatives have been documented and a recurrent theme is that many projects fail to create effective, transformative change and gain the critical mass, and the community participation, necessary to ensure the sustainability of land administration reform. Over the last decade there have been concerted efforts to develop more politically informed ways of thinking and working using a range of methodologies referred to, variously, as Thinking and Working Politicallyi (TWP), Problem Driven Iterative Adaptation (PDIA) and Doing Development Differently (DDD). There is little evidence that these different approaches have been applied in the land sector.

Where have we got to on Thinking and Working Politically? Update and a Mildly Heretical Thought. – FP2P - Green, Duncan (From Poverty to Power, 2022)
Headed off recently to discuss the state of Thinking and Working Politically within the aid sector. This is a loose network of aid wonks that came together to try and move aid from a pure focus on technical issues, towards taking account of power and politics and why they can facilitate/frustrate attempts to make change happen in any given context. It was great to be in a room with others (50/50 in person and online) – the neurons fire in a way that just doesn’t happen online (but I also need to brush up on my meeting skills, as when I accidentally clicked on a random video in my timeline and it started playing at full volume. Super awkward). On to the content (Chatham House rule, so no names or institutions). Some observations about the evolution of a movement I’ve been connected with for over a decade. I got a lot of pushback from participants on an earlier draft and have made quite a few changes, but they should definitely feel free to set me straight in comments!

Achieving disability inclusive employment – Are the current approaches deep enough? - Shaw, Jackie; Wickenden, Mary; Thompson, Stephen; Mader, Philip (Journal of International Development, 2022)
Diverse approaches to promoting disability inclusive employment aim to transform workplaces into truly inclusive environments, usually with intervention strategies targeting two main groups: employers and jobseekers with disabilities. However, they do not always consider other relevant stakeholders or address the relationships and interactions between diverse actors in the wider social ecosystem. These approaches often neglect deeper ‘vexing’ difficulties which block progress towards disability inclusive work environments. Most interventions rightly embrace hegemonic ‘social models of disability’ and use human rights arguments but may neglect entrenched structural factors. Disability inclusive employment is complex, with unaddressed invisible aspects that continue to limit progress. We explore some key relevant disability concepts and then interrogate evidence from the ‘Inclusion Works’ programme working in four middle- and low-income countries, considering some intractable barriers underlying the slow movement towards inclusive employment. Finally, we propose that a more participatory action orientated approach involving disabled people and others is needed to both generate deeper understanding and provide pathways towards new solutions to obstinate problems through progressive action learning processes in context. Programmatic interventions that work across the levels of the ecosystem and address power relations and interactions between stakeholders could lead to more substantial forms of disability inclusive employment.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/jid.3692

Evidence-led adaptive programming: Lessons from MUVA - Sharp, Samuel; Riemenschneider, Nils; Selvester, Kerry (ODI, 2022)
Calls for more ‘adaptive programming’ have been prominent in international development practice for over a decade. Learning-by-doing is a crucial element of this, but programmes have often found it challenging to become more learning oriented. Establishing some form of reflective practice, against countervailing incentives, is difficult. Incorporating data collection processes that generate useful, timely and practical information to inform these reflections is even more so.This paper explores MUVA - an adaptive female economic empowerment programme in Mozambique. MUVA, we suggest, is atypically evidence-led. It combines systematic, inclusive reflective practice with extensive real-time data collection. We describe the fundamental features of MUVA’s monitoring, evaluation and learning (MEL) approach that supported this. One, how data collection and analysis are synchronised with set cycles for learning and adapting projects. Two, how MEL systems are designed to prioritise actionable learning, with data collection oriented more to the needs of implementing staff than to the reporting requirements of funders.This approach was enabled by building collective ownership over the programme’s objectives and the purpose of MEL from the outset. Implementers are asked about their motivations, and these are related to the programme’s Theory of Change. The evidence culture is supported by the proximity of MEL staff to implementing staff; and through structuring upwards accountability to funders around justifying evidence-based adaptations instead of reporting on more narrow indicators. We conclude by considering the relevance, or not, of MUVA’s approach to programmes in other contexts or issue areas trying to replicate a similarly evidence-informed approach to adaptive management. Key messages Learning-by-doing is essential to adaptive programming, but it can be challenging to establish data collection processes that generate useful, timely and practical information. MUVA – a female economic empowerment programme in Mozambique – has an atypically evidence-led adaptive management approach. This has two fundamental features. One, data collection and analysis are synchronised with set cycles for learning and adapting projects. Two, data collection is oriented more to the needs of implementing staff than to the reporting requirements of funders. Monitoring, evaluation and learning (MEL) systems are designed to prioritise actionable learning. This approach was enabled by building collective ownership over the programme’s objectives and the purpose of MEL from the outset. Implementers are asked about their motivations, and these are related to the programme’s Theory of Change. The evidence culture is supported by the proximity of MEL staff to implementing staff; and through structuring upwards accountability to funders around justifying evidence-based adaptations instead of reporting on more narrow indicators.

The Learning Power of Listening - Guijt, Irene; Gottret, Maria Veronica; Hanchar, Anna; Deprez, Steff; Muckenhirn, Rita (PRACTICAL ACTION PUBLISHING, 2022)
Steff had the pleasure to co-author the first SenseMaker Practitioner Guide with a group of friends and colleagues supported and published by Oxfam and CRS. This practical guide is for those who wish to use SenseMaker to conduct assessments, monitor progress, and undertake evaluations or research. Drawing on more than a decade of experience, the authors share dozens of examples from international development, providing practical tips and ideas for context-specific adaptations. They show how the method can be used to for difficult-to-measure outcomes related to poverty reduction, social justice, peacebuilding, resilience, gender norms, behavior change, governance and environmental management. ​ SenseMaker is a unique participatory method of inquiry that encourages and enables novel insights not obtained from conventional quantitative and quantitative and qualitative methods. It is action-oriented and, therefore, well-suited for people needing data- informed insights for adaptive management. "Writing this guide together with Irene, Veronica, Anna and Rita was an enormous learning process in itself and has further shaped our thinking and practice. We hope it will support first-time and experienced users to enhance their practice and that it will inspire people to explore and innovate further with the method."
Pages: 1-188

(Re)making the case for adaptive management - Aston, Thomas (Medium, 2022)
Great overview of what to read on adaptive management. It’s a long one, so I’ve split it into two – second installment tomorrow. Christian Aid Ireland’s recent publication The Difference Learning Makes by Stephen Gray and Andy Carl made a bit of a splash. The study found that Christian Aid Ireland’s application of adaptive programming contributed to better development outcomes and supported more flexible delivery. The much vaunted MUVA programme in Mozambique is also coming to a close and presenting its results from using and adaptive approach. So, it struck me that we might be at a critical juncture in the conversation on adaptive management. We’ve had the crashing to earth of inflated expectations in recent misanthropic reflections, [misanthropic, moi? – Duncan] alongside a fragile institutionalisation of adaptive management in donor agencies, NGOs, and private sector organisations. However, I’d argue that we’ve reached the point where adaptive management has passed the proof-of-concept stage.

Thinking and Working Politically on Health Systems Resilience: Learning from the experience of Cameroon, Nepal and South Africa during COVID-19 - Williams, Gareth (TWP Community of Practice, 2022)

Redefining rigour: using stories to evaluate systems change? - Lowther, Keira (Centre For Public Impact (CPI), 2022)
What might a different way of understanding rigour for work in complex adaptive systems look like?

Beyond "Lack of Political Will": Elaborating Political Economy Concepts to Advance "Thinking and Working Politically" Comment on "Health Coverage and Financial Protection in Uganda: A Political Economy Perspective" - Ssennyonjo, Aloysius (International Journal of Health Policy and Management, 2022)
Political economy analysis (PEA) has been advanced as critical to understanding the political dimensions of policy change processes. However, political economy (PE) is not a theory on its own but draws on several concepts. Nannini et al, in concert with other scholars, emphasise that politics is characterised by conflict, contestation and negotiation over interests, ideas and power as various agents attempt to influence their context. This commentary reflects how Nannini et al wrestled with these PEA concepts - summarised in their conceptual framework used for PEA of the Ugandan case study on financial risk protection reforms. The central premise is that a common understanding of the PEA concepts (mainly structure-agency interactions, ideas, interests, institutions and power) forms a basis for strategies to advance thinking and working politically. Consequently, I generate several insights into how we can promote politically informed approaches to designing, implementing and evaluating policy reforms and development efforts.

Rethinking monitoring and evaluation in complex systems — when learning is a result in itself - Innovation, UNDP (Medium, 2022)
By Søren Vester Haldrup, UNDP’s Strategic Innovation Unit

Integrated Governance: Achieving Governance Results and Contributing to Sector Outcomes - Frazer, Sarah; Granius, Mark; Brinkerhoff, Derick W.; McGregor, Lisa (RTI Press, 2022)
Achieving broad-based socio-economic development requires interventions that bridge disciplines, strategies, and stakeholders. Effective sustained progress requires more than simply an accumulation of sector projects, and poverty reduction, individual wellbeing, community development, and societal advancement do not fall neatly into sectoral categories. However, researchers and practitioners recognize key operational challenges to achieving effective integration that stem from the structures and processes associated with the current practice of international development. Integration calls for the intentional linking of intervention designs, implementation, and evaluation across sectors and disciplines to achieve mutually reinforcing outcomes. In this report, we summarize the results of a study we conducted to explore the challenges facing governance programs that integrate with sector interventions to achieve governance outcomes and contribute to sector outcomes. Through a review of policy documents and project reports from recent integrated governance programs and interviews with donor and practitioner staff, we found three integrated governance programming variants, an emphasis on citizen and government collaboration to improve service delivery, interventions that serve as the glue between sectors, and a balancing act for indicators to measure contribution to sectoral outcomes. Our analysis identified four key success factors: contextual readiness, the application of learning and adapting approaches, donor support, and recognition of the limitations of integrated governance. We then discuss recommendations and implications and for answering the challenge of integrating governance and sector programming to achieve development outcomes.

Seeing the Combined Effects of Aid Programmes - Burge, Richard; Nadelman, Rachel; McGee, Rosie; Fox, Jonathan; Anderson, Colin (IDS, 2022)
Multiple aid agencies often try to support change in the same places, at the same time, and with similar actors. Surprisingly, their interactions and combined effects are rarely explored. This Policy Briefing describes findings from research conducted on recent aid programmes that overlapped in Mozambique, Nigeria, and Pakistan, and from a webinar with UK Foreign, Commonwealth & Development Office (FCDO) advisors and practitioners. The research found three distinct categories of ‘interaction effects’: synergy, parallel play, and disconnect. We explore how using an ‘interaction effects’ lens in practice could inform aid agency strategies and programming.
Accepted: 2022-05-10T09:42:35Z Publisher: Institute of Development Studies

Gambling on Development: Why Some Countries Win and Others Lose - Dercon, Stefan (C Hurst & Co Publishers Ltd, 2022)

Can PDIA become a regular part of how a government works? - Building State Capability - Harrington, Peter (Building State Capability, 2022)
Institutional change is part of the theory of change of PDIA – scaling through the diffusion of new ways of thinking and greater problem-solving know-how. And once a community of practice reaches critical mass across an eco-system, a tipping point can happen where the eco-system becomes generally more open to novelty, where success is a more effective route to legitimacy, and where leadership is oriented towards value creation.

Measuring and Monitoring Adaptive Learning: A Landscape Review - LaFond, Anne; Adrian, Haley (USAID MOMENTUM Knowledge Accelerator, 2022)
This landscape review on measuring and monitoring adaptive learning highlights the learning from five adaptive programming guidelines and toolkits and one implementation science framework to inform the monitoring and evaluation of adaptive learning. The introduction of adaptive learning processes and skillsets in global health programming is part of an emerging strategy to advance a learning culture within projects and teams to improve health program performance. The monitoring and evaluation of adaptive learning is an emergent field aiming to monitor how adaptive learning processes have been introduced, how they are used, and whether they are having the intended results. Although there is a growing body of literature on adaptive programming more generally, there is a limited knowledge base on the monitoring and evaluation of adaptive learning interventions and their impacts. Unlike other implementation strategies or program management approaches, there are no standard metrics or a monitoring and evaluation framework to track the integration, implementation, and effectiveness of adaptive learning in health programming.

Capacity Development in a Participatory Adaptive Programme: the Case of the Clarissa Consortium - Widmer, Mireille; Apgar, Marina; Afroze, Jiniya; Malla, Sudhir; Healey, Jill; Constant, Sendrine (IDS, 2022)
Doing development differently rests on deliberate efforts to reflect and learn, not just about what programmes are doing and achieving, but about how they are working. This is particularly important for an action research programme like Child Labour: Action- Research-Innovation in South and South-Eastern Asia (CLARISSA), which is implemented by a consortium of organisations from across the research and development spectrum, during a rapidly changing global pandemic. Harnessing the potential of diverse skills and complementary strengths across partners in responding to the complex challenge of the worst forms of child labour, requires capacity to work together in novel ways. This Research and Evidence Paper documents how CLARISSA approached capacity development, and what we learnt from our challenges and successes. From the start, the programme incorporated a capacity development strategy resting on self-assessment of a wide range of behavioural and technical competencies that were deemed important for programme implementation, formal training activities, and periodic review of progress through an after-action review (AAR) process. An inventory of capacity development activities that took place during the first year of implementation reveals a wide range of additional, unplanned activities, enabled by the programme’s flexibility and adaptive management strategy. These are organised into eight modalities, according to the individual or collective nature of the activity, and its sequencing – namely, whether capacity development happens prior to, during, or after (from) implementation. We conclude with some reflections on the emergent nature of capacity development. Planning capacity development in an adaptive programme provides a scaffolding in terms of time, resources, and legitimacy that sustains adaptiveness. We also recognise the gaps that remain to be addressed, particularly on scaling up individual learning to collective capabilities, and widening the focus from implementation teams to individuals working at consortium level.
Accepted: 2022-04-25T10:25:54Z Publisher: Institute of Development Studies

Innovating for inclusive rigour in peacebuilding evaluation - Apgar, Marina; Báez-Silva, Ángela Maria; Deng, Ayak Chol; Fairey, Tiffany; Rohrbach, Livia; Alamoussa, Dioma; Bradburn, Helene; Cubillos, Edwin; Gray, Stephen; Wingender, Leslie (Institute of Development Studies, 2022)
Inclusive and rigorous peacebuilding evaluation is both vital and complex. In this blog we share examples of how we are innovating our methodologies to move towards participatory and adaptive practice.

The collaborative exploration of alternative futures: A different approach to Theories of Change - CEDIL programme (2022)
ParEvo is a web application that enables the collaborative construction and exploration of a range of alternative futures: likely and unlikely, desirable and undesirable. These are described in the form of a branching narrative structure, developed over a series of iterations involving the interactions of a group of participants. These detailed storylines about the future contrast with optimistic, skeletal and largely singular views of the future found in diagrammatic ToCs often encountered by evaluators. This webinar will describe a recent ParEvo exercise implemented by the Centre for the Study of Existential Risk (CSER) in Cambridge. In this exercise 11 international experts explored ideas about how global risks associated with biotechnology research could be managed, and mismanaged, in the coming four years. Including how these alternative futures were evaluated by participants and the CSER facilitators. Issues to be discussed by the panel, and others, include comparisons with other representations of Theories of Change and other approaches to the exploration of alternative futures, described variously as scenario planning, futures or foresight work. Speakers: Rick Davies, Lara Mani Tom Hobson An overview of the app can be found here: https://mscinnovations.wordpress.com/ The app website is here: https://parevo.org/

Second (and Third) Thoughts on Adaptive Management and Thinking and Working Politically - Green, Duncan (From Poverty to Power, 2022)
Self-Critical reflections on AM and TWP. Linking it with The Hype Cycle - "it feels like we are heading downward to the ‘trough of disillusionment’ form the initial peak of ‘inflated expectations’, but we will bounce back to something more sustained, that becomes a permanent feature of the aid landscape".

System Change: A Guidebook for Adopting Portfolio Approaches - Wellsch, Brent (UNDP, 2022)
This guidebook codifies the principles and methods of applying systems change and portfolio approaches to complex development challenges with practical tools and examples. It is based on the empirical learning generated from the collaborative initiatives in UNDP Country Offices in Bhutan, Pakistan, the Philippines, and Viet Nam with support from Regional Innovation Centre for Asia and the Pacific.

What, so what, now what? - Aston, Thomas (Medium, 2022)
Getting serious about systems change

Lessons Learned From the Use of the Most Significant Change Technique for Adaptive Management of Complex Health Interventions - Ohkubo, Saori; Mwaikambo, Lisa; Salem, Ruwaida M.; Ajijola, Lekan; Nyachae, Paul; Sharma, Mukesh Kumar (Global Health: Science and Practice, 2022)
Introduction:The Most Significant Change (MSC) technique is a complex-aware monitoring and evaluation tool, widely recognized for various adaptive management purposes. The documentation of practical examples using the MSC technique for an ongoing monitoring purpose is limited. We aim to fill the current gap by documenting and sharing the experience and lessons learned of The Challenge Initiative (TCI), which is scaling up evidence-based family planning (FP) and adolescent and youth sexual and reproductive health (AYSRH) interventions in 11 countries in Asia and sub-Saharan Africa. Methods:The qualitative assessment took place in early 2021 to document TCI’s use and adaptation of MSC and determine its added value in adaptive management, routine monitoring, and cross-learning efforts. Focus group discussions and key informant interviews were conducted virtually with staff members involved in collecting and selecting MSC stories. Results:TCI has had a positive experience with using MSC to facilitate adaptive management in multiple countries. The use of MSC has created learning opportunities that have helped diffuse evidence-based FP and AYSRH interventions both within and across countries. The responsive feedback step in the MSC process was viewed as indispensable to learning and collaboration. There are several necessary inputs to successful use of the method, including buy-in about the benefits, training on good interviewing techniques and qualitative research, and dedicated staff to manage the process. Conclusion:Our assessment results suggest that the MSC technique is an effective qualitative data collection tool to strengthen routine monitoring and adaptive management efforts that allows for flexibility in how project stakeholders implement the process. The MSC technique could be an important tool for global health practitioners, policy makers, and researchers working on complex interventions because they continually need to understand stakeholders’ needs and priorities, learn from lessons and evidence-based practices, and be agile about addressing potential challenges.
Publisher: Global Health: Science and Practice Section: ORIGINAL ARTICLE

Theory of Change Workbook: A Step-by-Step Process for Developing or Strengthening Theories of Change - Salib, Monalisa (USAID, 2022)
While over time theories of change have become synonymous with simple if/then statements, a strong theory of change should actually be a much more detailed, context-specific articulation of how we *theorize* change will happen under a program.

Systems Thinking and Practice: A Guide to Concepts, Principles and Tools for FCDO and Partners - Woodhill, Jim; Millican, Juliet (Institute of Development Studies, 2022)
This guide is a basic reference on systems thinking and practice tailored to the context and needs of the UK Government’s Foreign, Commonwealth & Development Office (FCDO). It is an output of the FCDO Knowledge for Development Programme (K4D), which facilitated a Learning Journey on Systems Thinking and Practice with FCDO staff during 2021 and 2022. The guide offers a common language and shared framing of systems thinking for FCDO and its partners. It explores what this implies for working practices, business processes and leadership. It also offers links to additional resources and tools on systems thinking. We hope it can support systems thinking to become more commonplace within the culture and practices of FCDO and working relations with partner organisations.
Accepted: 2023-02-03T15:47:58Z Publisher: Institute of Development Studies

Thinking and working politically: What have we learned since 2013? – FP2P - Green, Duncan (From Poverty to Power, 2022)
It’s always a red letter day when a new paper from Graham Teskey drops. His most recent is Thinking and working politically: What have we learned since 2013? For those that don’t know him, Graham is a consummate insider-outsider within the aid sector – long stints at DFID (UK), DFAT (Australia) and now Abt (Management Consultants). From this vantage point he has been one of the leading proponents of ‘thinking and working politically’, always ready to call out the hand-wavey academics and demand some practical lessons, please. This paper is part biography of an idea, setting out the timeline, moments and key documents and policy wins in the evolution of TWP (which seems to have involved a lot of seminars that I missed due to Oxfam’s meagre travel budget). The other part is, to be honest, a bit of a lament – a study in ‘Why Change Hasn’t Happened’, because TWP has ‘got lost in the maelstrom’ of the wider, largely negative, changes in the aid sector. Overall, it’s a brilliant summary, and one I’ll be recommending to my increasingly long-suffering activism students….

The Difference Learning Makes - Factors that enable and inhibit adaptive programming - Gray, Stephen; Carl, Andy (Christian Aid, 2022)
Executive Summary When Christian Aid (CA) Ireland devised its multi-country and multi-year Irish Aid funded Programme Grant II (2017-2022), they opted to move away from a linear programme management approach and to explore an adaptive one. Across seven countries: Angola, Colombia, El Salvador, Guatemala, Israel and the occupied Palestinian territory, Sierra Leone, and Zimbabwe, CA and partner organisations support marginalised communities to realise their rights, reduce violence and address gender inequality. Since 2019, Adapt Peacebuilding has accompanied CA Ireland, CA country teams and partner organisations as they experimented with using a deliberate adaptive approach. The authors were also asked to follow up on an initial study by CA Ireland and Overseas Development Institute in 2018, which described the rationale for adopting this new approach and included early lessons from its first year of implementation. The aim of this study is to help deepen CA Ireland, CA country teams’ and partners’ understanding of (a) whether their application of adaptive programming has resulted in better development outcomes, and (b) how they can better understand the factors that enabled or inhibited the effectiveness of using this approach. Over the past three years, this study has found evidence and multiple examples that show adaptive programming contributed to better development outcomes. The main reasons cited were that these were made possible both from improvements to programming strategies based on proactive reflection and learning, as well as those that stem from the reactive capacity of adaptive programmes to change course in response to unanticipated changes in operating conditions. This study found that adaptive programming has enabled better development practice where organisations are enhancing their skills to better respond and be flexible to contextual challenges. 72% of partners surveyed described adaptive programming as the most useful approach to programme management that they have used. The programme approach has meant that CA and partner staff were better able to explore the significance of change in the context and their contributions to them. It also enabled spaces for meaningful engagement with communities in learning and programme planning processes and encouraged opportunities for experimentation in programming. The study also found that adaptive programming has supported flexible delivery. This led to better outcomes that would not have been possible were the programme not able to make flexible adjustments. The main focus has been the analysis of nine factors that can determine the effectiveness and impact (or otherwise) of using an adaptive approach, flagging important issues for understanding. These factors are identified as: 1) Leadership; 2) Organisational culture; 3) Conceptual understanding; 4) Staff capacities; 5) Partnership approaches; 6) Participation; 7) Methods and tools; 8) Administrative procedures; and 9) The operating context. Together these can provide an analytical framework for assessing an organisation’s ‘adaptive scope’, which can be used as a tool for better understanding an organisation’s potential to generate improved development outcomes via adaptive programming and how to strengthen them. The study concludes with several recommendations for CA Ireland, all of which have relevance for a broader community of donors and implementing organisations interested in the potential of adaptive programming.

Guidance Note for Adaptive Management - Ministry of Foreign Affairs of Denmark (Government of Denmark, 2022)
This note explains what adaptive aid management is; why and when it should be considered; and how it should be applied. It covers all Danish development support channels and modalities, including bilateral country assistance, assistance to and through civil society, the private sector and to and through multilateral organisations. This guide has three chapters. Chapter 1 provides an executive overview of what adaptive management is. Chapter 2 goes deeper into five key operational principles of adaptive management. Chapter 3 details the main tenets of adaptive management processes during the programming cycle.

The Patterns of Possibility - How to Recast Relationships to Create Healthier Systems and Better Outcomes - Winhall, Jennie; Leadbeater, Charles (The Rockwool Foundation, 2022)
In Building Better Systems, we introduced four keys to unlock system innovation: purpose and power, relationships and resource flows. These four keys make up a set. Systems are often hard to change because power, relationships, and resource flows are locked together in a reinforcing pattern to serve the system’s current purpose. Systems start to change fundamentally when this pattern is disrupted and opened up so that a new configuration can emerge, serving a new purpose. In this article series we delve deeper into these four keys and provide practical advice on how they can be put to use. This article is about relationships. Systems are defined by the patterns of interactions between their parts: their relationships. Those interactions generate the outcomes of the system as a whole. Transforming the outcomes of a system requires remaking its relationships and then unlocking the other keys to system innovation: purpose, power and resources. This shift in relationships allows all those in the system to learn faster, to be more creative. System innovators redesign the relationships in the system to allow dramatically enhanced learning across the system, and thereby generate far better outcomes.

PFM Reform Through PDIA: What Works and When it Works - Harris, Jamelia; Lawson, Andrew (Public Financial Management Blog - IMF, 2022)

Data-powered positive deviance: Combining traditional and non-traditional data to identify and characterise development-related outperformers - Albanna, Basma; Heeks, Richard; Pawelke, Andreas; Boy, Jeremy; Handl, Julia; Gluecker, Andreas (Development Engineering, 2022)
The positive deviance approach in international development scales practices and strategies of positively-deviant individuals and groups: those who are able to achieve significantly better development outcomes than their peers despite having similar resources and challenges. This approach relies mainly on traditional data sources (e.g. surveys and interviews) for identifying those positive deviants and for discovering their successful solutions. The growing availability of non-traditional digital data (e.g. from remote sensing and mobile phones) relating to individuals, communities and spaces enables data innovation opportunities for positive deviance. Such datasets can identify deviance at geographic and temporal scales that were not possible before. But guidance is needed on how this new data can be employed in the positive deviance approach, and how it can be combined with more traditional data to gain deeper, more meaningful, and context-aware insights. This paper presents such guidance through a data-powered method that combines both traditional and non-traditional data to identify and understand positive deviance in new ways and domains. This method has been developed iteratively through six development projects covering five different domains – sustainable cattle ranching, agricultural productivity, rangeland management, research performance, crime control – with global and local development partners in six countries. The projects combine different types of non-traditional data with official statistics, administrative data and interviews. Here, we describe a structured method for data-powered positive deviance developed from the experience of these projects, and we reflect on lessons learned. We hope to encourage and guide greater use of this new method; enabling development practitioners to make more effective use of the non-traditional digital datasets that are increasingly available.

Monitoring and evaluation for thinking and working politically - Aston, Thomas; Roche, Chris; Schaaf, Marta; Cant, Sue (Evaluation, 2022)
This article explores the challenges of monitoring and evaluating politically informed and adaptive programmes in the international development field. We assess the strengths and weaknesses of some specific evaluation methodologies which have been suggested as particularly appropriate for these kinds of programmes based on scholarly literature and the practical experience of the authors in using them. We suggest that those methods which assume generative causality are particularly well suited to the task. We also conclude that factoring in the politics of uncertainty and evidence generation and use is particularly important in order to recognize and value diverse experiential knowledge, integrate understandings of the local context, accommodate adaptation and realistically grapple with the power relations which are inherent in evaluation processes.
Publisher: SAGE Publications Ltd

Civil society organizations and managerialism: On the depoliticization of the adaptive management agenda - Gutheil, Lena; Koch, Dirk-Jan (Development Policy Review, 2022)
Motivation In the last decade, a movement formed around making aid delivery more adaptive, relying on principles such as context sensitivity, flexibility, and ownership. The approaches seem promising for civil society organizations (CSOs) to fulfil their mission of fostering social transformation. While several donor agencies have started engaging with such approaches, the authors hardly see their political implications in practice. Purpose The article aims to provide evidence on an adaptive project and demonstrate how the social transformative and political nature of adaptive development management is rendered technical and depoliticized in practice. Methods and approach We use a case study of a development programme based on a social transformative policy framework that is implemented through CSOs in Uganda and Vietnam. Data were collected by means of interviews, participant observation and document analysis. Findings We find that, in practice, the social transformative policy framework is competing with managerial logics. We compare this process with the depoliticization of the Paris Declaration on Aid Effectiveness, finding striking similarities. By using practice theory, we show how managerialism remains the dominant paradigm in the civil society aid sector, fuelling the “anti-politics machine.” Policy implications The article shows that policy frameworks do not always work as intended. Donors should therefore not only change policy frameworks, but also start addressing institutional and operational requirements.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/dpr.12630

Market systems change rubric - Loveridge, Donna (Oxford Policy Management, 2022)
This systems change rubric describes different performance levels according to various systems elements, such as policy (formal rules), practices and relationships and connections. Programmes can use the rubric to assess the performance of systems to help decide where and how to intervene, or during and post-implementation to conduct progress assessments, and assess the effectiveness of interventions and type, breadth and depth of systems change. Each performance level description highlights the type of data and information that needs to be collected. One analysis is completed, users can compare this to the performance descriptions to see which level best matches the analysis. This helps programmes draw conclusions about systems changes. The rubric was developed in 2020 and tested in 2021 and builds on systems change thinking and frameworks from two previous FSG publications. It can be used as: pre-intervention to conduct an assessment during an intervention to conduct progress assessments and reflect on the effectiveness of interventions to change systems and inform decision making post intervention to make judgements about whether interventions were valuable given the resources, time and effort spent Useful for: Implementation managers to determine the effectiveness of interventions, as well as by Monitoring, Evaluation and Learning (MEL) teams to track progress against expected outcomes.

The Relational Work of Systems Change - Millgan, Katherine; Zerda, Juanita; Kania, John (Stanford Social Innovation Review, 2022)
Collective impact efforts must prioritize working together in more relational ways to find systemic solutions to social problems. Sometimes we lose sight of a simple truth about systems: They are made up of people. Despite all of the frameworks and tools at our disposal and all of our learning as a field of practice, purely technical, rational approaches to systems change will not make much of a dent in shifting power or altering our most deeply held beliefs. If most collective impact efforts fall short of supporting people to change in fundamentally consciousness-altering ways, then, the system they are a part of will not significantly change either. However, over the past two decades, the prevailing view among many funders, board members, and institutional leaders has been that only quantifiable and predetermined outcomes can create impact. But if the interrelated, devastating, and deepening crises and divisions over the past two years have taught us anything, it is that complex, adaptive problems defy tidy logic models and reductive technical solutions. It is time to invest our collective energy in more relational and emergent approaches to transforming systems.

MOTION HANDBOOK - Developing a transformative Theory of Change - Palavicino, Carla Alvial; Matti, Cristian; Witte, Jenny (TIPC, Utrecht University, 2022)
A step-by-step guide on how to develop a Transformative Theory of Change, for innovation projects, programmes and organisations working on systems transformation. The MOTION project was initiated with one key question in mind: how can we help projects and organisations be more transformative, using the framework and concept provided by the multi-level perspective? And what kind of tools, methods and frameworks can we co-design that translate scientific concepts into practises relevant for policy practitioners? This led us into a co-creation journey during which researchers from the Transformative Innovation Policy Consortium (TIPC) and EIT Climate-KIC project partners experimented, reflected and learned from each other in building the approach that we share in this handbook. Through this journey, we gained a deeper understanding of what the portfolio approach means in a transformative system change context and which skills and competences are needed to facilitate processes of co-creation in the science-policy-practice interface. We had the opportunity to configure the key building blocks of our theoretical approach, the Transformative Outcomes, into practical insights and actions that can easily be applied by innovation organisations at many levels. This handbook is the culmination of the journey as it translates key learnings from the MOTION project into practical insights that are relevant to practitioners working on systems transformation.

Sensemaking Workshop Preparation Guide and Facilitator Guide and Sensemaking Training - UNDP (UNDP, 2022)
Based on experience from running Sensemaking workshops for UNDP offices and government partners, the Asia-Pacific Regional Innovation Centre developed the Sensemaking Preparation Guide and Facilitator Guide to share its knowledge with teams and organization that are interested in using the Sensemaking process.

Guidance Note: Practical introduction to adaptive management - DT Global (DT Global, 2022)
DT Global is proud to introduce our new Guidance Note: Practical Introduction to Adaptive Management There is a growing consensus around adaptive management as an effective (even necessary) approach when programs are tackling complex development problems. While there is no standard definition of adaptive management, there is general agreement that such programs need to routinely engage with and respond to program context; constantly test what works in that context; and adjust approaches, plans, and activities based on continuous learning. However, there remains a more limited body of evidence about what this looks like in practice—the enabling conditions, systems, resourcing, skills, and attitudes to effectively operationalise adaptive management. There is also limited guidance around when adaptive management is required, and to what extent—both critical and often overlooked considerations when planning for successful adaptive management. This Guidance Note draws together lessons and good practice in adaptive management from across DT Global’s diverse portfolio of donor-funded programs. It outlines our conceptual framework for adaptive management, with practical guidance on how it can be applied by our program teams. It is also designed to help our teams distinguish adaptive management from good (non adaptive) project management, consider when adaptive management is most useful on a program, and how adaptive a program (or part of a program) should be.

Evaluating programming that thinks and works politically: Challenges and emerging practice - Jacobstein, David; Swift, Sarah (New Directions for Evaluation, 2022)
Issues of power are not new to program evaluation. What is new is a consideration of how programming uses insights into incentives that shape and adapt implementation. How should one evaluate in a way that explicitly assesses the ways in which a program considers power? One of the innovative topics deriving from the democracy and governance space is the approach of thinking and working politically (TWP) which is seeing increased use in development programming. TWP suggests different mental models and practical approaches to achieving development objectives in ways that are more contextually grounded and informed by power dynamics. This article describes several of the core challenges to evaluation of TWP and also a rubric of considerations for more effective evaluation practices in this emerging field.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/ev.20527

Human Learning Systems: A practical guide for the curious - Lowe, Toby; Padmanabhan, Chandrima; McCart, Des; McNeill, Karen; Brogan, Andy; Smith, Mark (Centre for Public Impact, 2022)
Our new guide provides practical advice to help any organisation working in public service apply the Human Learning Systems approach to their work. In doing so, they will be better equipped to explore, learn and respond to the unique strengths and needs of each person, family and community they serve.

Context-monitoring for adaptive management - Pickwick, Sarah (World Vision, 2022)

Learning to change: The case for systemic learning strategies in the humanitarian sector - Ramalingam, Ben; Mitchell, John (ALNAP/ODI, 2022)
This paper presents the case for systemic organisational change in the humanitarian system. The paper firstly shows that that organisational learning has tended to reinforce existing ways of working and has not been able to shift a culture that values action over reflection. As a result, the rest of the paper asks about the most significant changes in the humanitarian sector

Nimble adaptation: Tailoring monitoring, evaluation, and learning methods to provide actionable data in complex environments - Serpe, Lauren; Ingram, Mason; Byom, Kate (New Directions for Evaluation, 2022)
This chapter examines good practices in implementing effective Monitoring, Evaluation, and Learning (MEL) systems within complex international development Democracy, Human Rights, and Governance (DRG) programs, which are characterized by challenges of non-linearity, limited evidence of theories of change, and contextual and politically contingent nature of outcomes. The chapter presents three cases of MEL systems in complex projects implemented by Pact across distinct and diverse operating contexts – Zimbabwe, Cambodia, and Somalia – to illustrate those projects’ MEL approaches that enabled continuous adaptation. The authors analyze the cases to respond to two questions: (1) What are the key elements of effective adaptive management-focused MEL systems in complex environments? (2) What is practical guidance for designing and enabling complexity-responsive and effective adaptive management-focused MEL systems? The case studies illustrate three key elements: (1) Information gathering that closely links context, research, and performance data; (2) Systems for reflection that offer scheduled learning moments of varying frequency and intensity, as well as multiple feedback mechanisms; and (3) Enabling structures that promote adaptive mindsets and attitudes within project teams.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/ev.20523

Storytelling for Systems Change: insights from the field - Thea Snow; David Murikumthara; Teya Dusseldorp; Rachel Fyfe; Lila Wolff; Jane McCracken (Centre for Public Impact, 2022)
Capturing the impact of community-led work The Centre for Public Impact, Dusseldorp Forum, and Hands Up Mallee have been exploring how stories can be used to more effectively communicate the impact of community-led systems change work. Community-led place based initiatives are modelling new ways of working - shifting away from top down, program-focussed approaches towards an approach grounded in systems thinking and community-led innovations. However, while these stories of change are sitting in communities, they’re often not being told or celebrated. We wanted to understand why this is, and what might be done to better enable these stories to be shared and heard. The story of storytelling We talked to a range of people to uncover the story of storytelling - including collective impact backbone team members, community members, storytelling experts, and those working in and around community-led systems change initiatives across Australia. We explored the roles stories play in different communities; what good storytelling looks like; what barriers to storytelling might be; and what role stories can play in supporting systems change. Our findings We have learned through this project that stories can be used both to change the system and to evaluate, understand and showcase the change that is occurring in communities. We have heard that different stories require different approaches – stories that are seeking to enable change look different to those that are seeking to celebrate change.

An introductory systems thinking toolkit for civil servants - UK Government (UK Government Office for Science, 2022)
This document is a an Introductory Toolkit for for civil servants. It is one component of a suite of documents that aims to act as a springboard into systems thinking for civil servants unfamiliar with this approach. These documents introduce a small sample of systems thinking concepts and tools, chosen due to their accessibility and alignment to civil service policy development, but which is by no means comprehensive. They are intended to act as a first step towards using systems thinking approaches to solve complex problems and the reader is encourage to explore the wider systems thinking field further.

CLA Maturity Tool - Card Deck (Implementing Partners version 1) - USAID LEARN (USAID, 2022)
USAID’s Bureau for Policy, Planning and Learning (PPL) and its support mechanism, LEARN, have developed a Collaborating, Learning, and Adapting (CLA) Framework and Maturity tool to help USAID missions think more deliberately about how to plan for and implement CLA approaches that fit the mission’s context and assist them in achieving their development objectives. While the tool is intended primarily for USAID audiences to be used in participatory self-assessment workshops, the CLA Framework and maturity spectrum are relevant to a wider audience. USAID’s CLA Framework identifies key components and subcomponents of daily work that may be opportunities for intentional, systematic, and resourced CLA. The framework recognizes the diversity of what CLA can look like in various organizations and programs while also giving CLA structure, clarity, and coherence across two key dimensions: • CLA in the Program Cycle: how CLA is incorporated throughout Program Cycle processes, including strategy, project, and activity design and implementation; and • Enabling Conditions: how an organization’s culture, business processes, and resource allocation support CLA integration. Recognizing that CLA is not binary—it’s not an issue of “doing it or not doing it”—PPL and LEARN have developed a spectrum of practice for each of the 16 subcomponents in the framework. The spectrum offers examples of what integration might look like at different stages: Not Yet Present, Emergent, Expanding, Advanced and Institutionalized. The maturity stage descriptions are only illustrative and are intended to spark reflection on current practice and opportunities for improvements. In this resource, each CLA subcomponent page describes the key concepts for that topic and includes a description of the maturity stages. Although the descriptions were originally developed for USAID, the majority of the concepts easily transfer or have equivalents in the partner community. For example, although organizations outside of USAID may not hold “Portfolio Reviews” (part of the Pause & Reflect subcomponent), the majority hold some type of meeting to review programmatic progress. This is the seventh version of the CLA Framework and maturity spectrum. PPL and LEARN will continue reviewed and periodically update them based on user feedback, so if you have comments about the content, please email learning@usaid.gov. We would also love to hear how you’ve used this content with your team or organization.

Collaborating, Learning and Adapting (CLA) Maturity Spectrum (v7) - USAID LEARN (USAID, 2022)
USAID’s Bureau for Policy, Planning and Learning (PPL) and its support mechanism, LEARN, have developed a Collaborating, Learning, and Adapting (CLA) Framework and Maturity tool to help USAID missions think more deliberately about how to plan for and implement CLA approaches that fit the mission’s context and assist them in achieving their development objectives. While the tool is intended primarily for USAID audiences to be used in participatory self-assessment workshops, the CLA Framework and maturity spectrum are relevant to a wider audience. USAID’s CLA Framework identifies key components and subcomponents of daily work that may be opportunities for intentional, systematic, and resourced CLA. The framework recognizes the diversity of what CLA can look like in various organizations and programs while also giving CLA structure, clarity, and coherence across two key dimensions: • CLA in the Program Cycle: how CLA is incorporated throughout Program Cycle processes, including strategy, project, and activity design and implementation; and • Enabling Conditions: how an organization’s culture, business processes, and resource allocation support CLA integration. Recognizing that CLA is not binary—it’s not an issue of “doing it or not doing it”—PPL and LEARN have developed a spectrum of practice for each of the 16 subcomponents in the framework. The spectrum offers examples of what integration might look like at different stages: Not Yet Present, Emergent, Expanding, Advanced and Institutionalized. The maturity stage descriptions are only illustrative and are intended to spark reflection on current practice and opportunities for improvements. In this resource, each CLA subcomponent page describes the key concepts for that topic and includes a description of the maturity stages. Although the descriptions were originally developed for USAID, the majority of the concepts easily transfer or have equivalents in the partner community. For example, although organizations outside of USAID may not hold “Portfolio Reviews” (part of the Pause & Reflect subcomponent), the majority hold some type of meeting to review programmatic progress. This is the seventh version of the CLA Framework and maturity spectrum. PPL and LEARN will continue reviewed and periodically update them based on user feedback, so if you have comments about the content, please email learning@usaid.gov. We would also love to hear how you’ve used this content with your team or organization.

Collaborating, Learning, and Adapting Framework & Key Concepts (Implementing Partner Version 1) - USAID LEARN (USAID, 2022)
Although collaborating, learning, and adapting (CLA) are not new to USAID and its implementing partners, they often do not happen regularly or systematically and are not intentionally resourced. The CLA Framework above identifies components and subcomponents to help you think more deliberately about what approach to CLA might be best tailored to your organizational or project context. The framework recognizes the diversity of what CLA can look like in various organizations and projects while also giving CLA structure, clarity, and coherence across two key dimensions: - CLA in the Program Cycle: how CLA is incorporated into planning and design processes throughout the Program Cycle in order to improve their effectiveness; and - Enabling Conditions: how an organization’s culture, daily operating processes, and resource allocation support CLA integration. Organizations need both integrated CLA practices appropriate for their context and conducive enabling conditions to become stronger learning organizations capable of managing adaptively. The framework stresses the holistic and integrated nature of the various components of CLA to reinforce the principle that CLA is not a separate workstream—it should be integrated into existing processes to strengthen the discipline of development and improve aid effectiveness.

Thinking and working politically: What have we learned since 2013 - Teskey, Graham (TWP Community of Practice, 2021)
The Thinking and Working Politically (TWP) Community of Practice (CoP) was established at a small meeting tacked on at the end of a meeting of Governance Advisers working for the United Kingdom’s Department of International Development (DFID) on South and South-East Asian countries, held in Delhi in November 2013. Since then, a number of meetings have been held throughout the world, each addressing different issues; ‘TWP’ has entered the lexicon of mainstream development; the CoP has expanded to more than 300 people; a Washington DC chapter has been established; and the International CoP has been granted modest funding from DFID’s successor, the Foreign, Commonwealth and Development Office (FCDO) and from Australia’s Department of Foreign Affairs and Trade (DFAT). It is legitimate to ask, however, what has been achieved operationally: how have the ideas underpinning TWP affected operational practice? This short paper traces the evolution of the idea and practice of TWP from 2013 to late 2021, and identifies what we have learned. What has been successful, and what has not? I asked in 2017 whether TWP had become a second orthodoxy (Teskey, 2017). Did this represent hubris or was 2017 in some ways the apogee of what might rather grandly be called the TWP ‘movement’?

Getting Real about Unknowns in Complex Policy Work - Andrews, Matt (Research on Improving Systems of Education (RISE), 2021)
As with all public policy work, education policies are demanding. Policy workers need to ‘know’ a lot—about the problems they are addressing, the people who need to be engaged, the promises they can make in response, the context they are working in, and the processes they will follow to implement. Most policy workers answer questions about such issues within the structures of plan and control processes used to devise budgets and projects. These structures limit their knowledge gathering, organization and sense-making activities to up-front planning activities, and even though sophisticated tools like Theories of Change suggest planners ‘know’ all that is needed for policy success, they often do not. Policies are often fraught with ‘unknowns’ that cannot be captured in passive planning processes and thus repeatedly undermine even the best laid plans. Through a novel strategy that asks how much one knows about the answers to 25 essential policy questions, and an application to recent education policy interventions in Mozambique, this paper shows that it is possible to get real about unknowns in policy work. Just recognizing these unknowns exist—and understanding why they do and what kind of challenge they pose to policy workers—can help promote a more modest and realistic approach to doing complex policy work.

Technical assistance: a practical account of the challenges in design and implementation - Nastase, Alexandra; Rajan, Alok; French, Ben; Bhattacharya, Debarshi (Gates Open Research, 2021)
Technical assistance is provided to country governments as part of international development programmes to support policymaking or strengthen state capability. This article presents the conceptual evolution of ‘technical assistance’ linked to capacity development, starting with programmes aiming exclusively to enhance individual capacity in the 1950s to 1970s and progressing to complex systems approaches in the past ten years. It also presents some of the frequent challenges in designing and implementing technical assistance, drawing from the existing literature and the authors’ experience in international development. The article summarises the latest thinking about delivering more effective development, including the adaptive management practices and the initiatives to strengthen evidence about what works. Finally, we complement this article with a follow-up open letter reflecting on the current policy options and opportunities for change.

System Innovation on Purpose - Leadbeater, Charles; Winhall, Jennie (The Rockwool Foundation, 2021)
In Building Better Systems, we introduced four keys to unlock system innovation: purpose and power, relationships and resource flows. These four keys make up a set. Systems are often hard to change because power, relationships, and resource flows are locked together in a reinforcing pattern to serve the system’s current purpose. Systems start to change fundamentally when this pattern is disrupted and opened up. Then a new configuration can emerge, serving a new purpose. In this essay series we delve deeper into these four keys and provide practical advice on how they can be put to use. This essay is about the role that purpose plays in orchestrating complex systems and how system innovators can create a new system around a new sense of purpose.

The Systems Work of Social Change: How to Harness Connection, Context, and Power to Cultivate Deep and Enduring Change - Rayner, Cynthia; Bonnici, François (OUP Oxford, 2021)
The issues of poverty, inequality, racial justice, and climate change have never been more pressing or paralyzing. Current approaches to social change, which rely on industrial models of production and power to "solve" social problems, are not helping. In fact, they are designed to entrench the status quo. In The Systems Work of Social Change, Cynthia Rayner and François Bonnici draw on two hundred years of history and a treasure trove of stories of committed social changemakers to uncover principles and practices for social change that radically depart from these approaches. Rather than delivering "solutions," these principles and practices focus on the process of change itself. Through rich storytelling and lucid analysis, Rayner and Bonnici show that connection, context, and power sit at the heart of the change process, ensuring broader agency for people and communities to create social systems that are responsive and representative in a rapidly changing world. Simple yet profound, this book distills a timely set of lessons for practitioners, leaders, scholars, and policymakers.

Building a culture of learning at scale: learning networks for systems change. - McKenzie, Fiona (Orange Compass & Paul Ramsay Foundation, 2021)
This scoping paper explores the question ‘what would it take to build a culture of learning at scale?’. It focuses on systems-wide learning that can help to inform systems change efforts in complex contexts. To answer this question, literature was reviewed from across diverse disciplines and the realms of education, innovation systems, systems thinking and knowledge management. This inquiry was also supported by in-depth interviews with numerous specialists from the for-purpose sector and the examination of several case studies of learning across systems. The goal was to derive common patterns to inform a ‘learning for systems change’ framework. Learning for systems change is critical when working with complexity. The dynamic nature of complex adaptive systems requires an ability to continually sense and learn from the system and adapt accordingly. This is because the nature of the challenge and ‘what works’ to meet the challenge is continually shifting (Lowe and Plimmer, 2019). This requires an ongoing process of iterative inquiry that draws upon wisdom and insights from across the system. Such learning challenges traditional siloes of expertise and organisational boundaries (Clarke et al., 2019). Learning is not simply a nice to have. It is critical for greater impact and improved outcomes, particularly in mission-driven organisations and initiatives (Price et al., 2019). In this paper, a ‘learning networks’ approach is proposed, one that draws upon individual, group and systems-wide learning to build capacity and resilience for systems change in uncertain environments. This fills a gap in the literature where the focus is largely on learning within organisations. Instead, the focus here is on what is required to support learning to occur across scales and boundaries - from the individual to system-wide. A simple meta-framework for developing learning networks is proposed that includes high level guidance on the enabling conditions - the mindsets, relationships, processes and structures- that would enable learning networks to flourish.

Twenty years of UK governance programmes in Nigeria - Piron, Laure-Hélène; Cummings, Clare; Williams, Gareth; Derbyshire, Helen; Hadley, Sierd (ODI, 2021)
This Flagship report analyses 20 years of governance programmes in Nigeria funded by the UK Department for International Development (DFID) and the Foreign, Commonwealth and Development Office (FCDO) in the North-western states of Jigawa (since 2001), Kano (since 2005) and Kaduna (since 2006), as well as the North-eastern state of Yobe (since 2011). The report’s main research question is whether, how, under what conditions and for whom UK-funded state-level governance programmes in Nigeria have contributed to sustained changes in governance, and related changes in health and education. ... The report concludes with the following recommendations: To international development partners: 1. Invest for the long term – 10 to 20 years – combining support for both state and nonstate actors. 2. Ensure programmes have the strategic-level mandate, managerial capacity and frontline staff skills to pursue politically savvy opportunities. 3. Take PEA to the next level by unpacking causal mechanisms, understanding incentives and designing interventions to make change happen. 4. Give governance programmes the ability to flex between core governance and service delivery issues. 5. Incentivise greater collaboration between governance and sector programmes. 6. Incentivise greater attention to gender, and to social inclusion beyond disability issues, in governance programming. To FCDO: 7. Empower and resource FCDO teams to enable TWP programmes, ensuring decision-making by country teams to respond to local priorities. 8. Re-imagine TWP for FCDO Nigeria, giving implementers the space to operate in TWP ways. 9. Incentivise stronger collaboration between PERL, Lafiya (health programme) and the Partnership for Learning for All in Nigerian Education. 10. Invest in impact data analysis. To partner governments in Nigeria and beyond: 11. Explicitly set out the objectives for which you would like to receive assistance. 12. Use TWP principles to decide how development partners can support your political objectives and the scope for politically-feasible and mutually-beneficial collaboration. 13. Invest in the coordination of development partners. To non-state partners in Nigeria and beyond: 14. Join coalitions to achieve your priorities. 15. Select development partners which can strengthen your skills, not just fund your activities.

Lessons for PFM Reform - the PDIA Approach in Africa - Bento, Joana (Public Financial Management Blog - IMF, 2021)
Some important lessons are as follows: First, identifying a policy problem is critical for reforms to get traction both at a political and administrative level. Second, appropriate solutions can emerge from a process of experimentation, iteration, and adaptation. Third, building teams and institutional capabilities is a critical part of solving complex problems in a sustainable way.

How Does Participatory Action Research Generate Innovation? Findings from a Rapid Realist Review - Snijder, Mieke; Apgar, J. Marina (Institute of Development Studies, 2021)
This Emerging Evidence Report shares evidence of how, for whom, and under what circumstances, Participatory Action Research (PAR) leads to innovative actions. A rapid realist review was undertaken to develop programme theories that explain how PAR generates innovation. The methodology included peer-reviewed and grey literature and moments of engagement with programme staff, such that their input supported the development and refinement of three resulting initial programme theories (IPTs) that we present in this report. Across all three IPTs, safe relational space, group facilitation, and the abilities of facilitators, are essential context and intervention components through which PAR can generate innovation. Implications from the three IPTs for evaluation design of the CLARISSA programme are identified and discussed. The report finishes with opportunities for the CLARISSA programme to start building an evidence base of how PAR works as an intervention modality, such as evidencing group-level conscientisation, the influence of intersecting inequalities, and influence of diverse perspectives coming together in a PAR process.
Accepted: 2021-07-23T08:48:45Z

What can Australia learn from the public service revolution taking hold in Europe? - Hurcombe, Sarah (Centre For Public Impact (CPI), 2021)
Sarah Hurcombe shares what she's learning from the public service revolution building momentum in Europe.

Designing a Participatory Programme at Scale: Phases 1 and 2 of the CLARISSA Programme on Worst Forms of Child Labour - Burns, Danny; Apgar, Marina; Raw, Anna (Institute of Development Studies, 2021)
CLARISSA (Child Labour: Action-Research-Innovation in South and South-Eastern Asia) is a large-scale Participatory Action Research programme which aims to identify, evidence, and promote effective multi-stakeholder action to tackle the drivers of the worst forms of child labour in selected supply chains in Bangladesh, Nepal, and Myanmar. CLARISSA places a particular focus on participants’ own ‘agency’. In other words, participants’ ability to understand the situation they face, and to develop and take actions in response to them. Most of CLARISSA’s participants are children. This document shares the design and overarching methodology of the CLARISSA programme, which was co-developed with all consortium partners during and since the co-generation phase of the programme (September 2018–June 2020). The immediate audience is the CLARISSA programme implementation teams, plus the Foreign, Commonwealth & Development Office (FCDO). This design document is also a useful reference point for other programmes trying to build large-scale participatory processes. It provides a clear overview of the CLARISSA programmatic approach, the design, and how it is being operationalised in context.

Complexity-Aware Monitoring and Evaluation - Hertz, Tilman; Brattander, Eva; Rose, Loretta (Journal of MultiDisciplinary Evaluation, 2021)
Background: Addressing today’s sustainability challenges requires adopting a systemic approach where social and ecological systems are treated as integrated social-ecological systems. Such systems are complex, and the international development sector increasingly recognises the need to account for the complexity of the systems that they seek to transform. Purpose: This paper sketches out the elements of a complexity-aware monitoring and evaluation (M&E) system for international development programmes in the area of sustainable development.  Setting: Not applicable. Data Collection and Analysis: The authors draw on existing literature on complexity and evaluation and on their own experience from working in the field of M&E. Findings: An M&E system should not be seen simply as a tool to track compliance against a pre-determined theory of change. Instead, it is most useful as a real-time approach, constantly defining and re-defining narratives for change that help push systems along trajectories of interest. Dealing with complexity involves embracing uncertainty; and this challenges established notions of accountability—something which funders and implementers must begin to redefine together. Keywords: monitoring; evaluation; complexity; social-ecological systems; international development programmes; narratives for change; theory of change
Number: 41

Energy Governance in Developing Countries — A New Approach - Mcculloch, Neil (The Policy Practice & Chemonics, 2021)
In 2015, leaders from around the world agreed to 17 Sustainable Development Goals (SDGs) to be achieved by 2030. The seventh goal (SDG7) is: “Ensure access to affordable, reliable, sustainable and modern energy for all.” In the same year, the world’s leaders concluded the Paris Agreement to tackle climate change, which will require a global transition in the energy sector away from the use of fossil fuels. Yet, despite growing investments in clean energy in many developing countries, the transition is happening much more slowly than needed. The central reason for this is poor energy governance. This technical brief shows how poor energy governance damages energy access and efforts to improve the quality and reliability of power. It explains the political reasons why energy governance is so bad in many countries and contrasts this with the current system of procuring technical assistance, which largely ignores the energy governance challenge. It shows that a new approach to tackling energy governance is emerging that is better matched to the nature of the problems faced and provides recommendations on how to implement it.

Why Tackling Energy Governance in Developing Countries Needs a Different Approach - McCulloch, Neil (The Policy Practice & Chemonics, 2021)
Global efforts to improve energy access and quality and to tackle climate change need a different approach to addressing poor energy governance. In 2015, leaders from around the world agreed to 17 Sustainable Development Goals (SDGs) to be achieved by 2030.1 The seventh goal (SDG7) is “Ensure access to affordable, reliable, sustainable and modern energy for all.” In the same year, the world’s leaders concluded the Paris Agreement to tackle climate change, which will require a global transition of the energy sector away from the use of fossil fuels. Yet, in many developing countries, despite growing investments in clean energy, the transition is happening much more slowly than needed to achieve SDG7 and avert damaging climate change. The central reason for this is poor energy governance. This paper outlines the size and nature of the energy challenge, with a focus on electricity. It describes the investments that are currently being made to improve the quality of power and access to electricity — and the growing evidence that investments often fail due to poor energy governance. The paper then delves more deeply into how bad governance influences the quality of and access to electricity, with specific country examples. It shows the importance of understanding how electricity fits into the political settlement of a country and how this affects the incentives of key actors in the sector. Unfortunately, donor projects designed to widen electricity access or to support reform of the power sector in developing countries often pay too little attention to the problem’s political nature; the same is true of measures to improve energy efficiency or to promote renewables. The paper outlines a new way of thinking about energy governance and shows how interventions can be better matched to the different governance challenges that they face. It concludes with recommendations for donors on how energy programs can be better designed and procured — as well as recommendations for implementors on how to improve the chances of successful implementation by adapting to the political realities of the contexts in which they operate.

Learning to adapt & adapting to learn - Using elements of outcome mapping in the ‘Resilient Adolescents in the Syria Crisis’ programme - van Ongevalle, Jan; Kvintradze, Ana; Rennesson, Gaël; Miller, David (Save the Children, 2021)
This learning paper highlights how elements of outcome mapping were used by Save the Children Sweden in a project (2018-2020) that supports adolescents, affected by the Syria crisis, to become more resilient. The paper first outlines how the spheres of influence framework has been applied to develop an actor focused theory of change. It then describes how progress markers, as an alternative to SMART indicators, were formulated to monitor the programme’s results. The paper also outlines how long lists of progress markers were categorised in a more realistic and practical results framework. The paper then continues to elaborate how outcome journals, qualitative data analysis techniques and regular review meetings and reflection workshops were utilised for data collection, for collective learning among programme stakeholders and for informing planning and programme adjustment. Various practical guidelines and tips on how to implement elements of outcome mapping are provided. The final part of the paper explores to what extent outcome mapping was able to foster several key enablers of adaptive programme management and highlights some of the challenges that programme stakeholders faced. Practical recommendations towards the use of outcome mapping in future programmes are also proposed.

Applying Systems Thinking to Education: The RISE Systems Framework - Spivack, Marla (Research on Improving Systems of Education (RISE), 2021)
Many education systems in low- and middle-income countries are experiencing a learning crisis. Many efforts to address this crisis do not account for the system features of education, meaning that they fail to consider the ways that interactions and feedback loops produce outcomes. Thinking through the feedback relationships that produce the education system can be challenging. The RISE Education Systems Framework, which is sufficiently structured to give boundaries to the analysis but sufficiently flexible to be adapted to multiple scenarios, can be helpful. The RISE Framework identifies four key relationships in an education system: politics, compact, management, and voice and choice; and five features that can be used to describe these relationships: delegation, finance, information, support, and motivation. This Framework can be a useful approach for characterising the key actors and interactions in the education system, thinking through how these interactions produce systems outcomes, and identifying ways to intervene that can shift the system towards better outcomes.

We have experimented with different approaches to systems transformation — here are five insights - Haldrup, Søren Vester (UNDP Innovation, 2021)
At UNDP Innovation we are on a journey to shift our approach to innovation to help tackle complex development challenges. In short, we are moving away from single point solutions, and instead we are…

PDIA in action - Andrews, Matt; Samji, Salimah (Center for International Development, Harvard University, 2021)
Learning from our experience in 2020, we asked the alumni of our HKS Implementing Public Policy (IPP) Executive Education program, if they wanted to work with our students on their nominated problems. Eight IPP alumni, William Keith Young, Adaeze Oreh, Milzy Carrasco, Kevin Schilling, Artem Shaipov, George Imbenzi, David Wuyep, and Raphael Kenigsberg, who had been trained on PDIA and implementation, signed up to work with our students. Thirty-seven students signed up to take the course beginning January 26th, 2021. The students worked across eight teams and adopted a problem driven approach to foster learning that could help their authorizers develop an action learning strategy to their nominated challenge. This book highlights the students’ work drawing from their blogs as well as the event series. There are 8 sections, one for each of the teams and the problems they worked on during the course. We hope you enjoy reading their stories! Scan the QR Code at the end of each section to learn more.

How to do Adaptive Management in 15 easy steps – from a top new toolkit – FP2P - Green, Duncan (From Poverty to Power, 2021)

A top Toolkit on Adaptive Management. But is that a good idea? – FP2P - Green, Duncan (From Poverty to Power, 2021)

Building a Movement of Public Problem Solvers - Building State Capability - Samji, Salimah (Building State Capability, 2021)
Solving public problems is a hard and thankless job. One that is undertaken with a shortage of time as well as resources, and often under pressure to deliver results. A common approach used to solve public problems is to develop a plan, sometimes with experts, and then to assume that implementation will happen on autopilot. To quote Mike Tyson, “Everyone has a plan ’till they get punched in the mouth.” The question is, what do you do after you get punched? Continue with your existing plan? Or do you learn from the punch?

Implementing adaptive management: A front-line effort — Is there an emerging practice? - Teskey, Graham; Tyrrel, Lavinia (Abt Associates, 2021)
Among the many principles that currently inform donor-funded development initiatives, three appear to stand out: they should be politically informed, locally led, and adaptive. There is as yet little practical guidance for aid implementers regarding how to operationalise these approaches. What will it take to shift practice away from linear and planned approaches, towards models which foster local leadership and which engage with emergent and complex systems? This paper suggests that the answer is not to throw out the discipline of the logical framework, results frameworks, or theories of change. Rather they need to be handled rather more reflectively and ‘elastically’. The purpose of this paper is to set out how this can be achieved, and to propose 15 tools for donors, implementors and front-line staff to apply adaptive management (AM) in practice, at critical stages of the project cycle and within the dominant aid paradigm. This is what we are calling PILLAR: politically informed, locally led and adaptive responses. We are framing PILLAR to cover the full project cycle (design, implementation and review), hence the nomenclature of an ‘end to end’ approach. Our hope is that these tools will eventually replace the current planned, log-frame driven and top-down approach to aid design and delivery which dominates the development sector.

A Guide to Assessing the Political Economy of Domestic Climate Change Governance - Worker, Jesse; Palmer, Niki (World Resources Institute, 2021)
This paper discusses how understanding the domestic political economy of climate governance is critical for developing informed strategies to build and sustain political ambition. It provides guidance and a methodology for domestic stakeholders to determine the types of institutional reforms, incentives, coalitions, and policy design that can entrench long-term political support for climate ambition. The assessment can also help users identify political barriers to more equitable climate action and identify reforms that may strengthen inclusion and accountability. EXECUTIVE SUMMARY Highlights ▪ There is overwhelming evidence of the social, economic, and environmental case to reduce greenhouse gas (GHG) emissions and rapidly scale up adaptation. Yet, despite a proliferation of climate laws and policies over the last 10–15 years, emissions are still rising, and adaptation needs remain urgent. ▪ This calls for a more sophisticated assessment of the political economy factors that may enable or constrain implementation of policies and actions and sustain political commitment at the country level. ▪ This guide offers an assessment methodology to understand how structural factors, rules and norms, stakeholders and interests, and ideas and narratives influence the political economy of climate action in a given country context. ▪ The methodology was developed on the basis of climate policy, governance, and political economy literature with contributions from subject matter experts. ▪ We intend the assessment to support civil society coalitions, reform-minded civil servants and politicians, international organizations, and other stakeholders. ▪ The resulting analysis should deepen the understanding of context while informing the advocacy, policy design, coalition building, capacity building, and communications of domestic stakeholders.

The Future of Development: “Make Happen” with Portfolios of Options - CHÔRA Foundation (CHÔRA Foundation, 2021)
This Green Paper intends to review key elements of the problem that Development actors will confront as a new decade opens up ahead of us. It will articulate a solution that we believe should become an inherent feature of Development programs and initiatives. This is the outcome of an intense period of experiences and reflections in the Development space across different geographies and institutional mandates and activities, during which the Foundation has collaborated with institutions such as the UNDP and Grand Challenges Canada. At the heart of our collaborations is a Strategic Innovation and System Transformation Framework, with its associated concepts, working definitions, processes, tools and people. Sourced from CHÔRA Foundation’s knowledge and practice assets, this is a capability we intend to make relevant, customise, scale up and distribute to our partners and stakeholders. We are looking to create with them a space that offers the world a transformational capability. Central to this capability we see a distinctive and robust practice: the design and dynamic management of Portfolios of Strategic Innovation and System Transformation Options. These Portfolios are unique, context relevant, embedded mechanisms for learning, sensemaking and problem solving that social systems leverage to have an impact on themselves and their problems, and to induce the transformations that are necessary to them. It is our view that Portfolios of Options are the most effective means by which human social systems can supply themselves with budgets of possibility that ensure choice and create opportunity. They will also support pragmatic evolutionary outcomes and enable resilience.

LearnAdapt: a synthesis of our work on adaptive programming with DFID/FCDO (2017–2020) - Laws, Ed; Pett, Jamie; Proud, Emma; Rocha Menocal, Alina (ODI, 2021)
Key takeaways. • Development is not linear or straightforward, but rather complex, uncertain and context-specific. This calls for international development actors to work differently, in ways that are based on deliberate experimentation, learning and adaptation, to inform decisions and drive effective development. • Although it might go by different names, adaptive programming has been used in a variety of areas and fields in both the public and private sectors. Development practitioners have much to learn from and contribute to these different approaches and experiences. • Trust and relationship-building across all relevant stakeholders are among the most critical enabling factors for adaptive management. They are essential to give partners the space, autonomy and authority needed to try, test, reflect, iterate and feed back at the frontline of implementation, and to give donors the confidence that decisions are being made on the basis of evidence and learning to improve effectiveness. • There is an urgent need to rethink how accountability requirements, results frameworks, value for money considerations, performance markers, procurement and contracting mechanisms and other processes are understood and applied so that they are better aligned with and can support adaptive management more effectively. • The role of senior managers leading adaptive programmes from the donor side should be to create a space for experimentation and learning. Funders should hold their partners accountable for learning and how it feeds into effective programming, rather than for delivering on predetermined targets. • While formal guidance is important, leadership, champions, institutional incentives, a supportive management culture and appropriate mindsets are essential to encourage adaptive ways of working. • Adaptive management is resource-intensive. It requires skill, commitment, time for building trust and investments in learning. It is a journey, not an immediate destination – so it calls for patience, open-mindedness and a more nuanced approach to risk.

Value for money and adaptive programming - Approaches, measures and management - Laws, Ed; Valters, Craig (ODI, 2021)
- The United Kingdom’s Foreign, Commonwealth and Development Office (FCDO)’s standard economy, efficiency, effectiveness/cost-effectiveness and equity (4E) framework is still relevant for approaching, measuring and managing value for money (VfM) for adaptive programmes. • However, this framework needs to be reframed to capture and incentivise flexibility, learning and adaptation. • VfM appraisal and reporting should be done in a way that draws on beneficiary feedback and informs good decision-making, rather than just being a compliance exercise. • If VfM appraisal and reporting cannot be done appropriately for adaptive programmes, it should be avoided or minimised. There is a risk of diverting time and resources from more suitable tools and methods.

Adaptive Learning Guide: A pathway to stronger collaboration, learning, and adapting - Ross, Joey; Karlage, James; Etheridge, James; Alade, Mayowa; Fifield, Jocelyn; Goodwin, Christian; Semrau, Katherine; Hirschhorn, Lisa (USAID MOMENTUM Knowledge Accelerator, 2021)
The purpose of this Adaptive Learning Guide is to provide MOMENTUM project teams with the information and resources to integrate adaptive learning into the design, implementation, and improvement of MNCH/FP/RH programs. This guide provides a conceptual introduction to adaptive learning using links to existing resources and real-world examples of how adaptive learning can drive continuous learning and improvement in project work. The guide is built upon three foundational assumptions: We work in dynamic, often unpredictable environments. Unexpected turns of events will occur. Progress is rarely, if ever, linear. Integrating the principles and practices of USAID’s Collaborating, Learning, and Adapting Toolkit into projects and initiatives requires designing for learning and adaptation. We intend the guide to serve as a “starting point” for interested individuals and teams to begin or strengthen the processes that support the integration of adaptive learning into project work.

Opportunities and challenges for DAC members in ‘adapting to context’ - Sharp, Samuel; Wild, Leni (2021)
Key Messages New principles for OECD DAC members on ‘Managing for Sustainable Development Results’ emphasise tailoring result management approaches to different contexts; balancing internal compliance with empowerment at ground level; and adapting implementation in the pursuit of long-term outcomes. However development organisations face numerous challenges in aligning with these principles in practice. Reporting and evidence collection processes do not consistently encourage adaptive practice, reflecting their orientation towards accountability over learning. Context analysis is common during programme design, but used less on an ongoing basis. Popular tools –such as logical frameworks and theories of change - are often intepreted in linear ways, not as ‘living documents’ that react and change over time. Organisations need to meaningfully empower staff to work adaptively, including examining incentives and cultures that can make staff more comfortable with traditional results management. Even when senior leadership is supportive of adaptive ways of working, they can lack a clear understanding of the resourcing required and appropriate governance and management processes. Development organisations and their partners have attempted to address these challenges through the use of different monitoring and evaluation tools and methods, changes to reporting frameworks and templates, and initiatives to create positive incentives and motivate staff, leadership and partners at different levels.
Keywords: _tablet

Peer reviews - Guidance for facilitators and participants - Wadley, Ian (Centre for Humanitarian Dialogue, 2021)
Essential points for practitioners and donors • Mediation offers a cost-effective and proven method for resolving armed conflict. Between 1985 and 2015, 75 per cent of armed conflicts in the world were resolved through agreement rather than by force. In most cases these processes will have involved third party facilitation or support. • Professional mediators understand the high stakes involved in their work to prevent, mitigate and resolve armed conflict. In addition, they and their financial supporters are increasingly required to demonstrate ‘value-for-money’ to ensure continued funding. • However, traditional monitoring and evaluation (M&E) methods are not well suited to this task, typically imposing artificially linear project models on a dynamic conflict situation, as well as compliance reporting that moves attention away from real value. • Traditional M&E methods tend to focus on documenting the past and generating vast amounts of data, rather than enabling timely adaptation of the project in the present. • Traditional M&E approaches rely heavily on external evaluation consultants. Even in the best of cases this may interfere with the mediation process and impose a heavy time burden on the project team, leading to low acceptance of traditional M&E approaches by mediation practitioners. • In contrast, an ideal M&E approach for mediation should deliver useful insights in even the most dynamic and sensitive mediation environments, impose a light reporting burden, and be readily accepted by mediation teams. It should protect discretion and trust, enable rapid adaptation, and also provide some assurance that donor funds are being well spent.

Doing Development Differently - Wild, Leni (Stanford Social Innovation Review, 2021)
International aid must use different approaches to address the massive systemic problems it seeks to solve.
Keywords: ⛔ No DOI found

A Political Economy Analysis Framework for EdTech Evidence Uptake - Pellini, Arnaldo; Nicolai, Susan; Magee, Arran; Sharp, Sam; Wilson, Sam (The EdTech Hub, 2021)

Assumptions and triple loop learning - Aston, Thomas (Medium, 2021)
Triple loop learning

Adaptive Management: Learning and Action Approaches to Implementing Norms-shifting Interventions - McLarnon, Courtney; Gayles, Jennifer; Deepan, Prabu (USAID / Passages, 2021)
What Passages has Learned about Adaptive Management: • Be reflective about information that is collected and create a culture of learning. • Be systematic about establishing monitoring and learning systems. • Be strategic about data sources and analysis, prioritizing areas for learning and addressing issues raised. • Be inclusive about information collection: who is collecting what, how, and how is it being used.

A Systems Framework for International Development: The Data-Layered Causal Loop Diagram - Blair, Courtney; Gralla, Erica; Wetmore, Finley; Goentzel, Jarrod; Peters, Megan (Production and Operations Management, 2021)
Meeting the United Nations Sustainable Development Goals (SDGs) will require adapting or redirecting a variety of very complex global and local human systems. It is essential that development scholars and practitioners have tools to understand the dynamics of these systems and the key drivers of their behavior, such as barriers to progress and leverage points for driving sustainable change. System dynamics tools are well suited to address this challenge, but they must first be adapted for the data-poor and fragmented environment of development work. Our key contribution is to extend the causal loop diagram (CLD) with a data layer that describes the status of and change in each variable based on available data. By testing dynamic hypotheses against the system's actual behavior, it enables analysis of a system's dynamics and behavioral drivers without simulation. The data-layered CLD was developed through a 4-year engagement with USAID/Uganda. Its contributions are illustrated through an application to agricultural financing in Uganda. Our analysis identified a lack of demand for agricultural loans as a major barrier to broadening agricultural financing, partially refuting an existing hypothesis that access to credit was the main constraint. Our work extends system dynamics theory to meet the challenges of this practice environment, enabling analysis of the complex dynamics that are crucial to achieving the SDGs.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/poms.13492

Change: How to Make Big Things Happen - Centola, Damon (Little, Brown Spark, 2021)
How to create the change you want to see in the world using the paradigm-busting ideas in this "utterly fascinating" (Adam Grant) big-idea book.​ Most of what we know about how ideas spread comes from bestselling authors who give us a compelling picture of a world, in which "influencers" are king, "sticky" ideas "go viral," and good behavior is "nudged" forward. The problem is that the world they describe is a world where information spreads, but beliefs and behaviors stay the same. When it comes to lasting change in what we think or the way we live, the dynamics are beliefs and behaviors are not transmitted from person to person in the simple way that a virus is. The real story of social change is more complex. When we are exposed to a new idea, our social networks guide our responses in striking and surprising ways. Drawing on deep-yet-accessible research and fascinating examples from the spread of coronavirus to the success of the Black Lives Matter movement, the failure of Google+, and the rise of political polarization, Change presents groundbreaking and paradigm-shifting new science for understanding what drives change, and how we can change the world around us.

Engage. Empower. Enact. - Citizen Engagement & Democratic Innovation Programme White Paper - Doyle, Linda; Smith, Bethan (Cognitive Edge, 2021)
The Cynefin Centre’s Citizen Engagement & Democratic Innovation programme provides tools for collective sense-making in the areas of community development and youth work; civic engagement and democratic innovation; collaborative service/policy design and evaluation; housing/tenant engagement; futures and planning; shared learning and peer to peer knowledge exchange.

Co-Creating Digital Public Services - Jarke, Juliane (Co-creating Digital Public Services for an Ageing Society: Evidence for User-centric Design, 2021)
This chapter reviews key literature and concepts relating to the co-creation of digital public services. For this task, it is firstly important to consider what kind of digital public services may be suitable for co-creation. In order to do so, the first section of this chapter defines what a digital public service is (e.g. with respect to different types of service providers, different types of services and service delivery) and considers what kind of digital public services allow for meaningful citizen participation. To better conceptualise different degrees of participation, the subsequent section reviews Arnstein’s (1969) “ladder of citizen participation” and related work. This allows distinguishing between different degrees of non-participation, (consultative) participation and beyond. Thirdly, the chapter reviews traditional participatory approaches that provide the basis to co-creating of digital public services: (1) co-production of public services, (2) co-design and (3) civic open data use. The chapter summarises and compares the different rationales for participation in these approaches, and reviews how they understand the sharing of control, the sharing of knowledge and the enabling of change.
Keywords: Civic Tech; Co-creation; Co-design; Co-production; Digital public services; Open data; Open government; Participation; Participatory design; User-centric services; e-services

Co-creating Digital Public Services for an Ageing Society: Evidence for User-centric Design - Jarke, Juliane (Springer International Publishing, 2021)
This open access book attends to the co-creation of digital public services for ageing societies. Increasingly public services are provided in digital form; their uptake however remains well below expectations. In particular, amongst older adults the need for public services is high, while at the same time the uptake of digital services is lower than the population average. One of the reasons is that many digital public services (or e-services) do not respond well to the life worlds, use contexts and use practices of its target audiences. This book argues that when older adults are involved in the process of identifying, conceptualising, and designing digital public services, these services become more relevant and meaningful.The book describes and compares three co-creation projects that were conducted in two European cities, Bremen and Zaragoza, as part of a larger EU-funded innovation project. The first part of the book traces the origins of co-creation to three distinct domains, in which co-creation has become an equally important approach with different understandings of what it is and entails: (1) the co-production of public services, (2) the co-design of information systems and (3) the civic use of open data. The second part of the book analyses how decisions about a co-creation project’s governance structure, its scope of action, its choice of methods, its alignment with strategic policies and its embedding in existing public information infrastructures impact on the process and its results. The final part of the book identifies key challenges to co-creation and provides a more general assessment of what co-creation may achieve, where the most promising areas of application may be and where it probably does not match with the contingent requirements of digital public services. Contributing to current discourses on digital citizenship in ageing societies and user-centric design, this book is useful for researchers and practitioners interested in co-creation, public sector innovation, open government, ageing and digital technologies, citizen engagement and civic participation in socio-technical innovation.

Don’t Build It: A Guide For Practitioners In Civic Tech / Tech For Development - Jordan, Luke (Grassroot and MIT Governance Lab, 2021)
If you just remember these... If you can avoid building it, don’t build it; if you have to build it, hire a CTO, ship early, and mature long; and no matter what, draw on a trusted crew, build lean and fast, and get close to and build with your users as soon as possible. — This guide aims to help you avoid bad projects, structure the team right, ship and learn quicker, and mature longer. The guide starts with project selection, including why the best project to select is no project at all. It moves on to team structure, and the extreme importance of a full-time senior tech lead (or chief technology officer (CTO), understood as an excellent engineering manager). It then covers timelines, emphasizing shipping early but having enormous patience getting to maturity, above all in finding product-use-fit, and avoiding vanity metrics. The guide then goes into some detail on hiring, covering the CTO role, senior contractors, designers and young engineers. The longest section, by some distance, is that on hiring. Hiring is the one thing considered critical in every piece of the lore, by founders and investors and managers alike, across all sectors. It is also the field in which I think I got it mostly right, and for reasons I can explain in ways that I believe will be helpful.

Agile: A New Way of Governing - Mergel, Ines; Ganapati, Sukumar; Whitford, Andrew B. (Public Administration Review, 2021)
The evolving concept of “agile” has fundamentally changed core aspects of software design, project management, and business operations. The agile approach could also reshape government, public management, and governance in general. In this Viewpoint essay, the authors introduce the modern agile movement, reflect on how it can benefit public administrators, and describe several challenges that managers will face when they are expected to make their organizations more flexible and responsive.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/puar.13202

Modelo HIP - Hexágono de la innovación pública - Oliván Cortés, Raúl (2021)

Online Learning and collaborative platform for systems thinking and systems change - SI (Systems Innovation, 2021)

Managing complexity (and chaos) in times of crisis. A field guide for decision makers inspired by the Cynefin framework - Snowden, Dave; Rancati, Alessandro (Publications Office of the European Union, 2021)
This field guide helps to navigate crises using the Cynefin framework as a compass. It proposes a four-stage approach through which we can: - assess the type of crisis and initiate a response; - adapt to the new pace and start building sensing networks to inform decisions; - repurpose existing structures and working methods to generate radical innovation; - transcend the crisis, formalise lessons learnt and increase resilience. The guide stresses the importance of setting and managing boundaries, building informal structures, keeping options open, distributing engagement and keeping an ongoing assessment of the evolving landscape. Action items, real life examples and demonstrations complement the references to the developing theoretical framework.

Thinking Tools Studio - Waters Center (Waters Center for Systems Thinking, 2021)
Tools to help you Think

What have we learned about learning? Unpacking the relationship between knowledge and organisational change in development agencies - Yanguas, Pablo (DIE - Deutsches Institut für Entwicklungspolitik, 2021)
Development cooperation has spent decades wrangling over the merits, evidence, and implications of what we may term “the learning hypothesis”: the idea that increased knowledge by development organisations must logically lead to increased effectiveness in the performance of their development activities. Organisations of all stripes have built research and monitoring and evaluation (M&E) departments, adopted a multitude of knowledge management systems and tools, and tinkered with different ways to structure their organograms to stimulate knowledge sharing and learning. The topic of organisational learning is particularly significant as the global development community grapples with increasingly complex problems and the aspiration of evidence-based policymaking. This paper presents an analytical framework for interrogating “the learning hypothesis”, breaking it down into causal steps: knowledge causes learning, learning causes organisational change, change causes effectiveness. The framework focuses on the first two sub-hypotheses, mapping out the conceptual space around them by outlining potential relationships between different types of knowledge – tacit and explicit, internal and external – and between different types of learning – operational and strategic. This map provides a foundation for three key research questions: What impact has the rising knowledge agenda had on development organisations? Which factors appear to enable or inhibit organisational learning? What is the relationship between operational and strategic learning and organisational change? A review of available evaluations and studies, including two cases from former UK Department for International Development (DFID) and the World Bank, reveals that there is insufficient evidence to support the causal claim that knowledge leads to learning and thereby to organisational change in development agencies. Sources point to tacit learning prevailing while explicit knowledge management systems flounder, and external advocacy agendas appear more compelling than internal research and evaluation products. It is not entirely clear how, or indeed, whether operational and strategic learning intersect, with delivery-level lessons hardly aggregating into structural or policy shifts. Organisational change – even that aimed at enhancing learning – is rarely based on lessons learned from practice. More research is necessary to fully unpack the learning hypothesis, but what limited evidence is available disproves rather than confirms its central claim. This has significant implications for the future of learning in development agencies as advocated by thought leaders, researchers, and reformers. In particular, the latter should consider an evidence-based reassessment of the function and value-for-money of research and M&E in development practice, and a more critical examination of the politics of external advocacy efforts around innovative aid approaches like thinking and working politically, adaptive management, or results-based management.
Publisher: German Development Institute / Deutsches Institut für Entwicklungspolitik (DIE) Version Number: 1.0

Intervention or Collaboration? Redesigning Information and Communication Technologies for Development. - Bon, Anna (2020)
How can we design and build digital technologies to support people in poor and low resource environments to achieve their objectives? And how can we do this inclusively and ethically, while considering the complexity of their living and working environments? This is the central question in my research. One of the grand challenges of international development cooperation is to make digital technologies available for social and economic development of poor regions of the world. To achieve this goal – often referred to as ICT4D – knowledge and technologies are transferred from wealthy countries to poor regions. Nevertheless, these efforts have often turned out unsuccessful and unsustainable, despite large budgets and numerous projects in prestigious international development programs. Mismatch between the transferred technologies and the target environment is a recurrent problem of ICT4D projects. Improvement can be achieved, for example, by involving end-users in the design process. International development organizations are aware of this, and terms like "co-creation", "participation" and "user-oriented design" have nowadays become part of the international development discourse. However, real co-creation and user-centered design are incompatible with unidirectional transfer of technologies and knowledge (this is how ICT4D is commonly organized, in conventional international development). Moreover, the term participation becomes meaningless, in the light of externally formulated development goals. One key question to ask is: what do the envisaged users want? Remarkably, many ICT4D projects, programs and policies do not really ask and (field) investigate this question, which can only be answered by extensive research on-the-ground. This thesis describes the search for and the design of an alternative approach to ICT4D. Ten years of field and action research with partners in Mali, Burkina Faso, and Ghana have led to a collaborative, iterative and adaptive approach, dubbed "ICT4D 3.0". What is novel of this alternative approach and how does it answer the central question? First of all, ICT4D 3.0 is a practical approach for critical investigation and action. It consists of a reconfigurable framework that guides the design and development of information systems, bridging the knowledge gap between developers and users to unlock and integrate different domains of (global, local, indigenous, academic, nonacademic) knowledge. It targets complex, resource-constrained environments where many (for the ICT developers and researchers) unfamiliar conditions or obstacles may exist. It fosters innovative capacity and learning in action, bringing together people with different backgrounds and perspectives in trans-disciplinary and multicultural teams. It is socio-technical, result-oriented, focused on the objectives of the stakeholders and the requirements of their livelihoods. This approach has been validated in various different contexts, by users, ICT developers, practitioners and students. Second, ICT4D 3.0 contributes to a theoretical understanding of ICT4D as a process of networked innovation in complex (adaptive) systems. The underlying idea is that knowledge sharing and diffusion of innovations are complex (non-linear) dynamic processes that evolve and propagate through social networks in rather unpredictable ways, whereby innovation works out differently, depending on context, and whereby contextual (e.g. social, cultural, environmental, political) factors play an important role, and have to be considered. This theoretical framework explains the effectiveness of a collaborative, iterative, adaptive approach in ICT4D. Third, ICT4D 3.0 is built on ethical principles. When reflecting on the meaning and purpose of digital development, it is clear that digital development is not only a question of technology and practice, and collaboration is more than a prerequisite for successful technological innovation and long-term sustainability: collaboration is a fundamental human, ethical value. Therefore, as a reflective practitioner, one has to ask oneself whose interests one is actually looking after, which goals one is trying to achieve, where they come from, how power and political issues play a role and which core values are at stake. This makes ICT4D 3.0 into a democratic process of dialogue and deliberation, in which all voices are heard, in which the local context and complexity are central and in which development goals are determined by the users themselves and not imposed from outside. In this light, the approach proposed in this thesis takes a value position and can be considered a decolonial approach, striving for democracy, emancipation, autonomy and social and economic betterment. Field experience shows that ICT4D can be a meaningful, collaborative, networked process of knowledge sharing, driven by local initiatives, realizing change for the better, in a complex world.

Risk navigation for Thinking and Working Politically: The work and disappearance of Sombath Somphone - Sims, Kearrin (Development Policy Review, 2020)
Abstract Motivation On December 15, 2012 Sombath Somphone was abducted at a police checkpoint in his home city of Vientiane, the capital of Laos; his whereabouts remain unknown. This article considers his work and disappearance through the lens of Thinking and Working Politically (TWP) approaches to development. The article is supportive of TWP, but emphasizes the significant risks of politicized programming in authoritarian contexts. Purpose By examining the case of Sombath Somphone, the article seeks to offer insights for safer, and more effective, TWP programming. It considers how specific events in authoritarian contexts can suddenly reposition development workers and/or organizations as political dissidents. Approaches and Methods The argument draws on analysis of grey literature; conversational and observational knowledge accrued during 18 months of fieldwork in Laos between 2011 and 2018; on‐going formal and informal interviews with members of Laos’ civil society sector; and extensive dialogue with Sombath Somphone’s wife, Ng Shui Meng. Findings The article identifies four key factors that contributed to the enforced disappearance of Sombath Somphone: international exposure; timing; particular elites; and strategies of oppression. It highlights the need for further consideration of how to anticipate and mitigate the dangers of politically oriented development work, as well as the different forms of risk experienced by local and international development actors working in authoritarian contexts. Policy Implications TWP has much to offer to development practice, but its contributions should not threaten the safety of local development actors. More attention must be given to preventing and mitigating such risks.

Instituciones que aprenden - Informe para la XXVII Cumbre Iberoamericana de Jefes y Jefas de Estado y de Gobierno - Oliván Cortés, Raúl (XXVII Cumbre Iberoamericana, 2020)
La pandemia de la Covid-19 ha brotado súbitamente en un momento de transición para las instituciones y organizaciones sociales de medio mundo. Cuando aún no se había superado la crisis de confianza de la última década entre los ciudadanos y los gobiernos, en un momento de gran impulso de las iniciativas de gobierno abierto, planes de innovación y transformación digital, para hacer más democráticas y eficientes las administraciones a través de programas políticos encaminados a configurar un nuevo contrato social, verde y digital en el marco de la Agenda 2030; el coronavirus ha provocado un shock histórico alterando el decurso del siglo XXI y exigiendo una aceleración de todos los procesos en marcha. La complejidad y dimensión de la pandemia ha puesto de manifiesto la necesidad de arquitecturas institucionales más flexibles, ágiles y resilientes, que sean capaces de incorporar toda la energía civil para aprender de su talento y creatividad, dándole mayor protagonismo a la ciudadanía (activistas, emprendedores, tejido asociativo, academia, makers…) no solo en la toma de decisiones sino también en el diseño e implementación de las estrategias. Conforme se centrifugaba a millones de empleados a teletrabajar desde sus casas, se hacía más poderosa la idea de pensar las organizaciones como flujos más allá de los organigramas estáticos de lugares y personas. Transformar las jerarquías en redes, concebirlas como cuerpos sociales dinámicos, no solo amplía su radio de acción y su conectividad exterior, también reactiva sus fortalezas internas, aflora los liderazgos ocultos, multiplica el valor social producido y maximiza el uso eficiente de los recursos en una época de limitaciones. Los laboratorios de innovación pública, social o ciudadana, o laboratorios de gobierno, junto a otras formas de innovación abierta y diseño social, se reivindican como proyectos inspiradores de un cambio de paradigma: de las instituciones que ordenan a las instituciones que aprenden. Pensar las organizaciones bajo el prisma de la ciencia de redes y la ética de los rizomas –nodos, enlaces, hubs, comunidades…– nos debería permitir una aproximación a la compleja y escurridiza tarea de configurar los ecosistemas de innovación y creatividad en el ámbito de lo público y lo social. Este informe propone un modelo denominado Hexágono de la Innovación Pública (HIP) que promueve un cambio sistémico a través de seis vectores (OPEN_ abierto, TRANS_ transversal, FAST_ ágil, PROTO_ modelado, CO_ colaborativo y TEC_ tecnológico) basados en las propiedades de las redes y en el análisis de 105 metodologías que usan las agencias más innovadoras del mundo. Se incluyen una herramienta de autodiagnóstico y el HIP-SIM, una primera aproximación a un software abierto para visualizar, modelar y simular la creación de ecosistemas innovadores con el que queremos propiciar una comunidad y un debate internacional.

Instituições que aprendem - Relatório para a XXVII Cimeira Ibero-Americana de Chefes de Estado e de Governo - Oliván Cortés, Raúl (XXVII Cimeira Ibero-Americana, 2020)
A pandemia da Covid-19 surgiu de súbito num momento de transição para as instituições e organizações sociais de meio mundo. Antes ainda de se ter ultrapassado a crise de confiança da última década entre os cidadãos e os governos, num momento de grande impulso das iniciativas de governo aberto e de planos de inovação e transformação digital para tornar mais democráticas e eficientes as administrações através de programas políticos encaminhados para configurar um novo contrato social, verde e digital no quadro da Agenda 2030, o coronavírus provocou um choque histórico alterando o curso do século XXI e exigindo uma aceleração de todos os processos em andamento. A complexidade e dimensão da pandemia revelou a necessidade de arquiteturas institucionais mais flexíveis, ágeis e resilientes, capazes de incorporar toda a energia civil para aprenderem com o seu talento e criatividade, dando maior protagonismo à cidadania (ativistas, empreendedores, tecido associativo, academia, makers…) não só na tomada de decisões mas também na configuração e implementação das estratégias. À medida que se afastava do centro a milhões de empregados para teletrabalhar a partir de casa, tornou-se mais poderosa a ideia de pensar nas organizações como fluxos que excedem os organigramas estáticos de lugares e pessoas. Transformar as hierarquias em redes, concebê-las como corpos sociais dinâmicos, não só alarga o seu raio de ação e conectividade externa, mas também reativa as suas forças internas, aflora as lideranças ocultas, multiplica o valor social produzido e maximiza o uso eficiente dos recursos numa época de limitações. Os laboratórios de inovação pública, social ou cidadã, ou laboratórios de governo, a par de outras formas de inovação aberta e configuração social, reivindicam-se como projetos inspiradores de uma mudança de paradigma: de instituições que ordenam para instituições que aprendem. Pensar nas organizações sob a ótica da ciência das redes e da ética dos rizomas – nós, ligações, hubs, comunidades… – deverá permitir-nos uma aproximação à complexa e subtil tarefa de configurar os ecossistemas de inovação e criatividade no âmbito público e social. Este relatório propõe um modelo denominado Hexágono da Inovação Pública (HIP) que promove uma transformação sistémica através de seis vetores (OPEN_ aberto, TRANS_ transversal, FAST_ rápido, PROTO_ modelado, CO_ colaborativo e TEC_ tecnológico) baseados nas propriedades das redes e na análise de 105 metodologias usadas pelas agências mais inovadoras do mundo. Incluem-se uma ferramenta de autodiagnóstico e o HIP-SIM, uma primeira aproximação a um software aberto para visualizar, modelar e simular a criação de ecossistemas inovadores com o qual queremos favorecer a comunidade e o debate internacional.

Principles for managing in complexity - Proud, Emma (LearnAdapt, 2020)
Written by Toby Lowe and Shaheen Warren (Centre for Public Impact) and Sam Sharp (Overseas Development Institute), with input from Jamie…

Development and radical uncertainty - Feinstein, Osvaldo (Development in Practice, 2020)
Development strategies, programmes and projects are designed making assumptions concerning several variables such as future prices of outputs and inputs, exchange rates and productivity growth. However, knowledge about the future is limited. Uncertainty prevails. The usual approach to deal with uncertainty is to reduce it to risk. Uncertainty is perceived as a negative factor that should and can be eliminated. This article presents an alternative approach which recognises that radical uncertainty is irreducible to risk, identifying a positive dimension of uncertainty and showing its implications for development practice.
Publisher: Routledge _eprint: https://doi.org/10.1080/09614524.2020.1763258

Discussing Adaptive Approaches for Development Programmes - Pett, Jamie (Medium - LearnAdapt, 2020)
What can adaptive approaches from other sectors teach development practitioners about dealing with uncertainty?

Agency in the face of path dependence: how organizations can regain scope for maneuver - Fortwengel, Johann; Keller, Arne (Business Research, 2020)
This paper tackles a key problem in path dependence research: how can locked-in organizations regain their scope for maneuver? Leveraging insights from two surprising and thus revelatory cases of organizations that have successfully escaped from path dependence, we develop the theoretical argument that regaining scope for maneuver can be achieved by interrupting the logic of a path’s underlying self-reinforcing mechanisms. More specifically, we argue that, through a targeted interruption of the working of these mechanisms, hyper-stable patterns inscribed in an organization can be gradually rewound—and alternative futures become possible. We position our paper within larger debates around the role of agency in path dependence theorizing, and we outline research frontiers to better understand the necessary antecedents of and exact relationship between mechanisms interruption and pattern unwinding.

Diseño transformacional de proyectos - Kehrer, Daniel (GIZ, 2020)
There are many definitions of the term ‘transformation’ or ‘transformational change’. The first section of the report develops a basic understanding of transformations or transitions (used synonymously) viewed from various perspectives. In this, transformations are defined as processes that use disruptive innovations to change systems into fundamentally new systems that subsequently form the new mainstream. Section two describes existing approaches to environmental and climate finance in international cooperation and discusses them in light of the proposed definition. All of the approaches have the potential to be further refined and in that process often to increase the precision of what is understood by each type of transformation. The definitions already state which criteria and indicators are referred to and how relevant they are. There is wide diversity in the type of criteria and indicators used by the various organisations, and how they are classified, but certain common features can be identified and with the aid of the literature on transformations they can be combined to form a comprehensive framework. With this in mind, the derivation of quality criteria for transformative interventions is explained in section 3.1. Transformational change at one and the same time calls for big decisions and innumerable projects in a particular field of transformation; the projects cannot be planned on the drawing board but still should be coordinated with each other. Section 3.2 offers guidance on this. Section 3.3 argues in favour of focusing more closely on the ‘process promise’ and employing a more iterative and more adaptable commissioning procedure. Finally, section 3.4 introduces two types of indicators under the various criteria: design indicators, which measure the quality of interventions that are aimed at influencing transformations (process orientation), and outcome indicators, which measure the process and/or progress of a transformation itself.

Transformative project design - Kehrer, Daniel (GIZ, 2020)
There are many definitions of the term ‘transformation’ or ‘transformational change’. The first section of the report develops a basic understanding of transformations or transitions (used synonymously) viewed from various perspectives. In this, transformations are defined as processes that use disruptive innovations to change systems into fundamentally new systems that subsequently form the new mainstream. Section two describes existing approaches to environmental and climate finance in international cooperation and discusses them in light of the proposed definition. All of the approaches have the potential to be further refined and in that process often to increase the precision of what is understood by each type of transformation. The definitions already state which criteria and indicators are referred to and how relevant they are. There is wide diversity in the type of criteria and indicators used by the various organisations, and how they are classified, but certain common features can be identified and with the aid of the literature on transformations they can be combined to form a comprehensive framework. With this in mind, the derivation of quality criteria for transformative interventions is explained in section 3.1. Transformational change at one and the same time calls for big decisions and innumerable projects in a particular field of transformation; the projects cannot be planned on the drawing board but still should be coordinated with each other. Section 3.2 offers guidance on this. Section 3.3 argues in favour of focusing more closely on the ‘process promise’ and employing a more iterative and more adaptable commissioning procedure. Finally, section 3.4 introduces two types of indicators under the various criteria: design indicators, which measure the quality of interventions that are aimed at influencing transformations (process orientation), and outcome indicators, which measure the process and/or progress of a transformation itself.

A Guide To Agile Project Management Methodology & Tools - Aston, Ben (The Digital Project Manager, 2020)
Looking to brush-up on agile? Here's your complete guide to agile project management, agile principles and key components, and the best agile tools for 2020.

Linking constituent engagement and adaptive management - Buell, Stephanie; Campbell, Megan; Pett, Jamie (Overseas Development Institute, 2020)
Constituent engagement is the two-way process of involving constituents in the design, delivery, monitoring and evaluation of programmes. Constituent engagement and adaptive management together can be a powerful combination; high-quality constituent engagement can reinforce effective adaptive management, and vice versa. By highlighting stories from leading practitioners and their organisations, this paper explores how programmes ensure that constituent engagement informs meaningful adaptation. Key messages Constituent engagement and adaptive management are both important tools for implementing responsive and effective development programmes. Together, they can be a powerful combination: input from constituent engagement can be a key source of information and evidence that meaningfully informs programme design and adaptation, and closing the feedback loop in this way increases the quality of future engagement. Both adaptive management and community engagement principles recognise that, for a programme to be effective, it must be responsive to the people meant to ultimately benefit from it. Beyond providing a key source of information for potential programme adaptations, constituent engagement efforts also help build trust with stakeholders, align expectations and promote accountability. This paper explores five key elements for ensuring that constituent engagement and adaptive management are effectively linked within a programme: strong internal systems and external channels; skilled staff that value engagement and adaptation; decision-maker champions; clear points for reflection and action; and a meaningful role for constituents.

Adaptive management: A practical guide to mitigating uncertainty and advancing evidence-based programming - Byom, K.; Ingram, M.; Oakley, A.; Serpe, L. (PACT, 2020)
Pact’s Adaptive Management Guide provides practical guidance to development practitioners globally on the mindsets, behaviors, resources, and processes that underpin an effective adaptive management system. It presents an approach to managing adaptively that is rooted in complexity analysis and program theory. It draws on Pact’s global experiences and work on topics as diverse as health, livelihoods, markets, governance, capacity development, women and youth, and more. This document begins with an introduction to adaptive management, then walks through successive steps to determine how much adaptation a project requires and how to design an appropriate system. The second half of this guidebook contains a toolkit of examples and templates that projects can tailor to their needs.

Using middle-level theory to improve programme and evaluation design - Cartwright, N (CEDIL, 2020)
What can middle-level theory do? Middle-level theory (MLT) has several uses in development planning and evaluation. It helps predict whether a programme can be expected to work in a new setting. It offers insights into what design features are needed for success. It provides invaluable information for monitoring to see if the programme is on track and to fix problems that arise. It reveals the causal processes and related assumptions to be tested in an evaluation and helps identify evaluation questions. It helps in interpreting evaluation findings, assessing their relevance and locating a description of them that is useful for programme design and evaluation in other settings

Building Better Systems - An introduction to System Innovation - Winhall, Jennie; Leadbeater, Charles (The Rockwool Foundation, 2020)
This paper lays out a series of steps people can take to create the new systems we need to meet shared, public challenges. Systems are ubiquitous and powerful. We rely on them to support our daily lives: every time we turn on a tap, flick a switch for electricity, drop our child at school, jump on a bus or visit a doctor we rely on a wider system. There is a widespread sense, among decision makers and citizens that in the coming decades society will need not just new products, software and services, but new systems for living sustainably in a socially inclusive society. The need for better, different systems will be heightened by the impact and lessons of the Covid-19 pandemic. Systems are productive precisely because they are more than standalone products. A system pulls together all the different ingredients needed to meet a need or to produce an outcome: the shipping container is a product, containerisation is a system; a contactless payment card is a product which only works as part of a payments system; an operation in a hospital can only take place because it is part of a wider health system. To understand how a system works it has to be seen as a whole, from the macro policy frameworks of social security systems right down to how a citizen goes about finding a job. Many of the systems we rely on for care and work, energy and transport, education and health are under pressure to change. Society faces both deeply entrenched and growing challenges that are outpacing the systems we have. We also have opportunities to create new, alternative systems as new knowledge, values and technologies emerge, from artificial intelligence and bitcoin, to circular and renewable systems of production. Rising to the challenge of fixing an existing system and exploring the possibility of creating a new system are different undertakings. The first is about optimising what exists, the second is about creating something different and better. We want this project to yield practical insights for those who want to respond to the systemic challenges of today by stepping into the possibilities of the future. Acting to change systems depends on new ways of seeing both challenge and opportunity: why systems come under strain and what unlocks the potential for alternatives. It depends on better understanding how new systems form, and what and who is part of initiating and driving the transition to them. In putting together this paper and the ones that will follow from it we want to clarify how to assess the need for, invest in and act on the process of deliberate system change.

Four ways development practitioners can borrow from private sector adaptive approaches - Pett, Jamie (LearnAdapt, 2020)
Agile, lean startup and human-centred design can be an answer — if you’re asking the right questions

5 Principles to Guide Adaptive Leadership - Ramalingam, Ben; Nabarro, David; Oqubuy, Arkebe; Carnall, Dame Ruth; Wild, Leni (Harvard Business Review, 2020)
How you respond to a crisis will have repercussions for years to come. The Covid-19 pandemic is constantly evolving, with leaders facing unpredictability, imperfect information, multiple unknowns, and the need to identify responses quickly — all while recognizing the multi-dimensional (health-related, economic, social, political, cultural) nature of the crisis. Responding to the crisis requires adaptive leadership, which involves what we refer to as the 4 A’s: Anticipation of likely future needs, trends and options. Articulation of these needs to build collective understanding and support for action. Adaptation so that there is continuous learning and the adjustment of responses as necessary. Accountability, including maximum transparency in decision-making processes and openness to challenges and feedback.
Keywords: Crisis management; Leadership

Book Review: ‘Thinking and Working Politically in Development’ - Green, Duncan (From Poverty to Power, 2020)
Review of a new book that explores the 'secret sauce' of Coalitions for Change - an unusually successful governance programme in the Philippines

What is Political Economy Analysis (PEA) and why does it matter in development? - Teskey, Graham (From Poverty to Power, 2020)
Graham Teskey shares a great internal links round up and guide to 'political economy analysis'

Navigating adaptive approaches for development programmes - Pett, Jamie (ODI, 2020)
This working paper compares six of the most prominent adaptive approaches to emerge over the past two decades. Three come from the world of innovation, largely in the private sector (agile, lean startup and human-centred design), and three from the global development sector (thinking and working politically, forms of adaptive management and problem-driven iterative adaptation). While all of these approaches are valuable when used in the right context, practitioners may be perplexed by the multiplicity of methods and jargon. This paper aims to address some of this confusion by mapping where these approaches have come from and showing how they can be applied across the adaptive programme cycle. Armed with this knowledge, practitioners might experiment with different combinations and sequences of adaptive approaches according to the kind of problem and context faced. In turn, this may help us move beyond a siloed view of approaches linked to innovation, adaptive management or more politically smart ways of working. Key messages: • Adaptive approaches have emerged in several sectors, including software development, product and service design, technology startups and international development. • Adaptive approaches can help practitioners counteract misplaced certainty. By talking to potential users, understanding institutions, interests and ideas and investigating the root causes of a problem, practitioners applying these approaches can illuminate the underlying nature of the problem and context. • Rather than building a whole solution straight away, these approaches commonly encourage practitioners to start small and use structured cycles of testing and learning. There is scope to further consider how different approaches can be better brought together and combined. • Adaptive approaches in development provide a wider range of options for what to create and facilitate – not only products or services, but also forms of collective action. There are also alternative ways to think about scale – considering how others might take up an idea and looking for leverage, rather than quantity.

SystemCraft - a primer: How to Tackle our Toughest Problems - Simpson, Kate; Randall, Ian (Wasafiri, 2020)
Systemcraft is our applied framework to help leaders and organisations get started and keep going when faced with complex problems. It is built on our practical experience. It draws on a broad body of research, action and theory from the worlds of complexity thinking, systems theory, adaptive management, leadership development, social movements, development theory and beyond. Systemcraft has been designed to make systems thinking something any leader can apply when they find themselves faced with a complex problem and asking, ‘So what do I do next?’

Reacting or adapting? Purposeful adaptation and response to contextual change. - Wood, Nik (Rebel with Causation, 2020)
Adaptive management is increasingly on the ticket for development programming, and has been crucial in the wake of covid-19. I’ve been working with adaptive programmes for most of my career, …

Webinar - Practicing Thinking and Working Politically (TWP): Voices from the Field - SID (Society for International Development., 2020)
Current thinking on effective international development interventions highlights the importance of “thinking and working politically” (TWP). Among the emerging lessons of experience is that thinking politically, using tools such as political economy analysis, is more easily undertaken than working politically. How can the two pillars of TWP be effectively integrated? What challenges exist and how have practitioners confronted them? This session focuses on listening to voices from the field to explore answers to these questions. The organizers solicited proposals from implementers, reaching out to SID-W members and the Washington, D.C.-based TWP community of practice. They selected the following four projects that illustrate different approaches to practicing TWP. • Mercy Corps: Integrated Maji Infrastructure and Governance Initiative for Eastern Congo, Democratic Republic of the Congo • Asia Foundation: Tourism Strategy Project, Timor-Leste • Counterpart International: Rights and Dignity Project, El Salvador • RTI International: Knowledge Sector Initiative, Indonesia Their voices will be bookended by Sarah Frazer (RTI International), who will summarize a recent study, Thinking and Working Politically: Lessons from Diverse and Inclusive Applied Political Economy Analysis, and Alina Rocha Menocal (Overseas Development Institute), who will provide commentary on the four projects and the study findings. Ann Hudock (Counterpart International) will moderate.

The Politics of Uncertainty : Challenges of Transformation - Scoones, Ian; Stirling, Andy; Stirling, Andy (Routledge, 2020)
Why is uncertainty so important to politics today? To explore the underlying reasons, issues and challenges, this book’s chapters address finance and banking,

Thinking and working politically with technology: State of the art meets art of the state - Thampi, Gopa; Nixon, Nicola (From Poverty to Power, 2020)
Based on its work in Sri Lanka, The Asia Foundation argues for greater attention to the local political dynamics into which digital solutions are introduced

Scaling the impact of sustainability initiatives: a typology of amplification processes - Lam, David P. M.; Martín-López, Berta; Wiek, Arnim; Bennett, Elena M.; Frantzeskaki, Niki; Horcea-Milcu, Andra I.; Lang, Daniel J. (Urban Transformations, 2020)
Amplifying the impact of sustainability initiatives to foster transformations in urban and rural contexts, has received increasing attention in resilience, social innovation, and sustainability transitions research. We review the literature on amplification frameworks and propose an integrative typology of eight processes, which aim to increase the impact of such initiatives. The eight amplification processes are: stabilizing, speeding up, growing, replicating, transferring, spreading, scaling up, and scaling deep. We aggregated these processes into three categories: amplifying within, amplifying out, and amplifying beyond. This integrative typology aims to stimulate the debate on impact amplification from urban and rural sustainability initiatives across research areas to support sustainability transformations. We propose going beyond an understanding of amplification, which focuses only on the increase of numbers of sustainability initiatives, by considering how these initiatives create transformative change.
Keywords: City; Rural; Scaling; Transformation; Transition; Transition initiative; Urban

Smart Implementation of complex change processes - Beier, Christoph; Kirsch, Renate (Global Solutions Journal, 2020)
Cooperation management facilitates the recoupling of progress toward sustainable development

Uncertainty and COVID-19: A turning point for Monitoring Evaluation, Research and Learning? - A discussion note for aid actors, policymakers and practitioners - Tyrrel, Lavinia; Roche, Chris; Jackson, Elisabeth (Abt Associates, 2020)
The COVID-19 pandemic has significantly shifted the context in which aid and development is being delivered. The global scale of the pandemic and the speed at which it is spreading mean that the ‘normal’ economic, ideological and organisational influences which shape (if not determine) aid delivery are in flux. This means that – for a relatively short-period – there is scope for aid actors to work collectively to embed more locally-led, politically-informed and adaptive forms of MERL in aid and development practice. These forms of Monitoring Evaluation Research and Learning (MERL) are not only well-suited to the current global pandemic. They also offer ways for aid program decision makers and practitioners to make sense of the complex and uncertain contexts in which much development work takes place. Applying locally-led, politically-informed and adaptive forms of MERL in the COVID-19 context and beyond requires a shift in mindset and approaches. Situations of complexity, in which it is difficult to predict the relationships between cause and effect, do not lend themselves to linear approaches and fixed indicators. Instead, they require ‘navigation by judgement’, ongoing learning and adaptation and greater privileging of local knowledge, and of the perspectives of those who are often excluded. Rather than being focused on upwards accountability, simple numbers and good news stories, the core function of MERL in this context is to support a better understanding – in real-time – of the changing operating context, to generate learning about the immediate impact of policy and program responses and their longer-term effects, and to inform decision making by front line staff. Whether the opportunities afforded by this ‘critical juncture’ are realised will depend on the degree to which those in the aid and development sector use this opportunity to promote a shift in the deep incentive structures within which development agencies are embedded. On the one hand, the pandemic underscores the limits of the linear understandings of change which underpin many orthodox approaches to planning, design and associated MERL. On the other hand, there is a vested interest in the status quo amongst many organisations, consultants, researchers and MERL practitioners. This is because approaches which promote locally-led development inevitably require those in power to relinquish control. While a range of factors make this shift difficult, there is more scope to change internal ways of working in development agencies than is commonly acknowledged. There is no time like the present to advocate for a ‘new normal’ for MERL.

A pragmatic approach to assessing system change - Webinar (DCED, 2020)
Few topics inspire as much confusion and debate as systemic change. What is it? How do you measure it? Does it even matter? Assessing changes in systems might be more doable than you think. This webinar explored a back-to-basics approach to assessing system change. In November 2019, thirty results measurement specialists, managers and consultants got together in Bangkok. They took part in workshops on a back-to-basics approach to assessing system changes, applying it to cases from participants’ programmes. Since then, the insights from the workshop have been further developed into a pragmatic approach to assessing system changes that builds on what programmes are actually doing and learning from practice. It can be: applied by programmes using a variety of different systemic change frameworks applied across a variety of sectors implemented with internal resources using familiar methods for information gathering The speakers walked through the approach using examples from the 2019 workshop, including PRISMA in Indonesia and Skills for Jobs (S4J) in Albania.

Deciding Well in Tumultuous Times - Moss, Ian David (Smarter decisions for a better world, 2020)
Practical advice for donors and institutions responding to COVID-19

LEARN End of Contract Report - Learning Lab (USAID, 2020)
In September of 2014, USAID’s Office of Learning, Evaluation & Research (LER) awarded the Learning and Knowledge Management (LEARN) contract to Dexis Consulting Group and subcontractor RTI International.1 This document—the End of Contract Report—captures five and half years of results and reflections for our stakeholders. Our intention is to share the good and the bad, and while this report would not be considered a “tell all,” we think we have a story worth sharing, particularly to USAID CORs and AORs, activity managers, and other implementers of institutional support contracts.2 LEARN’s primary purpose was to support organizational change at USAID. More specifically, the contract was focused on helping USAID staff integrate collaborating, learning, and adapting (CLA) approaches into the design, implementation, monitoring, and evaluation of programs (what is known at USAID as the Program Cycle). It was clear that most USAID staff, whether they realized it or not, were already integrating CLA into their work to some extent. The focus of our efforts, therefore, was to make those practices more systematic, intentional, resourced, and ultimately more widespread throughout the Agency, which would have a ripple effect on implementing partners and even other stakeholders, such as host country governments. This was based on the theory—later borne out by evidence—that by becoming a better learning organization, USAID could be a more effective development organization. And that theory brought the USAID CLA team within USAID’s Bureau for Policy, Planning & Learning (PPL) and LEARN contractors together, driven by a shared purpose of improving how USAID does business. LEARN was designed based on this belief and, as you might expect from a learning-oriented contract, began with more questions than answers. Primary among those questions was: could an institutional support contract do more than carry out requested services—could it actually accelerate positive organizational change at USAID? And if so, how and under what conditions?

Monitoring for problem-solving, adaptive management, reporting and learning - Dominique Morel; Dzino-Silajdzic, Velida; Hagens, Clara (Catholic Relief Services, 2020)
Internal and external stakeholders have different information needs over a project’s life, for purposes that include adaptive management, accountability, compliance, reporting and learning. A project’s monitoring, evaluation, accountability and learning, or MEAL, system should provide the information needed by these stakeholders at the level of statistical reliability, detail and timing appropriate to inform data use. In emergency contexts where the situation is still fluid, ‘informal monitoring’ has proved helpful to staff’s ongoing assessment of the broader environment in order to identify changes in the situation, in other actors’ responses, and in priority unmet needs that would require corresponding changes in the response.2 The same distinction between informal monitoring of possible changes in the project’s operating context—whether identified as project assumptions and risk factors or not—and formal monitoring of the activities included in the response and project indicators, is relevant for development contexts too. Informal monitoring: Ongoing assessment of changes in operating context Formal monitoring: Tracking progress against project activities and indicators Within formal monitoring, it is useful to further differentiate between light monitoring and rigorous monitoring: - Light monitoring aims to provide timely feedback on new activities (or new locations or target groups) or aspects of the project’s theory of change (activity-to-output or output-to-IR change) logic that staff are less confident about, to check for early signs that progress is being made and that assumptions are holding true while there is still ample time to make adjustments if necessary.3 - Rigorous monitoring aims to collect representative data for evidence-based project management, reporting and learning, not just at midterm but throughout project implementation.

Adaptive leadership in the coronavirus response - Ramalingam, Ben; Wild, Leni; Ferrari, Matt (ODI, 2020)
The coronavirus pandemic poses unprecedented challenges to science, policy and the interface between the two. How – and how quickly – policy-makers, practitioners and researchers react to this emerging and complex crisis is making a profound difference to people’s lives and livelihoods (WHO, 2020). But how can we ensure effective collective decision-making on the basis of emerging evidence, changing trends and shifting scientific understanding, all in the face of considerable uncertainty? Recent experience highlights the need for adaptive leadership in national and global responses to the outbreak. This briefing paper sets out key principles for what this might look like, and proposes a roadmap for policy-makers, practitioners and researchers to move towards such an approach as they tackle the unfolding crisis. Key messages Tackling the coronavirus outbreak requires adaptation at operational and leadership levels. Operationally, there is scope to strengthen evidence-based adaptive management practices, to adjust the mix and type of interventions being implemented and learn as we go so as to achieve shared goals. This requires adaptive leadership capacities, being open and transparent about learning, using collective decision-making processes and building trust with communities and individuals.

Cynefin St David’s Day 2020 (1 of 5) - Snowden, Dave (Cognitive Edge, 2020)
Series of blog posts discussing the last version (as of 2020) of the Cynefin framework.

Adaptation in practice: lessons from teenage pregnancy programmes in Sierra Leone - Castillejo, Clare; Buell, Stephanie (ODI, 2020)
A discussion of initial learning emerging from the SLRC ’Adaptive approaches to reducing teenage pregnancy in Sierra Leone’ action research project.

Politically informed approaches to gender in fragile and conflict-affected settings - Castillejo, Clare; Domingo, Pilar; George, Rachel; O’Connell, Shannon (ODI, 2020)
This report summarises the discussions at a meeting held in September 2019 of a group of global development research and policy experts and practitioners, convened by ODI and the Westminster Foundation for Democracy, to share experiences and knowledge, reflect on what we already know about working politically on gender in fragile and conflict-affected settings (FCAS), and identify what further evidence would be useful. Key messages: - It is important to identify, document and learn from politically informed and adaptive ways of working in practice on gender in FCAS. - Different analytical and monitoring, evaluation and learning tools are required for politically informed programming on gender. These should be embedded within programme teams and processes, and be both gender-responsive and responsive to the political economy context. - There is a need for more politically smart use of quantitative and qualitative data in order to identify plausible entry points and ways of working on gender in FCAS. This should include increasing the capacity of programme staff to use data to inform, adapt and correct programmes. - Staff promoting politically informed work on gender equality are often isolated, with little opportunity to share experiences or learn from others. Platforms should therefore be created to share experience and knowledge, and to bring together donors and implementers involved in this work.

Mainsreaming gender in an adaptive, politically smart governance programme - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
• This paper looks at the experience of gender mainstreaming in the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • When development programmes try to engage with political stakeholders and align with the priorities of wider coalitions there is a danger that gender equality is de-prioritised. • It is important that formal political economy analysis, as well as other data collection, analysis and consultation exercises, are gender-sensitive. Teams should also look for ways to make gendered political and power analysis part of the everyday routine practice of staff. • Working politically and adaptively to advance gender objectives calls for staff with a specific skillset, as well as links to appropriate networks and political stakeholders. It also implies establishing checks and incentives to hold staff and partners accountable for gender objectives, and strong and consistent messaging from team leaders.

Rethinking value for money for adaptive, politically smart programmes - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
- This short paper draws out lessons for working effectively with and through partners, based on the experience of the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • Cultivating effective partnerships can be a key part of delivering locally legitimate projects that have the potential to create sustainable change. Adaptive and politically informed ways of working create specific opportunities and challenges for doing this well. • Flexible and adaptive programmes are deliberately designed to experiment and to make small investments in different areas, to see what will work. While this is often important for making headway on complex challenges, it can also leave partners exposed and can undermine trust. • It can also be challenging to balance the need to meet accountability commitments to donors while allowing local partners to take the lead in pursuing their own objectives. • Co-creating plans, priorities and activities with partners has the potential to resolve some of these tensions. But the time and patience required to do this successfully should not be underestimated, and can be difficult to maintain in the face of pressure from donors to see results within a confined timeframe.

Working effectively through partnerships - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
• This paper looks critically at the approach to value for money (VfM) in the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • Adaptive, politically smart programmes like I4ID aim to deliver VfM by learning about what will work in complex environments, and quickly incorporating those lessons into delivery. When functioning properly, they can rapidly wind down activities as new information emerges and divert funding to more effective alternatives. • This means that adaptive programmes will achieve their potential to deliver strong VfM when their processes are good – when appraisal of experimental efforts is timely, consistent, knowledgeable and politically astute. As these programmes mature in their implementation phase, VfM evaluation should be focused on checking for a culture of adaptation and learning supported by strong adaptive processes. • While economy is important for adaptive programmes, it is also important that keeping costs low does not deprive teams of the resources, staff, and management and administration time they need to gather information, experiment, learn and adapt.

Evidence base for Collaborating, Learning, and Adapting: summary of the literature review (2020 update) - Learning Lab (USAID, 2020)
The LEARN contract and the United States Agency for International Development/Bureau of Policy, Planning, and Learning (USAID/PPL) are managing an area of work known as the Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer the following key learning questions: ● Does an intentional, systematic, and resourced approach to collaborating, learning, and adapting (CLA) contribute to organizational effectiveness and/or development outcomes? ● If so, how? And under what conditions? ● How do we know? How do we measure any contribution that CLA makes to development results? As we began this work, we identified the need to conduct a literature review looking at these questions to understand what is known, what remains unknown, and how others have tried to answer these questions to date. We were primarily interested in answering these questions: ● What evidence is there, if any, that collaborating, learning, and/or adapting contributes to organizational effectiveness, development outcomes, or both? What are the strongest pieces of evidence? ● Does the literature identify any factors critical to CLA that are not currently included in the CLA framework? ● Who else is working on measuring the impact of collaborating, learning and adapting? ● What methods and measures did researchers use to study the effects of collaborating, learning, and adapting? ● Where are there gaps in the research relevant to collaborating, learning, and adapting? ● When taken together, what practical guidance does the evidence for collaborating, learning, and adapting offer to practitioners and policy makers to improve organizational effectiveness and development outcomes?

What difference does CLA make to development? Key findings from a recent literature review (2020 update) - Learning Lab (USAID, 2020)
USAID’s Bureau for Policy, Planning and Learning and its LEARN support contract are working to integrate systematic, intentional and resourced collaborating, learning and adapting (CLA) throughout program planning and implementation to achieve more effective development programs. As part of this effort, USAID is exploring several approaches to understand whether and how strategic collaboration, continuous learning and adaptive management make a difference to organizational effectiveness and development outcomes. To begin this work, we have undertaken a foundational literature review of academic and gray literature to answer our key learning questions: • Does an intentional, systematic and resourced approach to collaborating, learning and adapting contribute to organizational effectiveness? To development outcomes? • If so, how? And under what circumstances? • How do we measure the contribution? The 13 key findings, mapped to the CLA Framework below, are described in greater detail in the following pages.

Getting intentional about M&E: choosing suitable approaches for adaptive programmes - Management, Global Learning for Adaptive (GLAM Blog, 2020)
Does the choice of monitoring and evaluation (M&E) approaches and tools matter for adaptive programmes? In short, yes: monitoring, evaluation and learning (MEL) and adaptive management (AM) are intertwined. While programme monitoring data and evaluation results are not the only sources of evidence that programmes use for learning and iteration, they often are amongst most important ones — or at least they should be. Selecting what type of information to collect and analyse — and how — is critical for any type of programme. However, what AM especially focuses on is intentionally building in opportunities for structured and collective reflection, ongoing and real-time learning, course correction and decision-making in order to improve effectiveness.

Transforming our work: Getting ready for transformational projects - Kehrer, Daniel; Flossmann-Kraus, Ursula; Ronco Alarcon, Sabrina Valeria; Albers, Vivien; Aschmann, Gwendolin (GIZ, 2020)

Self Sabotage: Why Doing the Right Thing Results in Failure - Newell, Peter (War on the Rocks, 2020)
In January 2010 improvised explosive device (IED) attacks against dismounted infantry squads in Afghanistan numbered in the single digits — with only two

A New Policy Narrative for Pastoralism? Pastoralists as Reliability Professionals and Pastoralist Systems as Infrastructure - Roe, Emery (ESRC STEPS Centre, 2020)
This paper proposes that pastoralist systems are better treated, in aggregate, as a global critical infrastructure. The policy and management implications that follow are significant and differ importantly from current pastoralist policies and recommendations. A multi-typology framework is presented, identifying the conditions under which pastoralists can be considered real-time reliability professionals in systems with mandates preventing or otherwise avoiding key events from happening. The framework leads to a different policy-relevant counternarrative to pastoralism as understood today. Some features of the counternarrative are already known or have been researched. The paper’s aim is to provoke further work (including case research and interactions with decisionmakers) on how robust the counternarrative is as a policy narrative for recasting today’s pastoralist policy and management interventions.
Accepted: 2020-01-14T10:22:59Z

Embracing complexity - Towards a shared understanding of funding systems change - Ashoka (Ashoka, 2020)

Thinking and Working Politically in development - Coalitions for Change in The Philippines - Sidel, John T.; Faustino, Jaime (The Asia Foundation, 2020)
The Asia Foundation and the Australian Embassy in the Philippines today released a new publication, Thinking and Working Politically in Development: Coalitions for Change in the Philippines. Written by London School of Economics and Political Science Professor John T. Sidel and The Asia Foundation’s Jaime Faustino, the book examines the first phase of the Coalitions for Change program (2012-2018) and the contributions to key development policy reforms in the Philippines. The book is a rigorous treatment of the Coalitions for Change program’s transformative policy reforms—alongside lessons from its failures—across diverse policy arenas and in a wide variety of cities and provinces. The chapters are organized thematically: excise tax reform (Chapter 2), land governance reform (Chapter 3), education (Chapter 4), electoral reform (Chapter 5), disaster risk reduction and management (Chapter 6), and subnational governance reform and conflict resolution in Mindanao (Chapter 7). The co-authors together combine an independent, academic perspective on the program’s impacts (Sidel) with a front-row view of doing policy reform in the Philippines – both its political and technical dimensions (Faustino). Based on the empirical research and comparative analysis undertaken by the authors, the book articulates – and substantiates – a strong set of arguments that help to explain the program’s mixed pattern of achievements and disappointments. Overall, the book concludes that the seven-year program achieved significant and sustainable impact using problem-driven, adaptive, and iterative approaches to developmental change. The authors assert the program was at the forefront of notable development approaches: aid effectiveness and development around thinking and working politically, doing development differently, and adaptive programming. Graham Teskey, an early advocate of ‘thinking and working politically’ explores how development agencies can replicate the conditions for success in his Afterword. With illustrative case studies and analyses, the book provides valuable lessons for policymakers, scholars, bilateral agencies, think-tanks, and anyone interested in successfully maneuvering the shifting dimensions of development in the Philippines and elsewhere.

Learning From Failure 2020 - What CARE’s evaluations tell us about how to improve our work - CARE (CARE, 2020)
“Ever failed. No matter. Try again. Fail again. Fail better.” –Samuel Beckett Here’s my favorite part of that quote: the ultimate goal is not a lack of failure; it’s better failures. That’s good news for CARE, because we just published round two of our Learning From Failure initiative, and…I know this will surprise everyone…we haven’t stopped failures yet. We do have some hopeful signs that we’re failing better; or at least, that we’re improving on some concrete weaknesses we identified in the first round. It’s an interesting process to launch the second phase of learning from failure. The first round, we didn’t know what we were going to find. We spent as much time talking about how it was the first-ever report of its kind as we did about the actual failures. Our case study admitted, “It's still very early to see specific development impacts.” Round two isn’t quite the same. It’s not new anymore, so there’s less excitement at having invented something. We’re not discovering data and themes for the first time. In a lot of ways, the stakes are higher. Round two of learning from failure becomes an exercise in continuous performance improvement, rather than a journey of discovery. If we don’t see improvements, we don’t have the excuse that it’s too early to tell. It also takes a sustained commitment. Launching an exploratory exercise at a small scale is easy, especially when no one quite knows what the answers will be. Pulling together a few pieces of content over a few months is pretty straightforward. It takes some staying power—and real support from leadership—to keep up the work over time, especially in the middle of a pandemic. That’s even more true once we’ve seen one round of results and had a chance to understand the work that it takes to improve.

Listen carefully. Tread lightly. Adapt quickly. Approaching Adaptive Management: Examples from our Somalia Education Programming - CARE (CARE, 2020)
Adaptive management approaches potentially offer us opportunities to deliver high quality results in circumstances where change is complex, including in fragile, unstable or conflict affected places. However, building adaptive programming continues to be a challenge for the sector. For CARE, our Department for International Development -UK Aid funded Girls’ Education Challenge (GEC) programming has provided useful learning on how to operationalise adaptive approaches. In this paper we expand on our learning from this project and offer some recommendations for how to create more opportunities for truly adaptive programming in the future. In particular: • Projects that are designed to adapt need budget structures, results frameworks and governance that enable the process of adaptation. In our GEC projects the approaches employed by DFID, including the introduction of Review and Adaptation meetings have served to support meaningful adaptation. • Adaptive projects require both strong participatory elements and flexible governance and accountability structures. Whilst rigorous and comprehensive Monitoring, Evaluation and Learning (MEL) systems are important without these other elements appropriate adaptation can be hindered. • Adaptive Management requires resources. Where the expected change is complex, adaptation is frequently necessary to ensure we are responding to context and evidence. This should be adequately resourced if we are to expect results. In an environment where many INGOs work consistently within complex environments, the sector also needs more opportunities to trial these approaches and could benefit from more funding streams available which include the kinds of approaches used by DFID in current GEC programming

Plans Are Worthless but Planning Is Everything: A Theoretical Explanation of Eisenhower’s Observation - Garcia Contreras, Angel F.; Ceberio, Martine; Kreinovich, Vladik (Decision Making under Constraints, 2020)
The 1953–1961 US President Dwight D. Eisenhower emphasized that his experience as the Supreme Commander of the Allied Expeditionary Forces in Europe during the Second World War taught him that “plans are worthless, but planning is everything”. This sound contradictory: if plans are worthless, why bother with planning at all? In this paper, we show that Eisenhower’s observation has a meaning: while directly following the original plan in constantly changing circumstances is often not a good idea, the existence of a pre-computed original plan enables us to produce an almost-optimal strategy—a strategy that would have been computationally difficult to produce on a short notice without the pre-existing plan.

Examining the results and adaptation ideas in foreign aid - Janus, Heiner (University of Manchester, 2020)
This thesis applies ideational and institutional theories to analyse how two specific ideas, results and adaptation, have changed the theory and practice of development cooperation. The thesis addresses the question of why the results and adaptation ideas are often treated as binaries and how this debate has evolved historically. In a first theoretical paper, the evolution of results and adaptation is conceptualised as a combination of institutional layering and diffusion within development organisations. The second theoretical paper applies ideational theory, in particular, the coalition magnet framework, to China as a donor country. The empirical papers apply ideational and institutional theories to study aid projects funded by the World Bank and China in the Rwandan agriculture sector. The third paper analyses through which mechanism, results-based principal-agent relationships or problem-driven iterative adaptation, the World Bankâs Program for Results in the agriculture sector in Rwanda has led to increased agricultural productivity. The paper combines causal process tracing and contribution analysis to investigate two underlying theories of change of the Program for Results. The fourth paper applies the same framework and methodology to the Chinese Agricultural Technology Demonstration Center in Rwanda. The fifth paper compares both projects, the World Bank project and the Chinese project. The thesis finds that the ideas of results and adaptation are often presented as mutually exclusive mainly at the general level of public philosophies or paradigms, but show overlap and potential for integration on the level of framing policy problems and policy solutions. The thesis also demonstrates that there is unexplored potential for convergence between China and Development Assistance Committee donors around âcoalition magnetâ ideas. The empirical part of the thesis reveals how results-based and adaptive causal mechanisms co-exist within given aid interventions by the World Bank and China, how these interact and how they ultimately contribute to achieving development outcomes. The key finding is that the broader political context of the Rwandan agricultural sector is the main factor for determining development outcomes, which neither the World Bank project nor the Chinese projects take into account. The comparison of the World Bankâs and Chinaâs interventions finds that donor organisations need to address how results-based ideas in combination adaptive development ideas can be better tailored to fit into the specific context of the Rwandan agriculture sector.

Crisis relief for adults & families everywhere - Featuring the mighty micro-VCoL - Lectica (Lectica Live, 2020)
In response to the COVID-19 pandemic and the resulting economic crisis, we're open-sourcing our most effective stress- and crisis-management learning tools. We call these tools micro-VCoLs™. All of the micro-VCoLs shared here can be practiced effectively just by following the instructions.

Virtuous cycles of learning (VCoL) and the +7 skills - Lectica (Lectica Live, 2020)
VCoL is a cycle of goal setting, information seeking, application, and reflection. Its +7 skills include reflectivity, awareness, seeking and evaluating information, making connections, applying knowledge, seeking and working with feedback, and recognizing and overcoming built-in biases. VCoLing engages the whole learner. By this, we mean that it engages learners emotionally, physically, and intellectually, leveraging both conscious and unconscious mental processes. VCoLing ensures that new knowledge is integrated into existing knowledge in a way that makes it useful and "sticky." When people work with our assessments, they're not only building knowledge, they're also nurturing the dispositions and skills required for a lifetime of learning and development.

AdaptScan - Improving your Team's Adaptive Management - Mercy Corps (Mercy Corps, 2020)

A Pragmatic Approach to Assessing System Change: How to put it into practice - Miehlbradt, Alexandra; Shah, Rachel; Posthumus, Hans; Kessler, Adam (DCED, 2020)
Planning for and assessing system change is a strategic management issue. It is critical for everything from developing a strategy and designing interventions, to adapting strategy, improving implementation and reporting impact. But many programmes get stuck when it comes to assessing system change. The private sector development field has struggled to agree on an approach that programmes can implement and stakeholders can understand. However some mature programmes are starting to assess system change more effectively. Building on these emerging practices, this paper outlines a process that programmes can use to assess system changes regularly and practically. Two complementary papers: Overview and How to put it into practice The Overview summarises the approach and How to put it into practice provides more detailed implementation guidance, worked examples, and useful tips. The Overview explores how to: develop a system change strategy and intervention plans that lay the groundwork for system change assessment, including how to set system boundaries and how to identify the system changes a programme aims to catalyse assess system changes using both: - an intervention lens focused on changes introduced by specific interventions - a helicopter lens that provides a whole system view By analysing findings from both lenses, programmes can improve their strategy and report on their contribution to system change. How to put it into practice uses two case examples for illustration throughout the paper - PRISMA’s work in the maize system in East Java and Indonesia and S4J’s work in the Vocational Education and Training (VET) system in Albania. It targets practitioners responsible for facilitating and/or assessing system change. The paper explains how to: articulate the system changes that a programme aims to catalyse assess those changes use the results to inform decision making and reporting The approach described in the paper builds on the practices outlined in the DCED Results Measurement Standard. The guidance provided has been designed to be useful to programmes that aim to catalyse system changes whether or not they apply the DCED Standard.

A new bird's eye view on the agile forest - Portman, Henny (PM World Journal, 2020)

A new bird's eye view on the agile forest (2022 update) - Portman, Henny (PM World Journal, 2020)
Some years ago, you could say “Scrum is agile” and ask “is Agile Scrum?” Now we know there is much more flesh on the bones. At this moment there are more than fifty known and less known agile approaches, frameworks or methods available. To get a first impression of the different approaches, I try to bring some structure in the jungle to approaches, methods and frameworks. In Figure 1, I position the best-known agile approaches in a structure. The approaches, frameworks or methods are positioned within the 'One-time programs / projects' sections or within 'Business as usual’ / indefinite, or both. On the other side the approaches, frameworks or methods are clustered around team, product or programme and portfolio level. In the dark blue boxes in Figure 1 we see agile approaches that are only applicable in IT-focused organizations. All other approaches can be used within IT and non-IT-oriented organizations (light blue coloured). I haven’t mapped all the known approaches, frameworks and methods in this figure, and to be honest, I think there is a lot of duplication and probably commercial drivers play a role too to ‘develop’ the next kid on the block without added value in comparison with the existing approaches, frameworks or methods. The team level, including Scrum and Kanban, is applicable in both IT-oriented and non-IT-oriented products and services development and operations. The engineering level focuses specifically on IT-oriented product development. The one-time, temporary projects and programme frameworks and methods are suitable for both IT and non-IT. The permanent umbrella frameworks (both product-targeted and team-targeted) focus specifically on IT and product development and the Culture-targeted approaches help organisations to increase their agility.

A Pragmatic Approach to Assessing System Change - Posthumus, Hans; Shah, Rachel; Miehlbradt, Alexandra; Kessler, Adam (DCED, 2020)
Planning for and assessing system change is a strategic management issue. It is critical for everything from developing a strategy and designing interventions, to adapting strategy, improving implementation and reporting impact. But many programmes get stuck when it comes to assessing system change. The private sector development field has struggled to agree on an approach that programmes can implement and stakeholders can understand. However some mature programmes are starting to assess system change more effectively. Building on these emerging practices, this paper outlines a process that programmes can use to assess system changes regularly and practically. Two complementary papers: Overview and How to put it into practice The Overview summarises the approach and How to put it into practice provides more detailed implementation guidance, worked examples, and useful tips. The Overview explores how to: develop a system change strategy and intervention plans that lay the groundwork for system change assessment, including how to set system boundaries and how to identify the system changes a programme aims to catalyse assess system changes using both: - an intervention lens focused on changes introduced by specific interventions - a helicopter lens that provides a whole system view By analysing findings from both lenses, programmes can improve their strategy and report on their contribution to system change. How to put it into practice uses two case examples for illustration throughout the paper - PRISMA’s work in the maize system in East Java and Indonesia and S4J’s work in the Vocational Education and Training (VET) system in Albania. It targets practitioners responsible for facilitating and/or assessing system change. The paper explains how to: articulate the system changes that a programme aims to catalyse assess those changes use the results to inform decision making and reporting The approach described in the paper builds on the practices outlined in the DCED Results Measurement Standard. The guidance provided has been designed to be useful to programmes that aim to catalyse system changes whether or not they apply the DCED Standard.

System Innovation Network - Si Network (Si Network, 2020)
The Si Network is an online platform for building the developing of systems innovation - connecting people around the world to learn and apply the ideas and methods of systems innovation towards addressing complex challenges and building better systems that work for all. Not sure what systems innovation is? Systems innovation is a new approach to innovation that tries to tackle complex social and environmental challenges through the use of more holistic & innovation driven approaches. It is a kind of innovation that aims to change the underlying structure of a system, thus potentially enabling a more transformational kind of change - systems change - rather than incremental "innovation as usual". What Do You Do? We are building an ecosystem of individuals and organizations co-learning and co-creating systems innovation across geographies and sectors. This ecosystem is enabled by our online platform which provides educational content, toolkits, organizes events and projects as well as provides various support services for organizations. Purpose Statement Our purpose is to build the world’s capacity for systems innovation - so as to better understand and address complex challenges and co-create a world where systems work for all. We envision a world where everyone thinks in systems and has an understanding of complex systems. From this understanding, we are able to design and develop regenerative systems that work for everyone. Our mission is to grow the field of systems innovation as a pathway to co-learn the ideas of systems thinking and apply them to co-creating new systems Who's Involved? We are a networked organization of some 17K+ members forming part of 20+ hubs in major cities around the world. Our community is broad and diverse in areas of work and interest from designers, innovators, and entrepreneurs, to researchers and management but they all share a common interest in learning and applying systems thinking ideas. The Si platform is developed and managed by a small core team based in London UK. We are registered as a business but operate as a social enterprise focused on our purpose of advancing the area of systems innovation in theory and practice. Core Value Creativity - We put creativity at the centre of what we do. Holding a space for curiosity, diversity of views, exploration and critical thinking as a pathway to transformative innovation. Openness - We strongly believe in openness in our ways of being, thinking and organizing as a sustainable pathway to creating an adaptive, scalable and dynamic community. Growth Mindset - We embrace challenges as opportunities for continuous personal and collective learning and development, with a never-ending potential to grow and start with a new beginning. Perseverance - When facing uncertainty and failure, perseverance is what is needed to maintain commitment and a resilient pathway aligned with our purpose. Care - Care is one of our core principles. We foster relationships based on honesty and empathy, striving to be present and conscious in what we do and taking responsibility for the effects of our actions.

Learning and Accountability - Simister, Nigel; Scholz, Vera (INTRAC, 2020)
Most people agree that monitoring and evaluation (M&E) should be used for both learning and accountability. However, there is no consensus about which one is more important. The debate matters as there is sometimes tension between the two purposes. In the past there has often been a disconnect between M&E and learning. Many M&E systems are primarily designed to enable accountability to donors.

Chaos Report 2020 - Standish Group (Standish Group, 2020)

Habits of a system thinker - WCST (Waters Center For Systems Thinking, 2020)
From the Waters Center For Systems Thinking. See: https://thinkingtoolsstudio.waterscenterst.org/courses/habits https://thinkingtoolsstudio.waterscenterst.org/cards

USAID Wildlife Asia as a case study in adaptive rigour - Ziegler, Jessica (ODI/GLAM, 2020)
This briefing note looks at how the United States Agency for International Development (USAID) Wildlife Asia programme has operationalised the concepts of adaptive rigour and adaptive management as part of its approach to collaborating, learning and adapting. As described by the Global Learning for Adaptive Management (GLAM) initiative, adaptive rigour is about ensuring that the data, information, methods, processes and systems that underpin adaptive management are robust, systematic and high‑quality. Key messages When faced with programmatic complexity, it is important to take an adaptive approach driven by continuous and iterative monitoring, evaluation and learning (MEL). USAID Wildlife Asia, which works to advance regional action towards ending illegal wildlife trafficking in Southeast Asia and China, has embraced this approach as a way of operationalising adaptive rigour. Throughout programming, MEL approaches should reflect the characteristics of adaptive rigour: comprehensiveness, usefulness, practicality, timeliness and support. Utilising performance monitoring and research in order to test and revise technical approaches and employing mixed methods to collect both qualitative and quantitative data, as well as looking for relevant lessons generated by others, can ensure access to the most useful information for decision-making throughout implementation. For adaptive management, it is not enough to monitor, evaluate and learn; it is also essential to pause and reflect in order to analyse and process evidence gained through MEL with colleagues and stakeholders to reach the right conclusions and make good decisions.

Adapting data collection and utilisation to a Covid-19 reality: Monitoring, evaluation and learning approaches for adaptive management - Ziegler, Jessica; Mason, Paige (ODI/GLAM, 2020)
This briefing note focuses on the remote collection and use of data for adaptive management during the Covid-19 pandemic, setting out key considerations to help practitioners think through a transition from more ‘traditional’ monitoring, evaluation and learning (MEL) to MEL for adaptive management (MEL4AM) that reflects the unique data collection challenges presented by Covid-19. The brief provides an overview of some key considerations in remote data collection, when this is required, and identifies other sources that address these issues in more detail. It concludes with a discussion of how to bring the information resulting from remote monitoring into decision-making to enable adaptive management. Key messages - When planning for remote data collection during the Covid-19 pandemic, first determine what information is still necessary, because data needs may have changed, e.g. if programming has pivoted or needs to pivot due to Covid-19. Then identify how the programme’s information needs align with existing data sources and what gaps remain, which will guide the need for remote data collection. - Also consider what data is ‘good enough’ for current decision-making needs in order to provide sufficient information to the right people at the right time to an acceptable standard of rigour. - There may be pragmatic reasons to reduce the number or scope of MEL activities, such as logistical constraints or ethical considerations introduced by the pandemic. - MEL activities should be accompanied by frequent feedback loops and pause points to reflect on emergent needs and challenges, information needs that have been met, and contextual changes that may affect MEL. - Be clear with decision-makers about the assumptions and gaps in the data, including proxies used and their limitations, sampling changes, and how these changes and assumptions may affect the decisions/options being discussed.

Applying Power Analysis: Using the ‘Powercube’ to explore forms, levels and spaces - Gaventa, John (Power, Empowerment and Social Change, 2019)
In a complex, globalised and rapidly changing world, power dynamics are multidimensional, constantly evolving, and full of complexity. The ‘powercube’ (Gaventa, 2006) is an approach to power analysis which can be used to examine the multiple forms, levels and spaces of power, and their interactions. Building on earlier work on power, and elaborated and popularised in collaboration with other colleagues through the web site powercube.net and numerous other resources, the powercube has been widely used around the world for analysis of power, education and awareness building, context analysis, programme and strategy development, and monitoring and evaluation. This article briefly outlines the evolution of the powercube, and provides examples of the issue areas in which it has been used, and for what purposes. Drawing on these, we then offer eight lessons of how to apply the powercube framework for analysing and transforming power relations.

Scrambling after Moving Targets: Monitoring & Evaluation Applied to Adaptive Management Approaches in Peacebuilding - Woodrow, Peter; Jean, Isabella (New Directions in Peacebuilding Evaluation, 2019)
In this landmark collection, the voices of pathMakers and innovators in peacebuilding evaluation are assembled to provide new direction for the field.
Keywords: IMPORTANT

Paradoxes and partnerships: a study of knowledge exploration and exploitation in international development programmes - Lannon, John; Walsh, John N. (Journal of Knowledge Management, 2019)
Purpose – This paper aims to look at how organisational partnerships balance knowledge exploration and exploitation in contexts that are rife with paradoxes. It draws on paradox theory to examine the partnership’s response to the explore-exploit relationship.

LAC MEL Specialists Use Peer Network to Improve Quality and Use of Evidence - Anderson, Todd M; Prevatt, Amy (USAID, 2019)
Based on consultations and stocktakings with LAC Missions, the LAC Bureau identified Mission Monitoring, Evaluation and Learning (MEL) Specialists as influential decision makers regarding data and evidence use. The LAC Bureau aims to improve the quality and use of evidence for decision making, and ultimately to improve development outcomes.

Failing Forward: How CARE is Focusing on What Goes Wrong to Improve Impact - Janoch, Emily (CARE, 2019)
CARE's Failing Forward initiative is sparking opportunities to showcase the ideas that don't work so we can spend more time implementing the ones that do. It's changing the conversation inside the organization, and leading to changes in the way we design and implement programs.

What’s Next for Design Thinking - Cone, Taylor (Medium, 2019)
Thoughts on the future of creative problem-solving from across the industry

VCoL in action: How to use micro-VCoLs to learn optimally on the fly - Dawson, Theo (Medium, 2019)
VCoL (the virtuous cycle of learning), is designed to optimize learning while leveraging human´s natural motivational system. It’s easiest to tap into this motivational system when VCoLs are small, focused, relevant, and habitual. We call VCoLs with these characteristics micro-VCoLs. What is a micro-VCoL? Micro-VCoLs are frequently iterated learning cycles that are embedded in everyday activities. Like any VCoL, they involve setting a learning goal, gathering information, applying information, and reflecting on outcomes (preferably with input from others). But in the case of the micro-VCoL, the focus is on the smaller skills (micro-skills) that make up complex sets of skills.

What we’re missing by not getting our TWP alphabet straight - Marquette, Heather (From Poverty to Power, 2019)
Heather Marquette grapples with aid's alphabet soup, and explains why DDD, TWP, PDIA etc are different and why that matters

A market system by any other name would smell as sweet - Kessler, Adam; Conroy, Kevin (BEAM Exchange, 2019)
How does Doing Development Differently (DDD) and Problem Driven Iterative Adaption (PDIA) connect to core principles of the MSD approach?

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of Institutions for Inclusive Development, Tanzania - Green, Duncan; Guijt, Irene (Itad, Oxfam and IDS, 2019)
Adaptive Management involves a dynamic interaction between three elements: delivery, programming and governance. This case study focuses on a large DfID governance project, the Institutions for Inclusive Development (I4ID), a five-year initiative in Tanzania. The study forms part of a research project to examine whether and how adaptive approaches can strengthen aid projects promoting empowerment and accountability in fragile, conflict and violence-affected settings (FCVAS). The research examines some of the assertions around the adaptive management approach and explores if and how adaptive approaches, including rapid learning and planning responses (fast feedback loops and agile programming) are particularly relevant and useful for citizen empowerment and government accountability (E&A) in FCVAS.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Top Tips: How to design and manage adaptive programmes - Valters, Craig; Wild, Leni (Overseas Development Institute, 2019)
Within DFID, there is now a commitment to more flexible and adaptive programming. This recognises that: • DFID works in contexts that continuously evolve and change, sometimes in unpredictable ways. To respond to this, the agency needs to remain flexible – to expect change and have a good understanding of context, with resources that can be adjusted and scope to change direction if needed. All DFID programmes should be able to do this. • Some DFID programmes aim to support change in complex systems, behaviours and incentives. Efforts to address women’s empowerment, improve sanitation or build more sustainable health systems, for instance, all require engagement with the way in which complex systems operate and the people and behaviours within them. Trying to deliver reforms in these circumstances is challenging because the pathway to reform itself will be unclear: as a reform is rolled out, the system itself will react and respond. These types of programmes therefore need to build in from the start deliberate processes of learning and testing, to allow for adaptations as more information is gathered for what works over time. These top tips are concerned with programmes that aim to be flexible and adaptive – which work in dynamic contexts and are trying to address complex problems. While there is growing commitment to these approaches, feedback suggests staff still have questions about how to do this well. This document highlights some of the commonly reported issues related to adaptive programming and a set of tips, strategies and examples to help in addressing them. It is aimed at programme managers and advisors who may be Senior Responsible Owners (SROs) or those managing and supporting adaptive programming in a range of ways. We have collated these lessons from discussions with country offices and SROs, feedback from surveys and the wider evidence. We have looked specifically at the adaptive programmes we can find in the DFID portfolio, but this is not an exhaustive list. It should be noted that there is as yet no wide variety of case law to review, but there is a growing set of examples within DFID that can provide continuous learning for the organisation.

Exploring the new world: practical insights for funding, commissioning and managing in complexity - Lowe, Toby; Plimmer, Dawn (Collaborate & Newcastle University, 2019)
The world is complex. If we want to contribute to creating positive social outcomes, we must learn to embrace this complexity. This is the New World that funders and commissioners are discovering: • People are complex: everyone’s life is different, everyone’s strengths and needs are different. • The issues we care about are complex: issues – like homelessness – are tangled and interdependent. • The systems that respond to these issues are complex: the range of people and organisations involved in creating ‘outcomes’ in the world are beyond the management control of any person or organisation. Building on the findings from our previous report, A Whole New World, we have spent the last 12 months working with a growing movement of funders, public sector commissioners, and organisations working on the ground to begin to explore this New World: to find examples of practice that will help people to navigate it effectively. This report explores the key features of their response: working in a way that is human, prioritises learning and takes a systems approach.

The Case for an Adaptive Approach to Empowerment and Accountability Programming in Fragile Settings: Synthesis report - Christie, Angela; Green, Duncan (Itad, Oxfam and IDS, 2019)
Fragile, conflict and violence-affected settings (FCVAS) are messy and ambiguous contexts in which to plan and implement development initiatives. To work there, external actors are increasingly adopting an adaptive approach to empowerment and accountability (E&A) programming, whatever the setting. This means using a compass rather than map, where real-time political economy analysis (PEA) in relation to context and programme monitoring and evidence-informed learning in relation to intervention are used in combination and in shorter-than-usual planning cycles to maintain and adapt strategic direction. This paper brings together three case studies of large Department for International Development (DFID) governance projects in Myanmar, Nigeria and Tanzania.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Implementing Adaptive Approaches in Real World Scenarios: A Nigeria Case Study, with Lessons for Theory and Practice - Bridges, Kate; Woolcock, Michael (The World Bank, 2019)
How does adaptive implementation work in practice? Drawing on extensive interviews and observations, this paper contrasts the ways in which an adaptive component of a major health care project was implemented in three program and three matched comparison states in Nigeria. The paper examines the bases on which claims and counterclaims about the effectiveness of these approaches were made by different actors, concluding that resolution requires any such claims to be grounded in a fit-for-purpose theory of change and evaluation strategy. The principles of adaptive development may be gaining broad acceptance, but a complex array of skills, expectations, political support, empirical measures, and administrative structures needs to be deftly integrated if demonstrably positive operational results are to be obtained, especially when undertaken within institutional systems, administrative logics, and political imperatives that are predisposed to serve rather different purposes.

From Thinking Politically To Working Politically: Are We Really Doing Development Any Differently? (2019)
In June it will be seven years since the Center for Global Development published the Problem Driven Iterative Adaptation (PDIA) paper. Few academic papers have had such an impact on development thinking. The question is whether the paper – and subsequent debate and experimentation - have had a demonstrable and beneficial impact on development practice. Experience to date suggests thinking politically is easier than working politically. Practitioners in development agencies, governments and contractors find that convincing theoretical literature can be tricky to operationalize in a fractious environment. Still, a growing number of programs have set out to be politically informed in design and politically savvy in implementation. Engaging the reality of politics creates the potential to promote change. To consider these issues, Abt Associates is hosting a workshop for international development practitioners in Washington, DC, on June 18th, 2019, to discuss the successes and failures in operationalizing this agenda. The session will allow practitioners to discuss experiences in TWP and propose solutions or approaches. Please join us in this Innovations in Governance series finale where four internationally renowned thinkers and doers will join us to offer their perspectives.

What Does the Evidence Tell Us about ‘Thinking and Working Politically’ in Development Assistance? - Dasandi, Niheer; Laws, Ed; Marquette, Heather; Robinson, Mark (Politics and Governance, 2019)
Abstract: This paper critically reviews evidence on ‘thinking and working politically’ in development. Scholars and practitioners have increasingly recognised that development is fundamentally political, and efforts are underway to develop more politically informed ways of thinking and working. The literature does not yet constitute a strong evidence base to link these efforts to more effective aid programming: much evidence is anecdotal, does not meet high standards of robustness, is not comparative, and draws on self-selected successes reported by programme insiders. We discuss factors commonly considered to explain the success of politically informed programmes in areas where conventional programming approaches fall short. We consider evidence in three areas—political context, sector and organization—and provide guidance on where to focus next. Finally, we outline ways of testing the core assumptions of the ‘thinking and working politically’ agenda more thoroughly, to provide a clearer sense of the contribution it can make to aid effectiveness.

Summer school on Adaptive Management - 2019 - CID (2019)
General description of the curriculum

Adaptive Management - Jenal, Marcus; Cunningham, Shawn (Annual Reflection 2019, 2019)

Knowledge Retention and Transfer (KRT) - Model and Matsurity Matrix - USAID (USAID LEARN, 2019)
The Maturity Matrix is not a standalone tool. It is one of the three major components of the KRT Model. The Maturity Matrix is meant to be used in conjunction with the KRT Toolkit and Implementation Plan.

Managing staff transistions through CLA: preserving institutional memory as staff come and go - USAID (USAID LEARN, 2019)
This document is relevant for any position or hiring mechanism. While this document does not explicitly address what happens when someone arrives into a newly-created position, which has its own set of challenges, many of the principles, actions, and resources can be applied in that context. Section 1 offers guidance for how to set up and implement systems at Mission/OU or office to ensure that all staff help preserve institutional memory and enable continuity of relationships. This section is for any staff in a Mission/OU working to build systems that improve handovers and knowledge capture and sharing across the Mission or OU. If a Mission or OU is just beginning to develop a system to manage staff transitions, you may want to start by developing a system within an office or team and then expand it out to other offices or to the Mission/OU writ large. Section 2 includes key principles and actions individuals could consider following when arriving or departing a position, regardless of hiring mechanism and position. This includes staff new to the Mission/OU and staff who are currently in the Mission/OU and are moving into a new position. Section 3 provides a select number of resources to help you take a systematic and comprehensive approach to manage staff transitions as effectively and efficiently as possible at the individual or organizational level.

Making Sense of Complexity: Using SenseMaker as a Research Tool - Van der Merwe, Susara E.; Biggs, Reinette; Preiser, Rika; Cunningham, Charmaine; Snowden, David J.; O’Brien, Karen; Jenal, Marcus; Vosloo, Marietjie; Blignaut, Sonja; Goh, Zhen (Systems, 2019)
There is growing interest in studying processes of human sensemaking, as this strongly influences human and organizational behavior as well as complex system dynamics due to the diverse lenses people use to interpret and act in the world. The Cognitive Edge SenseMaker® tool is one method for capturing and making sense of people’s attitudes, perceptions, and experiences. It is used for monitoring and evaluation; mapping ideas, mind-sets, and attitudes; and detecting trends and weak signals. However, academic literature describing the tool-set and method is lacking. This introduction aims to guide researchers in choosing when to use SenseMaker and to facilitate understanding of its execution and limitations. SenseMaker can provide nuanced insight into system-level patterns of human sensemaking that can provide insight to nudge systems towards more desirable futures, and enable researchers to measure beyond what they know.
Keywords: Mixed methods; SenseMaker tool; complex systems; sensemaking; social complexity

You might not be as agile as you think you are - Lindpaintner, Julia; Rivera, Stephanie (18F, 2019)
The mandate to be agile is everywhere. But agile isn’t an on-off switch. It’s a skill and a mindset that is developed over time, through dedicated work, open teams, and lots (and lots) of practice

Scaling Impact: Innovation for the Public Good - McLean, Robert; Gargani, John (Routledge, 2019)
Scaling Impact introduces a new and practical approach to scaling the positive impacts of research and innovation. Inspired by leading scientific and entrepreneurial innovators from across Africa, Asia, the Caribbean, Latin America, and the Middle East, this book presents a synthesis of unrivalled diversity and grounded ingenuity. The result is a different perspective on how to achieve impact that matters, and an important challenge to the predominant more-is-better paradigm of scaling. For organisations and individuals working to change the world for the better, scaling impact is a common goal and a well-founded aim. The world is changing rapidly, and seemingly intractable problems like environmental degradation or accelerating inequality press us to do better for each other and our environment as a global community. Challenges like these appear to demand a significant scale of action, and here the authors argue that a more creative and critical approach to scaling is both possible and essential. To encourage uptake and co-development, the authors present actionable principles that can help organisations and innovators design, manage, and evaluate scaling strategies. Scaling Impact is essential reading for development and innovation practitioners and professionals, but also for researchers, students, evaluators, and policymakers with a desire to spark meaningful change.
Google-Books-ID: 9X6YDwAAQBAJ
Keywords: Developing & Emerging Countries

The guiding logics and principles for designing emergent transdisciplinary research processes: learning experiences and reflections from a transdisciplinary urban case study in Enkanini informal settlement, South Africa - van Breda, John; Swilling, Mark (Sustainability Science, 2019)
Transdisciplinarity is not a new science per se, but a new methodology for doing science with society. A particular challenge in doing science with society is the engagement with non-academic actors to enable joint problem formulation, analysis and transformation. How this is achieved differs between contexts. The premise of this paper is that transdisciplinary research (TDR) methodologies designed for developed world contexts cannot merely be replicated and transferred to developing world contexts. Thus a new approach is needed for conducting TDR in contexts characterised by high levels of complexity, conflict and social fluidity. To that end, this paper introduces a new approach to TDR titled emergent transdisciplinary design research (ETDR). A core element of this approach is that the research process is designed as it unfolds, that is, it transforms as it emerges from and within the fluid context. The ETDR outlined in this paper emerged through a case study in the informal settlement (slum) of Enkanini in Stellenbosch, South Africa. This case study demonstrates the context from and within which the ETDR approach and identifies a set of guiding logics that can be used to guide ETDR approaches in other contexts. The study demonstrates that the new logics and guiding principles were not simply derived from the TDR literature, but rather emerged from constant interacting dynamics between theory and practice. Learning how to co-design the research process through co-producing transformative knowledge and then implementing strategic interventions to bring about incremental social change is key to theory development in ways that are informed by local contextual dynamics. There are, however, risks when undertaking such TDR processes such as under-valuing disciplinary knowledge, transferring risks onto a society, and suppressing ‘truth-to-power’.

Barrio Mio and Katye: PCI’s neighbourhood approach in cities - Campbell, Leah (ALNAP/ODI, 2019)

Help! I’m hiring new staff and I want them to work adaptively. A guide to hiring adaptive employees. - Salib, Monalisa (USAID LEARN, 2019)
If you are involved in hiring, this tool can help you increase your chances of selecting staff members skilled in adaptive management. It will help answer the questions: Which competencies should I recruit for in order to hire more adaptive employees? Which desired qualifications should I incorporate into position descriptions to attract adaptive employees? Which interview questions should I ask to screen for adaptive employee competencies? You should use this tool when you decide to hire a new individual - whether that be a direct hire, contractor, or consultant - or when you are changing an individual’s current position description or scope of work. Specifically, this tool will help you determine which qualifications are most important for the position and offers interview questions you can use with candidates. — You’re in luck! We just released a new guide for hiring adaptive employees. This visual and user-friendly tool will help increase your chances of selecting staff skilled in adaptive management. Here are the details: What do you mean by “work adaptively” or an “adaptive employee”? An adaptive employee is an individual who, in collaboration with relevant stakeholders, systematically acquires and uses knowledge to make decisions and adjustments in their work in order to achieve greater impact. Why focus on adaptive employees? Why does it matter? With industries, technologies, and organizations in a near constant state of flux, leaders are recognizing the importance of adaptability as a critical capacity. Because of this, it’s not surprising that a recent LinkedIn report found that adaptability was the most important soft skill hiring managers were screening for. In addition, evidence shows that teams that apply more data-driven and adaptive leadership practices perform better than those that focus less on these practices. It makes sense, then, that managers want to recruit more team members who are skilled in adaptive management - it helps achieve results. Who should use this tool? Anyone involved in hiring, responsible for developing or approving position descriptions, participating in interviews, and/or approving new hires. When should I use this tool? Use it as soon as you decide to hire a new staff person or when you’re adjusting existing position descriptions. What does the tool help me do? It will help you think through: Which competencies should I recruit for in order to hire more adaptive employees? Which desired qualifications should I incorporate into position descriptions to attract adaptive employees? (You can even copy and paste qualification language from the tool into scopes of work!) Which interview questions should I ask to screen for adaptive employee competencies? (You can copy and paste interview questions into your screening, interview, and reference check protocols!) Has the tool been tested? Yes, staff within USAID’s Global Development Lab and on the USAID LEARN contract tested the tool, providing feedback on the minimum viable product and subsequent versions. Testers confirmed finding the tool useful, and gave it a 9/10 score when asked if they would recommend it to colleagues. Some specific feedback from testers included: "The tool prompts deeper thought on what you might need and want in a job candidate" and "All [of the interview questions I used from the tool] worked well." What about the existing staff? How can they gain greater skills in adaptive management? Existing USAID staff and implementing partners can access online training in collaborating, learning, and adapting (CLA) and find resources in the CLA Toolkit. USAID staff also have access to an internal CLA community of practice and five-day, in-person CLA training.

A Guide to Digital Feedback Loops. An approach to strengthening program outcomes through data for decision making - Whittle, Dennis; Campbell, Megan (USAID, 2019)
Feedback is information about what happens as a result of what you do. Using that information to adapt what you do or how you do it creates what is called a feedback loop. A digital feedback loop uses digital technology at some stage of the feedback loop. Digital feedback loops help USAID missions improve the effectiveness and efficiency of their activities and can support partner countries on their journey to self-reliance through increased information sharing and improved government and civil society capacity. USAID missions and their partners have used digital feedback loops to improve HIV treatment targeting in Zimbabwe, engage three million young people in Nigeria in policy, and reduce field reporting times from one month to one day. Digital feedback loops provide access to information faster and more cheaply than ever before. As part of an adaptive management approach, digital feedback loops increase our ability to act on opportunities and respond to challenges. That in turn can improve outcomes and reduce the risk of waste and failure. This guide outlines the case for integrating digital feedback loops into your work, and provides tools, resources and guiding questions to support you as you get started. The guide includes examples of how USAID missions are using digital feedback loops to improve their programs in various sectors and provides worksheets to help you apply digital feedback loops to your own context.

Scale Up Sourcebook - Cooley, Larry; Howard, Julie (Scale Up Conference, 2019)
The Scale Up Sourcebook is informed and inspired by the September 2018 conference, Innovations in Agriculture: Scaling Up to Reach Millions, organized by Purdue University, in partnership with the African Development Bank. The Sourcebook consolidates, extends, and disseminates some of the scaling insights presented at the Purdue conference. It is intended as an easy-to-use guidebook targeted to a broad and diverse audience of stakeholders associated with scaling agricultural technologies and innovations to meet the needs of the world’s poor. The Sourcebook has nine chapters: designing with scale in mind; assessing scalability; using commercial markets to drive scaling; financing the transition to scale; creating an enabling environment for scale; tailoring metrics, monitoring, and evaluation to support sustainable outcomes at scale; and the critical role of intermediary and donor organizations. The Sourcebook provides guidance, tips, and examples, along with links and references to additional resources on scale up.

How Does the World Bank Build Citizen Engagement Commitments into Project Design? Results from Pilot Assessments in Mozambique, Myanmar, Nigeria, and Pakistan - Nadelman, Rachel; Le, Ha; Sah, Anjali (IDS, 2019)
How and to what degree is the World Bank putting its new institutional citizen engagement (CE) commitments into practice? This question guides an independent assessment that the Accountability Research Center (ARC) at American University has undertaken as part of the Institute of Development Studies-led Action for Empowerment and Accountability (A4EA) research programme’s investigation into how external actors can best support local processes of and conditions for empowerment and accountability. This report investigates the World Bank’s incorporation of CE into project design, the critical early stage of donor engagement. To accomplish this, ARC reviewed the World Bank’s fiscal year 2015–17 investment project portfolios for four A4EA priority countries, Mozambique, Myanmar, Nigeria, and Pakistan, which covers 57 projects that range from US$19 million to U$600 million. The analysis determines whether projects commit to seeking a strategic approach to CE, which involves combining multiple tactics so that the whole could be greater than the sum of the parts. This assessment of CE commitments is intended to help to inform possible national, civil society organisation strategies to monitor whether and how these commitments are actually implemented in practice.

Making adaptive rigour work - Principles and practices for strenghening monitoring, evaluation and learning for adaptive management - Ramalingam, Ben; Wild, Leni; Buffardi, Anne L (ODI/GLAM, 2019)
Adaptive programmes can be accountable, rigorous and high quality in how they use evidence by taking an ’adaptive rigour’ approach. Core development and humanitarian challenges are complex, and require processes of testing, learning and iteration to find solutions – adaptive management offers one approach for this. Yet large bureaucracies and development organisations can have low tolerance for experimentation and learning, and adaptive management can be viewed as an excuse for ‘making things up as you go along’. This briefing from the Global Learning for Adaptive Management (GLAM) initiative argues that adaptive programmes can be accountable, rigorous and high quality in how they use evidence – but this requires rethinking some key assumptions about how they are practised. The paper sets out three key elements of an ‘adaptive rigour’ approach: - Strengthening the quality of monitoring, evaluation and learning data and systems. - Ensuring appropriate investment in monitoring, evaluation and learning across the programme cycle. - Strengthening capacities and incentives to ensure the effective use of evidence and learning as part of decision-making, leading ultimately to improved effectiveness.

Learning from Results-Based Management evaluations and reviews - Vähämäki, Janet; Verger, Chantal (OECD, 2019)
What have we learned from implementing results-based management in development co-operation organisations? What progress and benefits can be seen? What are the main challenges and unintended consequences? Are there good practices to address these challenges? To respond to these questions this paper reviews and analyses the findings from various evaluations and reviews of results-based management systems conducted by members of the Development Assistance Committee (DAC), the OECD/DAC Results Community Secretariat and other bodies in the past four years (2015-2018). It also draws on emerging lessons from new methods for managing development co-operation results. This analytical work aims to: identify recent trends in results-based management, explore challenges faced by providers when developing their results approaches and systems, select good practices in responding to these challenges that can be useful for the OECD/DACResults Community, considering new approaches, new technologies and evolving contexts. This body of evidence will inform the development of a core set of generic guiding principles for results-based management in development co-operation.

How We Model Matters: A Manifesto for the Next Generation of Program Theorizing - Whynot, Jane; Lemire, Sebastian; Montague, Steve (Canadian Journal of Program Evaluation, 2019)
In this concluding article, grounded on the exemplary contributions contained in the preceding pages, the guest editors scale the proverbial soapbox and present a manifesto to guide the pursuit and advancement of the next generation of program theorizing. Formulating ten declarations for program theory development and examination, the modest hope of the authors is to motivate and inspire reflective evaluation practitioners to broaden their views, approaches, and techniques for future program theorizing.

Bringing adaptive management to life: Insights from practice - Arora, Anmol; Gogoi, Elizabeth; Joy, Divya; Kumar, Pankaj; Luthra, Rajni; Pal, Uma; Pervaiz, Arif (Oxford Policy Management, 2019)

How DFID can better manage complexity in development programming - Sharp, Samuel; Valters, Craig; Whitty, Brendan (ODI, 2019)
The United Kingdom’s (UK) Department for International Development (DFID) is an ambitious government department that is committed to reducing poverty and conflict overseas. Many of the issues on which DFID works are complex; whether focused on climate change, gender equality, health or other priorities, simple solutions rarely exist. And to tackle these complex challenges, DFID staff must interact with unpredictable systems of political, organisational and individual behaviours and incentives. There is a risk that complex problems spur more complicated programmes; that the complexity of development challenges is addressed through designing programmes with too many projects and implementers. While there may be valid reasons for this, too many of these complicated programmes will overburden staff. This briefing note is the outcome of an ongoing process within DFID to confront these issues and answer the question: how can DFID design and manage programmes to address complex development challenges without creating too much staff workload? Key messages DFID deals with complex problems, which require flexible systems to support testing, learning and adaptation. • Complex problems do not necessarily require workload-heavy delivery structures, but simpler approaches depend on delivery partners’ experience and competence. • However, programmes that tackle complex problems do require more hands-on engagement and face more workload from inflexible compliance requirements. We suggest that DFID and similar agencies: • Pay closer attention to delivery options in programme design, making use of existing options where possible and, where not, fostering local organisations through long-term investments. • Encourage programme designers to articulate how ambition matches resources and consider ‘good enough’ design. • Reduce the burden of compliance by cultivating partner autonomy, reassessing results and valuefor-money requirements and promoting more flexible contracting and procurement. • Plan and prioritise management resources across a portfolio of programmes to make sure they can be focused in the right areas, where the complexity of the problem requires greater engagement.

Agile Development in the Age of Adaptive Management - Davis, Taryn; Orton-Vipond, Sarah; Staid, Martha (Development Gateway, 2019)
Adaptive management – the idea that development projects should respond to real life complexities and be flexible enough to respond to unforeseen changes – is an often-praised approach to doing development differently, with donors and partners exploring how to apply it within their programming.

Towards ‘Targeted Systems Change’ - Rye, Sam (Fieldnotes by Sam Rye, 2019)
Modelling and communicating how to shift systems

Thinking and Working Politically in Economic Development Programmes – Some Sprints and Stumbles from a DFID Programme in Kyrgyzstan - Koleros, Andrew; Rinnert, David (From Poverty to Power, 2019)
A DFID programme in Kyrgyzstan offers useful insights into how the Thinking and Working Politically approach can escape from its governance ghetto
Keywords: Case Study

Short Course - Adaptive Management, an overview - Bazaz Smith, Komal (American University, 2019)

AID Programming Guide - DFAT (Australian Government, 2019)

Peacebuilding design, monitoring, and evaluation: A Training Package for participants and trainers at intermediate to advanced levels - Ernstorfer, Anita; Barnard-Webster, Kiely (Carnegie Corporation, 2019)
This training package includes 7 Training Modules and a set of Annexes (Annexes A-O). The Training Modules build on each other and should ideally be used in a sequenced way in a training setting. However, for groups with specific training needs around particular areas, modules can also be used individually, but need to be tailored by the trainers and facilitators to meet the needs of specific audiences. The annexes provide worksheets and hand-outs that can be used as resources during the training for specific modules and exercises.

Hospicing The Old - Robinson, Cassie (Stewarding Loss, 2019)
In 2010 I was introduced to the Berkana Institutes’s Two Loop model, and I come back to it again and again. As I’ve moved across different…

Digital Development: Elements of a Critical ICT4D Theory and Praxis - Bon, Anna; Akkermans, Hans (Information and Communication Technologies for Development. Strengthening Southern-Driven Cooperation as a Catalyst for ICT4D, 2019)
In recent years, critical research literature in ICT4D has grown. It is widely accepted that theory is to inform practice. However, the inverse directionality, practice informs theory, is much less present in ICT4D, including in critical research. In this paper, we discuss ways how ICT4D research and theory may be better informed by practice—in terms of (i) recognizing praxis-oriented research paradigms and integrating their results, (ii) development of foundational theories, (iii) critical analysis of ICT4D emerging policies, and (iv) positioning ICT4D in the wider development debate. This suggests several elements or directions in which critical research has the potential to push current boundaries of ICT4D in terms of content as well as relevance.
Keywords: Action research paradigm; Critical research; Network complexity theory; Principles for Digital Development

Polycentric Systems of Governance: A Theoretical Model for the Commons - Carlisle, Keith; Gruby, Rebecca L. (Policy Studies Journal, 2019)
Polycentricity is a fundamental concept in commons scholarship that connotes a complex form of governance with multiple centers of semiautonomous decision making. If the decision-making centers take each other into account in competitive and cooperative relationships and have recourse to conflict resolution mechanisms, they may be regarded as a polycentric governance system. In the context of natural resource governance, commons scholars have ascribed a number of advantages to polycentric governance systems, most notably enhanced adaptive capacity, provision of good institutional fit for natural resource systems, and mitigation of risk on account of redundant governance actors and institutions. Despite the popularity of the concept, systematic development of polycentricity, including its posited advantages, is lacking in the commons literature. To build greater clarity and specificity around the concept, we develop a theoretical model of a polycentric governance system with a focus on the features necessary or conducive for achieving the functioning predicted by commons scholars. The model is comprised of attributes, which constitute the definitional elements, and enabling conditions, which specify additional institutional features for achieving functionality in the commons. The model we propose takes the concept a step further toward specificity without sacrificing the generality necessary for contextual application and further development.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/psj.12212

Pocket Guide to Systems Wayfinding - Davidson, Seanna (The Systems School, 2019)

EvalC3 - Davies, Rick (2019)
Tools for developing, exploring and evaluating predictive models of expected outcomes

Adaptive Management Practice in the UK Government - The MUVA case - HLS (Human Learning Systems, 2019)
Case study about the MUVA programme in Mozambique. (Maybe it "misses the point of AP which is not learning for learning. Is learning for impact. The word impact doesn’t even come up once!") Adaptive Management programming within the Foreign & Commonwealth Development Office demonstrates that the UK Government has examples of optimising for learning within its existing management practice. However, currently, the adaptive management practices are unhelpfully framed by an approach which limits both their effectiveness and scope. The programmes use learning as their metastrategy. They succeed in connecting practicebased learning with strategic learning, and make a shift towards reframing accountability as accountability for learning. This learning strategy is enabled by funding and contract management arrangements which prioritise learning. Both at macro-level of programme management and micro level of de-risking experimentation and enabling necessary failure by decoupling people’s job security from potential failure.

Monitoring and Result Measurement for Adaptive Programming - How to Use Data to Manage a MSD Program: Lessons from PRISMA - Khan, Khaled; Seely, Kevin; Ridwan, Mustika; Mulya, Bodhiya (PRISMA, 2019)
Using monitoring data to improve interventions is harder than it seems. Decision-makers are often busy implementing activities, unclear about their roles in data collection and analysis, and uncertain what data matters most or when. PRISMA, an AUD77 million agricultural Market Systems Development (MSD) programme funded by DFAT Australia, has encountered these challenges. With the programme completing its first five year phase, this case study shares ten key lessons divided into three sections: shaping the culture, developing systems, and top management decisions. These lessons aim to help program, sector and intervention managers make better use of monitoring data to improve interventions.

Thinking and Working Politically: Learning from practice. Overview to Special Issue - McCulloch, Neil; Piron, Laure-Hélène (Development Policy Review, 2019)
Over the last 15 years, a set of ideas now referred to as “thinking and working politically” (TWP) has coalesced into a “second orthodoxy” about how to take context into account when implementing development interventions. This approach stresses the importance of obtaining a better understanding of the local context (“thinking politically”) in order to support local actors to bring about sustainable developmental change (“working politically”). However, the evidence base to justify this new approach remains thin, despite a growing number of programmes which purport to be implementing it. Officials in development agencies struggle with putting it into practice and it is unclear how TWP differs—or not—from similar approaches, such as Problem Driven Iterative Adaptation (PDIA) and Doing Development Differently (DDD). This Special Issue sheds light on what TWP means in practice by examining a set of initiatives undertaken by both development partners and government departments in Nigeria, the Occupied Palestinian Territories, China and India. This overview article outlines, in brief, each of the Special Issue's four papers and then draws out five lessons—for funders and for practitioners—from across all the papers. Our five lessons are: (1) the fundamental importance of undertaking political economy analysis (PEA) to adapt programmes to their contexts; (2) the importance of having a realistic level of ambition for interventions; (3) the need to support local ownership—not just “agreement ownership” (between a donor agency and government) or local “management ownership” of the programme, but critically “driver ownership” by generating trust with the key local actors driving change; (4) the need for a more effective set of tools for measuring results in complex programmes that attempt to achieve improvements in long-run governance; and, (5) that although the political economy of donors is often seen as a barrier to applying TWP, the articles show how much can be done with a TWP approach if the analysis takes into account the political economy of donors as well as that of the local context. We conclude with a set of operational recommendations for donors and implementors, as well as suggestions of avenues for further research.
Keywords: Adaptation; Development programmes; Political economy analysis; Reform space; thinking and working politically

Evaluation of development programmes - OECD - OECD (2019)
Data & research on evaluation of development programmes inc. paris declaration, budget support, multilateral effectiveness, impact evaluation, joint evaluations, governance, aid for trade

Planning & Navigating Social Change - Tools for Pacific voyagers - Orr, Douglas Epeli; Cavatore, Maria; Aston, Tom (Oxfam, 2019)
Those working to advance social change in the Pacific must understand, work with and respond to the complex and changing relationships and dynamics of power that exist within such networks, and situate their work in the context of decolonisation and self-determination. But the approaches typically used by NGOs to plan our projects and programs have failed to give due attention to these dynamics. The result is that our projects fall short of achieving their promise, despite being technically sound and logical. In this guide, we aim to provide a process and tools that prioritise and draw out the rich, often implicit, knowledge that Pacific Islanders have about our contexts to plan and manage social change initiatives in a manner that values and responds to this ocean of relationships. Drawing from these relationship-based and voyaging traditions, we emphasise the need to: • frame change in terms of change in people; e.g. change in the situation of groups of people and change in terms of the actions of people; • identify a course towards a particular ‘change destination’; • identify the signs to read that will help you determine where you are on that course; • be constantly attentive to the context as you make the journey, and • be ready to adjust your course in response to changes in your context. To support this way of working, we have selected a number of tools from approaches that we believe fit. In particular, we have drawn from the following approaches: • Thinking and Working Politically and other ‘politically aware’ approaches that recognise that the success of a development initiative will be determined by the interplay of relationships of power within a particular context, not just by having the right technical solution; • Outcome mapping because of its focus on people and relationships, and on identifying and supporting needed changes in the behaviour of specific actors in relation to others. This is key, because it’s individuals who deliver services, individuals who decide whether to allocate budget and resources to address a problem, and individuals who make the choice to believe whether a service is relevant to solving their issues; • Adaptive management because of its recognition that development initiatives take place within complex and changing systems and need to adjust to these and that this requires ongoing learning and adaptation.

The Rapid Evaluation, Action, and Learning (REAL) Approach: A toolkit to measure and refine changes and interventions in health campaigns - PATH (PATH, 2019)
Evaluative Tools for Improving Campaign Effectiveness Public health campaigns aim to control disease or deliver essential health services and products through time-limited and periodic channels. Many countries use campaigns to augment or replace routine service delivery, to target certain populations, or to accelerate progress towards coverage targets. The Root Cause Analysis and Rapid Evaluation, Action, and Learning toolkits present a systematic but flexible approach to identifying the root causes of campaign bottlenecks and then designing, testing, and refining solutions to optimize potential impact. These toolkits respond to a growing need for “fit-for-purpose” rapid-testing, adaptive learning approaches to evaluation and the need for a culture shift toward iterative adaptation and improvement that integrates measurement and evidence-informed decision-making into daily practice. The comprehensive package of toolkits, in addition to the individual Root Cause Analysis toolkit and Rapid Evaluation, Action, and Learning toolkit are available below.

Identifying general trends and patterns in complex systems research: An overview of theoretical and practical implications - Preiser, Rika (Systems Research and Behavioral Science, 2019)
Research on complex systems is becoming more prolific, and there is a need to provide some point of orientation to researchers and practitioners that are drawing on the body of literature that informs the field of complexity research. In this paper, I aim to give an overview of the development of the field and offer some overarching trends and patterns that are recognizable in research on complex systems. The paper then draws on the work to provide six organizing principles of complex systems to inform practical implications and methods for studying and understanding complex systems.
Keywords: complex systems; heuristics; trends and patterns

What is Uncertainty and Why Does it Matter? - Scoones, Ian (STEPS centre, 2019)
Uncertainty defines our times. Whether it is in relation to climate change, disease outbreaks, financial volatility, natural disasters or political settlements, every media headline seems to assert that things are uncertain, and increasingly so. Uncertainty, where we do not know the probabilities of either likelihoods or outcomes, is different to risk, the implications of which are explored in this paper through five different ways of thinking about uncertainty, derived from highly diverse literatures encompassing societal, political, cultural, practice and individual perspectives. The paper continues by examining how these perspectives relate to four domains: finance and banking; critical infrastructures; disease outbreaks and climate change; natural hazards and disasters. Reflecting on these experiences, the paper argues that embracing uncertainty raises some fundamental challenges. It means questioning simple, linear perspectives on modernity and progress. It means rethinking expertise and including diverse knowledges in deliberations about the future. It means understanding how uncertainties emerge in social, political and economic contexts, and how uncertainties affect different people, depending on class, gender, race, age and other dimensions of social difference. And, if uncertainty is not reducible to probabilistic risk, it means a radically different approach to governance; one that rejects control-oriented, technocratic approaches in favour of more tentative, adaptive, hopeful and caring responses. The paper concludes by asking whether we can learn from those who live with and from uncertainty – including pastoralists in marginal settings – as part of a wider conversation about embracing uncertainties to meet the challenges of our turbulent world.

Agile distributed software development in nine Central European teams: challenges, benefits and recommendations - Stadler, Manuel; Vallon, Raoul; Pazderka, Martin; Grechenig, Thomas (Information Technology, 2019)

Doing adaptive management at Sida - Tim Ruffer; Helen Bailey; Stefan Dahlgren; Patrick Spaven; Mark Winters (SIDA, 2019)
Lessons from the market systems development approach The evaluation focuses on Sida’s management of MSD projects. The projects are applying the MSD approach with an aim to: - contribute to improved MSD programming by Sida through better management practices across the project cycle - generate recommendations on how Sida can create conducive conditions for systems approaches and adaptive programming more generally. The brief assesses Sida’s organisational capacity for adaptive management in three dimensions: - leadership and culture - staff capacities - skills, and systems and procedures

Evaluation of the market systems development approach: Lessons for expanded use and adaptive management at Sida Volume I: Evaluation Report - Ruffer, Tim; Bailey, Helen; Dahlgren, Stefan; Spaven, Patrick; Winters, Mark (Sida, 2018)
This report presents the findings of an evaluation of Sida’s management of the market systems development (MSD) approach. It aims to inform thinking on how Sida can best manage its growing portfolio of MSD programs. Beyond this, it provides insights relevant to Sida’s wider support to complex and adaptive programs. The evaluation identified several factors that affect Sida’s ability to ensure that conducive conditions are in place for effective MSD programs and good development programming more generally. Sida’s relatively flexible framework of rules, guidelines and systems for project management provide the space needed for staff to innovate and manage adaptively. But for this to happen consistently and effectively, Sida needs to invest more deliberately in building the capacity of its staff in relevant areas. In addition, leadership and incentives are key to shaping a culture of active experimentation and learning. This needs to be supported with clearer guidance for those involved in the design and appraisal of MSD projects; and strengthened oversight of project performance, including through adjustments to Sida’s contracts and funding agreements.

Evaluation of the market systems development approach: Lessons for expanded use and adaptive management at Sida Volume II: Case studies - Ruffer, Tim; Bailey, Helen; Dahlgren, Stefan; Spaven, Patrick; Winters, Mark (Sida, 2018)
This report presents the findings of an evaluation of Sida’s management of the market systems development (MSD) approach. It aims to inform thinking on how Sida can best manage its growing portfolio of MSD programs. Beyond this, it provides insights relevant to Sida’s wider support to complex and adaptive programs. The evaluation identified several factors that affect Sida’s ability to ensure that conducive conditions are in place for effective MSD programs and good development programming more generally. Sida’s relatively flexible framework of rules, guidelines and systems for project management provide the space needed for staff to innovate and manage adaptively. But for this to happen consistently and effectively, Sida needs to invest more deliberately in building the capacity of its staff in relevant areas. In addition, leadership and incentives are key to shaping a culture of active experimentation and learning. This needs to be supported with clearer guidance for those involved in the design and appraisal of MSD projects; and strengthened oversight of project performance, including through adjustments to Sida’s contracts and funding agreements.

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of PERL, Nigeria - Punton, Melanie; Burge, Richard (Itad, Oxfam and IDS, 2018)
This paper examines adaptive approaches to aid programming in Nigeria. Through field research and desk reviews, we have investigated some of the assertions around the ‘adaptive management and programming’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blueprint and linear project plans. This is the second of three case studies in a series which explore if and how adaptive approaches, including rapid learning and planning responses, are particularly relevant and useful for promoting empowerment and accountability in fragile, conflict and violence-affected settings (FCVAS). This case study focuses on PERL (Partnership to Engage, Reform and Learn) in Nigeria, a five-year governance programme (2016-21) with a total budget of £100 million. It aims to promote better service delivery through bringing together government and citizens groups to collectively address governance challenges. PERL is viewed by DFID as the final stage of a 20-year investment, building on learning, experience and partnerships from 15 years of DFID-funded governance programming in Nigeria. It was designed to incorporate learning and adaptation through a ‘living’ theory of change, continuous political economy analysis at different levels, adaptive implementation by location-based delivery teams who are encouraged to be flexible and let partners take the lead, regular learning and reflection, and adaptive resourcing, HR and administrative systems. The case study draws on a conceptual framework (the ‘adaptive triangle’) that looks at three types of adaptation – adaptive management, adaptive programming and adaptive delivery – and the interconnections and tensions between them.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Evaluation and learning in complex, rapidly changing health systems: China’s management of health sector reform - Xiao, Yue; Husain, Lewis; Bloom, Gerald (Globalization and Health, 2018)
Healthcare systems are increasingly recognised as complex, in which a range of non-linear and emergent behaviours occur. China’s healthcare system is no exception. The hugeness of China, and the variation in conditions in different jurisdictions present very substantial challenges to reformers, and militate against adopting one-size-fits-all policy solutions. As a consequence, approaches to change management in China have frequently emphasised the importance of sub-national experimentation, innovation, and learning. Multiple mechanisms exist within the government structure to allow and encourage flexible implementation of policies, and tailoring of reforms to context. These limit the risk of large-scale policy failures and play a role in exploring new reform directions and potentially systemically-useful practices. They have helped in managing the huge transition that China has undergone from the 1970s onwards. China has historically made use of a number of mechanisms to encourage learning from innovative and emergent policy practices. Policy evaluation is increasingly becoming a tool used to probe emergent practices and inform iterative policy making/refining. This paper examines the case of a central policy research institute whose mandate includes evaluating reforms and providing feedback to the health ministry. Evaluation approaches being used are evolving as Chinese research agencies become increasingly professionalised, and in response to the increasing complexity of reforms. The paper argues that learning from widespread innovation and experimentation is challenging, but necessary for stewardship of large, and rapidly-changing systems.

Connect. Learn. Adapt. Repeat - Practicing adaptive management in complex, conflict-affected environments: barriers and promising practices - Queen, Emily Forsyth (2018)
To shift aid culture toward adaptive management, we can: - Stay humble, empathetic, and build skills in facilitation and listening. - Focus on working with more flexible foundations or individual donors. Or, work for more rigid donors and help make their policies more flexible. - Get clearer about goals and processes while finding ways to be less specific and more committed to local leadership about pathways to get to the goal. - Resist looking for a magic adaptive management tool and instead get clearer about when teams make what kinds of decisions and matching to tools that support that decision-making. - Validate that everyone’s perspective is a form of data and try out simple ways to document how teams learns and changes. - Broaden and ground the idea of expertise – remembering that, especially when working with folx on the margins, people are the only experts on their own life. Practitioners must also examine how dominant patriarchal, white supremacist, colonial ideas have pushed us toward wanting more control, less flexibility, and less space for equitable decision making.

Guidance: Rigor and Reproducibility in Grant Applications | grants.nih.gov - NIH (National Institutes of Health, 2018)

USAID ADS 201 - Program Cycle Operational Policy (Update 10/29/2018) - USAID (USAID, 2018)

Course: Introduction to Collaborating, Learning and Adapting (CLA) in the Program Cycle - USAID LEARN (USAID Learning Lab, 2018)

Advancing Work with the Grain at USAID - Jacobstein, David (USAID Learning Lab, 2018)
In December 2017, I wrote a blog about some of the insights gained during a workshop on Context-Driven Adaptation, where many of our sharpest field officers shared the ways that they assessed and adapted to shifts in context to keep programming relevant and effective.

Putting Gender into Political Economy Analysis: why it matters and how to do it - Brown, Emily; Haines, Rebecca; O’Neil, Tam (From Poverty to Power, 2018)
Gender specialists from Oxfam and Care introduce a new guide that covers both theory and practice of including gender in political economy analysis.
Keywords: Gender

Portfolios of Agile Projects: A Complex Adaptive Systems’ Agent Perspective - Sweetman, Roger; Conboy, Kieran (Project Management Journal, 2018)
While agile approaches can be extremely effective at a project level, they can impose significant complexity and a need for adaptiveness at the project portfolio level. While this has proven to be highly problematic, there is little research on how to manage a set of agile projects at the project portfolio level. What limited research that does exist often assumes that portfolio-level agility can be achieved by simply scaling project level agile approaches such as Scrum. This study uses a complex adaptive systems lens, focusing specifically on the properties of projects as agents in a complex adaptive portfolio to critically appraise current thinking on portfolio management in an agile context. We then draw on a set of 30 expert interviews to develop 16 complex adaptive systems (CAS)-based propositions as to how portfolios of agile projects can be managed effectively. We also outline an agenda for future research and discuss the differences between a CAS-based approach to portfolio management and traditional approaches.

Timely evaluation in international development - Webster, Jayne; Exley, Josephine; Copestake, James; Davies, Rick; Hargreaves, James (Journal of Development Effectiveness, 2018)
Impact and process evaluations are increasingly used in international development; however they are generally retrospective in outlook. A more timely approach to evaluation aims to identify necessary, feasible and effective changes during a programme or intervention’s lifetime. This paper aims to identify, categorise, describe and critically appraise methods to support more timely evaluation in international development. Potential methods were identified through scoping seminar, public symposium, targeted review of the literature, and the authors’ own experiences and opinions. Findings from the different data sources were reviewed collectively by the author group and triangulated to develop an analytical framework. We identified four purposes of timely evaluation for international development, and critiqued the use of approaches against four dimensions of timeliness and flexibility. Whilst we found significant interest in more timely approaches to evaluation in international development, there was a dearth of published empirical evidence upon which to base strong recommendations. There is significant potential for timely evaluation to improve international development outcomes. New approaches to mixing and adapting existing methods, together with new technologies offer increased potential. Research is needed to provide an empirical evidence base upon which to further develop the application, across sectors and contexts, of timely evaluation in international development.
Keywords: Adaptive learning; Outcome evaluation; Programme improvement; impact evaluation

Bringing Participation into Complexity-Aware MEL: What is the evidence? - Apgar, Marina; Higdon, Grace Lyn (2018)

Caja de Herramientas PDIA - Un enfoque “hazlo tú mismo” para resolver problemas complejos - Samji, Salimah; Andrews, Matt; Pritchett, Lant; Woolcock, MIchael (Center for International Development at Harvard University, 2018)
(Spanish version of he PDIA toolkit) The PDIAtoolkit is designed to guide you through the process of solving complex problems which requires working in teams. We call it a Do-it-Yourself (DIY) kit, where the ‘you’ is a committed team of 4-6 people mobilized to work together to solve a complex problem that cannot be solved by one person.

PDIA Toolkit - A DIY Approach to Solving Complex Problems - Samji, Salimah; Andrews, Matt; Pritchett, Lant; Woolcock, MIchael (Center for International Development at Harvard University, 2018)
The PDIAtoolkit is designed to guide you through the process of solving complex problems which requires working in teams. We call it a Do-it-Yourself (DIY) kit, where the ‘you’ is a committed team of 4-6 people mobilized to work together to solve a complex problem that cannot be solved by one person.

Learning from adaptive programmes - 10 lessons and 10 case studies - Valters, Craig (Overseas Development Institute, 2018)
Internal DFID document from the DevAdapt Programme. Based on another previous document (also internal).

A guide to agile communication - Defra digital - DEFRA Digital (Departmetn for Environment, Food & Rural Affairs (UK), 2018)
This guide is intended for: people planning communications activity on behalf of agile teams people doing the communications activity (especially blogging, presenting, or filmmaking) people who manage the people described above, who want to understand what they're doing and why The government service standard encourages teams to work in the open as much as possible, echoing item 10 in the government design principles, “make things open, it makes them better”. This guide was written to help teams do just that.

Building a global learning alliance on adaptive management - Wild, Leni; Ramalingam, Ben (ODI, 2018)

What can the Thinking and Working Politically community learn from peace and conflict mediation? - Douglas, Alex (From Poverty to Power, 2018)
Wily aid practitioners have long understood the importance of adapting their programs to the political environment, and even use their activities to push politics in a progressive direction. But this magic was spun secretly, hidden behind logframes and results frameworks. Only recently has a range of programs been permitted to escape the dead hand of technocracy. But there was one corner of the development and humanitarian world that never needed to shroud its political ambitions; those of us working on resolving violent conflicts. Donors have always understood our work could never be disembodied from politics. This field included elements of the UN, regional organisations, and NGOs, such as the one I work for: the Centre for Humanitarian Dialogue. With a new focus on development being enabled by a series of ‘deals’ between different actors, it seems timely to examine the strategies used to reach peace agreements and whether they contain broader lessons for TWP/DDD/Adaptive Management.

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of Pyoe Pin, Myanmar - Christie, Angela; Green, Duncan (Itad, Oxfam and IDS, 2018)
This paper examines adaptive approaches in aid programming in a fragile, conflict and violence-affected setting (FCVAS), namely Myanmar. A combination of desk review and field research has been used to examine some of the assertions around the ‘adaptive management’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blue-print and linear project plans. This paper explores if and how adaptive approaches, including rapid learning and planning responses (fast feedback loops and agile programming) are particularly relevant and useful for promoting empowerment and accountability in such ‘messy places’. This case study focuses on Pyoe Pin (‘Young Shoots’), a DFID-funded, British Council managed governance programme, which has been running since 2007.
Keywords: A4EA; Adaptive Development; Economy; Fishery

The fashion for agile management is spreading - The Economist (The Economist, 2018)
Executives need to be a cross between Spider-Man and Simone Biles

Addressing Maladaptive Coping Strategies of Local Communities to Changes in Ecosystem Service Provisions Using the DPSIR Framework - Ehara, Makoto; Hyakumura, Kimihiko; Sato, Ren'ya; Kurosawa, Kiyoshi; Araya, Kunio; Sokh, Heng; Kohsaka, Ryo (Ecological Economics, 2018)
The Driver-Pressure-State-Impact-Response (DPSIR) framework has been applied to various environmental problems at multiple spatial and temporal scales and attempts have been made to conceptually improve the framework to encompass various stakeholder perspectives. However, recent literature experiences in the field have challenged the inclusive character of the framework applications. In particular, the framework's inability to incorporate the aggregated informal responses of people affected by changes in ecosystem service provisions has not been fully addressed. This limits the framework's validity in categorizing and disseminating information for addressing particular environmental challenges. Herein, we address this problem by analyzing a case study of deforestation and its impact on non-timber forest product collections by rural residents in Cambodia. We incorporate the concept of maladaptive coping strategies into the DPSIR framework and then further elaborate Ness et al.'s (2010) approach of merging the DPSIR framework with Hägerstrand's (2001) system of nested spatial domains. This conceptualizes the incorporation of the aggregated informal responses into the system, as exemplified in the case study.
Keywords: DPSIR framework; Ecosystem services; Maladaptive coping strategy; Nested spatial domains

Scaling Up Inclusive Approaches for Marginalised and Vulnerable People - Carter, Becky; Joshi, Anu; Remme, Michelle (2018)
This rapid review summarises the evidence on how to scale up inclusive approaches to complex social change. It looks at how to design scalable inclusive change interventions, as well as how to plan and manage the scale-up process. Focusing on interventions with the aim of reaching the most marginalised and transform social norms, it covers programmes aiming to deliver inclusive outcomes for women and girls (with a particular focus on preventing violence against women and girls) and persons with disabilities. To date, many interventions seeking to change harmful gender and disability norms have been implemented as small-scale projects. There are limited experiences of scale-up and fewer evaluations of these experiences. However, there are some documented case studies as well as emerging analysis that draw out lessons learned. From this evidence base, this rapid desk review identifies eight critical issues commonly highlighted as important considerations when scaling up inclusive change interventions: 1. Opportunities for systemic approach, including integrating political and community-level scale-up, and coordinating across multiple sectors and stakeholders 2. Political support for scale-up 3. Strategic choices: balancing reach, speed, cost, quality, equity, and sustainability 4. Catalysing change: tipping points, diffusion effects, and local champions 5. Locally grounded, participatory, and adaptive approaches 6. Long-term approaches with funding models to match 7. Cost-effective and financially feasible scale-up strategies 8. Measuring impact and sustainability.

Humanitarian Innovation Guide - ELHRA (2018)
The Humanitarian Innovation Guide is a growing online resource to help individuals and organisations define humanitarian problems and successfully develop innovative solutions. ABOUT THE GUIDE The humanitarian sector is investing in exciting innovations, but it is not yet producing a steady pipeline of well-designed solutions that effectively address problems, evidence their impact, and have the potential to be scaled. As stated in a recent independent evaluation of the Humanitarian Innovation Fund (Triple Line, 2017), a review of the innovation ecosystem in 2015 found significant gaps in resources for innovation, including a shortage of guidance on the skills needed to manage successful innovation projects. These findings were echoed in the research carried out to inform this resource. As part of a grant agreement with the European Commission to provide financial and technical support to emerging humanitarian innovations, and in line with our strategic aim to develop the sector’s skills and capabilities in humanitarian innovation, this resource aims to translate our own learning, along with learning from across the sector, into a practical, grounded guide for innovators working in humanitarian contexts. Building on our unique position in the sector, the Humanitarian Innovation Guide is designed to provide targeted support to individuals and organisations attempting to develop innovative solutions to the challenges facing humanitarian assistance, resulting in a more effective humanitarian response. The Guide is written with two audiences in mind: humanitarian practitioners who are seeking to develop a new approach to their work and want to apply an innovation lens to solving problems; and social entrepreneurs from outside the sector who have identified an opportunity to engage with the sector and need a humanitarian framework to contextualise their innovation plans. We also hope that it will be a useful resource for innovation managers who are tasked with supporting innovation in their agencies, labs or networks. As the first step-by-step guide to managing innovation in the humanitarian sector, we hope that its continued development will better enable individuals, organisations and the wider sector to: Plan the activities involved in an innovation process and systematise the management of innovation. Manage a successful innovation project and generate evidence for innovation. Ensure that innovations are developed in an ethical way, with full consideration of risks and responsibilities.

3 fallacies of embracing complexity - Ang, Yuen Yuen (UNDP Blog, 2018)
Global development is seeing an exciting paradigm shift. Increasingly, leaders and practitioners recognize that development is not a “complicated” challenge that can be neatly parsed out into separate problems and siloed departments, like assembling a car. Rather, the various tasks of development—poverty eradication, improving governance, climate action, gender equality, and so on—are all connected, making development a “complex” challenge.

Context-Driven Adaptation (Overview) - Jacobstein, David (USAID Learning Lab, 2018)
CONTEXT-DRIVEN ADAPTATION COLLECTION

Thinking and working politically in Somalia: A case study on the Somalia Stability Fund - Laws, Ed (TWP Coommunity of Practice and ODI, 2018)

Program Cycle - Discussion Note: Designing Monitoring, Evaluation, and Learning Platforms - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

Digital Principles into practice - HDIF (HDIF, 2018)

Thinking and Working Politically through Applied Political Economy Analysis. A guide for practitioners - Rocha Menocal, Alina; Cassidy, Marc; Swift, Sarah; Jacobstein, David; Rothblum, Corinne; Tservil, Ilona (USAID, 2018)
Thinking and Working Politically (TWP) through Applied Political Economy Analysis (PEA). A guide for practitioners Have you ever done everything right in a development program — followed every technical best practice — but still missed the mark? When this happens, it often relates to factors in the context beyond any external development actor’s ability to control.

Program Cycle - Discussion Note: Managing Monitoring, Evaluation, and Learning Platforms - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

Managing to Adapt: Analysing adaptive management for planning, monitoring, evaluation, and learning - Desai, Harsh; Maneo, Gabriele; Pellfolk, Erica; Schlingheider, Annika (Oxfam, 2018)
Adaptive management is at the heart of ‘Doing Development Differently’. It emerges from stakeholders’ calls for development programmes to be more flexible and responsive to their contexts. Whether it becomes a mainstreamed practice depends on how much it is

Human-Centered, Systems-Minded Design - Both, Thomas (Stanford Social Innovation Review, 2018)
Both human-centered and systems-thinking methods fit within an effective design approach, and can work in conjunction to address social challenges.

Thinking big: How to use theory of change for systems change - Abercrombie, Rob; Boswell, Katie; Thomasoo, Rosanna (NPC, 2018)
We think that, applied well, theory of change can support charities and funders to take a systemic approach to their work. This report identifies five common pitfalls that organisations fall into when using theory of change, and walks through five rules of thumb that will help organisations to use the approach to tackle complex problems. We think that, applied well, theory of change can support charities and funders to take a systemic approach to their work. This report identifies five common pitfalls that organisations fall into when using theory of change, and walks through five rules of thumb that will help organisations to use the approach to tackle complex problems.

Thinking and working politically: An introduction to key ideas, examples and further reading - Laws, Ed; Marquette, Heather (2018)

Thinking and working politically: Reviewing the evidence on the integration of politics into development practice over the past decade - Laws, Ed; Marquette, Heather (TWP Community of Practice, 2018)

DRG Center practical tips to implement more context-adaptive programming - Jacobstein, David (#AdaptDev, 2018)
Hi #adaptdevers, The cross-sectoral programs team in the DRG Center have been working in support of ways that programming can be made more aware of, and responsive to, context considerations that have to do with incentives and relationships between different actors - often called power dynamics or political economy. Following several discussions with field folks, we were asked to come up with simple and practical tips that could help staff to implement more context-adaptive programming, or to better Work Politically to use TWP jargon. With assistance from many of our field staff and partners, we've put together three documents (to start) that have now been cleared to share publicly: • Tips on Making Your Solicitations Invite Context-Driven Adaptive Programming - suggestions spanning most sections of a typical solicitation to better weave in Thinking and Working Politically. I'm particularly excited that this document contains embedded links to excerpts from a set of solicitations that model good practice. You can also find a summary of all the excerpts from real solicitations, and links onward to the public posting of those solicitations on Fed Biz Ops or Grants.gov, here. • Tips on Power Dynamics and Theories of Change - suggestions relevant to those working on project designs and logic models. • Tips for Better Use of Advisory Councils - suggestions to set up better advisory bodies that help you to incorporate political economy more automatically into your programmatic adjustments. I hope that you'll find these practical and helpful! Feedback is always welcome. Best, David

Adaptive management: why we find it so hard to operationalise - Teskey, Graham (Abt Associates - Governance Soapbox, 2018)

Using elements of DCED Standards for CLA - Mitra, Bilash; Jalil, Mohammad Muaz (2018)
Introduction used in the DCED-BEAM seminar in Nairobi

Complexity & Development 2.0: From Agreeing We Should Adapt to Creating the Conditions that Enable Adaptation - Ang, Yuen Yuen (2018)
The field of global development has reached a critical turning point. Almost gone is the mechanical, one-size-fits-all “good governance” paradigm of the past. In its place is a growing embrace of complexity and systems thinking. While this is an encouraging shift in the right direction, the discussion mostly ends by concluding that we should adapt. Yuen Yuen Ang urges that it’s time to take our conversation on “complexity & development” to the next level: how to enable adaptation. Effective adaptation doesn’t automatically arise just because we desire it—rather, it requires certain enabling conditions. In How China Escaped the Poverty Trap (2016), she introduces a generic complexity 2.0 framework that she terms “directed improvisation.” Effective adaptation, Yuen Yuen argues, requires a paradoxical blend of top-down direction and bottom-up improvisation. Such a system can be created—and produce dramatic results and adaptive solutions—even within a closed political regime like China.

DFID’s approach to value for money in programme and portfolio management - ICAI (Independent Commission for Aid Impact (ICAI), 2018)
ICAI published this review on DFID’s approach to value for money in February 2018, and as value for money is both a process and an outcome and cuts across all aspects of DFID’s operations, did not score this review. We made five recommendations and published a follow-up to this review in July 2019. All UK government departments are required to achieve value for money in their use of public funds. In recent years, DFID has been working to build value for money considerations further into its management processes and its relationships with implementers and multilateral partners, establishing itself as a global champion on value for money. Review This review was published in February. Though it was not rated, ICAI made five recommendations, and found that the Department for International Development’s approach to value for money was helping to make UK aid spending go further, but improvements are still needed. Findings This review found that DFID has strengthened its processes and systems for ensuring it gains maximum value for each pound spent, has taken swift remedial action to tackle under-performing programmes, and has become a strong global champion on value for money. The review also found that DFID has been diligent in its efforts to cut waste, detect fraud, and improve efficiency, and that this work is improving the return on the UK investment in aid. However, the review found that DFID’s approach was not adequately reporting and capturing results and value for money at the country portfolio level, or how programmes work together to deliver lasting impact, including reducing future dependency on aid. It also found that weakness in the annual review process could undermine DFID’s approach to value for money. It found that targets were frequently revised, and that there could be pressures for optimistic scoring of programmes. Recommendations Based on this review, we made the following five recommendations to help DFID improve its approach to value for money still further: DFID country offices should articulate cross-cutting value for money objectives at the country portfolio level, and should report periodically on progress at that level. Drawing on its experience with introducing adaptive programming, DFID should encourage programmes to experiment with different ways of delivering results more cost-effectively, particularly for more complex programming. DFID should ensure that principles of development effectiveness – such as ensuring partner country leadership, building national capacity and empowering beneficiaries – are more explicit in its value for money approach. Programmes should reflect these principles in their value for money frameworks, and where appropriate incorporate qualitative indicators of progress at that level. DFID should be more explicit about the assumptions underlying the economic case in its business cases, and ensure that these are taken into account in programme monitoring. Delivery plans should specify points in the programme cycle when the economic case should be fully reassessed. Senior responsible owners should also determine whether a reassessment is needed following material changes in the programme, results targets or context. Annual review scores should include an assessment of whether programmes are likely to achieve their intended outcomes in a cost-effective way. DFID should consider introducing further quality assurance into the setting and adjustment of logframe targets.

Program Cycle - Discussion Note: Adaptive Management - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

Adapting to Learn and Learning to Adapt: Practical Insights from International Development Projects - Brinkerhoff, Derick W.; Frazer, Sarah; McGregor, Lisa (RTI Press, 2018)
Adaptive programming and management principles focused on learning, experimentation, and evidence-based decision making are gaining traction with donor agencies and implementing partners in international development. Adaptation calls for using learning to inform adjustments during project implementation. This requires information gathering methods that promote reflection, learning, and adaption, beyond reporting on pre-specified data. A focus on adaptation changes traditional thinking about program cycle. It both erases the boundaries between design, implementation, and evaluation and reframes thinking to consider the complexity of development problems and nonlinear change pathways.Supportive management structures and processes are crucial for fostering adaptive management. Implementers and donors are experimenting with how procurement, contracting, work planning, and reporting can be modified to foster adaptive programming. Well-designed monitoring, evaluation, and learning systems can go beyond meeting accountability and reporting requirements to produce data and learning for evidence-based decision making and adaptive management. It is important to continue experimenting and learning to integrate adaptive programming and management into the operational policies and practices of donor agencies, country partners, and implementers. We need to devote ongoing effort to build the evidence base for the contributions of adaptive management to achieving international development results.

Adapting to learn and learning to adapt: Practical insights from international development projects - Brinkerhoff, Derick; Frazer, Sarah (RTI, 2018)
Adaptive programming and management principles focused on learning, experimentation, and evidence-based decision making are gaining traction with donor agencies and implementing partners in international development. Adaptation calls for using learning to inform adjustments during project implementation. This requires information gathering methods that promote reflection, learning and adaption, beyond reporting on pre-specified data. A focus on adaptation changes traditional thinking about program cycle.

Reflection methods: Tools to make learning more meaningful - Gordijn, Femke; Eernstman, Natalia; Helder, Jan; Brouwer, Herman (Wageningen Centre for Development Innovation, 2018)
This handbook summarises methods that can be used to facilitate the process of reflection on the knowledge and experiences people acquire during a capacity development trajectory or training event. We believe that by explicitly integrating reflection in the learning process the learning will become clearer and better articulated and will contribute more strongly to meaningful change. Therefore we advise facilitators to deliberately include reflective learning sessions in their process design and implementation. This handbook can inspire you to do so and provides many methods which help to facilitate this.

Innovation lifecycle and the missing middle - Gray, Ian; McClure, Dan (Managing Humanitarian Innovation - The cutting edge of aid, 2018)

Collaboration for Impact (2018)
The site seeks to accelerate the adoption of system collaboration and Collective Impact in Australia. It does so by creating knowledge, network and tools; shining a light on successful Collective Impact initiatives; and building an Australian community of practice.

Lean Data Approaches to Measure Social Impact - ACUMEN (NovoEd, 2018)

An introduction to systems thinking and tools for systems thinking - Allen, Will; Kilvington, Margaret (Learning fro Sustainability, 2018)
Systems thinking is an approach to integration that is based on the belief that the component parts of a system will act differently when isolated from the system’s environment or other parts of the system. THIS PAGE PROVIDES PLENTY OF RESOURCES ON SYSTEM THINKING

Evaluating Systems Change Results: an inquiry framework - Cabaj, Mark (Tamarack Institute, 2018)

Global governance and local peace: accountability and performance in international peacebuilding - Campbell, Susanna (Cambridge University Press, 2018)
Local peacebuilding and global accountability – The country context–Burundi from 1999 to 2014 – Ingos in peacebuilding–globally unaccountable, locally adaptive – International organizations in peacebuilding–globally accountable, locally constrained – Bilateral development donors–accountable for global targets, not local change
OCLC: 1048387754

2018 Map of the Complexity Sciences - Castellani, Brian (Durham University, 2018)
A map that provides a macroscopic, trans-disciplinary introductions to the complexity sciences.

Strengthening Advocacy and Civic Engagemetn in Nigeria - Chemonics (Chemonics International, 2018)

Follow the rabbit: Field Guide to Systemic Design - CoLab (Government of Alberta, 2018)
This Field Guide is designed to support budding systemic designers to facilitate and lead systemic design projects. It’s designed for systemic designers who have basic familiarity with SD concepts and are looking for some practical tips and tools to put theory into action. While this Guide was designed with Government of Alberta staff in mind, the content applies across a range of issue areas, sectors, and intersections. The Guide goes through a systemic design project from concept to implementation. It takes you through the workshop planning process, and discusses workshop roles and client relations. In the FAQs, you’ll find explanations to some commonly asked questions about systemic design concepts to help you introduce others to SD and bring them along with you. You’ll get the most out of this field guide if you approach it with a systemic design mindset – open, willing to try things, a desire to learn, and a ‘yes, and’ orientation. Think of this field guide as an early stop in your systemic design journey: it’s not the end of your learning – it’s a jumping off point. In the Additional Resources section, you can connect to more in-depth explorations of concepts and practical applications.

Principles for Digital Development - digitalprinciples.org (2018)

The relationship between adaptive management of social-ecological systems and law: a systematic review - Frohlich, Miguel F.; Jacobson, Chris; Fidelman, Pedro; Smith, Timothy F. (Ecology and Society, 2018)
Adaptive management has been considered a valuable approach for managing social-ecological systems involving high levels of complexity and uncertainty. However, many obstacles still hamper its implementation. Law is often seen as a barrier for moving adaptive management beyond theory, although there has been no synthesis on the challenges of legal constraints or how to overcome them. We contribute to filling this knowledge gap by providing a systematic review of the peer-reviewed literature on the relationship between adaptive management and law in relation to social-ecological systems. We analyze how the scholarship defines the concept of adaptive management, identifies the legal barriers to adaptive management, and the legal strategies suggested for enabling this approach. Research efforts in this domain are still highly geographically concentrated in the United States of America, unveiling gaps concerning the analysis of other legal jurisdictions. Overall, our results show that more flexible legal frameworks can allow for adaptive management without undermining the role of law in providing stability to social interactions. Achieving this balance will likely require the reform of existing laws, regulations, and other legal instruments. Legal reforms can facilitate the emergence of adaptive governance, with the potential to support not only adaptive management implementation but also to make law itself more adaptive.

GIZ's Evaluation Policy: Principles, guidelines and requirements of our evaluation practice - GIZ (GIZ, 2018)

Summer School Course - Adaptive Management - Working Effectively in the Complexity of International Development (weekplan) - Green, Duncan; Guijt, Irene (Oxfam, 2018)

Navigation by Judgment: Why and when Top Down Management of Foreign Aid Doesn't Work - Honig, Dan (Oxford University Press, 2018)
Foreign aid organizations collectively spend hundreds of billions of dollars annually, with mixed results. Part of the problem in these endeavors lies in their execution. When should foreign aid organizations empower actors on the front lines of delivery to guide aid interventions, and when should distant headquarters lead? In Navigation by Judgment, Dan Honig argues that high-quality implementation of foreign aid programs often requires contextual information that cannot be seen by those in distant headquarters. Tight controls and a focus on reaching pre-set measurable targets often prevent front-line workers from using skill, local knowledge, and creativity to solve problems in ways that maximize the impact of foreign aid. Drawing on a novel database of over 14,000 discrete development projects across nine aid agencies and eight paired case studies of development projects, Honig concludes that aid agencies will often benefit from giving field agents the authority to use their own judgments to guide aid delivery. This "navigation by judgment" is particularly valuable when environments are unpredictable and when accomplishing an aid program's goals is hard to accurately measure. Highlighting a crucial obstacle for effective global aid, Navigation by Judgment shows that the management of aid projects matters for aid effectiveness.
Google-Books-ID: GT5MDwAAQBAJ

The water of Systems Change - Kania, John; Kramer, Mark; Senge, Peter (FSG, 2018)
Foundations involved in systems change can increase their odds for success by focusing on the least explicit but most powerful conditions for change, while also turning the lens on themselves. The Water of Systems Change aims to clarify what it means to shift these conditions. We offer the “inverted triangle” framework as an actionable model for funders and others interested in creating systems change, particularly those who are working to advance equity. Top Takeaways Systems change is about advancing equity by shifting the conditions that hold a problem in place. To fully embrace systems change, funders should be prepared to see how their own ways of thinking and acting must change as well. Shifts in system conditions are more likely to be sustained when working at three different levels of change: explicit, semi-explicit, and implicit.

The water of Systems Change: Action learning exercise - Kania, John; Kramer, Mark; Senge, Peter (FSG, 2018)
Based on the “inverted triangle” framework presented in The Water of Systems Change, this activity is designed to help individuals think systemically about social change, explore what is happening below the surface on issues they care about, and determine how they and their organizations can pursue large-scale change in a disciplined and holistic manner. The exercise is divided into 3 parts: Part I uses the “inverted pyramid” introduced in The Water of Systems Change to perform an external assessment of opportunities to make progress on the social or environmental issue you are focused on. Part II uses the same framework to consider internal conditions within yourself and your organization that should change in order for you to better support progress on your issue. Part III takes what was developed in Parts I and II and asks “What to do next?”

The landscape of innovation approaches - Leurs, Bas (States of Change, 2018)
An overview of innovation methods and approaches we’ve come across in government innovation practice.

States of Change - Learning programme - Nesta (Nesta, 2018)

Knowledge Management strategies and processes in Agile Software Development: a systematic literature review - Ouriques, Raquel Andrade Barros; Wnuk, Krzysztof; Gorschek, Tony; Svensson, Richard Berntsson (CoRR, 2018)
Knowledge-intensive companies that adopt Agile Software Development (ASD) relay on efficient implementation of Knowledge Management (KM) strategies to promotes different Knowledge Processes (KPs) to gain competitive advantage. This study aims to

Doing Development Differently at Scale - Pellini, Arnaldo; Karetji, Petrarca C.; Soekadis, Ade (Knowledge, Politics and Policymaking in Indonesia, 2018)
In recent decades there has been an increasing recognition that politics and political institutions matter for development. There is also a much greater interest in contextually grounded approaches. This has stemmed from an acknowledgement that purely technocratic approaches to development often result in failure because they do not take into account the nature of political institutions. Nor do they take account of the context in a particular developing country and the interests and incentives of powerful national actors. Policy processes are embedded in specific social, political and organisational contexts. Approaches that focus on implementing universal best practices in evidence-informed policymaking are unlikely to be successful. Instead, what is needed is an approach that takes the local context as the starting point for understanding what issues are relevant to policymakers and developing contextually appropriate solutions. The authors of this chapter reflect on the management approaches and systems that may be required to enable and support large-scale development programmes to be flexible and adaptive to the local policy context and circumstances. The chapter argues that such programmes struggle to adopt adaptive management principle and that to do that at scale requires some changes in the way such programmes are managed.
Keywords: Adaptive Management; Doing development differently; Evidence-informed policymaking; Indonesia; Knowledge sector; Thinking and working politically

Decision-Making and Data Use Landscaping [at DFID] - Powell, Josh; Orton-Vipond, Sarah; Bhatia, Vinisha; Kilroy, Annie (Development Gateway, 2018)
As DFID aims to harness the Data Revolution, ensuring that data1 drive decision-making, public accountability, and the achievement of the Sustainable Development Goals (SDGs), ensuring that systems, processes, and skills for data are aligned with these objectives is paramount. Across sector policy teams, country offices, and various analytical and technical cadres, different strengths and weaknesses, as well as needs and ambitions exist. To inform a strategic approach to data, as framed in its forthcoming Data Roadmap, DFID collaborated with Development Gateway to perform a Decision and Data Use Landscaping study. This report details lessons learned from approximately 60 interviews across 4 DFID country offices, all sector policy teams, senior managers, and various analytical and technical cadres and offices.

Exploring new territories for evaluation - Sharp, Cathy (Collective Leadership for Scotland, 2018)
Drawing on action research, this paper recasts evaluation as ‘action inquiry’, an embedded evaluative learning practice that can help navigate complexity when enacting collective leadership. It is offered as an invitation to inquiry amongst a reasonably well-informed audience of policy makers and practitioners who work in and for public services. It will particularly interest those who provide research, evaluation and facilitation support, and those seeking to develop a more relational approach to research and evaluation. Action inquiry is a model of practising change together in environments where ‘nothing is clear, and everything keeps changing’ that significantly challenges the prevailing discourse on evaluation. Action inquiry can be wrapped around and enmeshed within initiatives and programmes that work with complexity - anywhere where success will depend on the quality of relationships that can be developed. The paper reviews some important interrelated concepts that underpin the ideals of collective leadership and public service reform and which confront deeply embedded traditional notions of leadership, expertise and participation. These offer important challenges to ideas about how change happens and recognise that relationships are at the heart of practising change. This warrants a re-examination of the high expectations of evidence-based or informed practice. Collective leadership makes new demands of evidence as it rests on help to determine ‘wise actions’ in real-life situations. This confronts the practical reality of how to work together in conditions often expressed as ‘dynamic’ or ‘turbulent’ and the added human complexities of power, emotions and relationships; too often these elements are denied or avoided aspects of a change process. Facilitated action inquiry makes these elements part of the conversations, in the midst of ‘work-as-we-are-doing-it’, to increase areas of choice for individuals and a group as a whole. Within public policy, there is an overwhelming amount of evidence about ‘what works’ yet change seems to be stubborn and slow. The paper explores some of the deep-rooted vestiges of a ‘hierarchy of evidence’ and assumptions about standardisation and generalisability that act as a ‘barrier to transformation’. These include the narrow framing of what counts as evidence and consequent relegation of community perspectives, lived experience and practice-based evidence. The paper acknowledges the clear appetite for different approaches to evaluation, especially those that better reflect deeply held values and avoid creating a culture of ‘gaming’, rooted in fear of failure and loss of funding, at the expense of learning. The need for new forms of developmental evaluative thinking, collaborative inquiry and action research to create embedded learning is well overdue. Action inquiry is a desirable and necessary response to the complex situations and challenges of human services and recognises the essentialness of knowledge co-production. It is a model of co-creation at every stage and endorses the idea that people learn from participation in evaluation and by testing theories of change through action. Action inquiry builds on the idea of inquiry, or a moment-to-moment awareness and quality of attention and draws from several elements of action research practice. It sees inquiry as an intervention in itself, one that furthermore, explicitly seeks to enhance the probability of the success of a programme, focus on learning, the collaborative development of practice-based knowledge and positive relationships. The paper highlights the importance of building inquiry into living systems, the role of facilitation, systemic inquiry, and evaluative thinking. It proposes an expansion of ideas of appreciation as a relational and collaborative practice that is a driver of emergence. Social recognition that acknowledges someone’s social value to the community and implies mutual moral obligations to cooperation and participation is particularly crucial in a work context that requires successful coordination and multiple contributions to achieve results across hierarchies of position, professional rank and sectors. Hence, appreciation goes beyond the idea of positivity to include social recognition, valuing more explicit forms of inquiry, building participants’ aspirations to design new social systems and acting in new ways to embed change. In developing this discussion, the paper contributes to emerging dialogues about the need for a model of ‘5th generation evaluation’. Such a model would be based on the idea that appreciative and challenging inquiry that is contextual, relational and open-minded will create better opportunities for change and development. The paper sets out some ‘provocative propositions’ that can help us to navigate this terrain, perhaps of a fledgling ‘5th generation approach’ to inquiry. Facilitated action inquiry can hold the key to developing both new knowledge and an adaptive, collaborative and improvisational skill-set, able to respond in new ways to systemic and complex issues on the ground. It’s common to hear the expression ‘it’s all about relationships’ and it is clearly time to shift our focus to relationships; not relationships as ‘things’, but as co-created and dynamic relational processes in which we are embedded. In this way we can bring new qualities to our talking to each other about our various and shared visions of a better future.

Mission-Based Monitoring, Evaluation and Learning (MEL) Platforms Assessment Report - Arntson, Laura; Giannoni, Tonya; Peek, Nancy; Saarlas, Kristin (USAID, 2017)
In 2016, the Bureau of Policy, Planning and Learning (PPL) commissioned an internal stocktaking of USAID's mission-based MEL (Monitoring, Evaluation, and Learning) Platforms.

Adaptive management intentions with a reality of evaluation: Getting science back into policy - Hasselman, Lyndal (Environmental Science & Policy, 2017)
In Australia’s Murray-Darling Basin water reform has been contentious as government attempts to reconcile historical over allocation of water to irrigation with the use of water for environmental outcomes. However, in many aspects, scientific knowledge of the environment is either imperfect, incomplete or environmental responses are unpredictable, with this uncertainty preventing definitive policy and closure of political arguments. In response to uncertainty and knowledge gaps, adaptive management has been written into the legislation, along with provisions for periodic evaluation. This research ascertains how adaptive management is understood by policy makers, with this indicative of future implementation of adaptive management. The way in which adaptive management is constructed by policy makers is determined through legislation, public speeches, government reports and semi-structured interviews. The findings demonstrate that adaptive management has been subsumed by evaluation. The loss of adaptive management as a distinct concept is seen as a loss of science and discovery from the policy process, with the dominance of evaluation discussed as limiting innovation and reinforcing a ‘muddling through’ of policy.
Keywords: Accountability; Adaptive Management; Evaluation; Science; Uncertainty

Learning to Make All Voices Count: Lessons for OGP, donors, and practitioners - Moses, Michael; Soal, Sue (2017)
The Open Government Partnership (OGP), donors and multilaterals, and social accountability practitioners across the world are among various constituencies attempting to harness and actualise emerging insights about the nature of successful governance reform. But each of these groups faces challenges as they do so. This brief reviews the evidence from Learning to Make All Voices Count (L-MAVC), a programme funded by Making All Voices Count, and implemented in collaboration with Global Integrity. L-MAVC intended to support six Making All Voices Count grantees, working in five countries, in co-creating and applying a participatory, learning-centred, and adaptive approach to strengthening citizen engagement in governance processes in their contexts, including with respect to the Open Government Partnership (OGP). Two sets of lessons emerge from the experience of L-MAVC. First, supporting citizen engagement and government accountability in subnational contexts, and localising OGP in ways that matter to citizens, is not straightforward. Doing so successfully entails engaging with, navigating and shaping political and power dynamics in those contexts, and iteratively adapting to emerging lessons and challenges. Second, the effectiveness of adaptive ways of working depends in part on the extent to which they offer opportunities for cross-context peer learning, support the regular collection and use of data, and are themselves adaptive. These lessons have implications for the broader community of actors working to support governance reform, including OGP and its partners, donors and multilateral institutions, and practitioners and policy-makers. If these actors are to contribute more effectively to reforms that affect citizens’ lives, substantial changes – with respect to the nature of support provided to domestic stakeholders, grant-making practices, and practitioner approaches – may be warranted.

The five trademarks of agile organizations - Wouter Aghina; Karin Ahlbäck; Aaron De Smet; Clemens Fahrbach; Christopher Handscomb; Gerald Lackey; Michael Lurie; Monica Murarka; Olli Salo; Elizabeth Seem; Jannik Woxholth (McKinsey anc Company, 2017)
Our experience and research demonstrate that successful agile organizations consistently exhibit the five trademarks described in this article. The trademarks include a network of teams within a people-centered culture that operates in rapid learning and fast decision cycles which are enabled by technology, and a common purpose that co-creates value for all stakeholders. These trademarks complement the findings from The McKinsey Global Survey Results: How to create an agile organization.

Walking the Long Road Together - Stilger, Bob (Afternow: When We Cannot See the Future Where Do We Begin?, 2017)
On March 11, 2011, overwhelming and incomprehensible disaster struck the northeast coast of Japan. Life for those in the region would never be the same. This book is about the awakening that follows disaster. About the minutes and months and years that come after now. It is about what happens when we're smacked on the side of the head and open our eyes, startled out of the trance in which we have been living our days. It is about the opportunities always present, often invisible, to create the lives we want, now. AfterNow chronicles the author's journey with the Japanese people over 6 years – his own story of awakening after plunging into this disaster and the stories from people who found where to take their first step, and the next. It offers the tools and processes and worldview people discovered to create what comes after now. It is built around two big ideas. The first is that after disaster, we find our way forward, together. We come awake, together. Disaster obliterates the past, plunges the present into chaos and cocoons the future. We need each other to see and build the new. The second idea is that we don't have to wait for the tragedy of disaster to make the communities and lives we want. We can engage each other with respect, curiosity and generosity and begin to co-create what we want, now. We live in a period of precipitous, unpredictable change. The book is for those who want to make this time more livable and less insane. In Japan and all over the world, we are living in the messy middle where old forms are falling apart and new possibilities are in early stages. The ground is pulled out from under us on a regular basis. Our work right now is to learn to coexist with the messiness. We need to keep trying things, to keep learning. We need to remain focused on our purpose and follow the braided strand of intention and surrender as we find our way forward. embracing radical uncertainty, showing up as fully as we can each moment, each breath.

Adaptiveness through ‘simplest tools and practices’ - Prieto Martin, Pedro (Institute of Development Studies, 2017)
In recent years, more and more influential development organisations have been openly recognising the central role that adaptive management capacities – the ability to keep improving strategies and actions as programmes unfold – play for the success of complex interventions. As a result, there has been a rich exchange of ideas and experiences on how to promote adaptiveness in development. But development organisations and professionals are having a hard time translating the many adaptive theories and recommendations into improved practices and outcomes. They are generally failing to adjust the design and operation of programmes to accommodate incipient lessons learnt and the unexpected changes in the context. Nowadays, most programme adaptations still take the form of a change of direction once it is clear that things have gone really wrong. Why is so difficult to put what we know about adaptiveness into practice? And more importantly: what can be done to improve this situation?

Is there a new Washington Consensus? An analysis of five World Development Reports - Evans, Alice (From Poverty to Power, 2017)
Is there a new Washington Consensus? Alice Evans analyses the last five World Development Reports and finds significant changes in orthodoxy, but also big gaps

Scenario-based strategizing: Advancing the applicability in strategists' teams - Lehr, Thomas; Lorenz, Ullrich; Willert, Markus; Rohrbeck, René (Technological Forecasting and Social Change, 2017)
For over 40years, scenarios have been promoted as a key technique for forming strategies in uncertain environments. However, many challenges remain. In this article, we discuss a novel approach designed to increase the applicability of scenario-based strategizing in top management teams. Drawing on behavioural strategy as a theoretical lens, we design a yardstick to study the impact of scenario-based strategizing. We then describe our approach, which includes developing scenarios and alternative strategies separately and supporting the strategy selection through an integrated assessment of the goal-based efficacy and robustness. To facilitate the collaborative strategizing in teams, we propose a matrix with robustness and efficacy as the two axes, which we call the Parmenides Matrix. We assess the impact of the novel approach by applying it in two cases, at a governmental agency (German Environmental Ministry) and a firm affected by disruptive change (Bosch, leading global supplier of technology and solutions).
Keywords: Behavioural strategy; Scenario-based strategizing; Scenarios; Strategic foresight; Uncertainty

How INGOs are Doing Development Differently - Algoso, Dave (Care, IRC, Mercy Corps, Oxfam & World Vision, 2017)

Valuing peace: delivering and demonstrating mediation results - Dilemmas & options for mediators - Wadley, Ian (Centre for Humanitarian Dialogue, 2017)
Essential points for practitioners and donors • Mediation offers a cost-effective and proven method for resolving armed conflict. Between 1985 and 2015, 75 per cent of armed conflicts in the world were resolved through agreement rather than by force. In most cases these processes will have involved third party facilitation or support. • Professional mediators understand the high stakes involved in their work to prevent, mitigate and resolve armed conflict. In addition, they and their financial supporters are increasingly required to demonstrate ‘value-for-money’ to ensure continued funding. • However, traditional monitoring and evaluation (M&E) methods are not well suited to this task, typically imposing artificially linear project models on a dynamic conflict situation, as well as compliance reporting that moves attention away from real value. • Traditional M&E methods tend to focus on documenting the past and generating vast amounts of data, rather than enabling timely adaptation of the project in the present. • Traditional M&E approaches rely heavily on external evaluation consultants. Even in the best of cases this may interfere with the mediation process and impose a heavy time burden on the project team, leading to low acceptance of traditional M&E approaches by mediation practitioners. • In contrast, an ideal M&E approach for mediation should deliver useful insights in even the most dynamic and sensitive mediation environments, impose a light reporting burden, and be readily accepted by mediation teams. It should protect discretion and trust, enable rapid adaptation, and also provide some assurance that donor funds are being well spent.

Using what we know: How to ensure tech projects meet the brief - Walker, Tom (Making All Voices Count, 2017)
Making tech effective - building on what we already know

Scaling Agile @ LEGO and Spotify – my talk at EA träff - Kniberg, Henrik (Crisp, 2017)

Doing Digital Development Differently: Lessons in adaptive management from technology for governance initiatives in Kenya - Prieto Martin, Pedro; Hernandez, Kevin; Faith, Becky; Ramalingam, Ben (IDS, 2017)
Development projects don’t always work as planned. This has long been acknowledged by those in the sector, and has led to several approaches that seek to solve complex development problems through enabling and encouraging greater adaptiveness and learning within projects (e.g. Doing Development Differently and Problem-Driven Iterative Adaptation). Digital development projects experience many of these issues. Using technology for transparency and accountability (Tech4T&A) projects in Kenya as case studies, our research analysed the many different theoretical approaches to learning and adaptation, and then tested how these play out in reality. Firstly, we conducted an extensive review of the literature on the spectrum of approaches to adaptive learning. The findings were used to develop a framework through which to analyse adaptiveness at the different layers of complexity in projects (e.g. software design and development, programme design and management). The second part of the research consisted of interviews and focus group discussions with participants in Tech4T&A projects in Kenya. Respondents helped us identify the main characteristics of adaptiveness in their projects (e.g. who needs to adapt, and how and when) and the challenges and issues that inhibit projects’ abilities to be adaptive. This process also revealed how accountability interplays with adaptiveness, and considered how better collaboration flows can enable adaptiveness. From our literature review and empirical study, we draw several conclusions for increasing adaptiveness in digital development projects. These include simplifying the many adaptive theories that abound, increasing responsiveness to project beneficiaries and stakeholders, and for stakeholders to keep on experimenting, networking and advocating.
Keywords: IMPORTANT

How to create an agile organization - survey - Salo, Olli; Ahlbäck, Karin; Fahrbach, Clemens; Murarka, Monica (McKinsey & Co., 2017)
Eighteen practices for organizational agility The survey asked respondents about a series of specific actions that underlie each of the 18 practices (9 of them stable, and 9 dynamic) of organizational agility; all of the practices are summarized in the table below. To rate respondents’ organizations, we asked how frequently their performance units engaged in each action that supports a given practice.

Real World SAFe – Leapfrogging a successful waterfall company into Scaled Agile - Skarin, Mattias (CRISP, 2017)

Extreme Teaming: Lessons in Complex, Cross-Sector Leadership - Edmondson, Amy C.; Harvey, Jean-Francois (Emerald Group Publishing Limited, 2017)
Extreme Teaming Lessons in Complex, Cross-Sector Leadership Today’s global enterprises increasingly involve collaborative work by teams of experts operating across different professions, organizations, and industries. Extreme Teaming provides new insights into the world of complex, cross industry projects and the ways they must be managed. Leading experts Amy Edmondson and Jean-François Harvey analyze contemporary cases that expose the complex demands of cross-boundary collaboration on management, and inform our understanding of teams. Containing powerful insights and practical guidelines that allow managers to bridge professional divides and organizational boundaries in order to work together effectively, this is a new exploration of the challenges involved in today’s global enterprises. The authors demonstrate that the work done in the modern organization is less and less about looking inward and creating strong teams inside the company, and more about teaming across boundaries – that often are in flux. Extreme Teaming is a must-read book for all courses related to leading open innovation; teamwork and collaboration; project management; and cross-boundary work.

Strengthening the results chain: Synthesis of case studies of results-based management by providers - Zwart, Rosie (OECD, 2017)
This paper presents an analysis of evidence from seven case studies of results-based management by development co-operation providers. Analysis of themes from the case studies reveal six interrelated challenges which providers face in their efforts to manage for the results of development co-operation. The six challenges are: linking results to development goals, ensuring the purpose of results systems is well-defined, weighing up the benefits of aggregating and attributing results from standard indicators, enabling country ownership, using performance information alongside results information, and building and embedding a results culture. Providers continue to adopt a range of approaches to pursue a focus on results and there are many examples of good practice. The case studies suggest that in a complex development landscape some providers are prioritising the use of aggregated results information for domestic accountability, communication, and performance management over their use for learning and policy direction. In this context, the paper argues that in agency-wide results frameworks development co-operation results are often detached (or de-contextualised) from development results and discusses the implications of this, including the use of standard indicators to measure aggregated outputs. The paper uses case study evidence to discuss and suggest practical ways providers can build and maintain a strong results focus which enables analysis, insights and learning, and has achievement of development outcomes as its objective.

Systems Approaches to Public Sector Challenges: Working with Change - OECD (OECD, 2017)

One step back, two steps forward: CARE’s journey towards doing development differently - Aston, Tom (Care Insights, 2017)
The Doing Development Different (DDD) community emerged in August 2014 and advocates that (a) the barriers to development are as much political as tec...

NGOs Doing Development Differently - Green, Duncan (From Poverty to Power, 2017)
Report back from a meeting of international NGOs to set up a research and practice network on 'Doing Development Differently' that can complement other actors

Policy experimentation and innovation as a response to complexity in China’s management of health reforms - Husain, Lewis (Globalization and Health, 2017)
There are increasing criticisms of dominant models for scaling up health systems in developing countries and a recognition that approaches are needed that better take into account the complexity of health interventions. Since Reform and Opening in the late 1970s, Chinese government has managed complex, rapid and intersecting reforms across many policy areas. As with reforms in other policy areas, reform of the health system has been through a process of trial and error. There is increasing understanding of the importance of policy experimentation and innovation in many of China’s reforms; this article argues that these processes have been important in rebuilding China’s health system. While China’s current system still has many problems, progress is being made in developing a functioning system able to ensure broad population access. The article analyses Chinese thinking on policy experimentation and innovation and their use in management of complex reforms. It argues that China’s management of reform allows space for policy tailoring and innovation by sub-national governments under a broad agreement over the ends of reform, and that shared understandings of policy innovation, alongside informational infrastructures for the systemic propagation and codification of useful practices, provide a framework for managing change in complex environments and under conditions of uncertainty in which ‘what works’ is not knowable in advance. The article situates China’s use of experimentation and innovation in management of health system reform in relation to recent literature which applies complex systems thinking to global health, and concludes that there are lessons to be learnt from China’s approaches to managing complexity in development of health systems for the benefit of the poor.

Two Paths to Supporting Grassroots Innovation - Cooper, Nathan; Hazeldine, Shaun; Quaggiotto, Giulio (Stanford Social Innovation Review, 2017)
An innovation experiment in Indonesia yields insights on how international development organizations can effectively foster innovation within the communities they aim to help.

From Design Thinking to Systems Change - Conway, Rowan; Masters, Jeff; Thorold, Jake (RSA, 2017)
This report takes the Small Business Research Initiative (SBRI), a twophase pre-procurement innovation programme that aims to match social challenges with new ideas, as its primary case study. It suggests augmenting the excellent design thinking deployed through SBRI with a think like a system, act like an entrepreneur lens in order to drive better social outcomes from SBRI-originating innovations. Programmes like SBRI have great potential to drive change and address pressing challenges, but must be guided by a more developed understanding of how change happens. The stakes are too high to not raise our game when it comes to social innovation. Wicked problems can be overcome but will require sophisticated theories of change able to account for the complexity and unpredictability of modern life. We offer think like a system, act like an entrepreneur as a contribution to this effort. This report is based on the following research: •• Desk based review of relevant literature; •• A series of structured interviews with participants in SBRI competitions; and •• An expert round table that brought together policymakers, commissioners, procurement experts and entrepreneurs to consider and develop initial findings.
Keywords: ⛔ No DOI found

How to set up and manage an adaptive programme - Lessons from the Action on Climate Today (ACT) Programme - Cooke, Katherine (OPM, 2017)

Governance for Growth in Vanuatu: Review of a decade of thinking and working politically - Hadley, Sierd; Tilley, Helen (ODI, 2017)

Thinking and Working Politically: Lessons from FOSTER in Nigeria - Lopez Lucia, Elisa; Buckley, Joanna; Marquette, Heather; McCulloch, Neil (DLP Program, 2017)
The Facility for Oil Sector Transparency and Reform (FOSTER) was a £14 million programme that has helped Nigeria to transform its governance of the oil and gas industry. FOSTER ran from 2011 to mid-2016, and used an explicit ‘thinking and working politically’ (TWP) approach. It was funded by the UK Department for International Development (DFID) and managed by Oxford Policy Management (OPM). This paper seeks to identify the factors that drove – or constrained – FOSTER’s achievements, and asks what this can tell us about TWP, particularly in challenging political and sectoral contexts. FOSTER sought to help strengthen oversight and accountability in Nigeria’s oil sector. It aimed to support reformers within government institutions that ‘supply’ accountability (those governing how oil and gas revenues are collected and managed), and to support civil society organisations, parliament, the media and the Nigeria Extractive Industries Transparency Initiative to ‘demand’ reform. In addition, FOSTER commissioned a series of studies and provided media training to help broaden understanding of the sector and highlight the need for reform. This paper examines the outcomes from five ‘clusters’ of FOSTER interventions. The FOSTER team viewed the first three of these in the list below as successful, whereas the latter two did not deliver on expectations but offer important opportunities for learning: • Support to the Nigerian Extractive Industries Transparency Initiative • Support to demand-side actors to promote transparency and accountability in the oil sector • Support for the passage of the Petroleum Industry Bill • An oil spill-mapping social media project • Support to the Department of Petroleum Resources The analysis drew on 44 semi-structured interviews conducted during a month of fieldwork in Abuja and Lagos; on reviews of the programme’s monitoring, evaluation and learning frameworks; and on newspaper articles and grey literature on Nigeria’s oil sector.2

Case studies of results-based management by providers: Canada - OECD (OECD, 2017)

Case studies of results-based management by providers: World Bank Group - OECD (OECD, 2017)

Program Cycle - How-To Note: Strategy-Level Portfolio Review - USAID (USAID PPL, 2017)

The Beginner’s Guide to Political Economy Analysis (PEA) - Whaites, Alan (National School of Government International, 2017)
Over the last two decades aid agencies and academics have been on a journey of lesson learning and adaptation in relation to `politics.’ This journey has been driven by a determination to improve impact in all areas of development, but for some time it was particularly associated with work on public sector reform. Now, however, there is an increasing expectation that Political Economy Analysis (PEA) should be part and parcel of designing and implementing any programme or activity (and a brief history of the meandering journey of development actors on PEA can be found in The Policy Practice’s Briefing Paper 11 – see below). DFID in the UK is fairly typical among large development organisations in running an excellent course on political economy analysis, complete with 200 pages of resources and various online videos and case studies (and this type of course is recommended for those who want to take their exploration of PEA further). Even so, PEA is not just for those who have `done the course and bought the T-shirt,’ it is something that can be absorbed and implemented quickly by everybody. Indeed, the growth of interest in PEA is a reminder that this can look like a complex and daunting field and so this guide aims to offer an entry-point for all those who want to use PEA in their own work. In doing so, this guide borrows from the best materials that are available while also adapting some approaches by incorporating wider ideas on politics and institutions. This guide affirms that there should never be an official `orthodoxy’ for PEA and so the emphasis here is on questions, prompts and ideas to help thinking and practice. There is also an attempt to clarify jargon wherever needed, while recognising that The Policy Practice (TPP) and the Overseas Development Institute (ODI) have produced a more complete glossary of PEA terminology. The note will instead focus on `the essentials’ of PEA as they relate to the following questions:  Why do we do political economy analysis, and what is it?  What kinds of issues and ingredients are often included in a PEA?  How do we make sense of the different varieties of PEA?  What tools are out there to help us conduct a PEA?  What is thinking and working politically?

RFI-521-17-000015 - Improving Governance in Haiti Program (IGHI) - USAID (USAID, 2017)

Doing Urban Development Differently - Jones, Harry; Adhikari, Bishnu (From Poverty to Power, 2017)
Guest post from Harry Jones and Bishnu Adhikari, both of Palladium on what urban aid and development can learn from the Doing Development Differently movement

Participatory adaptive management leads to environmental learning outcomes extending beyond the sphere of science - Fujitani, Marie; McFall, Andrew; Randler, Christoph; Arlinghaus, Robert (Science Advances, 2017)
Resolving uncertainties in managed social-ecological systems requires adaptive experimentation at whole-ecosystem levels. However, whether participatory adaptive management fosters ecological understanding among stakeholders beyond the sphere of science is unknown. We experimentally involved members of German angling clubs (n = 181 in workshops, n = 2483 in total) engaged in self-governance of freshwater fisheries resources in a large-scale ecological experiment of active adaptive management of fish stocking, which constitutes a controversial management practice for biodiversity and ecosystem functioning when conducted inappropriately. The collaborative ecological experiments spanned several years and manipulated fish densities in 24 lakes with two species. In parallel, we experimentally compared changes in ecological knowledge and antecedents of proenvironmental behavior in stakeholders and managers who were members of a participatory adaptive management treatment group, with those receiving only a standard lecture, relative to placebo controls. Using a within-subjects pretest-posttest control design, changes in ecological knowledge, environmental beliefs, attitudes, norms, and behavioral intentions were evaluated. Participants in adaptive management retained more knowledge of ecological topics after a period of 8 months compared to those receiving a standard lecture, both relative to controls. Involvement in adaptive management was also the only treatment that altered personal norms and beliefs related to stocking. Critically, only the stakeholders who participated in adaptive management reduced their behavioral intentions to engage in fish stocking in the future. Adaptive management is essential for robust ecological knowledge, and we show that involving stakeholders in adaptive management experiments is a powerful tool to enhance ecological literacy and build environmental capacity to move toward sustainability. Participatory active adaptive management leads to far-reaching environmental learning outcomes in stakeholders. Participatory active adaptive management leads to far-reaching environmental learning outcomes in stakeholders.

A ‘real-time’ and anthropological response to the Ebola crisis - IDS (IDS, 2017)
Impact Summary The Ebola epidemic that began in the Guinea-Sierra Leone-Liberia border region in December 2013 spread fast through the villages, cities and trade routes of this highly-peopled,...

Agile – where are we at? - Kniberg, Henrik (2017)

Scaled Agile Framework – SAFe for Lean Software and System Engineering 4.5 - Scaled Agile (2017)

The Patterning Instinct: A Cultural History of Humanity's Search for Meaning - Lent, Jeremy (Prometheus Books, 2017)
This fresh perspective on crucial questions of history identifies the root metaphors that cultures have used to construct meaning in their world. It offers a glimpse into the minds of a vast range of different peoples: early hunter-gatherers and farmers, ancient Egyptians, traditional Chinese sages, the founders of Christianity, trail-blazers of the Scientific Revolution, and those who constructed our modern consumer society. Taking the reader on an archaeological exploration of the mind, the author, an entrepreneur and sustainability leader, uses recent findings in cognitive science and systems theory to reveal the hidden layers of values that form today's cultural norms. Uprooting the tired cliches of the science-religion debate, he shows how medieval Christian rationalism acted as an incubator for scientific thought, which in turn shaped our modern vision of the conquest of nature. The author probes our current crisis of unsustainability and argues that it is not an inevitable result of human nature, but is culturally driven: a product of particular mental patterns that could conceivably be reshaped. By shining a light on our possible futures, the book foresees a coming struggle between two contrasting views of humanity: one driving to a technological endgame of artificially enhanced humans, the other enabling a sustainable future arising from our intrinsic connectedness with each other and the natural world. This struggle, it concludes, is one in which each of us will play a role through the meaning we choose to forge from the lives we lead.

Teams that Do Development Differently - Khan, Jehanzeb; Fisher, Annette (Global Policy Journal, 2017)

Two Tunes, One Dance: Keeping Programming Agile - Learning Lab (USAID Learning Lab, 2017)

Critical agency and development: applying Freire and Sen to ICT4D in Zambia and Brazil - Poveda, Sammia; Roberts, Tony (Information Technology for Development, 2017)
(2017). Critical agency and development: applying Freire and Sen to ICT4D in Zambia and Brazil. Information Technology for Development. Ahead of Print. doi: 10.1080/02681102.2017.1328656

A Whole New World - Funding and Commissioning in Complexity - Knight, Annabel Davidson; Lowe, Toby; Brossard, Marion; Wilson, Julie (Collaborate & Newcastle University, 2017)
Collaborate and Newcastle University Business School Publish Research into Complexity-Friendly Funding

Learning, monitoring and evaluating: achieving and measuring change in adaptive programmes - Callaghan, Sarah; Plank, Georgia (DFID-LASER Programme, 2017)

Case studies of results-based management by providers: New Zealand - OECD (OECD, 2017)

Case studies of results-based management by providers: Sweden - OECD (OECD, 2017)

Case studies of results-based management by providers: Switzerland - OECD (OECD, 2017)

Case studies of results-based management by providers: The Netherlands - OECD (OECD, 2017)

Case studies of results-based management by providers: United Kingdom - OECD (OECD, 2017)

Amateur hour: CfC's 'surprising' success in addressing school congestion in the philippines - Sidel, John T. (Asia Foundation, 2017)
The international development community has increasingly embraced the idea that finding durable solutions to complex development problems requires new ways of working that move beyond industry norms. This paper makes an important contribution to the current debate by outlining an innovative monitoring system called Strategy Testing (ST). This is the third paper in the Working Politically in Practice paper series, launched together with the Australian Department of Foreign Affairs and Trade.
Keywords: IMPORTANT

Six things that help grant-makers learn and adapt - Murray, Aoife (Itad, 2017)
There’s an emerging body of literature identifying key strategies that can both improve learning and enable adaptive management amongst grant-makers. We recently reviewed a host of publications from eight grant-making organisations. Those organisations have diverse aims and approaches but we’ve identified six common themes that stand out: Strong leadership and facilitation enables successful learning and …

Systems Change in a Polarized Country - Kramer, Mark R. (Stanford Social Innovation Review, 2017)
A growing number of US foundations are adopting practices based on systems change to achieve their goals in the current political environment.

The Boda Boda Talk Talk Module - Internews (Internews & USAID, 2017)
Keywords: IMPORTANT

Evidence Base for Collaborating, Learning, and Adapting: summary of the literature review (2017 update) - Learning Lab (USAID, 2017)
LEARN and USAID/PPL are managing an area of work known as Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer key learning questions:

Using PDIA to Put Data Into Action - Bhatia, Vinisha; Powell, Josh (Development Gateway, 2017)
We recently wrote about how the data for development community needs to take a more context aware, demand-driven approach to data. Applying theories of change...

It’s About Results at Scale, Not Collective Impact - Edmondson, Jeff; Santhosh-Kumar, Parvathi (Stanford Social Innovation Review, 2017)
Improving outcomes at scale requires a paradigm shift in how we work.

Implementing the new development agenda - Wrap up - Teskey, Graham (2017)

Re-Perceiving Results: Aid Programs and Change in Fragile Societies - van Veen, Erwin; Rijper, Alies (Knowledge Platform Security & Rule of Law, 2017)
Aid programmes need to be able to adapt their objectives and operations to changes in their political environment, since development processes are subject to political contestation. Change takes time and is often a matter of seizing the opportunity.
Keywords: IMPORTANT

Thinking and Working Politically (Yangon, October 2016) - British Council (British Council Myanmar, 2017)
On 3-4 October 2016, British Council, Pyoe Pin, The Asia Foundation and UK DFID co-hosted a two day conference on ‘Thinking and Working Politically’ (TWP) for more effective and sustainable development assistance. The success or failure of development programmes is, in many – if not most – cases, determined by domestic politics within countries, rather than by the technical elegance of programme design by external donors. The event brought together international donors, implementing agencies and local partners. Participants compared experiences on what has worked, where and why – both in Myanmar, and across the world including case studies from Sudan, Zambia and the Philippines. Throughout the conference, participants familiarised themselves with politically smart development approaches and what it means to think and work politically in Myanmar. This has laid foundations for greater collaboration on TWP to help meet Myanmar’s critical development challenges.

Causality and attribution in market systems development - Jenal, Marcus; Liesner, Mollie (BEAM, 2017)
Resources that contain evidence of market systems interventions. Recently updated.

Landscape Analysis of Learing Agendas: USAID/Washington and beyond - Learning Lab (USAID, 2017)
EXECUTIVE SUMMARY U.S. government agencies and development organizations around the world are increasingly recognizing and supporting learning activities— often informed by a learning agenda—as important tools for improving organizational effectiveness and efficiency. A learning agenda comprises a set of broad questions directly related to the work that an agency conducts; when answered, they enable the agency to work more effectively and efficiently, particularly pertaining to evaluation, evidence, and decisionmaking. This report surveys the landscape of learning agendas at USAID and beyond to inform the learning agenda initiative planned by the Office of Learning, Evaluation, and Research (LER) in the Bureau for Policy, Planning and Learning (PPL). Reporting on research conducted over a 6-month period (September 2016 to February 2017), this landscape analysis focuses on six documented, office-, bureau-, or initiative-wide learning agendas being used at USAID/Washington. It also considers 11 new or noteworthy learning initiatives at USAID and five learning efforts at other federal agencies. The research team interviewed 60 staff from 20 USAID offices and bureaus, as well as staff from five other federal agencies. (See Annexes 1 through IV for more information.) The team also convened two focus groups: one with staff in USAID/Washington who had recently returned from serving in Missions, and one with PPL staff who discussed that bureau’s learning activities. The report details the interviewees’ remarks on six topics:  Motivations behind their decisions to pursue a learning agenda, such as expectations of accountability, especially in response to leadership demands  The key benefits emerging from their learning agenda efforts, which have included identifying gaps in knowledge and evidence, and supporting other cultural and organizational change processes  The participatory and consultative strategies they used to engage with stakeholders, including engagement with Mission staff and inclusion of academics and outside experts  The learning activities and products related to their initiatives  Challenges and strategies on resources, dissemination, and utilization, including ways to update their learning agenda to ensure that it remains a “living document”  Recommendations they had for PPL and others considering embarking on a learning agenda initiative

Thinking and Working Politically – Are We Seeing the Emergence of a Second Orthodoxy? - Teskey, Graham (Abt Associates, 2017)
There now is a persuasive volume of evidence that demonstrates that capacity and technical knowledge alone are insufficient to change deeply entrenched political interests and bureaucratic norms. These critiques demonstrate that an understanding of power asymmetries is frequently the critical missing ingredient in project design and implementation. Many eminent thinkers have looked at the difference between success and failure in development, and all point to the primacy of domestic politics. This point has not been lost on development agencies and some have tried to provoke greater attention to the role that politics plays. However, this recognition is yet to pass into the mainstream of development practice. Despite the slow but sure accretion of this knowledge the international community seems to be wedded to doing development traditionally. The purpose of this paper is to consider the extent to which a ‘second orthodoxy’ is slowly emerging which can stand alongside, and in some cases may supplant, the ‘first orthodoxy’ of the traditional project framework. Care has to be taken in making this argument, as there is certainly no consensus within the development community on its importance, and even among advocates, there are slightly differing interpretations of what this second orthodoxy looks like. Further, it is not absolutely clear that the two orthodoxies can co-exist. The paper does not call for any ‘paradigm shift’ in how development practitioners conceptualise programs and projects, nor does it demand that the project framework be scrapped; the former would be impossible and the latter undesirable. Equally readers will find no claims that Doing Development Differently or ‘Thinking and Working Politically’ will always and everywhere guarantee better development outcomes. Rather, the paper seeks to summarise how the two orthodoxies differ, where the second orthodoxy now stands, and propose how it can be taken forward in practical terms.

Project Cycle Hacker's Toolkit - changing the conversation around your projects - UNDP (UNDP, 2017)
The Istanbul Regional Hub partnered with Nesta and 4 country offices (fYR Macedonia, Moldova, Georgia and Kyrgyzstan) to develop a program that can help us bring innovation closer to the center of the organization by embedding it in the key project management business processes - The Project Cycle Hackers Toolkit.

Connecting the Dots: Systems Practice & Political Economy Analysis - Walker, Tjip; Jacobstein, David (2017)
This slide deck, from a presentation to the Local Systems Community by Tjip Walker and David Jacobstein, shows various ways in which assessing the political economy of a context and understanding that context through the lens of systems thinking can reinforce each other. Effective systems practice should be grounded in the incentives and power dynamics of a particular local system; thinking and working politically requires understanding the systems dynamics of an issue or sector.

Development is Going Digital: What is the role of INGOs? ICT for Development programmes in the Horn, East and Central Africa - Haikin, Matt; Flatters, George (Policy & Practice, 2017)
Development is going digital and INGOs like Oxfam have a vital convening role to play. This paper draws on ICT for Development in Oxfam’s programmes in the Horn, East and Central Africa to consider what this role is. In order to realise the opportunities

Fostering Learning in Large Programmes and Portfolios: Emerging Lessons from Climate Change and Sustainable Development - Harvey, Blane; Pasanen, Tiina; Pollard, Alison; Raybould, Julia (Sustainability, 2017)
In ﬁelds like climate and development, where the challenges being addressed can be described as “wicked”, learning is key to successful programming. Useful practical and theoretical work is being undertaken to better understand the role of reﬂexive learning in bringing together different knowledge to address complex problems like climate change. Through a review of practical cases and learning theories commonly used in the areas of resilience, climate change adaptation and environmental management, this article: (i) reviews the theories that have shaped approaches to reﬂexive learning in large, highly-distributed climate change and resilience-building programmes for development; and (ii) conducts a comparative learning review of key challenges and lessons emerging from early efforts to promote and integrate reﬂexive learning processes in programmes of this nature. Using a case study approach, the authors focus on early efforts made in four large, inter-related (or nested) programmes to establish, integrate and sustain learning processes and systems. Eight themes emerged from the review and are considered from the perspective of learning programmes as emergent communities of practice. By investigating how these themes play out in the nested programming, the paper contributes to the limited existing body of evidence on learning in large climate change programmes and identiﬁes areas where future efforts might focus.

PDIA Course: Alumni are already practicing what they learned - Samji, Salimah (Building State Capability, 2017)
written by Salimah Samji We offered 4 free PDIA online courses between November 2015 and June 2016. They were well received and 365 people, living in 56 countries, successfully completed the course…

Sense and Respond: How Successful Organizations Listen to Customers and Create New Products Continuously - Gothelf, Jeff; Seiden, Josh (Harvard Business Review Press, 2017)
The End of Assembly Line ManagementWe’re in the midst of a revolution. Quantum leaps in technology are enabling organizations to observe and measure people’s behavior in real time, communicate internally at extraordinary speed, and innovate continuously. These new, software-driven technologies are transforming the way companies interact with their customers, employees, and other stakeholders.This is no mere tech issue. The transformation requires a complete rethinking of the way we organize and manage work. And, as software becomes ever more integrated into every product and service, making this big shift is quickly becoming the key operational challenge for businesses of all kinds. We need a management model that doesn’t merely account for, but actually embraces, continuous change. Yet the truth is, most organizations continue to rely on outmoded, industrial-era operational models. They structure their teams, manage their people, and evolve their organizational cultures the way they always have.Now, organizations are emerging, and thriving, based on their capacity to sense and respond instantly to customer and employee behaviors. In Sense and Respond, Jeff Gothelf and Josh Seiden, leading tech experts and founders of the global Lean UX movement, vividly show how these companies operate, highlighting the new mindset and skills needed to lead and manage them—and to continuously innovate within them.In illuminating and instructive business examples, you’ll see organizations with distinctively new operating principles: shifting from managing outputs to what the authors call “outcome-focused management”; forming self-guided teams that can read and react to a fast-changing environment; creating a learning-all-the-time culture that can understand and respond to new customer behaviors and the data they generate; and finally, developing in everyone at the company the new universal skills of customer listening, assessment, and response.This engaging and practical book provides the crucial new operational and management model to help you and your organization win in a world of continuous change.

Putting theory into practice: how DFID is doing development differently - Wild, Leni; Booth, David; Valters, Craig (ODI, 2017)
Keywords: IMPORTANT

Lean vs Agile vs Design Thinking: What you really need to know to build high-performing digital product teams - Gothelf, Jeff (CreateSpace, 2017)
As companies evolve to adopt, integrate and leverage software as the defining element of their success in the 21st century, a rash of processes and methodologies are vying for their product teams' attention. In the worst of cases, each discipline on these teams – product management, design and software engineering – learn a different model. This short, tactical book reconciles the perceived differences in Lean Startup, Design Thinking and Agile software development by focusing not on rituals and practices but on the values that underpin all 3 methods.

ADS 201 Additional Help- Whole-of-Project Evaluation - USAID (USAID, 2017)

USAID ADS 201 - Program Cycle Operational Policy (Update 1/23/2017) - USAID (USAID, 2017)
The Program Cycle is USAID’s operational model for planning, delivering, assessing, and adapting development programming in a given region or country to advance U.S. foreign policy. It encompasses guidance and procedures for: 1) Making strategic decisions at the regional or country level about programmatic areas of focus and associated resources; 2) Designing projects and supportive activities to implement strategic plans; and 3) Learning from performance monitoring, evaluations, and other relevant sources of information to make course corrections as needed and inform future programming.

Building State Capability: Evidence, Analysis, Action - Andrews, Matt; Pritchett, Lant; Woolcock, Michael (Oxford University Press, 2017)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 licence. It is free to read at Oxford Scholarship Online and offered as a free PDF download from OUP and selected open access locations. Governments play a major role in the development process, and constantly introduce reforms and policies to achieve developmental objectives. Many of these interventions have limited impact, however; schools get built but children don't learn, IT systems areintroduced but not used, plans are written but not implemented. These achievement deficiencies reveal gaps in capabilities, and weaknesses in the process of building state capability.This book addresses these weaknesses and gaps. It starts by providing evidence of the capability shortfalls that currently exist in many countries, showing that many governments lack basic capacities even after decades of reforms and capacity building efforts. The book then analyses this evidence, identifying capability traps that hold many governments back - particularly related to isomorphic mimicry (where governments copy best practice solutions from other countries that make them look morecapable even if they are not more capable) and premature load bearing (where governments adopt new mechanisms that they cannot actually make work, given weak extant capacities). The book then describes a process that governments can use to escape these capability traps. Called PDIA (problem driveniterative adaptation), this process empowers people working in governments to find and fit solutions to the problems they face. The discussion about this process is structured in a practical manner so that readers can actually apply tools and ideas to the capability challenges they face in their own contexts. These applications will help readers devise policies and reforms that have more impact than those of the past.
Keywords: IMPORTANT

Donor perceptions and processes: Risks to success of adaptive programming? - Browse - Knowledge Platform Security & Rule of Law - Donovan, Elbereth (Knowledge Platform - Security & Rule of Law, 2017)
Keywords: IMPORTANT

Rapid experiments with a purpose - Moses, Michael (BEAM Exchange, 2017)
New insights, opinions and perspectives on market systems development, from experts and practitioners.
Keywords: IMPORTANT

Agile Metrics: The Good, the Bad, and the Ugly - Wolpers, Stefan (dzone.com, 2017)
Suitable agile metrics reflect either a team’s progress in becoming agile or your organization’s progress in becoming a learning organization.

Learning to Target for Economic Diversification: PDIA in Sri Lanka - Andrews, Matt; Ariyasinghe, Duminda; Batuwanthudawa, Thamari; Darmasiri, Shivanthika; Silva, Nilupul; Harrington, Peter; Jayasinghe, Prasanna; Jayasinghe, Upul; Jayathilake, Gamini; Karunaratne, Jayani; Katugampala, Lalit; Liyanapathirane, Jeewani; et al. (Center for International Development, Harvard University, 2017)

Political Economy Analysis – Guidance for legal technical assistance - Denney, Lisa; Domingo, Pilar (ROLE UK, 2017)
Political economy analysis is about understanding how change in relation to rule of law and international development is embedded within and shaped by political and economic relations that interact and are particular to each context. These political economy dynamics determine the distribution of power and resources within any given society and must be taken into account when attempting to achieve change. Political economy analysis is important in the justice sector because rule of law and dispute resolution processes reflect the rules of the game about who wins and who loses in the allocation of power and resources. Using political economy analysis in legal technical assistance can help to ensure more relevant and effective assistance that sustainably addresses concrete problems. It can also help to avoid the risk that poorly targeted assistance might inadvertently exacerbate existing power structures in a way that was not intended.

Systems Practice - Omidyar Group (The Omidyar Group, 2017)

18F Method Cards - A collection of tools to bring human-centered design into your project - 18F-GSA (18F-GSA, US Governement, 2017)
18F’s method cards describe how our organization puts human-centered design into practice.

+Acumen MOOC: Adaptive Leadership: Mobilizing for Change and Disrupting the Status Quo - +Acumen (NovoEd, 2017)
This four-module course by +Acumen and Adaptive Change Advisors on adaptive leadership, which is a practical leadership framework developed at Harvard Kennedy School for driving systemic change, particularly during times of uncertainty or when there are no easy answers.

Using adaptive processes and adverse outcome pathways to develop meaningful, robust, and actionable environmental monitoring programs - Arciszewski, Tim J.; Munkittrick, Kelly R.; Scrimgeour, Garry J.; Dubé, Monique G.; Wrona, Fred J.; Hazewinkel, Rod R. (Integrated Environmental Assessment and Management, 2017)
The primary goals of environmental monitoring are to indicate whether unexpected changes related to development are occurring in the physical, chemical, and biological attributes of ecosystems and to inform meaningful management intervention. Although achieving these objectives is conceptually simple, varying scientific and social challenges often result in their breakdown. Conceptualizing, designing, and operating programs that better delineate monitoring, management, and risk assessment processes supported by hypothesis-driven approaches, strong inference, and adverse outcome pathways can overcome many of the challenges. Generally, a robust monitoring program is characterized by hypothesis-driven questions associated with potential adverse outcomes and feedback loops informed by data. Specifically, key and basic features are predictions of future observations (triggers) and mechanisms to respond to success or failure of those predictions (tiers). The adaptive processes accelerate or decelerate the effort to highlight and overcome ignorance while preventing the potentially unnecessary escalation of unguided monitoring and management. The deployment of the mutually reinforcing components can allow for more meaningful and actionable monitoring programs that better associate activities with consequences. Integr Environ Assess Manag 2017;13:877–891. © 2017 The Authors. Integrated Environmental Assessment and Management Published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC)
Keywords: Adaptive monitoring; Environmental management; Environmental monitoring; Tier; Trigger

DFID Smart Rules: Better Programme Delivery - version VII (2017.04) - DFID (DFID, 2017)
Smart Rules provide the operating framework for the Department for International Development’s (DFID’s) programmes.
Keywords: IMPORTANT; Practice

Adaptive Programming and Business Environment Reform – Lessons for DFID Zimbabwe - Donovan, Elbereth; Manuel, Clare (DFID, 2017)
Keywords: IMPORTANT

Doing Development Differently: Understanding the Landscape and Implications of New Approaches to Governance and Public-sector Reforms - Fritz, Verena (Transformation, Politics and Implementation, 2017)
Seeking to accelerate development, the agencies and individuals involved have regularly advanced new ideas of how external support can function better, deliver more, and achieve greater impact. There has been a particular flourishing of new ideas within the broad field of governance and public-sector reforms in the 2000s. This chapter starts off with a review of the “landscape of new ideas,” focusing on five proposed approaches in particular: political economy analysis (PEA), Problem-Driven Iterative Adaptation (PDIA), Doing Development Differently (DDD), Thinking and Working Politically (TWP), and the “science of delivery.” It sets out the “problem-diagnostic” that underpins each of these

One step to a thousand miles: building accountability in Liberia - Gilberds, Heather (Accountability Lab Liberia, 2017)
Lessons for enabling accountability and integrity in Liberia

Toolkit Digitalisation: Tools to Support Strategic Planning and Implementation - GIZ (2017)

Transformation, politics and implementation: smart implementation in governance programs - Kirsch, Renate; Siehl, Elke; Stockmayer, Albrecht (Nomos, 2017)
Working in environments characterised by a high degree of uncertainty, uncontrollability and unpredictability, development agents try to organise complex realities into manageable units. What principles influence the decision on adequate approaches and necessary steps? Through theoretical considerations and nine case studies, the GIZ traces implementation processes and identifies underlying guiding principles which provide the flexibility and adaptability that is necessary for acting in complex contexts. Main findings show that an adaptive and reflexive management structure is crucial for successful implementation. Quick iteration and tight feedback loops facilitate adaptation and reorientation. Contextsensitive knowledge and constant monitoring create a space for learning and innovation. A joint vision for the future which is used for orientation purposes and can be modified according to new findings and developments fosters fruitful cooperation.
OCLC: 1000398466

An analysis of what CLA looks like in Development Programming - Learning Lab (USAID, 2017)

How can we be more adaptive? AdaptScan identifies critical areas for improvement - Mercy Corps (Mercy Corps & IRC, 2017)
Keywords: IMPORTANT

Adaptive Leadership in Development course - Moran, Mark; Curth-Bibb, Jodie; Grice, Tim; Glavey, Sarah (University of Queensland, 2017)

Bridging Real-Time Data and Adaptive Management in International Devepment - Case Study Report - Ramalingam, Ben; Barnett, Inka; Valters, Craig; Oppenheimer, Carrie; Levy, Anna; Hernandez, Kevin (IDS, 2017)

Confronting the Contradiction - An exploration into the dual purpose of accountability and learning in aid evaluation - Reinertsen, Hilde; Bjørkdahl, Kristian; McNeill, Desmond (Expertgruppen för biståndsanalys (EBA), 2017)
Keywords: IMPORTANT

ING’s agile transformation - Schlatmann, Bart (McKinsey Quarterly, 2017)
Two senior executives from the global bank describe their recent journey.

Conflict Aid Goes “Lean” - Shinkle, Whitney (Stanford Social Innovation Review, 2017)
Iterative design methods are essential to development work—even (or especially) in regions marked by war and violence.

I know what I know (but how do I know what I don’t?) - Smit, Debbie; de Lanerolle, Indra; Braam, Tamara; Byrne, Deborah; Legong, Gontse (MAVC, 2017)
An important support function of Making All Voices Count South Africa is to design, plan and facilitate community of practice gatherings for sustained learning and sharing across Making All Voices Count grantees. This report aims to capture the content of a one-day Making All Voices Count South African Community of Practice (CoP) Meeting held in November 2016. The South African MAVC CoP has been running for three years and has met between two and four times a year. It is a space for MAVC grantees and others working to foster innovation in the fields of transparency and accountability, to share experiences and knowledge, and collaborate in learning and improving work.

FOCEVAL – Promoting Evaluation Capacities in Costa Rica:: Smart(er) Implementation with Capacity WORKS? - Storm, Sabrina (Transformation, Politics and Implementation, 2017)
The National Monitoring and Evaluation System of Costa Rica and its corresponding laws were established during the 1990s. Since then, the country has endeavored to implement monitoring and evaluation (M&E) activities as part of its public policy framework. Nevertheless, hardly any systematic evaluations had been conducted, and monitoring activities had been reduced mainly to the institutional self-reporting of implementation compliance. Persisting regional disparities and growing levels of inequality among the population raised the level of pressure on the government to present reliable information on the effectiveness of public interventions. Hence, results-oriented evaluations were promoted by some Costa Rican departments as

Thinking and working politically in large, multi-sector Facilities: lessons to date - Teskey, Graham; Tyrrel, Lavinia (Abt Associates, 2017)

What exactly do we mean by systems? - Vexler, Dan (Stanford Social Innovation Review, 2017)
Everyone is talking about systems. Or at least, that's how it seems in my wonkish corner of the philanthropic world. You can't attend a conference or even have a meeting without hearing about systems, whether it's people trying to disrupt them, map them, learn from them, or catalyze them.

World Development Report 2017: Governance and the Law - World Bank (The World Bank, 2017)

'Leaving No One Behind': Why Ideas Matter - Evans, Alice (2016)

The context v intervention 2x2 | From Poverty to Power - Green, Duncan (From Poverty to Power, 2016)
Lots of discussion on my US trip around the strengths/weaknesses of the context v intervention 2x2 that suggests particular theories of change acc to situation
Keywords: IMPORTANT

Adaptive Management looks like it’s here to stay. Here’s why that matters. - Green, Duncan (From Poverty to Power, 2016)
First installment of reflections on my US trip. This is on the rise of adaptive management approaches in USAID, and some of the questions it raises
Keywords: IMPORTANT

Real-Time Data for Adaptive Management at USAID - Doshi, Samir (2016)

Managing Policy Mess - Roe, Emery (Governance in Turbulent Times, 2016)
What are the conditions for political development and decay, and the likelihood of sustained political order? What are the limits of established rule as we know it? How much stress can systems tackle before they reach some kind of limit? How do governments tackle enduring ambiguity and uncertainty in their systems and environments? These are some of the big questions of our time. Governance in turbulent times may serve as a stress-test of well-known ways of governing in the 21st century. Governance in Turbulent Times discusses this pertinent challenge and suggests how governments and organizations cope with and live with turbulence. The book explores how organizations and institutions respond to precipitous, conflicting, and novel-in short, turbulent-governance challenges. This book is a comprehensive and ground-breaking endeavor to understand how governance systems respond to turbulent challenges, and how turbulent times provide excellent opportunities to investigate the sustainability of governance systems. The book illustrates how politics, administrative scale and complexity, uncertainty, and time constraints can collide to produce turbulence. Building on prior work in organization theory and political science, we argue that turbulence refers to four properties related to the interaction of demands for action: variability, consistency, expectation, and unpredictability. Turbulence occurs where the interaction of demands is experienced as highly variable, inconsistent, unexpected, and/or unpredictable.
Google-Books-ID: IYSuDQAAQBAJ
Keywords: Comparative Politics; International Relations; Political Process; Political science; Public Affairs & Administration

How to Apply Agile Principles to International Development M&E - ICTworks (ICT Works, 2016)
We all want to be good at our jobs. We want to accomplish the things we set out to do. If we aren’t accomplishing them, we want to figure out why or try new solutions. The trend toward Adaptive M&E is exactly that: a desire to be better at our jobs. Similar trends exist in the software world (agile) and in manufacturing and start-ups (lean). But by any name, this process of seeking to improve is about speeding up decision-making and solution delivery by focusing on incremental, iterative planning and execution. I presented on agile with Monalisa Salib of USAID Learning Lab at MERL Tech 2016. I talked about creating software; she talked about creating evaluation tools for USAID missions, but we were describing the same basic process: Develop, Release, Reflect, and Adapt. You can see our slide deck for more details, but here are the key discussion takeaways that won’t show up there: 1: Eyes on the Prize Any effort should start with a clear definition of what you’re hoping to achieve.
Keywords: IMPORTANT

Assumptions, conjectures, and other miracles: The application of evaluative thinking to theory of change models in community development - Archibald, Thomas; Sharrock, Guy; Buckley, Jane; Cook, Natalie (Evaluation and Program Planning, 2016)
Unexamined and unjustified assumptions are the Achilles’ heel of development programs. In this paper, we describe an evaluation capacity building (ECB) approach designed to help community development practitioners work more effectively with assumptions through the intentional infusion of evaluative thinking (ET) into the program planning, monitoring, and evaluation process. We focus specifically on one component of our ET promotion approach involving the creation and analysis of theory of change (ToC) models. We describe our recent efforts to pilot this ET ECB approach with Catholic Relief Services (CRS) in Ethiopia and Zambia. The use of ToC models, plus the addition of ET, is a way to encourage individual and organizational learning and adaptive management that supports more reflective and responsive programming.
Keywords: Assumptions; Community development; Critical thinking; Evaluation capacity building; Evaluative thinking; International Development; Theory of change

Causal inferences on the effectiveness of complex social programs: Navigating assumptions, sources of complexity and evaluation design challenges - Chatterji, Madhabi (Evaluation and Program Planning, 2016)
This paper explores avenues for navigating evaluation design challenges posed by complex social programs (CSPs) and their environments when conducting studies that call for generalizable, causal inferences on the intervention’s effectiveness. A definition is provided of a CSP drawing on examples from different fields, and an evaluation case is analyzed in depth to derive seven (7) major sources of complexity that typify CSPs, threatening assumptions of textbook-recommended experimental designs for performing impact evaluations. Theoretically-supported, alternative methodological strategies are discussed to navigate assumptions and counter the design challenges posed by the complex configurations and ecology of CSPs. Specific recommendations include: sequential refinement of the evaluation design through systems thinking, systems-informed logic modeling; and use of extended term, mixed methods (ETMM) approaches with exploratory and confirmatory phases of the evaluation. In the proposed approach, logic models are refined through direct induction and interactions with stakeholders. To better guide assumption evaluation, question-framing, and selection of appropriate methodological strategies, a multiphase evaluation design is recommended.
Keywords: Causal inferences; Complex social programs; Experimental designs; Impact evaluations; Mixed methods

Assumption-aware tools and agency; an interrogation of the primary artifacts of the program evaluation and design profession in working with complex evaluands and complex contexts - Morrow, Nathan; Nkwake, Apollo M. (Evaluation and Program Planning, 2016)
Like artisans in a professional guild, we evaluators create tools to suit our ever evolving practice. The tools we use as evaluators are the primary artifacts of our profession, reflect our practice and embody an amalgamation of paradigms and assumptions. With the increasing shifts in evaluation purposes from judging program worth to understanding how programs work, the evaluator’s role is changing to that of facilitating stakeholders in a learning process. This involves clarifying purposes and choices, as well as unearthing critical assumptions. In such a role, evaluators become major tool-users and begin to innovate with small refinements or produce completely new tools to fit a specific challenge or context. We interrogate the form and function of 12 tools used by evaluators when working with complex evaluands and complex contexts. The form is described in terms of traditional qualitative techniques and particular characteristics of the elements, use and presentation of each tool. Then the function of each tool is analyzed with respect to articulating assumptions and affecting the agency of evaluators and stakeholders in complex contexts.
Keywords: Agency; Assumption-aware; Complex context; Complex programs; Participatory approaches; Program design; Program evaluation; Program tools; Theory-based

Conclusion: Agency in the face of complexity and the future of assumption-aware evaluation practice - Morrow, Nathan; Nkwake, Apollo M. (Evaluation and Program Planning, 2016)
This final chapter in the volume pulls together common themes from the diverse set of articles by a group of eight authors in this issue, and presents some reflections on the next steps for improving the ways in which evaluators work with assumptions. Collectively, the authors provide a broad overview of existing and emerging approaches to the articulation and use of assumptions in evaluation theory and practice. The authors reiterate the rationale and key terminology as a common basis for working with assumption in program design and evaluation. They highlight some useful concepts and categorizations to promote more rigorous treatment of assumptions in evaluation. A three-tier framework for fostering agency for assumption-aware evaluation practice is proposed-agency for themselves (evaluators); agency for others (stakeholders); and agency for standards and principles.
Keywords: Agency; Complexity

Policy messes and their management - Roe, Emery (Policy Sciences, 2016)
This paper presents a framework for better managing policy messes and draws implications for bad and good mess management in policy analysis and management. The framework has three foci: (1) the cognitive space in which policy messes develop, particularly in terms of gaps between macro-designers and micro-operators; (2) the unique domain of competence within that space where professionals manage the resulting messes by virtue of their skills in recognizing system-wide patterns, formulating locally specific contingency scenarios and translating both patterns and scenarios in highly reliable services; and (3) the ability of those mess and reliability professionals to be reliable in their domain and with these skills by maneuvering across different performance modes as conditions dictate—just-in-case, just-on-time, just-for-now or just-this-way.

Rethinking systemic change: economic evolution and institutions. Discussion paper - Cunningham, Shawn; Jenal, Marcus (BEAM Exchange, 2016)
The primary aim of this research project was to find a conceptually sound definition of systemic change. To do so, it was essential to gain a better understanding of how economies change. The central part of the research work, therefore, was an extended literature review on three bodies of knowledge: evolutionary economics new institutional economics complexity theory There is a growing interest in these bodies of knowledge, combined often called New Economic Thinking, and how they affect economic development. Hence, while rethinking systemic change, this work also contributes to answering the broader question of how market systems approaches can contribute to inclusive economic development. The answer, in short, is to shift the focus away from improving transactions at the micro level towards enabling actors to continuously shape an institutional landscape that supports inclusive economic evolution. This discussion paper briefly presents the key messages from the literature review and seven principles drawing from this literature. The principles can be used by market development practitioners, including technical advisers in donor organisations, programme designers and team leaders, to shape programmes and become more in line with how change happens in the economy. A list of selected references is presented at the end. A technical paper contains a much more detailed discussion of the findings and the principles and an extensive list of references. A case study offers a practitioner perspective through the lens of one market systems development programme: DFID-funded Northern Uganda: Transforming the Economy through Climate Smart Agribusiness – Market Development (NUTEC-MD).

Rethinking systemic change: economic evolution and institutions. Technical Paper - Cunningham, Shawn; Jenal, Marcus (BEAM Exchange, 2016)
The primary aim of this research project was to find a conceptually sound definition of systemic change. To do so, it was essential to gain a better understanding of how economies change. The central part of the research work, therefore, was an extended literature review on three bodies of knowledge: evolutionary economics, new institutional economics and complexity theory. There is a growing interest in these bodies of knowledge, combined often called New Economic Thinking, and how they affect economic development. Hence, while rethinking systemic change, this work also contributes to answering the broader question of how market systems approaches can contribute to inclusive economic development. The answer, in short, is to shift the focus away from improving transactions at the micro level towards enabling actors to continuously shape an institutional landscape that supports inclusive economic evolution. This technical paper provides an in-depth review of the fields of evolutionary economics, new institutional economics and complexity and social change. It is argued that economic development is a complex, non-linear and continuous evolutionary process. Both market and non-market institutions matter greatly in shaping economic performance. The paper then explores the consequences of this understanding for market development practice. It discusses how market development practitioners can engage in and shape an intentional change processes. To translate the theory into practice, seven principles are suggested that can be applied to market systems development practice. The paper concludes with a reframed look at systemic change in market systems development. A discussion paper presents the key messages from the literature review and seven principles drawing from this literature, and a case study offers a practitioner perspective through the lens of one market systems development programme: DFID-funded Northern Uganda: Transforming the Economy through Climate Smart Agribusiness – Market Development (NUTEC-MD).

Scaling accountability through vertically integrated civil society policy monitoring and advocacy - Fox, Jonathan (IDS, 2016)
This working paper argues that the growing field of transparency, participation and accountability (TPA) needs a conceptual reboot, to address the limited traction gained so far on the path to accountability. To inform more strategic approaches and to identify the drivers of more sustainable institutional change, fresh analytical work is needed. This paper makes the case for one among several possible strategic approaches by distinguishing between “scaling up” and “taking scale into account”. This proposition grounds an explanation of the vertical integration strategy, which involves multi-level coordination by civil society organisations of policy monitoring and advocacy, grounded in broad pro-accountability constituencies. To spell out how this strategy can empower pro-accountability actors, the paper contrasts varied terms of engagement between state and society, proposing a focus on collaborative coalitions as an alternative to the conventional dichotomy between confrontation and constructive engagement. The paper grounds this discussion by reviewing the rich empirical terrain of existing multi-level approaches, summarizing nine cases – three each in three countries – to demonstrate what can be revealed when TPA initiatives are seen through the lens of scale. It concludes with a set of broad analytical questions for discussion, followed by testable hypotheses proposed to inform future research agendas

Rethinking systemic change in practice - perspectives from NUTEC-MD in northern Uganda - Koleros, Andrew (BEAM Exchange, 2016)
Document description This document is currently being finalised and will be published shortly. Please try again soon. Recent research by The BEAM Exchange seeks to understand theoretical perspectives on how market systems approaches can contribute to inclusive economic development through systemic change. It produced three main insights. Economies are evolving systems, building on the mechanisms of variety creation, selection and amplification. Current economic performance, including aspects like the inclusiveness of growth and economic evolution, are shaped by the ability of a society to explore different options for institutional arrangements and adjust them over time. This process of evolution is complex. While some aspects can be designed and managed, others need to be explored through a process of learning and adjustment. This paper responds to these insights by providing a practitioner perspective through the lens of one programme: “Northern Uganda: Transforming the Economy through Climate Smart Agribusiness – Market Development (NUTEC-MD)”, implemented by Palladium Group. It begins with a brief introduction to the programme and key aspects of its design phase. It then provides a summary of the three main research insights, with reflections on their applicability for programme design based on the NUTEC-MD experience. Finally, it provides some conclusions for the wider practitioner community based on this case.

Doing Development Differently: Who we are, What we’re doing, What we’re learning - ODI (ODI, 2016)
In November 2014, the doing development differently community got together in Harvard to discuss what successful development interventions look like. Two years on, our community is broader than aid. It's broader than donors. It's about all organisations delivering change, producing real solutions to real problems that have real impact. It's about building trust, empowering people and promoting sustainability. Over the past two years, the community has been putting these ideas into practice across the world – being honest about what we are learning, including where we are not getting things right. This document aims to be an entry point for anyone interested in doing development differently. It explores the things that could be stopping you including: You are constrained by a disabling environment. You have strict reporting requirements. People aren't sold on the idea. It's easier to do things the way you've always done it. It's difficult to do in practice. If you are facing one, several, or all of these constraints, this document gives you a place to start. Using 43 case studies from practitoners within donors, governments, implementing organisations and NGOs across the globe, we aim to draw out some key lessons learnt, and give some advice for people considering this approach. These case studies are split across five categories: Swimming against the tide. Working in and with government. Feedback loops and data. Organisational change. Diffusion. Finally, if you want to know more, the document concludes with a suggested list of blogs and reports which explain these concepts in more detail.
Keywords: IMPORTANT

The Science in Adaptive Management - Ripley, Matt; Jaccard, Sabine (ILO, 2016)
‘Adaptive management’ is all the rage in international development circles. But to avoid yet another buzzword – we need to learn from the experience of natural resource science.
Keywords: IMPORTANT

Nigeria Public Sector Accountability and Governance Programme - Business Case - SAVI (DFID, 2016)
In May 2016, SAVI transitioned into a successor programme – the ‘Engaged Citizens Pillar’ (ECP) of a wider DFID-funded governance reform programme ‘The Partnership to Engage, Reform and Learn’ (PERL). ECP is managed by the same service provider, Palladium, and the same core management team as SAVI, and many of the SAVI front line staff...

SAVI Approach Paper 11: Managing and Staffing an Adaptive Citizen Engagement Programme - SAVI (DFID, 2016)
SAVI, a DFID funded programme implemented by Palladium, is an adaptive programme putting learning and adaptation at the centre of all decision-making. In relation to management and staffing SAVI has established the following approaches to facilitate this: – An adaptive approach to programme management: Full time strategic technical leadership, that works closely with and complements...

SAVI Approach Paper 12: Managing Programme Finances to Support Adaptive, Locally-led Processes of Citizen Engagement in Governance - SAVI (DFID, 2016)
SAVI, is seeking to support processes of citizen engagement in governance in ways that are effective in influencing reform, and that are able to take on a life of their own without continuing donor support. SAVI is also an adaptive programme, putting learning and adaptation at the centre of all decision-making. Money is used and...

SAVI Approach Paper 13: Measuring Value for Money and using Value for Money Analysis - SAVI (DFID, 2016)
SAVI has established its own framework for assessing Value for Money in annual performance – in relation to expenditure, economy, efficiency, effectiveness and equity. Routine tracking and analysis of expenditure and economy ensure that inputs are supplied and services delivered to partners in line with SAVI’s core values, whilst also meeting DFID requirements and competing...

SAVI Approach Paper 14: Learning, Adaptation and Communications - SAVI (DFID, 2016)
SAVI, a DFID funded programme implemented by Palladium, is an adaptive programme, aiming to put learning and adaptation at the centre of all decision-making. Learning and adaptation takes place in SAVI at three levels: the work of partners; the work of SAVI delivery teams; and the enabling environment of the programme as a whole. Achieving...

SAVI Approach Paper 15: Introduction to PERL: the SAVI Successor Programme - SAVI (DFID, 2016)
In May 2016, SAVI transitioned into a successor programme – the ‘Engaged Citizens Pillar’ (ECP) of a wider DFID-funded governance reform programme ‘The Partnership to Engage, Reform and Learn’ (PERL). ECP is managed by the same service provider, Palladium, and the same core management team as SAVI, and many of the SAVI front line staff...

Forget the money: De-linking technical assistance - Manuel, Clare (DFID-LASER Programme, 2016)

From analysis to action: operationalising learning and adaptation in Savings at the Frontier - Salehi, Yusef (2016)
Keywords: IMPORTANT

Global Learning for Adaptive Management (GLAM) - DFID (DFID Development Tracker, 2016)
To improve the value for money and impact of development interventions by promoting the use of better monitoring, evaluation and learning strategies that support development programmes to gather and respond to emergent evidence on the effects of interventions, as well as changes in the development context. The Global Learning for Adpative Management programme will make available technical assistance to DFID, USAID and partners to develop this ‘adaptive management’ approach, as well as build an evidence base to understand links between the use of adaptive management and more effective, efficient, relevant and sustainable development interventions.

Shoulder to Shoulder - Hymowitz, Dan (Tony Blair Africa Governance Initiative, 2016)

Overcoming Premature Evaluation - Roche, Chris (2016)
Guest post from Chris Roche on practical ways of introducing adaptive management, learning from failure etc in aid programmes

Scaling Assessment Map: An Evolving Tool Supporting Innovation Scale Up - McClure, Dan; Gray, Ian (ThoughtWorks, 2016)
Nearly three years ago we wrote about the “Missing Middle” in the innovation lifecycle[i], a gap that kept successful pilot programs from reaching the goal of replication and optimization in multiple contexts. Since then, scaling humanitarian innovation has received a great deal of attention from the sector, with a number of new initiatives specifically focused on the scaling challenge.

Positive Deviance Initiative (2016)

Why Diverse Teams Are Smarter - Rock, David; Halvorson, Heidi Grant (Harvard Business Review, 2016)
Research shows they’re more successful in three important ways.

Why the Problem with Learning Is Unlearning - Bonchek, Mark (Harvard Business Review, 2016)
Don’t get stuck in your current ways of thinking.

LEARN Monitoring, Evaluation, Research, and Learning Plan - Learning Lab (USAID, 2016)
LEARN and USAID/PPL are managing an area of work known as Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer key learning questions:

What is adaptive management? - Wilson, Gregory (ΔNTYLLES, 2016)
Recently there has been growing recognition that most development challenges are in actual fact ‘wicked’ problem that requires development actors to recognize that the optimal management approaches…

Should the Principles of Digital Development be Agile? - ICTworks (ICT Works, 2016)
Recently, Abt Associates endorsed the “Principles of Digital Development.” These nine principles have been widely adopted by international development funders and practitioners to absorb and disseminate technology best practices in the field of international development. More than 50 organizations ranging from various offices in the United Nations and the U.S. Agency for International Development (USAID) down to niche technology providers have endorsed the principles. The principles are aimed at moving the field away from a disconnected series of technology pilots, each of which are largely ad hoc and duplicate many of the same lessons, and toward scalability and sustainability. Ann Mei Chang, the Executive Director of the U.S. Global Development Lab at USAID in her foreword to the recent report “From Principle to Practice: Implementing the Principles for Digital Development”, characterized the problem that these principles are trying to address as follows: “Pilots have failed to move

Top-down vs. Bottom-up Hierarchy: Or, How to Design a Self-Managed Organization - Sisney, Lex (Organizational Physics - Systems thinking for breakthrough business performance, 2016)
Top-down vs. Bottom-up Hierarchy: Or, How to Design a Self-Managed Organization

Agile vs Lean vs Design Thinking - Gothelf, Jeff (Medium, 2016)
There’s an unforgettable scene in my favorite movie, Goodfellas, where Joe Pesci, Robert DeNiro and Ray Liotta pay a late night visit to…

PDIA Notes 2: Learning to Learn - Samji, Salimah (Building State Capability, 2016)
written by Peter Harrington After over two years of working with the government of Albania, and as we embark on a new project to work with the government of Sri Lanka, we at the Building State Capa…

Design Thinking is not enough – Innovate DFID - DFID, Innovate (Medium, 2016)
By Tamara Giltsoff

Contracts for adaptive programming - Bryan, Kevin; Carter, Paddy (ODI, 2016)
Adaptive programming is an approach to development that encourages experimentation, learning & adaptation. This report examines the contractual underpinnings of this approach.

Thinking and Working politically to support developmental leadership and coalitions: The Pacific Leadership Program - Denney, Lisa; McLaren, Rebecca (DLP Program, 2016)

DFID Smart Rules: Better Programme Delivery - version VI (2016.10) - DFID (DFID, 2016)
Smart Rules provide the operating framework for the Department for International Development’s (DFID’s) programmes.
Keywords: IMPORTANT; Practice

Collaborating, Learning, and Adapting (CLA). Framework and Maturity Matrix Overview - Learning Lab (USAID, 2016)

Grow - Scale - Impact: How to help inclusive business achieve scale - Pérez Castro, Andrea A.; Tora, Krisztina (GIZ, 2016)

The 5 Rs Framework in the program cycle - USAID (2016)
USAID’s Program Cycle Operational Policy (ADS 201) provides guidance to missions and other operating units on how to implement the Program Cycle. A key principle of the Program Cycle is to “Promote Sustainability through Local Ownership.” The purpose of this Technical Note is to describe the “5Rs Framework”, a practical methodology for supporting sustainability and local ownership in projects and activities through ongoing attention to local actors and local systems. This Note is rooted in USAID’s 2014 Local Systems Framework paper, which establishes that achieving sustained improvement in development results depends on the contributions of multiple and interconnected local actors. That document also states that USAID needs to improve its systems practice if it is to engage local actors and strengthen local systems more effectively and thus realize sustained results more consistently. The 5Rs Framework, also introduced in the Local Systems Framework, is intended as a simple and practical tool to promote good systems practice. The 5Rs Framework highlights five key dimensions of systems: Results, Roles, Relationships, Rules and Resources. Collectively these 5Rs can serve as a lens for assessing local systems and a guide for identifying and monitoring interventions designed to strengthen them. This Technical Note is divided in two parts. The first part provides an introduction to the 5Rs Framework and the systems practice from which it emerges. The second part demonstrates how systems practice can be embedded in the Program Cycle by continuously applying the 5Rs, especially to the design, implementation, and monitoring of USAID projects and their accompanying activities.

Building justice and peace from below? Supporting community dispute resolution in Asia - Valters, Craig (ODI, 2016)

Announcement of CLA Learning Network Launch - Lab, Learning (USAID Learning Lab, 2016)
USAID’s Bureau for Policy, Planning and Learning (PPL), together with the Bureau for Economic Growth, Education, and Environment’s localworks program, is pleased to announce the launch of a Learning Network focused on building the evidence base for Collaborating, Learning and Adapting (CLA).

Adaptive Programming: The “Space of Possibility” - Seavey, Sara Mizuta (USAID Learning Lab, 2016)
Sara Mizuta Seavey, M.A., is a Senior Program Officer at FHI360 for the Mobile Solutions Technical Assistance and Research (mSTAR) project, where she works with USAID’s Digital Development Team to conceive, design, and test how real-time data systems can enable a more adaptive and participatory approach to development. She is passionate about systems thinking and participatory approaches to international development. What does space travel have to do with international development?

Forward Look - A vision for the World Bank Group in 2030 - World Bank (World Bank, 2016)

The fascinating world of unconscious bias and development policy - d’Almeida, André Corrêa; Grossi, Amanda Sue (The Guardian, 2016)
In the last few years scientists have exposed thinking patterns that may skew our decision-making. How can we counter these biases in humanitarian work?
Keywords: Academic experts; Higher Education Network; Neuroscience; Psychology; education; higher education

edX MOOC: Adaptive Leadership in Development - edX (edX, 2016)
Gain the skills to be an adaptive leader in development and learn how to uncover local solutions to complex problems in developing countries.

Moving ICTD research beyond bungee jumping: practical case studies and recommendations - Dearden, Andy; Tucker, William (IEEE Technology and Society Magazine, 2016)
The global spread of Internet and mobile communications has been accompanied by a growing interest in how information and communication technologies (ICTs) can contribute to social and economic development. There are a considerable number of such examples in developing countries. For example, M-Pesa in Kenya allows workers in the cities to send money back to families living in the countryside using SMS messages on basic mobile phones. In Ghana, the Motech project allows community health workers to use feature phones and network services to track ante-natal (and post-natal) care with the objective of improving outcomes for both mothers and babies. Other examples include Gram Vaani's (GRINS) open-source software for community radio stations, or Ushahidi's initiatives, which began with tracking post-electoral violence in Kenya in 2008 using mobile phones and Google maps. These examples illustrate different ways of leveraging ICT to improve lives and livelihoods worldwide. Such stories are inspiring many young (and not so young) researchers and innovators alike to explore how technology might support social and economic development and inclusion in global knowledge exchange

How China Escaped the Poverty Trap - Ang, Yuen Yuen (Cornell University Press, 2016)
Before markets opened in 1978, China was an impoverished planned economy governed by a Maoist bureaucracy. In just three decades it evolved into the world's second-largest economy and is today guided by highly entrepreneurial bureaucrats. In How China Escaped the Poverty Trap, Yuen Yuen Ang explains this astonishing metamorphosis. Rather than insist that either strong institutions of good governance foster markets or that growth enables good governance, Ang lays out a new, dynamic framework for understanding development broadly. Successful development, she contends, is a coevolutionary process in which markets and governments mutually adapt.By mapping this coevolution, Ang reveals a startling conclusion: poor and weak countries can escape the poverty trap by first harnessing weak institutions―features that defy norms of good governance―to build markets. Further, she stresses that adaptive processes, though essential for development, do not automatically occur. Highlighting three universal roadblocks to adaptation, Ang identifies how Chinese reformers crafted enabling conditions for effective improvisation.How China Escaped the Poverty Trap offers the most complete synthesis to date of the numerous interacting forces that have shaped China’s dramatic makeover and the problems it faces today. Looking beyond China, Ang also traces the coevolutionary sequence of development in late medieval Europe, antebellum United States, and contemporary Nigeria, and finds surprising parallels among these otherwise disparate cases. Indispensable to all who care about development, this groundbreaking book challenges the convention of linear thinking and points to an alternative path out of poverty traps.
Keywords: IMPORTANT

Cognitive bias cheat sheet. An organized list of cognitive biases because thinking is hard - Benson, Buster (Better Humans, 2016)

Doing Development Differently at the World Bank: updating the plumbing to fit the architecture - Bain, Katherine A.; Booth, David; Wild, Leni (ODI, 2016)
Keywords: IMPORTANT

Developing ICT Services in a Low-Resource Development Context - Bon, Anna; Akkermans, Hans; Gordijn, Jaap (Complex Systems Informatics and Modeling Quarterly, 2016)
Keywords: IMPORTANT

Collaborating, Learning, and Adapting. Framework & Key Concepts - Learning Lab (USAID, 2016)

Adaptive management: What it means for CSOs - O’Donnell, Michael (Bond, 2016)
Keywords: IMPORTANT

Delivering institutional reform at scale: Problem-driven approaches supported by adaptive programming - Manuel, Clare (DFID-LASER Programme, 2016)
LASER synthesis papers aim to help donors and other stakeholders better understand why and how to approach investment climate reform programming differently. The papers reflect emerging best practice and lessons learnt on what works and what does not work in doing development differently. The papers have been peer-reviewed by experts in the field including senior advisers at DFID, World Bank, IFC and the Donor Committee for Enterprise Development (amongst others). Second synthesis paper - Delivering institutional reform at scale: problem-driven approaches supported by adaptive programming February 2016 Drawing on our experience on the ground, this peer-reviewed paper suggests how problem driven approaches, supported by adaptive programme management can be implemented at scale in relation to donor programming aimed at institutional reform and improving state capability.
Keywords: IMPORTANT

Evidence Base for Collaborating, Learning, and Adapting: summary of the literature review (2016.08) - Learning Lab (USAID, 2016)
LEARN and USAID/PPL are managing an area of work known as Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer key learning questions:

This startup uses machine learning and satellite imagery to predict crop yields - Brokaw, Alex (The Verge, 2016)
Mark Johnson wants to beat the United States Department of Agriculture at its own game: predicting yields of America's crops. The USDA puts boots on the ground, deploying hundreds of workers to...

Payment by Results in Development Aid: All That Glitters Is Not Gold - Clist, Paul (The World Bank Research Observer, 2016)
Payment by Results (PbR), where aid is disbursed conditional upon progress against a pre-agreed measure, is becoming increasingly important for various donors. There are great hopes that this innovative instrument will focus attention on ultimate outcomes and lead to greater aid effectiveness by passing the delivery risk on to recipients. However, there is very little related empirical evidence, and previous attempts to place it on a sure conceptual footing are rare and incomplete. This article collates and synthesises relevant insights from a wide range of subfields in economics, providing a rich framework with which to analyze Payment by Results. I argue that the domain in which it dominates more traditional forms is relatively small and if it is used too broadly, many of the results it claims are likely to be misleading. The likelihood of illusory gains stems from the difficulty of using a single indicator to simultaneously measure and reward performance: ‘once a measure becomes a target, it ceases to be a good measure.’ This does not mean PbR should not be used (indeed it will be optimal in some settings), but it does mean that claims of success should be treated with caution.
Keywords: Conditionality; Contract theory; F35; Foreign Aid; Multitask model; performance

Adaptive programming in practice: shared lessons from the DFID-funded LASER and SAVI programmes - Derbyshire, Helen; Donovan, Elbereth (DFID-LASER Programme, 2016)
LASER synthesis papers aim to help donors and other stakeholders better understand why and how to approach investment climate reform programming differently. The papers reflect emerging best practice and lessons learnt on what works and what does not work in doing development differently. The papers have been peer-reviewed by experts in the field including senior advisers at DFID, World Bank, IFC and the Donor Committee for Enterprise Development (amongst others).
Keywords: IMPORTANT; Practice

Alignment at Scale - Kniberg, Henrik (2016)

Politics matters, so what? Time for bigger bets (and more learning) on adaptive programming - Alan (www.globalintegrity.org, 2016)
By Alan Hudson, Executive Director, Global Integrity, July 26, 2016 Politics matters. Context too. And blueprints have limited value. Our strategy is based on these insights, so we’re totally on board. A World Development Report (WDR) that puts power and politics...

Adaptive development: great progress and some niggles - Vowles, Pete (Medium, 2016)
After 3 years in DFID headquarters, championing adaptive approaches to the delivery of aid and development programmes, I am back in an…

mHero and the Principles for Digital Development: Development Done Right | iHRIS (2016)

Making design core to the agile process: a look into how we built Salesforce's Lightning Experience - Schoen, Ian (Medium, 2016)
A look into how we built Salesforce’s Lightning Experience

Adaptive Management Leaders Launch Practical Adaptation Network (PAN) - Labs, Feedback (FeedbackLabs, 2016)
Great things can happen at the frontier of theory and practice. When Feedback Labs worked with USAID’s Global Development Lab to bring together leaders in adaptive management at the White House on June 15th, we were pleased that we were able to move past the ongoing conceptual conversations toward discussing what we could do in concrete terms to implement adaptive management in practice.

Strategy Deployment and Spotify Rhythm - Scotl, Karl (AvailAgility, 2016)
Last month, Henrik Kniberg posted slides from a talk he gave at Agile Sverige on something called Spotify Rhythm - "Spotify’s current approach to getting aligned as a company". While looking through the material, it struck me that what he was describing was a form of Strategy Deployment. This interpretation is based purely on those slides - I haven't had a chance yet to explore this more deeply with Henrik or anyone else from Spotify. I hope I will do some day, but given that caveat, here's how I currently understand the approach in terms of the X-Matrix Model.

Using beneficiary feedback to improve development programmes: findings from a multi-country pilot - World Vision (World Vision, 2016)
This briefing summarises the findings from Beneficiary Feedback Mechanisms pilots and is intended to inform organisations and their funders about the development and implementation of feedback mechanisms.

The road to adaptive management: knowledge, leadership, culture and rules - Byrne, Karri Goeldner; Sparkman, Timothy; Fowler, Ben (The BEAM Exchange, 2016)
Keywords: IMPORTANT; Practice

Social network analysis handbook: connecting the dots in humanitarian programs - IRC (International Rescue Committee, 2016)
The following handbook is designed to provide a step by step guide to the application of Social Network Analysis for the IRC.
Keywords: IMPORTANT

The Scrum Guide - Schwaber, Ken; Sutherland, Jeff (scrum.org, 2016)

Christian Practical Wisdom: What It Is, Why It Matters - Bass, Dorothy C.; Cahalan, Kathleen A.; McLemore, Bonnie J.; Nieman, James R.; Scharen, Christian B. (Wm. B. Eerdmans Publishing Company, 2016)
Why is the very kind of knowledge that people need to live well ― practical wisdom ― often the least understood, the hardest to learn, and the most devalued kind of knowledge?In this book five distinguished practical theologians examine the wisdom that is basic for faithful Christian living, question why it has been largely devalued, and advocate for its renewal. After first showing several concrete situations in which this kind of wisdom is visible ― marriage, church, community, culture, and more ― the authors then delve into the reasons for the decline of practical wisdom and set forth constructive cases for its renewal through biblical imagination and spiritual practice.

ADAPT: Analysis Driven Agile Programming Techniques - IRC (International Rescue Committee (IRC), 2016)
A growing body of research indicates that aid agencies are most successful when able to operate flexibly, particularly in fragile environments. Yet our systems and tools are often too rigid to effectively address complex problems, and program incentives frequently undermine adaptation instead of supporting it. To drive improvements in impact we need to be better able to analyse the dynamics of a given situation, anticipate how these might evolve, and be sufficiently agile to adapt to changes in context and need.

A Low-resource Aware Framework for ICT Service Development in Rural Africa - Bon, Anna; Gordijn, Jaap; Akkermans, Hans (Proceedings of the CAiSE'16 Forum, 2016)
Technological innovation and information & communication technologies (ICTs) are considered enabling factors for social and economic development, even in very poor parts of the world. However,...

Participation in ICT Development Interventions: Who and How? - Thapa, Devinder; Sæbø, Øystein (The Electronic Journal of Information Systems in Developing Countries, 2016)
The aim of participatory development (PD) in the context of using Information and Communication Technologies (ICT) for development (ICT4D) is to empower underprivileged communities and disadvantaged segments of the stakeholders. The literature on ICT4D is replete with empirical evidence showing that ICT interventions often fail since they are often externally initiated, with very limited involvement from the affected (Heeks, 2002). Clearly, the principles and concepts of PD are relevant to ICT4D. However, we should not consider PD a panacea but need to understand the caveats and processes by which PD happens. Questions to ask include: What are the various challenges in PD? Who are the relevant stakeholders? Why and how do actors enrol in the project? How do we create sustainable ICT4D projects through PD? To understand these research questions, we present a case analysis of a project in Nepal called the Nepal Wireless Networking Project (NWNP). Investigating the specific initiatives that they enabled, telemedicine, education and jobs, we propose that the key participants in the NWNP were activist actors and the affected and that activists drew upon existing Social Capital to enrol the affected through a process explained by Actor Network Theory (ANT). In the process, they built other forms of Social Capital, which in turn extended the benefits of PD to several mountain villages.

Where have we got to on adaptive learning, thinking and working politically, doing development differently etc? Getting beyond the People’s Front of Judea - Algoso, Dave; Hudson, Alan (From Poverty to Power, 2016)
Dave Algoso and Alan Hudson at Global Integrity compare and contrast 9 different initiatives that are all heading in roughly the right direction in aid reform
Keywords: IMPORTANT

Spotify Rhythm - how we get aligned - Kniberg, Henrik (AvailAgility, 2016)
Last month, Henrik Kniberg posted slides from a talk he gave at Agile Sverige on something called Spotify Rhythm - "Spotify’s current approach to getting aligned as a company". While looking through the material, it struck me that what he was describing was a form of Strategy Deployment. This interpretation is based purely on those slides - I haven't had a chance yet to explore this more deeply with Henrik or anyone else from Spotify. I hope I will do some day, but given that caveat, here's how I currently understand the approach in terms of the X-Matrix Model.

Experiential Learning: Fostering lasting behavioural change - Norton, Brittney M. (Mercy Corps, 2016)
The term ‘experiential learning’ is often mistakenly used to describe any learning experience that involves participatory activities. This paper presents an overview of what true experiential learning is and how this form of learning allows for real-world application - thus promoting lasting behavioural change. Furthermore, it explains how experiential learning was adopted as the methodological core of the Prospects psychosocial programme in Liberia, which builds ‘pre-employment skills’ in 3,500 vulnerable youth aged 15-24 years. The goal of the paper is to provide other youth and education development practitioners with a resource that can be used to strengthen youth and behaviour change programmes through the incorporation of the experiential learning theory. In addition, this paper explains its application in the Prospects programme, before concluding with key considerations of such a design. 1

Designing Regenerative Cultures - Wahl, Daniel Christian (Triarchy Press Ltd, 2016)
This is a 'Whole Earth Catalog' for the 21st century: an impressive and wide-ranging analysis of what's wrong with our societies, organizations, ideologies, worldviews and cultures - and how to put them right. The book covers the finance system, agriculture, design, ecology, economy, sustainability, organizations and society at large. In this remarkable book, Daniel Wahl explores ways in which we can reframe and understand the crises that we currently face, and he explores how we can live our way into the future. Moving from patterns of thinking and believing to our practice of education, design and community living, he systematically shows how we can stop chasing the mirage of certainty and control in a complex and unpredictable world. The book asks how can we collaborate in the creation of diverse regenerative cultures adapted to the unique biocultural conditions of place? How can we create conditions conducive to life? *** "This book is a valuable contribution to the important discussion of the worldview and value system we need to redesign our businesses, economies, and technologies - in fact, our entire culture - so as to make them regenerative rather than destructive." –Fritjof Capra, author of The Web of Life, co-author of The Systems View of Life: A Unifying Vision *** "This is an excellent addition to the literature on ecological design and it will certainly form a keystone in the foundations of the new MA in Ecological Design Thinking at Schumacher College, Devon. It not only contains a wealth of ideas on what Dr Wahl has termed 'Designing Regenerative Cultures' but what is probably more important, it provides some stimulating new ways of looking at persistent problems in our contemporary culture and hence opens up new ways of thinking and acting in the future." – Seaton Baxter OBE, Prof. in Ecological Design Thinking, Schumacher College, UK [Subject: Systems Thinking, Education, Social Anthropology, Environmentalism, Ecology, Regenerative Culture, Sociology]

Doing Anti-corruption Differently - Jorge (www.globalintegrity.org, 2016)
By Alan Hudson, Executive Director Corruption and how to tackle it is center-stage in London this week, with the spotlight brighter than ever as a result of the Panama Papers. This is welcome news. The Anti-Corruption Summit, hosted by the...

Learning to Adapt: Building Adaptive Management as a Core Competency in Development Practice - Ramalingam, Ben (Institute of Development Studies, 2016)
Key messages 1. Development policies and programs increasingly operate in situations of high complexity and uncertainty. 2. There are growing efforts across the sector to design, plan and implement more adaptive responses that are more relevant and appropriate in such contexts 3. At the heart of effective adaptive programming is the capability to gather, interpret and use knowledge, information and data in real-time 4. Strengthening this capability requires a positive enabling environment—including tools and methods, structures and processes, leadership and management and culture and mindsets. 5. For adaptive development to succeed, there needs to be greater attention and investment in both knowledge, information and data systems and in appropriate enabling environments
Keywords: IMPORTANT

When theory meets reality: assumptions, feasibility and implications of a complexity-informed approach - Buffardi, Anne (Methods Lab, 2016)
Over the last half century, repeated calls for adaptive learning in development suggests two things: many practitioners are working in complex situations that may benefit from flexible approaches, and such approaches can be difficult to apply in practice. • Complexity thinking can offer useful recommendations on how to take advantage of distributed capacities, joint interpretation of problems and learning through experimentation in complex development programmes. • However, these recommendations rely on underlying assumptions about relationships, power and flexibility that may not hold true in practice, particularly for programmes operating in a risk averse, results-driven environment. • This paper poses guiding questions to assess the fit and feasibility of integrating complexity informed practices into development programmes.

Reforming solid waste management in Phnom Penh - Denney, Lisa (2016)
This paper tracks the efforts of an Asia Foundation team and local stakeholders as they worked to support improvements in the solid waste management sector in Phnom Penh, Cambodia. The team worked in a flexible way with a range of partners, and with particular focus on understanding the incentives and politics affecting service delivery. While reform of the sector remains in progress, steps have been taken to introduce more competition and better public sector management of solid waste collection in the city. This case study lays out the real-time decisions and processes which drove the strategy and implementation of this project, providing useful insights into how politically astute and flexible programs can be successfully implemented. This case has emerged from an action research process, which was led by a researcher from the Overseas Development Institute (ODI) and conducted over the course of almost two years. By capturing and analyzing the experiences of the program team in Phnom Penh, the paper intends to provide practical insights for others in the development community aiming to implement similar kinds of programming.

Wheeling in the Trojan Mice - Mahendra, Jackie (Stanford Social Innovation Review, 2016)
One way to make risk-taking more palatable for social change organizations is to run small, light, nimble experiments––tests not built to win wars, but rather to quickly infiltrate new territory, attack new problems, and inform future tactics.

“There’s no money for that.” Three Ways to Resource Collaborating, Learning, and Adapting - Salib, Monalisa (USAID Learning Lab, 2016)
This blog is the third in an ongoing series exploring the components of USAID's CLA Framework. Here is the first blog on organizational culture and the second on effective learning.

Simple Habits for Complex Times: Powerful Practices for Leaders - Berger, Jennifer Garvey; Johnston, Keith (Stanford University Press, 2016)

Learning and adaptation: 6 pitfalls to avoid - Valters, Craig (Devex, 2016)

More books on complexity than you can shake a stick at—plus a mea culpa - Algoso, Dave (Praxis, 2016)
Last month, Duncan Green was kind enough to post my overly ambitious multi-book review on complexity thinking in development on his From Poverty to Power blog. It covered three books: Ben Ramalingam’s Aid on the Edge of Chaos; Jean Boulton, Peter Allen, and Cliff Bowman’s Embracing Complexity; and Danny Burns and Stuart Worsley’s Navigating Complexity in International Development. It...

The Future is a Choice: The Oxfam Framework and Guidance for Resilient Development - Jeans, Helen; Thomas, Sebastien; Castillo, Gina (Policy & Practice, 2016)
This guide provides a framework for Oxfam staff to design programmes and campaigns that contribute to resilient development. Oxfam defines resilience as ‘the ability of women and men to realize their rights and improve their well-being despite shocks, stresses

A Critique of the Claims About Mobile Phones and Kerala Fisherman. The Importance of the Context of Complex Social Systems - Steyn, Jacques (The Electronic Journal of Information Systems in Developing Countries, 2016)
This paper challenges some fundamental aspects of research and conclusions relating to the use of technology for community development. Views of technology, in this case the mobile phone, as a tool for increased economic welfare are often skewed due to extreme reductionism, ambiguous interview questions and poor data sources. Research of complex social systems or sub-systems give the wrong answers when reductionist methodologies are used. To demonstrate such shortcomings, the 2007 paper of Robert Jensen serves as an example. His conclusion that mobile phones enable Kerala fishermen to increase their economic welfare is the most cited paper on ICT4D topics, but there are fundamental methodological and logical problems with the claim, while other research came to contradictory conclusions. This critique is presented on many levels: ideological, paradigmatic, methodology, logical, statistical and semantic.

Reflections on implementing politically informed, searching programs: lessons for aid practitioners and policy makers - Cole, William; Ladner, Debra; Koenig, Mark; Tyrrel, Lavinia (2016)

The Science of Using Science: Researching the Use of Research Evidence in Decision-Making - Langer, Laurenz; Tripney, Janice; Gough, David (EPPI-Centre, Social Science Research Unit, UCL Institute of Education, University College London, 2016)

Impact evaluation for portfolio programmes on policy influence: Reflections on the Indonesian Poverty Reduction Support Facility - Mackenzie, Jessica; Hearn, Simon (Methods Lab, 2016)
• Donors are increasingly using portfolio-based programmes that embrace ‘good failure’ and adaptive, political programming. • However, measuring the impact of these programmes is challenging, especially for those working on policy influence and building country systems; not only do you need to measure the positive and negative impact of the overall portfolio, but also the different pathways tested. • Programmes, therefore, need a light-touch monitoring and evaluation system that allows it to remain flexible. • Good practice examples of portfolio-based programmes present six strategies to evaluate impact: 1. Develop appropriate logic models 2. Collect observational data throughout implementation 3. Develop stories of change or case studies 4. Understand causal relationships without a counterfactual 5. Purposefully select which activities to study 6. Be explicit about how impact will be valued across the portfolio. • These strategies are only useful if monitoring and evaluation is placed at the centre of programme decision-making.

Adaptive Management in Practice: a case study on the Prospects program - Maclay, Chris (Mercy Corps, 2016)
Recognising that aid and development programming takes place in complex contexts, Mercy Corps is increasingly seeking to understand how best to manage programs which iterate, adapt and respond to the consistently evolving settings in which we work. This brief Practice Paper provides some examples of what adaptive management looks like in practice on the Prospects youth employment program in Liberia. It does not seek to function as a manual or set of guidelines, but simply provides some practical examples and insights into how a youth employment program governed by principles of adaptive management operates.

Innovation for International Development: Navigating the Paths and Pitfalls - Ramalingam, Ben; Bound, Kirsten (NESTA, 2016)
Experiences, insights and practical advice from over 20 leading practitioners in innovation for international development, brought together in one collection.

Built to improve: Leveraging realtime M&E for adaptive youth employment programming - Skelton, John (Mercy Corps, 2016)
Recognising that aid and development programming takes place in complex contexts, Mercy Corps is increasingly seeking to understand how best to manage programs which iterate, adapt and respond to the consistently evolving settings in which we work. This brief Practice Paper provides some examples of what adaptive management looks like in practice on the Prospects youth employment program in Liberia. It does not seek to function as a manual or set of guidelines, but simply provides some practical examples and insights into how a youth employment program governed by principles of adaptive management operates.

Dealing with uncertainty: Reflections on donor preferences for pre-planned project models - Tyrrel, Lavinia; Cole, William (2016)
Keywords: IMPORTANT

Redesigning Field Papers’ User Interface - Jacks, Lindsey (Cadasta, 2016)
For the past three months, I've been working with Cadasta and Stamen on the atlas creation pages of the Field Papers map annotation tool. The end result is now live on the Field Papers website. We took the four step “wizard” process for creating an atlas, combined it all into a single-page, and...
Keywords: IMPORTANT

Life and death in the App Store - Newton, Casey (The Verge, 2016)
As last year began, the app developer Pixite held its company retreat at a converted Old West movie set outside of Palm Springs. They spent a few days dreaming about the future while eating...

Technical challenges in the application of adaptive management - Williams, Byron K.; Brown, Eleanor D. (Biological Conservation, 2016)
Adaptive management is an approach for simultaneously managing and learning about natural resources, by acknowledging uncertainty and seeking to reduce it through the process of management itself. Adaptive decision making can be applied to pressing issues in conservation biology such as species reintroduction, disease and invasive species control, and habitat restoration, as well as to management of natural resources in general. After briefly outlining a framework and process for adaptive management, we focus on an overview of the key technical issues related to problem framing and the ability of resource managers to learn from their experience. These technical issues include the treatment of uncertainty and its propagation over time; nonstationarity in long-term environmental trends; the applicability of adaptive management across scales; requirements for models and management alternatives that promote learning; the value of the information produced with adaptive management; the challenge to management of uncertainty and surprise; and institutional (social) learning. To accommodate these and other challenges that are now coming into focus, the learning-based approach of adaptive management will need to be adjusted and expanded in the future.
Keywords: Adaptive Management; Learning; Nonstationarity; Resilience; Uncertainty; Value of information

Politically smart support to economic development: DFID experiences - Booth, David (ODI, 2016)

Using political economy analysis in conflict, security and justice programmes - Denney, Lisa (ODI, 2016)

Leather sector reform in Bangladesh - Harris, Dan (2016)
This paper examines the Asia Foundation’s efforts to support change in Bangladesh’s leather sector. Working closely with local partners, the Asia Foundation team has specifically supported efforts to move tanneries out of a dangerously polluted location to a modern industrial park that will improve compliance with health and environmental protection standards, and potentially lead to growth in the sector. At the time of release, this critical relocation has already begun. This case study lays out the real-time decisions and processes which drove the strategy and implementation of this project, providing useful insights into how politically astute and flexible programs can be successfully implemented. This case has emerged from an action research process, which was led by a researcher from the Overseas Development Institute (ODI) and conducted over the course of almost two years. By capturing and analyzing the experiences of the program team in Bangladesh, the paper intends to provide practical insights for others in the development community aiming to implement similar kinds of programming. This is the seventh paper in the DFAT-TAF Partnership Working Politically in Practice Paper Series released under the Australian Government Department of Foreign Affairs and Trade (DFAT) and The Asia Foundation (TAF) Partnership.

Using adaptive development to support feminist action - O’Neil, Tam (ODI, 2016)
This paper looks at how adaptive development is being applied by gender programmes and argues that gender and adaptive development communities have much to offer each other.

‘Learning journeys’ for adaptive management – Where does it take us? - Ørnemark, Charlotte (Global Partnership for Social Accountability, 2016)
Keywords: IMPORTANT

SPACES MERL: Systems and Complexity White Paper - USAID (2016)
The Strategic Program for Analyzing Complexity and Evaluating Systems (SPACES MERL) project is an activity funded by USAID’s Global Development Lab and the Bureau for Policy, Planning and Learning (PPL). This three-year activity aims to bring a variety of tools and methodologies that decision-makers can use (alone or in combination) to provide comprehensive systems analysis. The activity is being implemented from 2015 to 2018 by a consortium of organizations expert in systems and complexity, including the Global Obesity Prevention Center (GOPC) at Johns Hopkins University (Prime), Global Knowledge Initiative (GKI), LINC and ResilientAfrica Network (RAN). This Systems and Complexity White Paper is a collaborative effort of the SPACES MERL team, designed to frame the international development landscape, with particular reference to USAID-funded activities, for application of systems and complexity approaches to design, monitoring and evaluation. Customized to the systems and complexity layperson with in-depth knowledge of international development practice, the objectives of this white paper are three-fold:  Provide an overview of systems and complexity practice, its current state of application and relevance to international development practice;  Establish a taxonomy of systems and complexity tools, highlighting the fit of those offered by SPACES MERL within the wider landscape; and  Review and provide information on application of SPACES MERL tools, their purpose and construction, required data, and their applicability to specific contexts.

Putting learning at the centre: Adaptive development programming in practice - Valters, Craig; Cummings, Clare; Nixon, Hamish (ODI, 2016)
Adaptive programming suggests, at a minimum, that development actors react and respond to changes in the political and socio-economic operating environment. It emphasises learning and the development practitioner is encouraged to adjust their actions to find workable solutions to problems that they may face. Being prepared to react to change may seem like common sense – and indeed it is. However much development thinking and practice remains stuck in a linear planning model which discourages learning and adaptation, in part because projects are seen as ‘closed, controllable and unchanging systems’ (Mosse, 1998: 5). This paper critically engages with this problem and makes clear why and how learning needs to be at the centre of adaptive development programming. It begins by clarifying why and what kind of learning matters for adaptive programming. The paper then turns its focus to how strategies and approaches applied throughout a programme’s conception, design, management and M&E can enable it to continually learn and adapt.
Keywords: IMPORTANT

USAID Applied Political Economy Analysis - Field Guide - Cammack, Diana (USAID, 2016)
Political Economy Analysis (PEA) is a field-research methodology used to explore not simply how things happen in an aid-recipient country, but why things happen. It results in a written assessment with recommendations for a mission's County Development Cooperation Strategy (CDCS), project or activity design, or course correction during implementation.USAID's Applied PEA is a problem-focused method specially intended to be used by Mission staff to inform the design of aid interventions at any phase of the USAID program cycle and at any level of effort.

Redefining Rigor: Describing Quality Evaluation in Complex, Adaptive Settings - Preskill, Hallie; Lynn, Jewlya (FSG, 2016)
Traditionally, evaluation has focused on understanding whether a program is making progress against pre-determined indicators. In this context, the quality of the evaluation is often measured in part by the “rigor” of the methods and scientific inquiry.

Moving Targets, Widening Nets: monitoring incremental and adaptive change in an Empowerment and Accountability programme. The experience of the State Accountability and Voice Initiative in Nigeria - Derbyshire, Helen; Barr, Julian; Fraser, Steve; Mwamba, Wilf (DFID, 2016)
Keywords: IMPORTANT; Practice

Politically smart approaches to donor investment climate programming. A Guidance Note - LASER (DFID-LASER Programme, 2016)
In order to help enhance the effectiveness of donors and development practitioners on the ground, LASER has produced a range of practical guidance and tools. These are primarily intended for the international development community engaged in designing and implementing investment climate programmes, though can also be used more widely by other stakeholders across sectors. General guidance and tools: Politically smart approaches to donor investment climate programming (and annexes) Revised February 2016 - sets out practical advice on how to adopt a politically smart (which requires being both ‘politically informed’ and ‘politically astute’) approach to programming. The annexes include a traffic light matrix for initial high level analysis; a problem diary template with examples; and an example of a flexible theory of change for adaptive, large scale programming
Keywords: Practice

Balancing Inclusiveness, Rigour and Feasibility: Insights from Participatory Impact Evaluations in Ghana and Vietnam - van Hemelrijck, Adinda; Guijt, Irene (CDI, 2016)
This paper by Adinda Van Hemelrijck and Irene Guijt explores how impact evaluation can live up to standards broader than statistical rigour in ways that address challenges of complexity and enable stakeholders to engage meaningfully. A Participatory Impact Assessment and Learning Approach (PIALA) was piloted to assess and debate the impacts on rural poverty of two government programmes in Vietnam and Ghana funded by the International Fund for Agricultural Development (IFAD). We discuss the trade-offs between rigour, inclusiveness and feasibility encountered in these two pilots. Trade-offs occur in every impact evaluation aiming for more than reductionist rigour, but the pilots suggest that they can be reduced by building sufficient research and learning capacity.

From principle to practice: Implementing the Principles for Digital Development - Waugaman, Adele (2016)
The Principles for Digital Development (download PDF here) find their roots in the efforts of individuals, development organizations, and donors alike who have called for a more concerted effort by donors and implementing partners to institutionalize lessons learned in the use of information and communication technologies (ICTs) in development projects.
Keywords: IMPORTANT

How ICT4D Research Fails the Poor - Harris, Roger W. (Information Technology for Development, 2016)
Research can improve development policies and practices and funders increasingly require evidence of such socioeconomic impact from their investments. This article questions whether information and communication technologies for development (ICT4D) research conforms to the requirements for achieving socioeconomic impact. We report on a literature review of the impact of research in international development and a survey of ICT4D researchers who assessed the extent to which they follow practices for achieving socioeconomic impact. The findings suggest that while ICT4D researchers are interested in influencing both practice and policy, they are less inclined toward the activities that would make this happen, especially engaging with users of their research and communicating their findings to a wider audience. Their institutions do not provide incentives for researchers to adopt these practices. ICT4D researchers and their institutions should engage more closely with the users of their research through more and better communications with the public, especially through the use of information and communication technologies.
Keywords: ICT4D; Policy making; Practice; Research; impact

Collaborative Overload - Cross, Rob; Rebele, Reb; Grant, Adam (Harvard Business Review, 2016)
Too much teamwork exhausts employees and saps productivity. Here’s how to avoid it.

Making politics work for development: harnessing transparency and citizen engagement - Khemani, Stuti; Ferraz, Claudio; Finan, Frederico S.; Johnson, Stephenson; Louise, Corinne; Abrahams, Scott David; Odugbemi, Adesinaola Michael; Dal Bó, Ernesto; Thapa, Dikshya (The World Bank, 2016)
Too often, government leaders fail to adopt and implement policies that they know are necessary for sustained economic development. They are encumbered by adverse political incentives, which prevent them from selecting good policies, and they run the risk of losing office should they try to do the right thing. Even when technically sound policies are selected by leaders, implementation can run into perverse behavioral norms among public officials and citizens, who seek to extract private benefits from the public sector. Such behavior might be supported by widespread beliefs that corruption is the norm. Even countries with low corruption and strong institutions experience problems of political incentives and behavior that prevent the public sector from solving shared problems. Ideological polarization among citizens and capture by special interests can lead to policy gridlock and the failure of the state to provide public goods, even in advanced economies. Even educated citizens can hold ideological beliefs about the role of public policy that lead them to deny technical evidence contrary to these beliefs. Too often, government leaders fail to adopt and implement policies that they know are necessary for sustained economic development. Political constraints can prevent leaders from following sound technical advice, even when leaders have the best of intentions. Making Politics Work for Development: Harnessing Transparency and Citizen Engagement focuses on two forces—citizen engagement and transparency—that hold the key to solving government failures by shaping how political markets function. In today’s participative world, citizens are not only queueing at voting booths, but are also taking to the streets and using modern communication technology to select, sanction, and pressure the leaders who wield power within government. This political engagement can function in highly nuanced ways even within the same formal institutional context and across the political spectrum, from autocracies to democracies. Political engagement becomes unhealthy when leaders are selected and sanctioned on the basis of their provision of private benefits rather than public goods, giving rise to a range of government failures. The solutions to these failures lie in fostering healthy political engagement within any institutional context, and not in circumventing or suppressing it. Transparency—citizen access to publicly available information about the actions of those in government and the consequences of these actions—can play a crucial role by nourishing political engagement. The report distills policy lessons for governments, international development partners, and civil society on how best to target transparency initiatives so that the provision of public goods becomes the focus of political contestation. Even so, unhealthy political engagement may persist. But to build institutions that are capable of tackling public goods problems, politics needs to be addressed and cannot be side-stepped. Targeted transparency is one way to move in the right direction: it complements everything else policy makers do and holds the potential to make politics work for development rather than against it. " This pathbreaking report places politics at the heart of the development dialogue—exactly where it belongs. It provides constructive ideas for harnessing the forces of transparency and citizen engagement in ways that are suited to diverse institutional contexts so that reform leaders can overcome political constraints to their countries’ development goals. " Asli Demirgüç-Kunt, Director of Research, Development Research Group, The World Bank "This book not only provides an authoritative statement of what we know about how to align political incentives with the interests of society, but it does so with an eye to making change happen even in the face of political opposition. The World Bank will never be the same again. " James Robinson, University Professor, Harris School of Public Policy, University of Chicago " A lesson for us at the World Bank also comes out of this research. We can do more…to work with our clients to diminish political constraints to achieving development goals…To do this we have to overcome the fear of talking about politics, and confront it as part of the challenge of development. That is what we are doing through this report. " Kaushik Basu, Senior Vice President and Chief Economist, The World Bank

Exploring ways to reconcile accountability and learning in the evaluation of niche experiments - Regeer, Barbara J.; de Wildt-Liesveld, Renée; van Mierlo, Barbara; Bunders, Joske F. G. (Evaluation, 2016)
While evaluation is seen as a mechanism for both accountability and learning, it is not self-evident that the evaluation of niche experiments focuses on both accountability and learning at the same time. Tensions exist between the accountability-oriented needs of funders and the learning needs of managers of niche experiments. This article explores the differences in needs and expectations of funders and managers in terms of upwards, downwards and internal accountability. The article shows that as the multi-stakeholder contexts in which niche experiments take place give rise to various requirements, tensions in evaluation are essentially a specific manifestation of tensions between niche experiments and their multiple contexts. Based on our findings, an adjusted accountability framework is proposed, including several strategies that can reconcile a learning approach with accountability needs in niche experiments aiming to change current practices in a more sustainable direction.

From political economy analysis to doing development differently: a learning experience - Booth, David; Harris, Daniel; Wild, Leni (ODI, 2016)
A study of how development efforts can be strengthened by an awareness of political economy, reflecting on the experiences of PoGo policy researchers.
Keywords: IMPORTANT

Thinking and Working Politically: from theory building to building an evidence base - Dasandi, Niheer; Marquette, Heather; Robinson, Mark (DLP, 2016)
This paper discusses the steps required to build a robust evidence base for 'thinking and working politically' (TWP) in development. It argues that better understanding what works, when and why is an important step in moving TWP into mainstream development programming. The paper reviews the existing evidence base on TWP, building on this and on other literature on public sector reform and 'pockets of effectiveness' to suggest research questions, case study selection criteria, and a four-level analytical framework: 1) political context; 2) sector; 3) organisation; and 4) individual. The framework aims to help build a 'rigorous enough' evidence base to show whether and how TWP happens and whether or not it influences the effectiveness of programme implementation and outcomes. The paper also calls for more focus on gender issues, and on different – and often more fragile – political contexts.
Keywords: IMPORTANT

Everyday Political Analysis - Hudson, David; Marquette, Heather; Waldock, Sam (Developmental Leadership Program, 2016)
This short note introduces a stripped-back political analysis framework designed to help frontline development practitioners make quick but politically-informed decisions. It aims to complement more in-depth political analysis by helping programming staff to develop the 'craft' of political thinking in a way that fits their everyday working practices. Everyday Political Analysis involves two steps: Understanding interests: What makes people tick? Understanding change: What space and capacity do people have to effect change? For each step five questions, accompanied by prompts, aim to help staff to conduct quick political analysis. The EPA framework can be used at any stage of the aid management cycle, and can help users to respond rapidly to unexpected change. We are keen to hear back from people on their experience of using EPA to help us adapt the framework. Was it useful (or not)? Do people tend to use just one or both steps? Are there missing statements or prompts that would improve the analysis? Please email us at info [at] dlprog.org.

Monday morning in Kigali: what do you do when you get off the plane? Practical guidance for PDIA practitioners - LASER (DFID-LASER Programme, 2016)
In order to help enhance the effectiveness of donors and development practitioners on the ground, LASER has produced a range of practical guidance and tools. These are primarily intended for the international development community engaged in designing and implementing investment climate programmes, though can also be used more widely by other stakeholders across sectors. General guidance and tools: Monday morning in Kigali January 2016 - what do you do when you get off the plane? Practical guidance for PDIA practitioners
Keywords: IMPORTANT; Practice

Rethinking Rigor - Increasing Credibility and Use - Lynn, Jewlya; Preskill, Hallie (Spark Policy Institute & FSG, 2016)
Evaluations of complex systems change strategies or adaptive, innovative programs cannot use the traditional “rigor” yardstick to measure quality. This paper proposes a new definition of rigor, one that applies in any setting, but particularly in complex, adaptive ones. Top Takeaways: 4 criteria for the new definition of rigor: - Quality of thinking - Credible and legitimate claims - Cultural context and responsiveness - Quality and value of the learning process Regardless of its other positive attributes, an evaluation of a complex, adaptive program that fails to take into account systems thinking will not be responsive to the needs of that program.

Case study: Embedding reform and exiting: LASER’s application of the hourglass approach to achieve sustainable results - Manuel, Clare (DFID-LASER Programme, 2016)
This case study describes how LASER has gone about enabling systemic change and sustainable uptake of reforms that address complex institutional problems in Kenya, Rwanda, Sierra Leone, Somaliland and Uganda. In each of these countries LASER has designed-in a sustainable approach from the start based on: (i) local ownership and leadership of reforms based on developing country (rather than donor) priorities; (ii) use of country (rather than donor programme) systems; and (iii) an understanding that the role of the donor / development practitioner is to support (rather than buy) reform. The case study uses LASER’s hour glass methodology, illustrated with examples from LASER interventions, to show how these principles guide LASER operations every step of the way.
Keywords: IMPORTANT; Practice

Summarising portfolio change: results frameworks at organisational level - Simister, Nigel (Intrac, 2016)

TWP CoP (Thinking and Working Politically - Community of Practice, 2016)

Adapting Aid: Lessons from six case studies - Algoso, Dave; Beloe, Jon; Hemberger, Alison; Hill, Philippa; Proud, Emma (MercyCorps & IRC, 2016)
Keywords: IMPORTANT

Doing Iterative and Adaptive Work - Andrews, Matt; Pritchett, Lant; Woolcock, Michael (Center for International Development at Harvard University, 2016)
Many of the challenges in international development are complex in nature. They involve many actors in uncertain contexts and with unclear solutions. Our work has proposed an approach to addressing such challenges, called Problem Driven Iterative Adaptation (PDIA). This paper is the most recent in a series intended to show how one can do PDIA, building on the first paper, "Doing Problem Driven Work.” The current paper addresses a key part of the approach one moves to once a problem has been identified, performing real-time experimental iterations. This is intended as a practical paper that builds on experience and embeds exercises for readers who are actually involved in this kind of work.
Keywords: IMPORTANT

Leading Change Through Adaptive Design - Berstein, Maya; Linsky, Marty (Stanford Social Innovation Review, 2016)
By integrating two practices—design thinking and adaptive leadership—social innovators can manage projects in a way that’s both creatively confident and relentlessly realistic.

Adaptive management: an overview of the concept and its practical application in the Scottish context - Blackstock, Kirsty; Brown, Katrina; Gimona, Alessandro; Prager, Katrin; Irvine, Justin (The James Hutton Institute, 2016)

The MSP Tool Guide: Sixty tools to facilitate Multi-Stakeholder Partnerships - Brouwer, Herman; Brouwers, Jan (CDI, Wageningen University and Research, 2016)
What is ‘The MSP Tool Guide’ all about? This compilation of 60 tools is an companion to The MSP Guide, the Wageningen University & Research CDI resource on how to design and facilitate effective multi-stakeholder partnerships. At the request of many readers we have compiled them into one document to enable easy storing and sharing. These tools are available in summarized version in the MSP Guide in Chapter 6. The detailed versions on how to use the tool, and when to use it, are available on the portal www.mspguide.org/tools-and-methods. The content of this portal is compiled in this Tool Guide.

The MSP Guide: How to Design and Facilitate Multi-Stakeholder Partnerships - Brouwer, Herman; Woodhill, Jim; Hemmati, Minu; Verhoosel, Karèn; van Vugt, Simone (Practical Action Publishing, 2016)
In recent years, multi-stakeholder partnerships (MSPs) have become popular for tackling the complex challenges of sustainable development. This guide provides a practical framework for the design and facilitation of these collaborative processes that work across the boundaries of business, government, civil society and science. The guide links the underlying rationale for multistakeholder partnerships, with a clear four phase process model, a set of seven core principles, key ideas for facilitation and 60 participatory tools for analysis, planning and decision making. The guide has been written for those directly involved in MSPs – as a stakeholder, leader, facilitator or funder – to provide both the conceptual foundations and practical tools that underpin successful partnerships. What’s inside draws on the direct experience of staff from the Wageningen Centre of Development Innovation (WCDI), at Wageningen University & Research, in supporting MSP processes in many countries around the world. The guide also compiles the ideas and materials behind WCDI’s annual three week international course on facilitating MSPs and social learning. This work has been inspired by the motivation and passion that comes when people dare to “walk in each other’s shoes” to find new paths toward shared ambitions for the future.

Scaling up - From Vision to Large-Scale Change - A Management Framework for Practitioners - Cooley, Larry; Kohl, Richard; Ved, Rajani R. (MSI, 2016)
This document was originally published in 2006 and re-issued in a substantially revised Second Edition in 2012.

Measuring the Barriers to Big Data for Development: design-reality gap analysis - Fernando Gomez, L.; Heeks, R. (Manchester University Development Informatics Working Paper Series, 2016)

Open Policy Making toolkit - gov.uk (2016)
This manual includes information about Open Policy Making as well as the tools and techniques policy makers can use to create more open and user led policy.

More than just luck: Innovation in humanitarian action - Obrecht, Alice; Warner, Alexandra T. (Humanitarian Innovation Fund, 2016)
In South Sudan, a new water treatment system that provides a community with more clean water at a lower cost. In Sierra Leone, a poster explaining how to prevent the...

Winners and Losers in the Global App Economy - Pon, Bryan (2016)

All about behaviour: KAPE, Adaptation and ' Sticky' Institutional Change - Power, Greg (Global Partners Governance, 2016)
This paper describes Global Partners Governance’s (GPG’s) approach to institutional reform and political change. Developed over the last decade of working in some of the most complex and sensitive political environments with politicians and officials in parliaments, political parties, ministries and local government, it describes the KAPE® (knowledge-application-practice-effect) methodology that we adopt to get ‘sticky’ institutional and behavioural change. Contents 1) Two dimensions of ‘adaptive programmes’: Flexible delivery and getting behaviour change 2) Enabling Change: KAPE and The Logic of Institutional Reform (Knowledge-Application-Practice-Effect) - K: Knowledge – Defining the problem and what to do about it - A: Application – Making Systems Work in Practice - P: Practice – Pockets of good practice and establishing ‘the new normal’ - E: Effect – Improved performance and the ‘Ripple Effect’ 3) Measuring Impact: Monitoring and Evolving 4) Conclusion: Behavioural insights, adaptive management and sticky change

State Accountability and Voice Initiative (SAVI) - Approach Paper Series - SAVI (DFID, 2016)
We are piloting a new approach to identifying and supporting our partners. This breaks with convention in many ways in order to improve impact. Our approach is summarized in the Introduction to SAVI’s way of working. We have broken our approach down into key components – depicted in the form of our ‘knowledge tree’ –...
Keywords: IMPORTANT

Towards an Alternative Development Management Paradigm? - Shutt, Cathy (Expertgruppen för biståndsanalys (EBA), 2016)
Demonstrating results has been a concern in international development cooperation ever since it was started and in recent years there has been an increased focus on achieving and reporting on “results”. Despite the fact that everyone involved in development cooperation wants to make a difference there has been a growing criticism from practitioners about the “results agenda” based on a concern that the approaches used are not fit for purpose. In the EBA-report, Cathy Shutt, at the University of Sussex, scrutinizes the recent critical debate about results based management, and the main arguments and motives behind the criticism. She shows that the debate is not only a matter of obsessive measurement and reporting of meaningless numbers for political accountability, but also a matter of problematic assumptions and how we think about development, evidence and learning. In the report, Shutt also explores what could be learned from those who are not just critiquing results based management approaches but also proposing alternatives. Are these new alternatives an answer to the criticism?
Keywords: IMPORTANT

An introduction to multi-stakeholder partnerships - Stibbe, Darian; Prescott, Dave (The Partnering Initiative, 2016)
This briefing document for the GPEDC High Level Meeting in November 2016 offers a definition of multi-stakeholder partnerships (MSPs) and shows how they are being used, where they have come from, and what the different sectors bring to the table. It provides an overview of the challenges the present, what they require from individuals and organisations, and how they get started. The report was written with the support of the PEP Initiative, and funded by the Netherlands Ministry of Foreign Affairs.

Program Cycle Road Map - USAID (2016)

40 Agile Methods in 40 Minutes - Smith, Craig (2015)

Multi-project programmes functions, forms and implications for evaluation and learning - Buffardi, Anne; Hearn, Simon (Methods Lab, 2015)
Multi-project programmes can serve different purposes. For instance, they may coordinate multiple implementing entities; standardise management and technical support; compare intervention approaches across different contexts; enhance leverage through joint action; or foster sustainability by building relationships among organisations. • At the same time, multi-project programmes are costly, potentially duplicate other mechanisms that fulfil similar functions, and can dilute focus and create confusion. • To guide decisions on what coordination, evaluation and learning mechanisms are needed, it is helpful to articulate the intended purpose of using a programme model. Identifying the purpose(s) can help staff determine what types of knowledge sharing strategies may be most useful to the programme, and how project and programme theories of change can be sequenced

Team of Teams: New Rules of Engagement for a Complex World - McChrystal, General Stanley; Silverman, David; Collins, Tantum; Fussell, Chris (Portfolio Penguin, 2015)
As commander of Joint Special Operations Command (JSOC), General Stanley McChrystal discarded a century of management wisdom and pivoted from a pursuit of mechanical efficiency to organic adaptability. In this book, he shows how any organization can make the same transition to act like a team of teams - where small groups combine the freedom to experiment with a relentless drive to share their experience.Drawing on a wealth of evidence from his military career and sources as diverse as hospital emergency rooms and NASA's space program, McChrystal frames the existential challenge facing today's organizations, and presents a compelling, effective solution.

Learning to Adapt: Exploring Knowledge, Information and Data for Adaptive Programmes and Policies - Workshop Summary Report - fhi360 (IDS, 2015)
Adaptive management is increasingly seen as critical capability for development programmes and policies that are more effective, efficient, relevant and sustainable. There is increasing recognition that such work requires significant changes to the organizational structures, management processes, accountability and performance cultures and indivi

Fostering Systems Change - Gopal, Srik; Kania, John (2015)
Five simple rules for foundations seeking to create lasting social change.

Try, learn, adapt, repeat: T/A Learn reflections - Alan (www.globalintegrity.org, 2015)
By Alan Hudson — November 16, 2015. I spent last week in Rio de Janeiro (tough assignment, I know), participating in the Transparency and Accountability Initiative’s third T/A Learn Annual Workshop. As the report of the second Annual Workshop, held...

Building capability by delivering results: Putting Problem-Driven Iterative Adaptation (PDIA) principles into practice - Andrews, Matt; Pritchett, Lant; Samji, Salimah; Woolcock, Michael (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Release the pressure on governance practitioners - de Weijer, Frauke; Hauck, Volker (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

The ethical limits of bungee research in ICTD - Dearden, Andrew; Tucker, William D. (2015 IEEE International Symposium on Technology and Society, 2015)
Research in ICTD is difficult because engineers with technical expertise are separated from the challenges that they are trying to address by large physical distances and significant social differences. To overcome these challenges, much research involves occasional short visits by external researchers to developing regions to investigate problems and generate ideas which are then developed back at the engineers' home base before further return visits for deployment and evaluation. This paper highlights the ethical limitations of this `bungee research', and reflects on our experiences in evolving more fruitful research practices. We argue that relying on bungee research as a primary model of research engagement is unethical, and we suggest some minimal conditions that are necessary, but not sufficient, for such visits to be ethically defensible in ICTD research.

Mind the gaps: What's missing in political economy analysis and why it matters - Hudson, David; Marquette, Heather (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

It's the politics! Can donors rise to the challenge? - Unsworth, Sue (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Theory of Change Thinking in Practice - van Es, Marjan; Guijt, Irene; Vogel, Isabel (2015)
Want to know better how your interventions can contribute to change? A Theory of Change (ToC) approach helps in deepening your understanding - and that of your partners - of how you collectively think change happens and what the effect will be of your intervention. Not only does it show what political, social, economic, and/or cultural factors are in play, it also clarifies your assumptions. Once a ToC has been developed, it can be used to continually reflect on it in ways that allow for adaptation and checking of assumptions of your intervention. This user friendly guideline helps you to use a Theory of Change approach. Theories of change are the ideas and beliefs people have – consciously or not – about why and how the world and people change. How people perceive and understand change and the world around them is infused by their underlying beliefs about life, human nature and society. They are deep drivers of people’s behaviour and of the choices they make. Social change processes are complex and characterised by non-linear feedback loops: our own actions interact with those of others and a myriad of influencing factors. This triggers reactions that cannot be foreseen and makes outcomes of change interventions unpredictable. Given these uncertainties, how can we plan strategically and sensibly? How can social change initiatives move forward in emerging change processes in a flexible way, while remaining focused on the goal? In this context of complexity, Hivos has found a theory of change (ToC) approach useful in guiding its strategic thinking and action, as well as its collaborative efforts with others. As it fosters critical questioning of all aspects of change interventions and supports adaptive planning and management in response to diverse and quickly changing contexts. It contributes to the quality and transparency of strategic thinking, and therefore to personal, organisational and social learning. This guide builds on the experiences of Hivos working with a ToC approach. It is a practical guide for Hivos staff in applying a Theory of Change approach, but is also very useful for others working on social change such as social entrepreneurs and innovators. This guide builds on the work of a ToC Learning Group initiated by Hivos and comprising of staff of the Centre for Development Innovation (CDI) of Wageningen University and Research Centre and of experts Iñigo Retolaza Eguren, Isabel Vogel and Irene Guijt. For current thinking and work on the use of Theory of Change thinking in complex change processes, see http://www.theoryofchange.nl

A Governance Practitioner’s Notebook: Alternative Ideas and Approaches - Whaites, Alan; Gonzalez, Eduardo; Fyson, Sara; Teskey, Graham (OECD, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Implementing Innovation: A User's Manual for Open Government Programs - Reboot Design (2015)
This guide draws from our experience around the world helping government reformers achieve real change. It is a practical resource for anyone working to implement an open government initiative.

Why Lean Enterprise Transformation is Hard - McClure, Dan (ThoughtWorks, 2015)

Systems Thinking For Social Change: A Practical Guide to Solving Complex Problems, Avoiding Unintended Consequences, and Achieving Lasting Results - Stroh, David Peter (Chelsea Green Publishing, 2015)
Donors, leaders of nonprofits, and public policy makers usually have the best of intentions to serve society and improve social conditions. But often their solutions fall far short of what they want to accomplish and what is truly needed. Moreover, the answers they propose and fund often produce the opposite of what they want over time. We end up with temporary shelters that increase homelessness, drug busts that increase drug-related crime, or food aid that increases starvation. How do these unintended consequences come about and how can we avoid them? By applying conventional thinking to complex social problems, we often perpetuate the very problems we try so hard to solve, but it is possible to think differently, and get different results. Systems Thinking for Social Change enables readers to contribute more effectively to society by helping them understand what systems thinking is and why it is so important in their work. It also gives concrete guidance on how to incorporate systems thinking in problem solving, decision making, and strategic planning without becoming a technical expert. Systems thinking leader David Stroh walks readers through techniques he has used to help people improve their efforts to end homelessness, improve public health, strengthen education, design a system for early childhood development, protect child welfare, develop rural economies, facilitate the reentry of formerly incarcerated people into society, resolve identity-based conflicts, and more. The result is a highly readable, effective guide to understanding systems and using that knowledge to get the results you want.

Navigating Complexity in International Development: Facilitating Sustainable Change at Scale - Burns, Danny; Worsley, Stuart (Practical Action Publishing, 2015)
Governments and organizations invest huge sums of money in development interventions to explicitly address poverty and its root causes. However, a high proportion of these do not work. This is because interventions are grounded in flawed assumptions about how change happens – change is rarely linear, yet development interventions are almost entirely based on linear planning models. Change is also characterized by unintended consequences, which are not predictable by planners and by power dynamics, which drive outcomes towards vested interests rather than real need. Development processes need to engage effectively with these sorts of complex system dynamics. This book provides a conceptual framework for this thinking, offers detail case studies of interventions which have been built on this philosophy and which demonstrate key facets of it. It articulates some clear methodological underpinnings for this work, and draws out the implications both for development, practice and practitioners.
Keywords: IMPORTANT

Barriers to Political Analysis in Aid Bureaucracies: From Principle to Practice in DFID and the World Bank - Yanguas, Pablo; Hulme, David (World Development, 2015)
Politics has become a central concern in development discourse, and yet the use of political analysis as a means for greater aid effectiveness remains limited and contested within development agencies. This article uses qualitative data from two governance “leaders” – the United Kingdom Department for International Development and the World Bank – to analyze the administrative hurdles facing the institutionalization of political analysis in aid bureaucracies. We find that programing, management, and training practices across headquarters and country offices remain largely untouched by a political analysis agenda which suffers from its identification with a small cross-national network of governance professionals.
Keywords: DFID; United Kingdom; World Bank; aid effectiveness; foreign aid; political economy analysis

Beyond the toolkit: supporting peace processes in Asia - Denney, Lisa; Barron, Patrick (The Asia Foundation, 2015)

Operationalizing the Science of Delivery Agenda to Enhance Development Results - Gonzalez Asis, Maria; Woolcock, Michael (Washington, DC: World Bank, 2015)
The clear development gains achieved in recent decades should not deflect attention from the scale and type of challenges that remain. The strategies largely responsible for these initial gains have been technical reforms promoting economic growth and logistical systems supplying basic inputs. Today, strategies are needed that focus on enhancing the quality of implementation— for example, ensuring learning and not just building schools and enrolling students. This concern now spans numerous domains of professional practice (especially health) and has entered World Bank discussions framed as the “science of delivery.” At the World Bank, the Global Delivery Initiative (GDI) is an operational manifestation and extension of these ideas. To date, the GDI has prepared a number of different case studies across numerous sectors on ways in which innovative teams solve particular problems during project implementation. On the basis of the initial case studies, the authors outline five key principles of how high-quality implementation occurs and invite others to add to this growing storehouse of knowledge. Specifically, task teams are encouraged to develop “live” case studies by and for their staff, documenting how, in real time, implementation challenges are being met. Projects must “learn” more rapidly and systematically how to solve the myriad range of complex implementation challenges they inevitably encounter, since most of these (by definition) cannot be anticipated ex ante. Delivery challenges of this kind will only intensify in the coming years as citizens demand effective responses to ever-more complex—and contentious—policy domains, such as justice, regulation, and taxation.

Embracing Complexity: Strategic Perspectives for an Age of Turbulence - Boulton, Jean G.; Allen, Peter M.; Bowman, Cliff (Oxford University Press, 2015)
The book describes what it means to say the world is complex and explores what that means for managers, policy makers and individuals. The first part of the book is about the theory and ideas of complexity. This is explained in a way that is thorough but not mathematical. It compares differing approaches, and also provides a historical perspective, showing how such thinking has been around since the beginning of civilisation. It emphasises the difference between a complexity worldview and the dominant mechanical worldview that underpins much of current management practice. It defines the complexity worldview as recognising the world is interconnected, shaped by history and the particularities of context. The comparison of the differing approaches to modelling complexity is unique in its depth and accessibility. The second part of the book uses this lens of complexity to explore issues in the fields of management, strategy, economics, and international development. It also explores how to facilitate others to recognise the implications of adopting a complex rather than a mechanical worldview and suggests methods of research to explore systemic, path-dependent emergent aspects of situations. The authors of this book span both science and management, academia and practice, thus the explanations of science are authoritative and yet the examples of changing how you live and work in the world are real and accessible. The aim of the book is to bring alive what complexity is all about and to illustrate the importance of loosening the grip of a modernist worldview with its hope for prediction, certainty and control.

Design for Sustainability: Countering the Drivers of Unsustainability in Development Projects - Meyer, Isabel; Marais, Mario Alphonso (The Journal of Community Informatics, 2015)
Development projects aim to make a difference in communities. Funders often require that the intervention needs to last, or that it needs to effect change that will last, over an extended period of time. In short, a sustainable difference needs to be made and this is an important measure of success. However, there are inherent drivers in the combined system of donors and beneficiaries that counter sustainability. This article explores these drivers, and identifies project design elements that need to be in place in order to promote sustainability by countering the drivers. This approach is applied to an education project, and implications for ICT4D projects are developed.
Keywords: Development; Project design; Systems Approaches; sustainability

Webinar: Operationalizing Adaptive Management: What it takes. Why it matters. - Mercy Corps (Mercy Corps, 2015)
Development actors increasingly agree that managing programs adaptively – especially complex interventions – can improve their effectiveness. A growing body of evidence supports this claim. But what does adaptive management look like in practice? What does it require of managers and donors to make happen? How can we reconfigure incentives and success metrics to support adaptation, while remaining compliant?

Black Box Thinking: The Surprising Truth About Success - Syed, Matthew (Hachette UK, 2015)
The Sunday Times No.1 Bestseller From the Bestselling Author of BounceWhat links the Mercedes Formula One team with Google?What links Team Sky and the aviation industry?What connects James Dyson and David Beckham?They are all Black Box Thinkers.Black Box Thinking is a new approach to high performance, a means of finding an edge in a complex and fast-changing world. It is not just about sport, but has powerful implications for business and politics, as well as for parents and students. In other words, all of us.Drawing on a dizzying array of case studies and real-world examples, together with cutting-edge research on marginal gains, creativity and grit, Matthew Syed tells the inside story of how success really happens - and how we cannot grow unless we are prepared to learn from our mistakes.
Google-Books-ID: f1eNBQAAQBAJ
Keywords: Psychology; Sports & Recreation / Sports Psychology; Strategic Planning

Strategy Testing: An innovative approach to monitoring highly flexible aid programs - Ladner, Debra (The Asia Foundation, 2015)
The international development community has increasingly embraced the idea that finding durable solutions to complex development problems requires new ways of working that move beyond industry norms. This paper makes an important contribution to the current debate by outlining an innovative monitoring system called Strategy Testing (ST). This is the third paper in the Working Politically in Practice paper series, launched together with the Australian Department of Foreign Affairs and Trade.

SAVI Approach Paper 1: Core Values - SAVI (London, 2015)
Governance reform is about government and citizens working together in more responsive, inclusive and accountable ways for the benefit of citizens. More responsive, inclusive and accountable attitudes and behaviour on the part of government and non-government stakeholders are the critical factors which lead to meaningful reform processes, and replicate and sustain reforms beyond the lifetime...

SAVI Approach Paper 10: Engaging State Governments - SAVI (DFID, 2015)
SAVI as a programme does not directly work with state governments – but we work in close conjunction with sister programmes who are supporting state governments on governance and sector reforms. SAVI supports non-government and SHoA partners to play their part in promoting more responsive, inclusive and accountable state governance delivering better services for citizens....

SAVI Approach Paper 2: Programme Design - SAVI (DFID, 2015)
SAVI supports citizen engagement in governance through a facilitated partnership approach, in contrast to the usual approach of grants to civil society organisations (CSOs). The overall aim is to facilitate and support working relationships and processes of reform that are home-grown, self-sustaining and, after initial engagement, not dependent on external support. Our way of working...

SAVI Approach Paper 3: Theory of Change - SAVI (DFID, 2015)
SAVI’s theory of change is a simple, practical guide that staff and partners use to plan and to monitor change – as well as to reflect on and enhance their own effectiveness. It sets out broad stages of attitude and behaviour change over time to facilitate effective citizen engagement in governance processes, systems and structures....

SAVI Approach Paper 4: Thinking and Working Politically - Supporting partners and staff through a participatory apporach to political economy analysis - SAVI (DFID, 2015)
Thinking and acting politically is central to the SAVI programme. We support staff and partners to analyse the power relations that shape change in their state, and to use this knowledge to inform their decision-making. This includes decisions made by SAVI state teams relating to the issues and partners they engage with and support, and...

SAVI Approach Paper 5: Defining and Measuring Results - SAVI (DFID, 2015)
SAVI aims to facilitate replicable and sustainable processes of citizen engagement in governance. The programme in each state is locally defined, flexible and adaptive, and results are not predictable in advance. Standardised monitoring tools are not applicable, and consequently we have evolved our tools and frameworks during the programme through processes of learning by doing....

SAVI Approach Paper 6: Engaging Civil Society - SAVI (DFID, 2015)
SAVI state teams provide support to CS groups to become more effective agents of citizens’ voice and public accountability, through a variety of mutually reinforcing interventions. These include: hands-on support to demonstration civil society Advocacy Partnerships (APs) facilitating working partnerships between civil society APs, SHoAs, and the media brokering working relationships between all of these...

SAVI Approach Paper 7: Promoting Gender Equality and Social Inclusion - SAVI (DFID, 2015)
We promote attention to gender equality and social inclusion in all of our engagement with CS groups, the media and SHoAs, and in all of the issues and processes they work on. In all the states we work in, we also support partners to focus on some issues and form some partnerships and networks which...

SAVI Approach Paper 8: Engaging the Media - SAVI (DFID, 2015)
The overall aim of SAVI engagement with the media is for media representation of citizens’ interests to become normal, and play its part in helping state governments to be more responsive, inclusive and accountable to their citizens. Media partners – individual media personnel and selected media houses – are supported to be more effective agents...

SAVI Approach Paper 9: Engaging State Houses of Assembly - SAVI (DFID, 2015)
The overall aim of SAVI engagement with SHoAs is to promote lasting reforms that are not dependent on external funding and which promote an increasingly more responsive and accountable relationship between Nigerian state governments and their citizens. SHoAs are supported to be more effective agents of citizen voice and public accountability, demanding better performance from...

Theories of Change: time for a radical approach to learning in development - Valters, Craig (ODI, 2015)
The Theory of Change approach demands a radical shift towards more and better learning in development thinking and practice, creating a productive and much-needed space for critical reflection.

Engineering Complex Scaled Up Innovations in the Humanitarian and Development Sector - McClure, Dan; Gray, Ian (ThoughtWorks, 2015)

What Startups Can Learn from General McChrystal about Combining Strategy and Execution - Pisoni, Adam (First Round, 2015)
Yammer Co-founder Adam Pisoni speaks with General Stanley McChrystal about the lessons technology companies might take away from his new book Team of Teams.

Guidelines for writing a case study on implementation (Book Project: Smart Implementation in Governance) - Kirsch, Renate (GIZ GmbH, 2015)

Dialogic Organization Development: The Theory and Practice of Transformational Change - Bushe, Gervase R. (EDS Publications Ltd., 2015)
Dialogic Organization Development is a compelling alternative to the classical action research approach to planned change. Organizations are seen as fluid,socially constructed realities that are continuously created through conversations and images change happens when those conversations and images change. Leaders and consultants can help foster, support, or accelerate the emergence of transformational possibilities by encouraging disruptions to taken-for-granted ways of thinking and acting and the use of generative images to stimulate new organizational conversations and narratives. Dialogic OD is a different mindset, but it s also the previously unrecognized underpinning of such diverse change methods as Appreciative Inquiry, the Art of Convening, Future Search, and many more.

The Politics of Evidence and Results in International Development: Playing the Game to Change the Rules? - Eyben, Rosalind; Guijt, Irene; Roche, Chris; Shutt, Cathy (Practical Action Publishing, 2015)
Understanding and demonstrating the effectiveness of efforts to improve the lives of those living in poverty is an essential part of international development practice. But who decides what counts as good or credible evidence? Can the drive to measure results do justice to and promote transformational change change that challenges the power relations that produce and reproduce inequality, injustice and the non-fulfillment of human rights? The Politics of Evidence in International Development provides a critical examination of the results agenda, with practical strategies for rendering it more helpful in supporting transformative development. The book deconstructs the origins and concepts of the results and evidence agendas employed in international development. It describes with concrete examples the current effects and consequences of the agenda, and goes on to outline a range of strategies used by individuals and organizations to resist, adapt or comply with the useful and problematic demands for results-oriented measurement and evidence of value for money."

Inclusive rigour for complexity - Chambers, Robert (Journal of Development Effectiveness, 2015)
Rigour can be reductionist or inclusive. To learn about and understand conditions of complexity, emergence, nonlinearity and unpredictability, the inclusive rigour of mixed methods has been a step in the right direction. From analysis of mixed methods and participatory approaches and methods, this article postulates canons for inclusive rigour for research and evaluation for complexity: eclectic methodological pluralism; improvisation and innovation; adaptive iteration; triangulation; plural perspectives; optimal ignorance and appropriate imprecision; and being open, alert and inquisitive. Inclusive rigour is inherent in participatory methods and approaches, visualisations, group-visual synergy, the democracy of the ground and participatory statistics. Transparent reflexivity, personal behaviour and attitudes, and good facilitation are fundamental. Fully inclusive rigour for complexity demands many personal, institutional and professional revolutions.
Keywords: Evaluation; Mixed methods; Participatory methodologies; Research; paradigm; rigour

Using Data to Influence Government Decisions. Opportunities and Challenges for User-Centered Design to Improve Governance Data Impact - Reboot (Reboot & OSF, 2015)

Managing the Journey to Scale Up Innovation in the Humanitarian and Development Sector - McClure, Dan; Gray, Ian (ThoughtWorks, 2015)

Managing Complexity: Adaptive Management at Mercy Corps - Mercy Corps (2015)
Managing Complexity: Adaptive management at Mercy Corps

Systems change: A guide to what it is and how to do it - Ellen Harries; Rachel Wharton; Rob Abercrombie (NPC, 2015)
Systems change has been attracting the attention of those in the social sector who want to deal with the root causes of problems, but, despite the buzz, much of what is written is abstract in tone. With the support of LankellyChase Foundation we have produced this guide to plug a gap in the systems change literature—providing accessible material and recommendations for action. Systems change has been attracting the attention of a range of progressive charities, funders and practitioners who are interested in dealing with the root causes of social problems. But while there is a buzz about a subject relatively new to the social sector, it is easy to feel frustrated by the literature—much of what is written is abstract in tone and there are few examples of success. We have produced this paper to address this problem and offer accessible material and recommendations for action. This systems change guide: Clarifies what is meant by systems and systems change Describes the main perspectives on systems change Outlines good practice for systems change Identifies what is and is not agreed upon by experts in the field Provides recommendations for charities, funders and the public sector on how to act systemically. We hope this presents a manageable introduction to the systems change field, especially for those new to it, and also guides those interested in acting systemically to improve the lives of people in need. Our conclusion is that although it may not be as novel as some claim, there is a good deal of value in a systems change approach and it offers a welcome reminder of what effective action looks like when it comes to the pursuit of social change.

DFID’s approach to delivering impact - ICAI (Independent Commission for Aid Impact (ICAI), 2015)
UK aid, at its best, makes a real and positive difference to the lives and livelihoods of poor people around the world. Ensuring the best possible performance across a large and multifaceted aid programme is, however, a complex management challenge. This report reviews ICAI’s previous 44 reports and looks at how well DFID ensures positive, long-term, transformative impact across its work.

A flowering of approaches to complexity and development? - Thorpe, Ian (KM on a dollar a day, 2015)
We are an important juncture in development at the moment with the Sustainable Development Goals due to be finalized later this year, and with discussion now turning full swing into what needs to h…

Navigating by Judgment: Organizational Structure, Autonomy, and Country Context in Delivering Foreign Aid - Honig, Daniel (Harvard University, Graduate School of Arts & Sciences, 2015)
This dissertation examines when initiatives by International Development Organizations (IDOs) are more, and less, successful. The core argument is that allowing field-level agents to drive initiatives – what I call organizational Navigation by Judgment – will often be the most effective way to deliver aid. This inverts what a classical application of the principal agent model – the workhorse of studies of public management and bureaucracy – would predict, with better performance resulting from less control. In the delivery of foreign aid the costs of monitoring to the principal are often overshadowed by the deleterious effects of the monitoring itself. The core of the argument is that development implementation requires soft information, tacit knowledge, and flexibility that are crowded out by tight controls or an organizational navigation strategy focused on short term measurement and targets. As a result there are increasing returns to Navigation by Judgment in environments that are uncertain or difficult to understand from the outside and tasks where outputs are difficult to observe and/or poorly correlated with long term intervention goals. Insecure political authorizing environments which constrain the autonomy of IDOs prevent these organizations from Navigating by Judgment in situations where this is the best strategy. Empirically, this dissertation examines a cross-IDO dataset of projects (including over 14,000 projects over 50 years over 9 organizations), which I have assembled. It also examines eight cases of development interventions in Liberia and South Africa. These cases are matched pairs comparing the performance and navigation strategies of the US Agency for International Development (a low autonomy IDO) and the UK’s Department for International Development (a higher autonomy IDO) in capacity building and health sector interventions.
Keywords: IMPORTANT

Scrum For Dummies - Layton, Mark C. (John Wiley & Sons, 2015)
Practice an agile form of management to stop wasting time and money Scrum For Dummies is an easy to use guide to managing the tricky transition from a traditional project management methodology to the new and most popular agile framework. As the most efficient, successful methodology for team project management, Scrum relies on transparency, flexibility, and fluidity to deliver a final product that fulfills the needs of all stakeholders. Written in easy–to–read Dummies style, this book walks you through the core principles of Scrum and provides a roadmap for tangible implementation. The vast majority of projects go over budget, and billions of dollars are wasted every year on overruns. Put a stop to this wasteful leakage by switching to a management style that keeps all participants informed, up–to–date, and accountable. Authored by a Certified Scrum Trainer, Mark Layton, Scrum For Dummies covers the key ideas and processes behind Scrum methodologies, and presents the inner workings of the plan in an engaging and accessible format. Topics include: The Scrum values, roles, artifacts, and activities that make up the principle of this methodology When and how best to use Scrum The differences between Scrum and other agile methodologies Using Scrum for IT, finance, construction, health care, and more The book also delves into the everyday use of Scrum, and how it can help you achieve your own personal goals outside of work. There′s a reason why scrum is quickly becoming the standard approach to project management it works! If you want to stop wasting time and start producing more effectively, Scrum For Dummies is the guide that will get you there.

Why Greatness Cannot Be Planned: The Myth of the Objective - Stanley, Kenneth O.; Lehman, Joel (Springer, 2015)
Why does modern life revolve around objectives? From how science is funded, to improving how children are educated – and nearly everything in-between – our society has become obsessed with a seductive illusion: that greatness results from doggedly measuring improvement in the relentless pursuit of an ambitious goal. In Why Greatness Cannot Be Planned, Stanley and Lehman begin with a surprising scientific discovery in artificial intelligence that leads ultimately to the conclusion that the objective obsession has gone too far. They make the case that great achievement can't be bottled up into mechanical metrics; that innovation is not driven by narrowly focused heroic effort; and that we would be wiser (and the outcomes better) if instead we whole-heartedly embraced serendipitous discovery and playful creativity.Controversial at its heart, yet refreshingly provocative, this book challenges readers to consider life without a destination and discovery without a compass.

Investment Climate Reform: Doing it Differently - Manuel, Clare (DFID-LASER Programme, 2015)
LASER synthesis papers aim to help donors and other stakeholders better understand why and how to approach investment climate reform programming differently. The papers reflect emerging best practice and lessons learnt on what works and what does not work in doing development differently. The papers have been peer-reviewed by experts in the field including senior advisers at DFID, World Bank, IFC and the Donor Committee for Enterprise Development (amongst others). First synthesis paper - Investment climate reform: doing it differently June 2015 Drawing on our experience in taking a problem-focused approach to investment climate reform, we discuss in this peer-reviewed paper emerging lessons and reflections on what works, both in recent literature and in practical experience.

Measuring Impact. Making Use of the Portfolio: Organizational Learning at USAID - Peabody, Shawn (USAID, 2015)
This technical analysis explores previous and ongoing social learning efforts, best practices, challenges, and lessons in USAID as a foundation for improving the implementation and design of the Agency’s forestry and biodiversity programs. This analysis is particularly relevant as the Bureau of Economic Growth, Education and the Environment’s Office of Forestry and Biodiversity (E3/FAB) begins to develop a Cross-Mission Learning Program under the Measuring Impact initiative, a five-year activity to promote the adoption of best practices in the USAID program cycle among Missions using biodiversity funds. The findings reported in this document can help inform the overall design and structure of the Learning Program and provide insight into possible challenges and best practices.

Experiential Learning: Experience as the Source of Learning and Development - Kolb, David (Pearson FT Press, 2015)

Supporting Learning? Exploring the relationship between grantee learning and grantmaking practice in the transparency and accountability sector - Ross, Jenny (INTRAC, 2015)
Learning is fundamental to work on transparency and accountability in complex environments. But how can funding practices best support learning?

Scaling: Innovations Missing Middle - McClure, Dan; Gray, Ian (ThoughtWorks, 2015)

Thinking and Working Politically: Professional Development Reading Pack - Booth, David (GSDRC Applied Knowledge services, 2015)

Effective Governance. Strategy for Australia’s aid investments - DFAT (Department of Foreign Affairs and Trade, Australian Government, 2015)

Adapting development: improving services to the poor - Wild, Leni; Booth, David; Cummings, Clare; Foresti, Marta; Wales, Joseph (ODI, 2015)
On current trends, it will take decades or longer to bring basic services to the world’s most disadvantaged people. Meeting this challenge means recognising the political conditions that enable or obstruct development progress - a radical departure from the approach of the Millennium Development Goals.
Keywords: Practice

Meant to Keep Malaria Out, Mosquito Nets Are Used to Haul Fish In - Gettleman, Jeffrey (The New York Times, 2015)
Nets like his are widely considered a magic bullet against malaria — one of the cheapest and most effective ways to stop a disease that kills at least half a million Africans each year. But Mr. Ndefi and countless others are not using their mosquito nets as global health experts have intended. Nobody in his hut, including his seven children, sleeps under a net at night. Instead, Mr. Ndefi has taken his family’s supply of anti-malaria nets and sewn them together into a gigantic sieve that he uses to drag the bottom of the swamp ponds, sweeping up all sorts of life: baby catfish, banded tilapia, tiny mouthbrooders, orange fish eggs, water bugs and the occasional green frog

(Breaking) The Iron Triangle of Evaluation - Reynolds, Martin (IDS Bulletin, 2015)
Keywords: Evaluation; impact

The limits of agile - can we apply it to policy making? - Ollerhead, Lisa (2015)
Bringing new policy tools and techniques to the UK Government

Thoughts on the use of hypotheses in adaptive management - Sparkman, Timothy (BEAM Exchange, 2015)
New insights, opinions and perspectives on market systems development, from experts and practitioners.

Management not models: adaptability, responsiveness, and a few lessons from football - Maclay, Christopher (Development in Practice, 2015)
Despite a swathe of critiques of logframes and other blueprint approaches to development over the last 30 years, most aid infrastructure continues to concentrate on the design and subsequent implementation of closed models. This article does not propose an alternative to blueprints, but challenges the inflexibility of their implementation, which is inadequate given the complex nature of social change. It proposes a supplementary management and learning approach which enables implementers to be dynamic, adaptive, and responsive to problems and opportunities. Emphasising the role of donors, the paper presents a case study of one donor-led programme in Bangladesh doing just this.
Publisher: Routledge _eprint: https://doi.org/10.1080/09614524.2015.983460

Agile Glossary and Terminology - Agile Alliance (Agile Alliance, 2015)
Learn the unique terminology used in Agile development from the experts at Agile Alliance.

Subway Map to Agile Practices - Agile Alliance (Agile Alliance, 2015)
AGILE 101

Doing Problem Driven Work - Andrews, Matt; Pritchett, Lant; Woolcock, Michael (Harvard University, 2015)
Keywords: IMPORTANT

Digital lives in Ghana, Kenya and Uganda - Bailur, Savita; Donner, Jonathan; Locke, Chris; Schoemaker, Emrys; Smart, Charlotte (Caribou Digital, 2015)
Keywords: IMPORTANT

Institutional Change, Political Economy, and State Capabilities : Learning from Edo State, Nigeria - Bain, Katherine; Porter, Doug; Watts, Michael (World Bank, 2015)
This paper is one of a series aimed at deepening the World Bank’s capacity to follow through on commitments made in response to the World Development Report (WDR) 2011, which gave renewed prominence to the nexus between conflict, security, and development. Nigeria is a remarkable illustration of how deeply intractable the cycle of poverty, conflict, and fragility can become when tied to the ferocious battles associated with the political economy of oil. This paper places the corpus of analytic and programmatic work concerning institutional reform in conversation with a now substantial body of work on resource politics and most especially, the debate over the politico-institutional character (sometimes called political settlements or pacting arrangements associated with the order of power) and reform landscape of the petro-state. Recent institution reform policy writing appears to have little to say about the political and economic conditions in which crises and institutional disjunctures may authorize, and thereby enable, agents to embark on institutional reforms. The authors focus on Edo state for two reasons. First, it does not on its face appear to be an obvious location in which to explore a reform experience, given its entanglement in the Niger Delta conflict and the maladies typically associated with state fragility. Second, Edo is of interest also because of the changes that its experience is contributing to the World Bank country team’s effort to engage operationally across all its instruments with the political economy of institutional reform in Nigeria, its largest client country in Africa.

Introduction - Towards Systemic Approaches to Evaluation and Impact - Befani, Barbara; Ramalingam, Ben; Stern, Elliot (IDS Bulletin, 2015)

Still watering white elephants? The blueprint versus process debate thirty years on - Booth, David (Perspectives on politics, production and public administration in Africa: essays in honour of Ole Therkildsen, 2015)
OCLC: 913447024

Impact assessment and the quest for the Holy Grail - Bymolt, Roger (KIT Royal Tropical Institute, 2015)

Producer-led value chain analysis: The missing link in value chain development - Ghore, Yogesh (Coady, 2015)
Introduction and rationale The concept of a value chain is increasingly being applied in the design and implementation of development programs aimed at poverty reduction. As an analytical tool, it provides a useful framework for understanding key activities, relationships, and mechanisms that allow producers, processors, buyers, sellers, and consumers—separated by time and space—to gradually add value to products and services as they pass from one link of the chain to another, making it a “value chain” (UNIDO, 2009). While it has been popular in the private sector ever since it was conceptualized by Michael Porter in the 1980s, more recently various donors and governments have shown interest in its use and have applied it to a range of development interventions, particularly in the area of sector development, livelihoods promotion, small and medium enterprise (SME) development, and rural and economic development. Academics and development organizations have designed numerous instruments for value chain analysis (VCA) and implementation. Beginning in the early 2000s, international organizations and donor agencies have sponsored the development of these tools, including the United States Agency for International Development (USAID) Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ), the World Bank, the International Finance Corporation (IFC), and the International Labour Organization (ILO). These guides and tools have been used in many development programs to address organizational, donor and local and regional priorities for development. While VCA guides and tools are important in understanding markets and relationships among key stakeholders, a recent comparative review of popularly used guides by Donovan et al. (2013) suggests that most of these guides are designed to be implemented independently of the local context and do not sufficiently focus on mutual learning, whether related to tool design or to the outcomes and impacts of the designed project activities. VCA is often conducted by external experts and the knowledge generated in the process is often confined to reports. Without the capacity building and effective participation of women and men producers—smallholder farmers who hold critical knowledge about the local context—an important link is missing in the entire process of VCA. The insufficient attention to the human, social, and other contextual factors undermines the full potential of the value chain systems approach, not only for economic outcomes, but for the long term sustainability of the intended benefits. So what are the ways to effectively engage producers in the community in the VCA? The producer-led process described here tries to address this basic question. It introduces simplified tools and an approach that ensures farmer participation in data collection, analysis, and identification of opportunities and constraints, and design of value chain interventions. This participation requires: a) an environment in which they feel comfortable to share their knowledge and insights, which is often not the case when extractive surveys and questionnaires are administered to collect information; and b) the use of simple and participatory tools that will allow them to provide inputs into the process of VCA and also help them to understand complex value chain systems and use this understanding for making livelihood decisions. The key steps and tools described are aimed at empowering the women and men farmers to make informed decisions about their own enterprises and how they relate to the value chain, thereby directly contributing to, and influencing, the overall process of value chain development. The process of VCA involving these steps and tools was developed at Coady Institute and first tested with Oxfam Canada and its local partners in Ethiopia in August 2012.

Cooperation Management for Practitioners: Managing Social Change With Capacity Works - GIZ (Springer Gabler, 2015)
OCLC: 893897509

Enabling citizen-driven improvement of public services. Leveraging Technology to Strengthen Accountability in Nigerian Healthcare - ICT4SA (World Bank and Reboot, 2015)
Effective public service delivery begins with knowing whether the services offered are working as intended. We launched a system to enable citizen input on the delivery of public services.

The field guide to human-centered design: design kit - IDEO (IDEO, 2015)
Keywords: Design; IMPORTANT; Methode

Improving development aid design and evaluation: Plan for sailboats, not trains - Kleinfeld, Rachel (Carnegie Endowment for International Peace, 2015)
How do reforms that require political engagement differ from traditional technical reforms? Why is political engagement different, and what are the implications for design and evaluation? How should development programmes that engage politics be designed? And how can those who fund or implement such programmes evaluate whether their efforts are contributing to reform? This report …
Keywords: IMPORTANT

Before the Backlash, Let’s Redefine User-Centered Design - Lee, Panthea (Stanford Social Innovation Review, 2015)
We must better understand user-centered design’s limitations—not just its strengths—in the context of international development. And we must adapt it from its original uses designing commercial products to solving for social good.

ICT4D and Sustainability - Marais, Mario (The International Encyclopedia of Digital Communication and Society, 2015)

The Promise of Lean Experimentation - Murray, Peter; Ma, Steve (Stanford Social Innovation Review, 2015)
By adopting a model from business, nonprofit organizations can launch, test, and implement new programs and services more efficiently. Includes magazine extras.
Keywords: IMPORTANT

Adaptive Management: Responding to the evolving needs of PRIME's complex systems - Picon, Diana; Wild, Lorenz (Mercy Corps, 2015)

Introduction to SAVI's way of working - State Accountability and Voice Initiative (SAVI) - SAVI (DFID, 2015)
We are piloting a new approach to identifying and supporting our partners. This breaks with convention in many ways in order to improve impact. SAVI Approach Papers summarise key aspects of SAVI’s way of working. They explain what we do, and why – and link to relevant tools and frameworks. Our approach is summarized in...
Keywords: Practice

The 2015 State of Scrum Report: How the world is applying the most popular Agile approach to projects - Scrum Alliance (Scrum Alliance, 2015)

USAID/Colombia Introduces Political Economy Analysis to Better Adapt Programming to Local Contexts - Sharp, Preston (USAID, 2015)

Chaos Report 2015 - Standish Group (Standish Group, 2015)

The Operational Guide - for the making markets work for the poor (M4P) approach (Second Edition) - The Springfield Centre (SDC & DFID, 2015)
In 2008, SDC and DFID published three documents aimed at improving the understanding and use of the Making Markets Work for the Poor (M4P) approach: the M4P Synthesis, M4P Perspectives and M4P Operational Guide. Since then the field has grown, diversified and, importantly, learned much more. A second edition was commissioned to capture that learning, maintain the momentum and realise the ambition that development can still 'do better'. The second edition provides an accessible resource to help practitioners put the market systems development approach into practice. It explains the key principles and frameworks which guide effective intervention in – and development of – market systems. It addresses common challenges with examples of good practice based on practitioner experience. Who is it for? The Operational Guide is for people whose job entails trying to make market systems work better for poor women and men. These people include: Individuals currently involved in funding or implementing the approach. Development agencies wishing to incorporate market systems thinking and practice in their work. National stakeholders that wish to play a more strategic and catalytic role within market systems. What is new? Application, application, application! Whilst the key principles and frameworks will be familiar, the advice on their operational application – from start to finish – has been significantly bolstered Enhanced guidance on facilitation. Greater emphasis on what constitutes good facilitation practice, building on a wealth of practitioner experience More real-life examples. The Operational Guide is laced with examples from programmes past and present, working in a diverse array of systems Peer learning focus. Direct insights from practitioners, highlighting 'bumps in the road' and how to avoid them. The Guide aims to provide an accessible operational resource to help practitioners put the market systems development approach into practice. It explains the key principles and frameworks which guide the process of effective intervention in – and development of – market systems, addressing common challenges with examples of good practice based on practitioner experience. HOW SHOULD IT BE USED? The Guide explores, sequentially, the key elements of the implementation process: strategy, diagnosis, vision, intervention, measurement and management. It is not intended to be read from cover to cover; readers can go directly to the chapter most relevant to their needs without having read preceding chapters. However each chapter does build upon the preceding one and may refer to other chapters. THE GUIDE IS STRUCTURED AS FOLLOWS: INTRODUCTION Overview of the objectives, structure and format of the Guide CONTEXT A reminder of what market systems development means 1. STRATEGY Core principles and framework for setting programme strategy 2. DIAGNOSIS Core principles and framework for diagnosing system constraints 3. VISION Core principles and frameworks for defining and planning intervention 4. INTERVENTION Core principles and framework to guide effective intervention 5. MEASUREMENT Core principles and framework for measuring results 6. MANAGEMENT Key considerations in managing market systems development programmes GLOSSARY Definition of key terms used in market systems development

Collaborate Learn Adapt - Case Competition - USAID (USAID Learning Lab, 2015)

Developing an effective adaptive monitoring network to support integrated coastal management in a multiuser nature reserve - Vugteveen, Pim; van Katwijk, Marieke M.; Rouwette, Etiënne; Lenders, H. J. Rob; Hanssen, Lucien (Ecology and Society, 2015)
ABSTRACT. We elaborate the necessary conceptual and strategic elements for developing an effective adaptive monitoring network to support Integrated Coastal Management (ICM) in a multiuser nature reserve in the Dutch Wadden Sea Region. We discuss quality criteria and enabling actions essential to accomplish and sustain monitoring excellence to support ICM. The Wadden Sea Long-Term Ecosystem Research project (WaLTER) was initiated to develop an adaptive monitoring network and online data portal to better understand and support ICM in the Dutch Wadden Sea Region. Our comprehensive approach integrates ecological and socioeconomic data and links research-driven and policy-driven monitoring for system analysis using indicators of pressures, state, benefits, and responses. The approach and concepts we elaborated are transferable to other coastal regions to accomplish ICM in complex social-ecological systems in which scientists, multisectoral stakeholders, resource managers, and governmental representatives seek to balance long-term ecological, economic, and social objectives within natural limits.
Keywords: IMPORTANT

MSP Guide - Wageningen University (MSP Guide, 2015)
The MSP Guide Designing and facilitating effective multi-stakeholder partnerships Get started Download now The MSP Guide(EN, FR, ES) Explore the rationale, principles and process of designing and facilitating effective MSPs Get it now The MSP Tool Guide Detailed descriptions of 60 tried-and-tested tools to facilitate multi-stakeholder partnerships Get it now Reflection Methods: Practical Guide Proven…

Learning and Results in World Bank Operations: Toward a New Learning Strategy - World Bank (IEG , The World Bank, 2015)
This report is the second in a program of evaluations that the Independent Evaluation Group (IEG) is conducting on the learning that takes place through World Bank projects. Learning and knowledge are treated as parts of a whole and are presumed to be mutually reinforcing.
Keywords: IMPORTANT

World Development Report 2015: Mind, Society, and Behavior - World Bank (The World Bank, 2015)
Development economics and policy are due for a redesign. In the past few decades, research from across the natural and social sciences has provided stunning insight into the way people think and make decisions. Whereas the first generation of development policy was based on the assumption that humans make decisions deliberatively and independently, and on the basis of consistent and self-interested preferences, recent research shows that decision making rarely proceeds this way. People think automatically: when deciding, they usually draw on what comes to mind effortlessly. People also think socially: social norms guide much of behavior, and many people prefer to cooperate as long as others are doing their share. And people think with mental models: what they perceive and how they interpret it depend on concepts and worldviews drawn from their societies and from shared histories.The World Development Report 2015 offers a concrete look at how these insights apply to development policy. It shows how a richer view of human behavior can help achieve development goals in many areas, including early childhood development, household finance, productivity, health, and climate change. It also shows how a more subtle view of human behavior provides new tools for interventions. Making even minor adjustments to a decision-making context, designing interventions based on an understanding of social preferences, and exposing individuals to new experiences and ways of thinking may enable people to improve their lives.The Report opens exciting new avenues for development work. It shows that poverty is not simply a state of material deprivation, but also a “tax” on cognitive resources that affects the quality of decision making. It emphasizes that all humans, including experts and policy makers, are subject to psychological and social influences on thinking, and that development organizations could benefit from procedures to improve their own deliberations and decision making. It demonstrates the need for more discovery, learning, and adaptation in policy design and implementation. The new approach to development economics has immense promise. Its scope of application is vast. This Report introduces an important new agenda for the development community.

Strategic Framework for mainstreaming citizen engagemente in World Bank Group operations - World Bank (The World Bank, 2014)

Virtuous cycles of learning: Using formative, embedded, and diagnostic developmental assessments in a large-scale leadership program - Stein, Z.; Dawson, Theo; Van Rossum, Zachary; Rothaizer, Joel; Hill, S. (Journal of Integral Theory and Practice, 2014)
This article presents preliminary results from a series of ongoing action-research projects involving the use of embedded diagnostic developmental assessments (called LectaTests™) in leadership education contexts. These findings are presented to support a particular metatheoretical approach to learning and education in which embedded assessments form a crucial part of ongoing virtuous cycles of action, feedback, support, and learning. We present two types of evidence. First, we compare developmental growth across eight program evaluations in which LectaTests were and were not embedded. Second, we examine how embedding LectaTests in a large-scale leadership development program affected the growth of managers and their direct reports. We review these findings with an eye toward detecting the benefits of using developmental assessment as embedded diagnostics alongside their use as research instruments. We begin by using Integral Theory to structure a discussion about the ideal function of developmental assessments in educational contexts.

Development entrepreneurship: how donors and leaders can foster institutional change - Faustino, Jaime; Booth, David (The Asia Foundation, 2014)
Various communities of practice have been established recently to advance the general idea of thinking and working politically in development agencies. This paper makes a contribution by describing the practice of what has been called development entrepreneurship and explaining some of the ideas from outside the field of development that have inspired it.

Sustainability and Value through Improved Decision-making - Meyer, Isabel; Marais, Mario (Designing and implementing an Information and Communication Technology for Rural Education Development (ICT4RED) initiative in a resource-constrained environment: Nciba school district, Eastern Cape, South Africa, 2014)

Stop Trying to Save the World: Big ideas are destroying international development - Hobbes, Michael (New Republic, 2014)
Gives some examples of poorly designed interventions (e.g. The play pump)

Social Design and Neocolonialism - Janzer, Cinnamon L.; Weinstein, Lauren S. (Design and Culture, 2014)
This article examines the current field of social design: its claims, practices, and methodologies. Findings discovered through qualitative research illuminate the current application of social design practices and offer critique around their use in the social sphere. This article argues that designers must be sensitive to a variety of complex social and cultural cues and structures or they risk contributing to, or practicing, design neocolonialism. The article offers two key theoretical suggestions to further the emerging field's progress. First, social design must shift its focus from one that is human-centered to one that is situation-centered. Second, it is imperative that social design develops a shared framework for understanding, executing, and evaluating its initiatives and interventions. Additionally, this article introduces a matrix to serve as an early iteration of a shared framework.
Keywords: Design Methodology; Design Thinking; Framework; Human-centered design; IMPORTANT; social design

Evaluating Complexity. Propositions for improving practice - Preskill, Hallie; Gopal, Srik (FSG, 2014)
9 propositions can help evaluators measure progress on complex social problems.
Keywords: IMPORTANT

Can policy-makers think like designers? - Adler, Natalia (2014)
This is the poster used by Natalia Adler, from Unicef, at the Doing Development Differently workshop in 2014. Can policy-makers think like designers? Since 2012, UNICEF has been supporting two autonomous governments in Nicaragua to develop empathy-driven policies for children. While policies are the final product, the goal of the Designing for Children Initiative is to make government officials think like designers. A good policy or service is nothing without active and engaged frontline workers. From the onset, our objective was to transform public employees into ‘public entrepreneurs.’ In doing so, we have disrupted the traditional assumptions about participatory governance, where it normally suffices to hold a meeting and have people talk about their needs and aspirations. For participation to work, government officials have to relearn how to listen. They have to let go of pre-determined assumptions and their expert status, and put themselves in the shoes of the people they are trying to reach. This is the process of empathy-driven policy-making. For the past two years, we have used a Human Centered Design (HCD) approach to make this happen. While HCD is often seen as an innovation in itself, for us, it’s just a means to an end: common-sense development.

The Doing Development Different Manifesto - DDD Community (DDD Community, 2014)
Statement from the October 2014 ‘Doing Development Differently’ workshop Too many development initiatives have limited impact. Schools are built but children do not learn. Clinics are built but sic…

A workshop on Doing Development Differently - CID (CID at Harvard University and ODI, 2014)
October 22-23, 2014 A workshop on Doing Development Differently Harvard Kennedy School, Cambridge, MA Hosted by the Building State Capability (BSC) program at the Center for International Development at Harvard University, and the Overseas Development Institute (ODI) with funding from the Governance Partnership Facility.

40 Agile Methods in 40 Minutes - Smith, Craig (2014)
My presentation from Scrum Australia 2014 called “40 Agile Methods in 40 Minutes” is available on Slideshare. With 73% of the world using Scrum as their predominant Agile method, this session will …

Scaling up co-design - Dearden, Andrew; Light, Ann; Zamenopoulos, Theodore; Graham, Paula; Plouviez, Emma; de Sousa, Sophia (PDC 2014 : Reflecting connectedness : proceedings of the 13th Participatory Design Conference, 2014)
In this paper we reflect on our experiences in a project where academic researchers and social change organizations are working together to explore how participatory and co-design practices can be disseminated and spread within the 'third sector'. The research project is itself co-designed and co-produced, but within various constraints arising from research funding models. We explore both our immediate outputs and our learning about successful co-research models for this challenge.

Navigating complexity: Adaptive management in the Northern Karamoja Growth, Health & Governance program - Allana, Amir (MercyCorps, 2014)
Development actors increasing agree that managing programs adaptively – especially complex interventions – can improve their effectiveness. But what does adaptive management look like in practice?
Keywords: IMPORTANT; Practice

The SAVI programme in Nigeria: Towards politically smart, locally led devlopment - Booth, David; Chambers, Victoria (ODI, 2014)
 More examples are needed of aid programming that works by being responsive to country realities: politically smart, problem-driven and locally led  DFID’s SAVI programme has revealed a hitherto untapped potential for change leading to better development results at state level in Nigeria  SAVI provides low-profile support to state-level organisations and partnerships, building their capacity to engage constructively with government  It avoid the pitfalls of a donor-driven approach by ‘taking the money off the table’  This illustrates the power of facilitated multi-stakeholder engagement and the disadvantages of seeing this in terms of ‘supply side’ and ‘demand side’ governance  The set-up of the DFID suite of state-level programmes, with separately managed sector support and ‘governance’ initiatives, has limited realisation of the potential  Key enabling conditions were that DFID provided space for an experience-based design process and permitted tangible results to be judged retrospectively, not pre-programmed

‘We have the solutions to our own problems’: supporting civil society in Nigeria - Overseas Development Institute (ODI, 2014)
Development assistance programmes that start from careful analysis of what works and what does not in country contexts are still remarkably rare. One reason for this is the lack of well documented examples of ‘politically’ smart aid programming. To this end, this film outlines the experience of the State Accountability and Voice Initiative (SAVI), a DFID-funded programme in Nigeria providing support to civil society, media and governmental organisations.

Theory of Action: Creating Craddle to Career Proof Points - Strive Together (Strive Together, 2014)
StriveTogether’s Theory of Action provides a framework for improving educational outcomes and ensuring a community transforms how it serves children.

CLA for More Effective Development Programs (video) - USAID (USAID LearningLab, 2014)
This presentation features USAID/PPL's Stacey Young discussing the history of learning at USAID; how collaborating, learning, and adapting (CLA) can enhance development outcomes, and the role of implementing partners in supporting this vision.

Scrum: The Art of Doing Twice the Work in Half the Time - Sutherland, Jeff (Crown Business, 2014)
We live in a world that is broken. For those who believe that there must be a more agile and efficient way for people to get things done, here from Scrum pioneer Jeff Sutherland is a brilliantly discursive, thought-provoking book about the leadership and management process that is changing the way we live. In the future, historians may look back on human progress and draw a sharp line designating "before Scrum" and "after Scrum." Scrum is that ground-breaking. It already drives most of the world's top technology companies. And now it's starting to spread to every domain where leaders wrestle with complex projects. If you've ever been startled by how fast the world is changing, Scrum is one of the reasons why. Productivity gains of as much as 1200% have been recorded, and there's no more lucid - or compelling - explainer of Scrum and its bright promise than Jeff Sutherland, the man who put together the first Scrum team more than twenty years ago. The thorny problem Jeff began tackling back then boils down to this: people are spectacularly bad at doing things with agility and efficiency. Best laid plans go up in smoke. Teams often work at cross purposes to each other. And when the pressure rises, unhappiness soars. Drawing on his experience as a West Point-educated fighter pilot, biometrics expert, early innovator of ATM technology, and V.P. of engineering or CTO at eleven different technology companies, Jeff began challenging those dysfunctional realities, looking for solutions that would have global impact. In this book you'll journey to Scrum's front lines where Jeff's system of deep accountability, team interaction, and constant iterative improvement is, among other feats, bringing the FBI into the 21st century, perfecting the design of an affordable 140 mile per hour/100 mile per gallon car, helping NPR report fast-moving action in the Middle East, changing the way pharmacists interact with patients, reducing poverty in the Third World, and even helping people plan their weddings and accomplish weekend chores. Woven with insights from martial arts, judicial decision making, advanced aerial combat, robotics, and many other disciplines, Scrum is consistently riveting. But the most important reason to read this book is that it may just help you achieve what others consider unachievable - whether it be inventing a trailblazing technology, devising a new system of education, pioneering a way to feed the hungry, or, closer to home, a building a foundation for your family to thrive and prosper.

Politically smart, locally led development - Booth, David; Unsworth, Sue (ODI, 2014)
Aid donors have found it hard to move from thinking politically to working differently, but there is evidence that they can do so and that this improves outcomes. This paper presents seven examples of where adopting a politically smart, locally led approach has led to better outcomes.
Keywords: Practice

Taking Innovations to Scale: Methods, Applications and Lessons - Cooley, Larry; Linn, Johannes F. (R4D, 2014)
The international development community increasingly recognizes the need to go beyond fragmented, one-of projects. In response, there is now much talk and some action on scaling up successful innovations and pilot projects with an explicit goal of achieving sustainable impact at scale. However, many questions remain about the practical implications of pursuing a systematic scaling up approach and about how the approaches being pursued by diferent institutions and practitioners relate to each other.

The direction of evolution: The rise of cooperative organization - Stewart, John E. (Biosystems, 2014)
Two great trends are evident in the evolution of life on Earth: towards increasing diversification and towards increasing integration. Diversification has spread living processes across the planet, progressively increasing the range of environments and free energy sources exploited by life. Integration has proceeded through a stepwise process in which living entities at one level are integrated into cooperative groups that become larger-scale entities at the next level, and so on, producing cooperative organizations of increasing scale (for example, cooperative groups of simple cells gave rise to the more complex eukaryote cells, groups of these gave rise to multi-cellular organisms, and cooperative groups of these organisms produced animal societies). The trend towards increasing integration has continued during human evolution with the progressive increase in the scale of human groups and societies. The trends towards increasing diversification and integration are both driven by selection. An understanding of the trajectory and causal drivers of the trends suggests that they are likely to culminate in the emergence of a global entity. This entity would emerge from the integration of the living processes, matter, energy and technology of the planet into a global cooperative organization. Such an integration of the results of previous diversifications would enable the global entity to exploit the widest possible range of resources across the varied circumstances of the planet. This paper demonstrates that it's case for directionality meets the tests and criticisms that have proven fatal to previous claims for directionality in evolution.
Keywords: Direction of evolution; Evolution of a global entity; Evolution of cooperation; Evolutionary progress; Major evolutionary transitions

Agile, is it just a delivery mechanism? - Carignan, Louis-Philippe (Scrum.org Community Blog, 2014)
As a Agile coach, I refer to a few tools to help me think about where my Scrum teams should go next on their path to Agility. One of these tools is the Agile subway map, a list of Agile practices grouped in different categories. It helps me think how a specific practice could help …

Time for a Donor Funding Charter? - kiwanja.net (Donor's Chapter, 2014)

Adaptive Learning - Guerzovich, Florencia; Poli, Maria (Global Partnership for Social Accountability, 2014)

Theories of change in international development: Communication, learning, or accountability? - Valters, Craig (JSRP, 2014)

Why Learning & Adaptation are Central to Making All Voices Count - Halloran, Brendan (Making All Voices Count, 2014)

Beyond 'Technology for Development' and 'Sustainability' towards Systemic and Holistic Rural Innovation: Success Factors from the Southern African Experience over 20 years - Buisson, Uys Du; Cronje, Braam; Marais, Mario; Haruperi, Emmanuel; Rensburg, Johann (2014)
Abstract: This paper describes essential, real-world activities and processes needed to develop and deploy people-centred networks enabled with innovative technologies that in turn produce "...

The politics of legal empowerment: Legal mobilisation strategies and implications for development - Domingo, Pilar; O'Neil, Tam (ODI, 2014)
 Legal mobilisation can improve the lives of poor or marginalised people by: o contributing to pro-poor change in policy, law and regulation of service delivery across different sectors; o advancing the realisation of rights, and achieving redress for rights violations; o contesting unjust and illegal practices of resource allocation and power relations, including in relation to land and natural resources; o enabling citizens to exercise social accountability through legal action.  The outcomes of legal empowerment of the poor are not politically neutral and need to be understood within broader social and political environments;  Better coordination between justice, sector and governance interventions will maximise the development and social impact of international support for legal empowerment.

Complexity and the Art of Public Policy: Solving Society's Problems from the Bottom Up - Colander, David; Kupers, Roland (Princeton University Press, 2014)
Complexity science–made possible by modern analytical and computational advances–is changing the way we think about social systems and social theory. Unfortunately, economists' policy models have not kept up and are stuck in either a market fundamentalist or government control narrative. While these standard narratives are useful in some cases, they are damaging in others, directing thinking away from creative, innovative policy solutions. Complexity and the Art of Public Policy outlines a new, more flexible policy narrative, which envisions society as a complex evolving system that is uncontrollable but can be influenced. David Colander and Roland Kupers describe how economists and society became locked into the current policy framework, and lay out fresh alternatives for framing policy questions. Offering original solutions to stubborn problems, the complexity narrative builds on broader philosophical traditions, such as those in the work of John Stuart Mill, to suggest initiatives that the authors call "activist laissez-faire" policies. Colander and Kupers develop innovative bottom-up solutions that, through new institutional structures such as for-benefit corporations, channel individuals' social instincts into solving societal problems, making profits a tool for change rather than a goal. They argue that a central role for government in this complexity framework is to foster an ecostructure within which diverse forms of social entrepreneurship can emerge and blossom.

Thinking and working politically in the transparency and accountability field - Halloran, Brendan (Transparency & Accountability Initiative, 2014)

How DFID learns - ICAI (Independent Commission for Aid Impact (ICAI), 2014)
Excellent learning is essential for UK aid to achieve maximum impact and value for money. We take learning to mean the extent to which DFID uses information and experience to influence its decisions. Each ICAI review assesses how well learning takes place. Our reports to date indicate a mixed performance. This review seeks to identify the way DFID learns and what inhibits it from doing so consistently. We drew on our reviews, assessed data from DFID’s own surveys and carried out interviews inside and outside the department. Review DFID generates considerable volumes of information, much of which, such as funded research, is publicly available. DFID does not clearly or consistently link this investment to how it can deliver better impact. We made five recommendations and gave an amber-red score. Findings DFID does not clearly identify how its investment in learning links to its performance and delivering better impact. DFID has the potential to be excellent at organisational learning if its best practices become common. DFID staff learn well as individuals. They are highly motivated and DFID provides opportunities and resources for them to learn. DFID is not yet, however, managing all the elements that contribute to how it learns as a single, integrated system. DFID does not review the costs, benefits and impact of learning. Insufficient priority is placed on learning during implementation. The emphasis on results can lead to a bias to the positive. Learning from both success and failure should be systematically encouraged. Recommendations DFID needs to focus on consistent and continuous organisational learning based on the experience of DFID, its partners and contractors and the measurement of its impact, in particular during the implementation phase of its activities. All DFID managers should be held accountable for conducting continuous reviews from which lessons are drawn about what works and where impact is actually being achieved for intended beneficiaries. All information commissioned and collected (such as annual reviews and evaluations) should be synthesised so that the relevant lessons are accessible and readily usable across the organisation. The focus must be on practical and easy-to-use information. Knowhow should be valued as much as knowledge. Staff need to be given more time to acquire experience in the field and share lessons about what works and does not work on the ground. DFID needs to continue to encourage a culture of free and full communication about what does and does not work. Staff should be encouraged always to base their decisions on evidence, without any bias to the positive.

Beyond the Pioneer: Getting inclusive industries to scale - Koh, Harvey; Hedge, Nidhi; Karamchandani, Ashish (Deloitte Touche Tohmatsu India Private Ltd (DTTIPL), 2014)

Working Politically: A story of Change about the contribution of research evidence to the new Village Law in Indonesia - Pellini, Arnaldo; Angelina, Maesy; Purnawati, Endah (Austrialian Community Development and Civil Society Strenghtening Scheme (ACCESS), 2014)
On 18 December 2013, the Indonesian House of Representatives passed the new Village Law, a vote that was the culmination of a journey that had started in 2007. This Story of Change takes the passing of the Village Law as its starting point and describes the relative influence that research-based evidence, produced by the Institute for Research and Empowerment (IRE), has had at critical junctions of the legislative process. This Story of Change concludes that good quality, research-based evidence is necessary but not sufficient to influence policy-making processes. Researchers and research organisations need to think and work politically to achieve their influencing goals and to adapt to changes in local circumstances.

Problem-driven iterative approaches and wider governance reform - Rao, Sumedh (GSDRC, University of Birmingham, 2014)
Identify evidence which suggests that problem-driven, iterative approaches to public sector reform can deliver more substantial, wider, long-term governance reform.

Local Systems: a framework for supporting sustained development - USAID (USAID, 2014)

Six Simple Rules: How to Manage Complexity without Getting Complicated - Morieux, Yves; Tollman, Peter (Harvard Business Review Press, 2014)
New tools for managing complexityDoes your organization manage complexity by making things more complicated? If so, you are not alone.According to The Boston Consulting Group’s fascinating Complexity Index, business complexity has increased sixfold during the past sixty years. And, all the while, organizational complicatedness—that is, the number of structures, processes, committees, decision-making forums, and systems—has increased by a whopping factor of thirty-five. In their attempt to respond to the increasingly complex performance requirements they face, company leaders have created an organizational labyrinth that makes it more and more difficult to improve productivity and to pursue innovation. It also disengages and demotivates the workforce.Clearly it’s time for leaders to stop trying to manage complexity with their traditional tools and instead better leverage employees' intelligence. This book shows you how and explains the implications for designing and leading organizations.The way to manage complexity, the authors argue, is neither with the hard solutions of another era nor with the soft solutions—such as team building and feel-good “people initiatives”—that often follow in their wake. Based on social sciences (notably economics, game theory, and organizational sociology) and The Boston Consulting Group’s work with more than five hundred companies in more than forty countries and in various industries, authors Yves Morieux and Peter Tollman recommend six simple rules to manage complexity without getting complicated.Showing why the rules work and how to put them into practice, Morieux and Tollman give managers a much-needed tool to reinvigorate people in the face of seemingly endless complexity. Included are detailed examples from companies that have achieved a multiplicative effect on performance by using them.It’s time to manage complexity better. Employ these six simple rules to foster autonomy and cooperation and to effectively handle business complexity. As a result, you will improve productivity, innovate more, reengage your workforce, and seize opportunities to create competitive advantage.
Keywords: Complexity; Design Thinking

Global Delivery at the World Bank Group - GDI (Global Delivery Initiative, 2014)

DIY - Development Impact and You: Practical Tools to Trigger and Support Social Innovation - Nesta (NESTA, 2014)
Keywords: IMPORTANT

Manifesto for Half-Arsed Development Reforms - Ramalingam, Ben (Aid on the Edge of Chaos, 2014)
Keywords: IMPORTANT

Aid on the Edge of Chaos: Rethinking International Cooperation in a Complex World - Ramalingam, Ben (Oxford University Press, 2014)
It is widely recognised that the foreign aid system - of which every country in the world is a part - is in need of drastic overhaul. There are conflicting opinions as to what should be done. Some call for dramatic increases to achieve longstanding promises. Others bang the drum for cutting it altogether, and suggest putting the fate of poor and vulnerable people in the hands of markets or business. A few argue that what is needed is creative, innovative transformation. The arguments in Aid on the Edge of Chaos are firmly in the third of these categories. In this ground-breaking book, Ben Ramalingam shows that the linear, mechanistic models and assumptions that foreign aid is built on are more at home in early twentieth century industry than in the dynamic, complex world we face today. The reality is that economies and societies are less like machines and more like ecosystems. Aid on the Edge of Chaos explores how thinkers and practitioners in economics, business, and public policy have started to embrace new, ecologically literate approaches to thinking and acting, informed by the ideas of complex adaptive systems research. It showcases insights, experiences, and dramatic results of a growing network of practitioners, researchers, and policy makers who are applying a complexity-informed approach to aid challenges. From transforming approaches to child malnutrition, to rethinking process of macroeconomic growth, from rural Vietnam to urban Columbia, Aid on the Edge of Chaos shows how embracing the ideas of complex systems thinking can help make foreign aid more relevant, more appropriate, more innovative, and more catalytic. It argues that taking on these ideas will be a vital part of the transformation of aid, from a post-WW2 mechanism of resource transfer, to a truly innovative and dynamic form of global cooperation fit for the twenty-first century.

Probes, toolkits and prototypes: three approaches to making in codesigning - Sanders, Elizabeth B.-N.; Stappers, Pieter Jan (CoDesign, 2014)
The role of making in the design process has been growing, taking on new forms and involving new players over the past 10 years. Where we once primarily saw designers using making to give shape to the future, today we can see designers and non-designers working together, using making as a way to make sense of the future. In this paper, we describe the landscape of design research and practice at the end of 2013 with special attention to the role of making across these perspectives: approach (cultural probes, generative toolkits and design prototypes), mindset (designing for people and designing with people), focus in time (the world as it is, the near future and the speculative future) as well as variations in design intent (provoking, engaging and serving).

Assessing the use of technological tools and strategies by Oxfam Novib partners in Angola, Burundi, Egypt, Niger, Pakistan, Rwanda and Uganda - The Engine Room (2014)
This report presents findings and insights from the Oxfam Novib pilot module of TechScape, which assessed how Oxfam Novib partners in seven countries related to the use of technology in their work. This report does not aim to draw conclusions about the nature of technology use by Oxfam Novib partners per se, or even the partners included in this assessment. The dramatic difference in organizational activities, contexts and objectives are too great for that. Detailed analysis of how partners are relating to technology in their work, and specific recommendations for greater efficiency and impact are presented in the TechScape Country Briefs. This report aims instead: • to describe the context in which the assessments took place, • to propose insights gained from the cumulative process about measurement, learning and capacity development, and • to identify opportunities for Oxfam Novib to pursue capacity development and knowledge sharing between countries and across the network, through mechanisms that minimize resource demands and directly target documented needs.

Adaptive management in aid programmes (BEAM Exchange, 2014)
Aid works better – especially in complex and conflict-affected environments – when there is scope to trial and adapt programme strategies. So argues Amir Allana in Navigating Complexity, a case study of Northern Karamoja's Growth, Health and Governance (GHG) Programme that is adopting an 'adaptive management' approach. This BEAM Exchange webinar invited Amir, Tim Sparkman and Peter Roggekamp to discuss lessons from their work in Uganda and Cambodia. What does adaptive management look like in practice? And what does it require of managers and funders to make it happen? Tim and Peter share their experiences of applying adaptive management techniques to the Growth, Health and Governance Programme and the Cambodia Agricultural Value Chain Program (CAVAC). Amir highlight insights from the Navigating Complexity report, including the importance of office culture, consistent management signals, and the role of supportive tools and processes.

Guidelines for good market development program design. A managers’ perspective - Bekkers, Harald; Roggekamp, Peter (BEAM Exchange, 2014)
Good programme design is a key factor contributing to the success of market development programmes. Unfortunately, too many current designs have major flaws which prevent programmes becoming successful even before they get started. This document considers what makes market development programmes consistently successful and how to prevent programme design from being a hurdle to sustainable and efficient impact as scale.

Assessing Impact in Dynamic and Complex Environments: Systemic Action Research and Participatory Systemic Inquiry - Burns, Danny (IDS, 2014)
This CDI Practice Paper is about the uses of Systemic Action Research (SAR) and Participatory Systemic Inquiry (PSI) for impact assessment (Burns 2006, 2007, 2011, 2012, 2013; Wadsworth 2001, 2010).

Behavioral Design: A New Approach to Development Policy - Datta, Saugato; Mullainathan, Sendhil (Review of Income and Wealth, 2014)

Learning and adapting: the use of monitoring and evaluation in countering violent extremism: a handbook for practitioners - Dawson, Laura; Edwards, Charlie; Jeffray, Calum; Royal United Services Institute for Defence and Security Studies (Royal United Services Institute for Defence and Security Studies, 2014)
IN 2013, the Royal United Services Institute for Defence and Security Studies (RUSI) was awarded a grant under the Kanishka Project to develop a handbook for monitoring and evaluating counter violent extremism (CVE) policies and programmes. The aim of this handbook is to support CVE policy-makers and practitioners (those who design, manage and evaluate CVE programmes), by providing them with key terms regarding violent extremism and radicalisation, describing the purpose of evaluation, and providing examples of key methodologies they can employ to conduct monitoring and evaluation (M&E) in this emerging policy field. The handbook will enable readers to understand why, when and how to conduct an evaluation of a CVE policy, programme or project. .
OCLC: 1079851950

The case for thinking and working politically. The implications of 'doing development differently' - DLP (DLP, 2014)
This paper discusses the steps required to build a robust evidence base for 'thinking and working politically' (TWP) in development. It argues that better understanding what works, when and why is an important step in moving TWP into mainstream development programming. The paper reviews the existing evidence base on TWP, building on this and on other literature on public sector reform and 'pockets of effectiveness' to suggest research questions, case study selection criteria, and a four-level analytical framework: 1) political context; 2) sector; 3) organisation; and 4) individual. The framework aims to help build a 'rigorous enough' evidence base to show whether and how TWP happens and whether or not it influences the effectiveness of programme implementation and outcomes. The paper also calls for more focus on gender issues, and on different – and often more fragile – political contexts.

Capacity WORKS - GIZ (2014)
One of GIZ’s core competencies is understanding how cooperation works in societies, and supporting that process. The kind of process we mean is cooperation between state, civil society and private-sector actors who wish to jointly shape societal changes. GIZ has systematised its knowledge on how to achieve this, and made it available in the Capacity WORKS management model. The model describes how to manage cooperation systems.

Capacity Works - online training - GIZ (GIZ, 2014)

Systemic Design Principles for Complex Social Systems - Jones, Peter H. (Social Systems and Design, 2014)
Keywords: IMPORTANT

Steering E-Government Projects from Failure to Success: Using Design-Reality Gap Analysis as a Mid-Implementation Assessment Tool - Lessa, Lemma; Negash, Solomon; Belachew, Mesfin (Emerging Issues and Prospects in African E-Government:, 2014)
There are many e-government failures in developing countries. Most studies look at these after the event (post hoc), but this chapter takes an original approach to look mid-implementation (durante hoc) in order to provide recommendations for improvement. The authors chose a partial failure/partial success land management information system being implemented in one Ethiopian city. The project has made retrieval of land information quicker and simpler but is only partly implemented, and is still—on occasion—circumvented by public servants for personal gain. They used design-reality gap framework to understand why the project had partly failed. The authors used the design-reality gap analysis to propose an action plan that would help institutionalise the system, steering it from partial failure to success. They demonstrate the value of this framework as a tool for mid-implementation analysis of e-government projects. The authors recommend its usage on other ongoing e-government projects in developing countries.

Political economy analysis: Topic Guide - Mcloughlin, Claire (GSDRC, University of Birmingham, 2014)
Political economy analysis (PEA) aims to situate development interventions within an understanding of the prevailing political and economic processes in society – specifically, the incentives, relationships, and distribution and contestation of power between different groups and individuals. Such an analysis can support more politically feasible and therefore more effective development strategies by setting realistic expectations …

Power Above and Below the Waterline: Bridging Political Economy and Power Analysis - Pettit, Jethro; Mejía Acosta, Andrés (IDS Bulletin, 2014)

From best practice to best fit: understanding and navigating wicked problems in international development - Ramalingam, Ben; Laric, Miguel; Primrose, John (ODI, 2014)

Adapting lean thinking to market systems development: Principles and practices for donors/funders - Rasmussen, Leanne (Engineers without borders, 2014)
The purpose of this paper is to provide funders and implementers of market systems development (MSD) projects with principles, practices, and structures that enables these projects to thrive. It is based on a book that has sold millions of copies worldwide, and a school of thought taught at institutions such as Harvard Business School and practiced in companies ranging from giants such as Toyota to the most successful tech start-ups in Silicon Valley. Published in 2011, Eric Ries wrote the Lean Startup as a remedy to the countless start-ups that create their own demises by getting started with the wrong goals, the wrong structures, and the wrong processes. He outlines an approach that enables the startup to navigate ambiguity and risk while using resources effectively. The conditions a MSD project faces are remarkably similar to those which a startup business faces; it needs structures and processes that are matched to the unpredictable, complex environment which it is attempting to influence. MSD projects can thus benefit from private-sector thought leadership on how start-ups can situate themselves for success. This paper starts with an overview of lean thinking, a concept that derives from lean manufacturing which is widely accepted as the leading approach to modern manufacturing. It explains how Ries’s Lean Startup adapts these principles, and then it in turn adapts these ideas for market systems development. The following three sections provide an overview of Lean Startup concepts, applying them to the development sector as appropriate. The final section summarizes and makes suggestions on next steps for funders who wish to set MSD projects up for success using a lean approach. Overall, the paper builds a case for how the Lean Startup’s approach can enable MSD projects to work successfully in ambiguity and increase their potential for achieving robust and sustainable results, all while using donor resources more efficiently.
Keywords: Adaptive Development; Lean

The politics of public sector performance: pockets of effectiveness in developing countries - Roll, Michael (Routledge, 2014)
OCLC: 869850351

Adaptive Management: From More Talk to Real Action - Williams, Byron K.; Brown, Eleanor D. (Environmental Management, 2014)
The challenges currently facing resource managers are large-scale and complex, and demand new approaches to balance development and conservation goals. One approach that shows considerable promise for addressing these challenges is adaptive management, which by now is broadly seen as a natural, intuitive, and potentially effective way to address decision-making in the face of uncertainties. Yet the concept of adaptive management continues to evolve, and its record of success remains limited. In this article, we present an operational framework for adaptive decision-making, and describe the challenges and opportunities in applying it to real-world problems. We discuss the key elements required for adaptive decision-making, and their integration into an iterative process that highlights and distinguishes technical and social learning. We illustrate the elements and processes of the framework with some successful on-the-ground examples of natural resource management. Finally, we address some of the difficulties in applying learning-based management, and finish with a discussion of future directions and strategic challenges.
Keywords: IMPORTANT

Building tech-powered public services - Bickerstaffe, Sarah (Institute for Public Policy Research, 2013)
Given the rapid pace of technological change and take up by the public it is a question of when not if public services become tech powered This new paper asks how we can ensure that innovations are successfully introduced and deployed

Adaptive Leadership: Accelerating Enterprise Agility - Highsmith, Jim (Addison-Wesley Professional., 2013)

Politics, Political Change and International Development - Halloran, Brendan (Politics, Governance and Development, 2013)
As my inaugural post on my new blog, I thought I would re-post a short piece I wrote earlier this year about foreign aid (original here). Thomas Carothers and Diane de Garamont address this issue i…

Adaptive programming - Vowles, Pete (DFID Bloggers, 2013)
Staff blogs from the UK Department for International Development. Get real-life perspectives from those on the ground to fight poverty and join in the debate.

Lessons for Effective resilience programs: a case study of the RAIN program in Ethiopia - Kleiman, Shanti (Mercy Corps, 2013)
The RAIN program experience affirms the importance of multi-year and flexible funding as key program design features if progress in resilience building is to be supported in areas with high levels of structural and temporal vulnerability. These features enable management to respond effectively to changing circumstances in order to better meet the needs of communities and to create the necessary conditions for relief-to-development strategies to take hold. Finally, this study found that deliberate and effective coordination between donor agencies can ensure that development gains achieved during one program period are directly leveraged by subsequent programs, thereby increasing the effectiveness of resilience programs.

An analysis of factors influencing success of ICT4D projects: a case study of the Schools Computerisation Programme in Mashonaland West Province, Zimbabwe. - Musiyandaka, Donna; Ranga, Gideon; Kiwa, Jacqueline Fungai (The Journal of Community Informatics, 2013)
Keywords: ICT4D programmes; success factors

Development Aid Confronts Politics: The Almost Revolution - Carothers, Thomas; de Gramont, Diane (EDS Publications Ltd., 2013)
A new lens on development is changing the world of international aid. The overdue recognition that development in all sectors is an inherently political process is driving aid providers to try to learn how to think and act politically. Major donors are pursuing explicitly political goals alongside their traditional socioeconomic aims and introducing more politically informed methods throughout their work. Yet these changes face an array of external and internal obstacles, from heightened sensitivity on the part of many aid-receiving governments about foreign political interventionism to inflexible aid delivery mechanisms and entrenched technocratic preferences within many aid organizations. This pathbreaking book assesses the progress and pitfalls of the attempted politics revolution in development aid and charts a constructive way forward.

It's All About MeE: Using Structured Experiential Learning (“e”) to Crawl the Design Space - Pritchett, Lant; Samji, Salimah; Hammer, Jeffrey (Center for Global Development, 2013)
This paper argues that within-project variations in design can serve as their own counterfactual, reducing the incremental cost of evaluation and increasing the direct usefulness of evaluation to implementing agencies. It suggests combining monitoring (‘M’), structured experiential learning (‘e’), and evaluation (‘E’) so as to facilitate innovation and organisational capability building while also providing accountability …

Reflections on applying iterative and incremental software development methodologies to aid and development work in developing countries - Haikin, Matt (MattHaikin.com, 2013)

Making the Most of Mess: Reliability and Policy in Today's Management Challenges - Roe, Emery (Duke University Press Books, 2013)
In Making the Most of Mess, Emery Roe emphasizes that policy messes cannot be avoided or cleaned up; they need to be managed. He shows how policymakers and other professionals can learn these necessary skills from control operators who manage large critical infrastructures such as water supplies, telecommunications systems, and electricity grids. The ways in which they prevent major accidents and failures offer models for policymakers and other professionals to manage the messes they face.Throughout, Roe focuses on the global financial mess of 2008 and its ongoing aftermath, showing how mismanagement has allowed it to morph into other national and international messes. More effective management is still possible for this and many other policy messes but that requires better recognition of patterns and formulation of scenarios, as well as the ability to translate pattern and scenario into reliability. Developing networks of professionals who respond to messes is particularly important. Roe describes how these networks enable the avoidance of bad or worse messes, take advantage of opportunities resulting from messes, and address societal and professional challenges. In addition to finance, he draws from a wide range of case material in other policy arenas. Roe demonstrates that knowing how to manage policy messes is the best approach to preventing crises.

Adaptive management: where are we now? - Rist, Lucy; Campbell, Bruce M.; Frost, Peter (Environmental Conservation, 2013)
Adaptive management (AM) emerged in the literature in the mid-1970s in response both to a realization of the extent of uncertainty involved in management, and a frustration with attempts to use modelling to integrate knowledge and make predictions. The term has since become increasingly widely used in scientific articles, policy documents and management plans, but both understanding and application of the concept is mixed. This paper reviews recent literature from conservation and natural resource management journals to assess diversity in how the term is used, highlight ambiguities and consider how the concept might be further assessed. AM is currently being used to describe many different management contexts, scales and locations. Few authors define the term explicitly or describe how it offers a means to improve management outcomes in their specific management context. Many do not adhere to the idea as it was originally conceived, despite citing seminal work. Significant confusion exists over the distinction between active and passive approaches. Over half of the studies reporting to implement AM claimed to have done so successfully, yet none quantified specific benefits, or costs, in relation to possible alternatives. Similarly those studies reporting to assess the approach did so only in relation to specific models and their parameterizations; none assessed the benefits or costs of AM in the field. AM is regarded by some as an effective and well-established framework to support the management of natural resources, yet by others as a concept difficult to realize and fraught with implementation challenges; neither of these observations is wholly accurate. From a scientific and technical perspective many practical questions remain; in particular real-world assessments of the value of experimentation within a management framework, as well as of identified challenges and pathologies, are needed. Further discussion and systematic assessment of the approach is required, together with greater attention to its definition and description, enabling the assessment of new approaches to managing uncertainty, and AM itself.
Keywords: Adaptive Management; Decision making; Natural resource management; conservation; experimental management; uncertainty

Improving the Evaluability of INGO Empowerment and Accountability Programmes - Shutt, Cathy; McGee, Rosemary (Centre for Development Impact, 2013)

The Limits of Institutional Reform in Development: Changing Rules for Realistic Solutions - Andrews, Matt (Cambridge University Press, 2013)
Institutional reforms are common across the globe. Think of efforts to build new governments in Afghanistan and Iraq; or decades worth of interventions intended to improve fiscal management, reduce corruption or introduce efficient public sector service delivery in African countries.These reforms often have limited results, however. They lead to new laws that are not properly implemented, and new organizations that have poor capacities and fail to function as needed. In this book, Matt Andrews explains why reform results are frequently limited and suggests ways to overcome these limits. In the first half of the book, Andrews argues that reforms fail to make governments better when they are introduced as signals to gain short-term support–from donors and others. Reforms as signals introduce unrealistic best practices that do not fit developing country contexts and are not considered relevant by implementing agents. The result is a set of new forms that do not function properly. Andrews uses examples to prove this point, ranging from efforts to introduce fiscal rules in Argentina to reforms aimed at international accounting standard adoption in many African countries, and anti corruption interventions in Malawi and Uganda. In the second half of the book, Andrews notes that there are instances where reforms are not being introduced as signals, and are having more of an impact on government effectiveness. Examples include local government reforms in Rwanda, anti corruption initiatives in Indonesia, and a variety of initiatives ranging from results based management to civil service modernization and internal control regime adoption in governments like Kenya, Kosovo and Afghanistan. Andrews uses these examples to discuss ways in which reforms can actually provide realistic solutions to governance challenges in developing countries. Lessons from these experiences suggest that reform limits can be overcome by focusing interventions on problem solving, and promoting incremental and localized processes to find solutions, involving multiple agents who can authorize and implement reforms.

Learning Lab - Collaborate, Learn and Adapt for better development outcomes - Learning Lab (USAID, 2013)
CLA is: a component of several missions' CDCSes. a conceptual framework for some principles and operational processes that can enable USAID to become a more effective learning organization and thereby a more effective development organization. an approach to facilitating local participation and capacity and promoting country-led development. For more information on CLA visit:

Embracing Emergence: How Collective Impact Addresses Complexity - Kania, John; Kramer, Mark (Stanford Social Innovation Review, 2013)
Collective impact is upending conventional wisdom on how we achieve social progress.

Systems Innovation - Discussion Paper - Mulgan, Geoff; Leadbeater, Charlie (NESTA, 2013)
Introduction Over the past few years there has been growing interest in systemic innovation. We are defining this as an interconnected set of innovations, where each influences the other, with innovation both in the parts of the system and in the ways in which they interconnect. Yet rather than simply theorising, we want to make this practical. We want to explore the potential of systemic innovation to help tackle some of the key challenges the UK currently faces, from supporting an ageing population to tackling unemployment. We would also like to open up the discussion, to engage with the wide and diverse range of experts already working this space to help sharpen up thinking about systemic innovation and influence practical work to advance it. About this paper The two essays contained within this paper are intended to contribute to this debate. The first paper by Geoff Mulgan addresses a number of questions about systemic – or ‘joined–up’ – innovation, asking what it means to truly transform a system, encompassing the means, methods, and actions needed to realise its potential. The second paper from Charlie Leadbeater argues that companies, governments, cities, and entire societies need to move from seeing innovation in products and services as a source of competitive advantage, to focussing on innovation with entire systems. Our next steps: helping make systemic innovation useful and useable This report is just the start. We want to work with academics, practitioners, policymakers, and others in the field, to help realise the great potential of connecting and joining up innovative products, services and processes so that the whole is more than the parts. Over the coming months we will be building upon the rich and diverse literature available (we have start collating this as an annex to this paper), as well as practitioner experience, to ensure we understand systems more rigorously, as well as the skills, capabilities, methods and means needed to help them change for the better.

Utilization-Focused Evaluation (U-FE) Checklist - Patton, Michael Quinn (The Evaluation Center, 2013)
Utilization-Focused Evaluation begins with the premise that evaluations should be judged by their utility and actual use; therefore, evaluators should facilitate the evaluation process and design any evaluation with careful consideration of how everything that is done, from beginning to end, will affect use. Use concerns how real people in the real world apply evaluation findings and experience and learn from the evaluation process. The checklist is based on Essentials of Utilization-Focused Evaluation (Patton, 2012, Sage Publications). All references in the checklist to exhibits and menus refer to this book. Step 1 Assess and build program and organizational readiness for utilization-focused evaluation. Step 2 Assess and enhance evaluator readiness and competence to undertake a utilizationfocused evaluation. Step 3 Identify, organize, and engage primary intended users. Step 4 Conduct situation analysis with primary intended users Step 5 Identify primary intended uses by establishing the evaluation’s priority purposes. Step 6 Consider and build in process uses if appropriate. Step 7 Focus priority evaluation questions. Step 8 Check that fundamental areas for evaluation inquiry are being adequately addressed. Step 9 Determine what intervention model or theory of change is being evaluated. Step 10 Negotiate appropriate methods to generate credible findings and support intended use by intended users. Step 11 Make sure intended users understand potential controversies about methods and their implications. Step 12 Simulate use of findings. Step 13 Gather data with ongoing attention to use. Step 14 Organize and present the data for use by primary intended users. Step 15 Prepare an evaluation report to facilitate use and disseminate significant findings to expand influence. Step 16 Follow up with primary intended users to facilitate and enhance use. Step 17 Metaevaluation of use: Be accountable, learn, and improve

Explaining positive deviance in public sector reforms in development - Andrews, Matt (World Institute for Development Economic Research (UNU-WIDER), 2013)
Public sector reforms are commonplace in developing countries. Much of the literature about these reforms reflects on their failures. This paper asks about the successes and investigates which of two competing theories best explain why some reforms exhibi
Keywords: Development; Innovation; Reform; case survey; governance; growth; leadership

Use Case and Requirements Analysis in a Remote Rural Context in Mali - Bon, Anna; de Boer, Victor; Gyan, Nana Baah; van Aart, Chris; De Leenheer, Pieter; Tuyp, Wendelien; Boyera, Stephane; Froumentin, Max; Grewal, Aman; Allen, Mary; Tangara, Amadou; Akkermans, Hans (Requirements Engineering: Foundation for Software Quality, 2013)
[Context & motivation] Few studies have reported on a systematic use case and requirements analysis of low-tech, low-resource contexts such as rural Africa. This, despite the widespread agreement on the importance of Information and Communication Technologies (ICT) for social and rural development, and despite the large number of ICT projects targeting underprivileged communities. [Question/problem] Unfamiliarity with the local context and differences in cultural and educational backgrounds between end-users and software engineers are the challenges for requirements engineering (RE) we encountered. [Principal ideas/results] We describe a systematic approach to RE in developing areas, based on the Living Lab methodology. Our approach is supported by extensive field research and based on co-creation within a multi-disciplinary and multi-cultural team of developers and users. This approach creates a shared understanding of the problem and its local context, and optimizes communication. [Contribution] We illustrate the approach using a case study of web- and voice-based communication services, that we developed for a rural context in Mali.

Signal Left, Turn Right: Central Rhetoric and Local Reform in China - Huang, Haifeng (Political Research Quarterly, 2013)
How have local governments in China been able to break through central policy restrictions in a unitary and authoritarian political system? Why is China's official discourse in the reform era often so conservative and unfavorable to reform? The author argues the two issues are components of a signaling game between China's central government and local officials, in which local officials know that the center may be reformist, but the reformist center imitates the rhetoric of a conservative center to control the pace of local liberalization. The result is a gradualist reform of "signaling left, turning right," with glaring incongruity of speech and actions in the process.

Design reality gap issues within an ICT4D project: an assessment of Jigawa State Community Computer Center - Kanya, Rislana Abdulazeez; Good, Alice (2013)
This paper evaluates the Jigawa State Government Community Computer centre project using the design reality gap framework. The purpose of this was to analyse the shortfall between design expectations and implementation realities, in order to find out the current situation of the project. Furthermore to analyse whether it would meet the key stakeholder’s expectation. The Majority of Government ICT Projects is classified as either failure or partial failure. Our research will underpin a case study of Jigawa State Community Computer centre project. To support our argument we conducted a qualitative case study in which we conducted two interviews, and a survey to find out the current status of the project. Our findings indicated that the project can be classified as a partial failure because few of the centres, operating in some areas of the community, offered socio-economic advancement. Our results also indicated that the project design reality gap is quite significant. This gap occurred due to poor planning and implementation of the project. Our research reveals several challenges that could impact upon the successfulness of the project provide a foundation for further research and add to existing literature. The challenges associated with the project we identify include poor state of power supply, lack of community engagement during the project planning and implementation, lack of commitment from the Local Government Administration. Our research has potential in adding ICT4D literature, reveals how ICT4D project evaluation can be carried out using design reality gap framework and provides guideline for policy makers.

Managing Upward and Downward Accountability in an International Development Project - A Case Study of a World Bank Telecommunications Infrastructure Project in Benin - Kolker, Eva; Kulldorff, Catharina (Master's Thesis, Stockholm School of Economics, 2013)
Keywords: Downward accountability; Upward accountability

Definitions of Agile Software Development and Agility - Laanti, Maarit; Similä, Jouni; Abrahamsson, Pekka (Systems, Software and Services Process Improvement, 2013)
The Agile Manifesto and Agile Principles are typically referred to as the definitions of "agile" and "agility". However, many other definitions exist in the literature. Thus the different definitions provide interesting source for research. For each definition we examine where their emphasis is and compare that to the emphases found in the Agile Principles.

Mapping Context for Social Accountability: A resource paper - O'Meally, Sion C. (The World Bank, 2013)

Power Analysis: A Practical Guide - Pettit, Jethro (Sida, 2013)

Perspectives on Participation in Design - Sanders, Elizabeth (Wer gestaltet die Gestaltung? Praxis, Theorie und Geschichte des partizipatorischen Designs, 2013)
OCLC: 930782596
Keywords: Design

Routledge international handbook of participatory design - Simonsen, Jesper; Robertson, Toni (Routledge, 2013)
"Participatory Design is about the direct involvement of people in the co-design of the technologies they use. Its central concern is how collaborative design processes can be driven by the participation of the people affected by the technology designed. Embracing a diverse collection of principles and practices aimed at making technologies, tools, environments, businesses, and social institutions more responsive to human needs, the International Handbook of Participatory Design is a state-of-the-art reference handbook for the subject. The Handbook brings together a multidisciplinary and international group of highly recognized and experienced experts to present an authoritative overview of the field and its history and discuss contributions and challenges of the pivotal issues in Participatory Design, including heritage, ethics, ethnography, methods, tools and techniques and community involvement. The book also highlights three large-scale case studies which show how Participatory Design has been used to bring about outstanding changes in different organisations. The book shows why Participatory Design is an important, highly relevant and rewarding area for research and practice. It will be an invaluable resource for students, researchers, scholars and professionals in Participatory Design"–
OCLC: 754734489

Chris Argyris: theories of action, double-loop learning and organizational learning - Smith, Mark K. (The encyclopedia of pedagogy and informal education, 2013)
Chris Argyris: theories of action, double-loop learning and organizational learning. The work of Chris Argyris (1923-2013) has influenced thinking about the relationship of people and organizations…

Scaling Agile @ Spotify with Tribes, Squads, Chapters & Guilds - Kniberg, Henrik; Ivarsson, Anders (Spotify, 2012)

What about the results? Lessons from long-term process support to strengthen results-based management (RBM) for Swedish framework NGOs operating in Western Balkans - Ørnemark, Charlotte (NCG, 2012)
The observations and lessons outlined in this report should be seen as a contribution to the on-going learning and reflections in a wider debate on how to assess and monitor results from support to CSOs involved in complex social change processes (as opposed to those involved in more ‘classical’ service delivery and more linear development assistance). These lessons, though directly emerging from the consultancy to provide long-term RBM support to the FOs and their local CSO partners in Western Balkans, also draws on previous experiences and similar lessons from on-going initiatives. In brief, these lessons call for a certain ‘paradigm shift’ in the way we (as development professionals) regard and support RBM for actors involved in less tangible social change processes in highly contested political spaces. Some of these shifts, outlined in more detail in different sections of this report, are summarised below:  From a linear, aggregated cause-and-effect thinking around RBM to one that is linked to human factors and is embedded in systems,  From pushing the burden of reporting down in the system to a clearer division of labour between donors, recipient governments, intermediary agents like framework NGOs (FOs) and implementing CSOs with each actor using its comparative advantage and appropriate role in the RBM process and for its own learning,  From operating in programming and results frameworks where outcomes and impact are largely assumed to be predictable to setting up systems that deal with uncertainty and that capture emerging result patterns through tracking of gradual changes,  From a project/programme perspective to a focus on institutions and systems as actors and arenas for change, where organisations are enabled to act as change agents towards clearly identified processes of social transformation,  From SMART to REAL results frameworks – although SMART (specific, measurable, achievable, realistic and time-bound) principles are always good to keep in mind for the formulation of goals and indicators, the danger of coming up with fictive measuring frameworks calls for a more systematic incorporation of ‘real’ concerns, including making RBM processes rights-based, embedded in local realities (and empowering for those involved), aligned to national reform efforts and national and international human rights commitments, and learning-oriented for all different levels of operations.

Escaping Capability Traps through Problem-Driven Iterative Adaptation (PDIA) - Andrews, Matt; Pritchett, Lant; Woolcock, Michael (Harvard University, 2012)
Keywords: IMPORTANT

Complexity, Adaptation, and Results - Barder, Owen; Ramalingam, Ben (Center For Global Development, 2012)
In the last of a series of three blog posts looking at the implications of complexity theory for development, Owen Barder and Ben Ramalingam look at the implications of complexity for the trend towards results-based management in development cooperation. They argue that is a common mistake to see a contradiction between recognising complexity and focusing on results: on the contrary, complexity provides a powerful reason for pursuing the results agenda, but it has to be done in ways which reflect the context. In the 2012 Kapuscinski lecture Owen argued that economic and political systems can best be thought of as complex adaptive systems, and that development should be understood as an emergent property of those systems. As explained in detail in Ben’s forthcoming book, these interactive systems are made up of adaptive actors, whose actions are a self-organised search for fitness on a shifting landscape. Systems like this undergo change in dynamic, non-linear ways; characterised by explosive surprises and tipping points as well as periods of relative stability. If development arises from the interactions of a dynamic and unpredictable system, you might draw the conclusion that it makes no sense to try to assess or measure the results of particular development interventions. That would be the wrong conclusion to reach. While the complexity of development implies a different way of thinking about evaluation, accountability and results, it also means that the ‘results agenda’ is more important than ever.
Keywords: IMPORTANT

The Art of Community: Building the New Age of Participation - Bacon, Jono (O'Reilly Media, 2012)
Online communities provide a wide range of opportunities for supporting a cause, marketing a product or service, or building open source software. The Art of Community helps you recruit members, motivate them, and manage them as active participants. Author Jono Bacon offers experiences and observations from his 14-year effort to build and manage communities, including his current position as manager for Ubuntu.Discover how your community can become a reliable support network, a valuable source of new ideas, and a powerful marketing force. This expanded edition shows you how to keep community projects on track, make use of social media, and organize collaborative events. Interviews with 12 community management leaders, including Linus Torvalds, Tim O’Reilly, and Mike Shinoda, provide useful insights.Develop specific objectives and goals for building your communityBuild processes to help contributors perform tasks, work together, and share successesProvide tools and infrastructure that enable members to work quicklyCreate buzz around your community to get more people involvedHarness social media to broadcast information, collaborate, and get feedbackUse several techniques to track progress on community goalsIdentify and manage conflict, such as dealing with divisive personalities

The Implications of Complexity for Development - Barder, Owen (2012)
In this lecture, adapted from his May 2012 Kapuściński Lecture, Owen Barder explores the implications of complexity theory for development policy. He explains how traditional economic models have tried and failed to understand why some countries have managed to improve living standards while other countries have not.
Keywords: IMPORTANT

Agile Project Management For Dummies - Layton, Mark C. (John Wiley & Sons, 2012)
Be flexible and faster with Agile project management As mobile and web technologies continue to evolve rapidly, there is added pressure to develop and implement software projects in weeks instead of months. Agile Project Management For Dummies can make that happen. This is the first book to provide a simple, step–by–step guide to Agile Project Management approaches, tools, and techniques. With the fast pace of mobile and web technology development, software project development must keep pace; Agile Project Management enables developers to complete and implement projects more quickly and this book shows you how. Offers a practical context for understanding and applying Agile techniques, moving from theory into actual practice Explains when to use Agile and how to avoid common pitfalls Written by experts who know how to apply the principles in real–world situations Agile Project Management For Dummies enables you to understand and apply Agile principles for faster, more accurate development.

Adapt: Why Success Always Starts with Failure - Harford, Tim (Abacus, 2012)
Everything we know about solving the world's problems is wrong. Out: Plans, experts and above all, leaders. In: Adapting - improvise rather than plan; fail, learn, and try againIn this groundbreaking new book, Tim Harford shows how the world's most complex and important problems - including terrorism, climate change, poverty, innovation, and the financial crisis - can only be solved from the bottom up by rapid experimenting and adapting.From a spaceport in the Mojave Desert to the street battles of Iraq, from a blazing offshore drilling rig to everyday decisions in our business and personal lives, this is a handbook for surviving - and prospering - in our complex and ever-shifting world.

Delivering large-scale IT projects on time, on budget, and on value - Bloch, Michael; Blumberg, Sven; Laartz, Jürgen (McKinsey on Business Technology, 2012)
Large IT efforts often cost much more than planned; some can put the whole organization in jeopardy. The companies that defy these odds are the ones that master key dimensions that align IT and business value.

Teaming: how organizations learn, innovate, and compete in the knowledge economy - Edmondson, Amy C. (Jossey-Bass, 2012)
New breakthrough thinking in organizational learning, leadership, and change Continuous improvement, understanding complex systems, and promoting innovation are all part of the landscape of learning challenges today's companies face. Amy Edmondson shows that organizations thrive, or fail to thrive, based on how well the small groups within those organizations work. In most organizations, the work that produces value for customers is carried out by teams, and increasingly, by flexible team-like entities. The pace of change and the fluidity of most work structures means that it's not really about creating effective teams anymore, but instead about leading effective teaming. Teaming shows that organizations learn when the flexible, fluid collaborations they encompass are able to learn. The problem is teams, and other dynamic groups, don't learn naturally. Edmondson outlines the factors that prevent them from doing so, such as interpersonal fear, irrational beliefs about failure, groupthink, problematic power dynamics, and information hoarding. With Teaming, leaders can shape these factors by encouraging reflection, creating psychological safety, and overcoming defensive interpersonal dynamics that inhibit the sharing of ideas. Further, they can use practical management strategies to help organizations realize the benefits inherent in both success and failure. Presents a clear explanation of practical management concepts for increasing learning capability for business results Introduces a framework that clarifies how learning processes must be altered for different kinds of work Explains how Collaborative Learning works, and gives tips for how to do it well Includes case-study research on Intermountain healthcare, Prudential, GM, Toyota, IDEO, the IRS, and both Cincinnati and Minneapolis Children's Hospitals, among others Based on years of research, this book shows how leaders can make organizational learning happen by building teams that learn.

Participatory design with marginalized people in developing countries: Challenges and opportunities experienced in a field study in Cambodia - Hussain, Sofia; Sanders, Elizabeth B.-N.; Steinert, Martin (International Journal of Design, 2012)

Adaptability: the art of winning in an age of uncertainty - McKeown, Max (Kogan Page, 2012)
Keywords: Adaptability (Psychology); Success

Quality Flaws: Issues and Challenges in Software Development - Mohan, P.; Shankar, A. Udaya; JayaSriDevi, K. (Computer Engineering and Intelligent Systems, 2012)
A statement “Prevention is better than cure” for illnesses in medical sciences also applies to the software development life cycle in terms of software defects. A defect is a deviation from actual functionality of the application in terms of the correctness and completeness of the specification of the customer requirements. Defective software fails to meet its customer requirements leading to the development of applications with poor quality. Quality is a top priority in every enterprise these days. Organizations struggle in a treadmill race to deliver quality software to stay ahead with new technology, deal with accumulated development backlogs, handle customer issues as software teams work as hard as they can make their organizations stay alive and competitive in the market place. Software companies face an immense pressure to virtually release a bug-free product or a software package. The culture of an organization is a critical success factor in the efforts of process improvement. The paper aims at assessing quality as a function for monitoring and measuring the strength of development processes and any successful application development enterprise requires an unambiguous understanding of customer expectation and maximizing participation of customers in the development activities thereby ensuring that people involved in development activities do the right thing and do the thing right for delivering high quality software . Keywords: Software development, process improvement, software defect, bug-free product, software package

Lean from the Trenches: Managing Large-Scale Projects with Kanban - Kniberg, Henrik (Pragmatic Bookshelf, 2011)
You know the Agile and Lean development buzzwords, you've read the books. But when systems need a serious overhaul, you need to see how it works in real life, with real situations and people. Lean from the Trenches is all about actual practice. Every key point is illustrated with a photo or diagram, and anecdotes bring you inside the project as you discover why and how one organization modernized its workplace in record time.Lean from the Trenches is all about actual practice.Find out how the Swedish police combined XP, Scrum, and Kanban in a 60-person project. From start to finish, you'll see how to deliver a successful product using Lean principles. We start with an organization in desperate need of a new way of doing things and finish with a group of sixty, all working in sync to develop a scalable, complex system. You'll walk through the project step by step, from customer engagement, to the daily "cocktail party," version control, bug tracking, and release. In this honest look at what works–and what doesn't–you'll find out how to:Make quality everyone's business, not just the testers.Keep everyone moving in the same direction without micromanagement.Use simple and powerful metrics to aid in planning and process improvement.Balance between low-level feature focus and high-level system focus.You'll be ready to jump into the trenches and streamline your own development process.

Complexity, Institutions and Public Policy: Agile Decision-making in a Turbulent World - Room, Graham (Edward Elgar Pub, 2011)
Graham Room argues that conventional approaches to the conceptualization and measurement of social and economic change are unsatisfactory. As a result, researchers are ill-equipped to offer policy advice. This book offers a new analytical approach, combining complexity science and institutionalism. It also provides tools for policy makers in turbulent times. Part 1 is concerned with the conceptualization of socio-economic change. It integrates complexity science and institutionalism into a coherent ontology of social and policy dynamics. Part 2 is concerned with models and measurement. It combines some of the principal approaches developed in complexity analysis with models and methods drawn from mainstream social and political science. Part 3 offers empirical applications to public policy: the dynamics of social exclusion; the social dimension of knowledge economies; the current financial and economic crisis. These are supplemented by a toolkit for the practice of 'agile policy making'. This is a stimulating, provocative and highly original book. It will appeal to academics and students in social and policy studies and to a wide range of scholars in other disciplines where complexity science is already well-developed. It will also be of major interest for decision makers coping with complex and turbulent policy terrains.Contents: Preface 1. Introduction Part I: Concepts 2. The Complexity Paradigm 3. Complex Adaptive Systems 4. The Economy as a Complex Adaptive System 5. Institutional Settings and Architectures 6. Institutional Dynamics 7. The Struggle for Positional Advantage 8. Conceptualising Social Dynamics Part II: Methods 9. Attractors and Orbits in Dynamic Systems 10. Patterns in Time and Space 11. Connections and Networks 12. Mobility on Social Landscapes 13. Towards a Generic Methodology Part III: Policies 14. Agile Policy-Making 15. Poverty and Social Exclusion 16. Social Dynamics of the Knowledge Economy 17. Global Turbulence and Crisis Postscript: Tools for Policy-Makers References Index

Why your IT project may be riskier than you think - Flyvbjerg, Bent; Budzier, Alexander (Harvard Business Review, 2011)
New research shows surprisingly high numbers of out-of-control tech projects—ones that can sink entire companies and careers.

Essentials of Utilization-Focused Evaluation - Patton, Michael Quinn (SAGE Publications, 2011)
Based on Michael Quinn Patton's best-selling Utilization-Focused Evaluation, this briefer book provides an overall framework and essential checklist steps for designing and conducting evaluations that actually get used. The new material and innovative graphics present the utilization-focused evaluation process as a complex adaptive system, incorporating current understandings about systems thinking and complexity concepts. The book integrates theory and practice, is based on both research and professional experience, and offers new case examples and cartoons with Patton's signature humor.
Google-Books-ID: BaMgAQAAQBAJ
Keywords: Reference / Research; Research

Virtuous cycles of learning: Redesigning testing during the digital revolution - Dawson, Theo; Stein, Zachary (2011)
This paper explores positive new directions for the future of educational testing by examining trends at the interface of the learning sciences and advances in educational technologies. A brief history of the relation between testing and technology sets the stage for a look at emerging “edu-tech” trends and what these might mean for the future of testing. This historical-critical look at past and present testing practices reveals that the learning sciences have been less influential in shaping the growth of testing infrastructures than cumulative advances in technology that have enabled large-scale standardization and automation. We argue that during the current “digital revolution” the learning sciences ought to assume more responsibility for shaping the adoption of new testing technologies. We propose a set of principles that, if followed, would move tomorrow’s testing infrastructures toward learning-centric design. Combining the affordances of new digital technologies with advances in our understanding of learning make it possible to build tests that promote multi-level learning in educational systems, catalyzing virtuous cycles of learning for everyone they affect—students, teachers, school leaders, policy makers, and researchers. The DiscoTest™ Initiative is presented as a reform effort that is guided by these design principles, serving as an example of positive new possibilities for testing at the interface of the learning sciences and new educational technologies.

Is (Web) Science Ready for Empowerment? - Akkermans, Hans; Gyan, Nana Baah; Bon, Anna; Tuyp, Wendelien; Grewal, Aman; Boyera, Stéphane; Allen, Mary (2011)

System Stewardship. The future of policy making? - Hallsworth, Michael (Institute for Government, 2011)
This working paper looks at the future of policy making in a world of decentralisation and more complex problems. It argues that policy makers need to see themselves less as sitting on top of a delivery chain, but as stewards of systems with multiple actors and decision makers – whose choices will determine how policy is realised. We are keen to open up a debate on what this means.

Making Good Use of Adaptive Management - Doremus, Holly; Andreen, William L.; Camacho, Alejandro E.; Farber, Daniel A.; Glicksman, Robert L.; Goble, Dale D.; Karkkainen, Bradley C.; Rohlf, Dan; Tarlock, A. Dan; Zellmer, Sandra B.; Jones, Shana Campbell; Huang, Yee (Center for Progressive Reform, 2011)

Learning how to learn: eight lessons for impact evaluations that make a difference - Ramalingam, Ben (ODI, 2011)
This Background Note outlines key lessons on impact evaluations, utilisation-focused evaluations and evidence-based policy. While methodological pluralism is the key to effective impact evaluation in development, the focus here is on the factors that need to be considered for impact evaluations to be used in policy and practice – regardless of the method employed.

Thinking and Working Politically: What does it mean, Why is it important and How do you do it? - Leftwich, Adrian (Politics, Leadership and Coalitions in Development: Policy Implications of the DLP Research Evidence, Research and Policy Workshop, 2011)
This paper suggests that working politically in a developmental context means directing attention and support to the agents of reform and development (leaders and organisations). This allows investment in the local processes that will resolve problems – such as problems of collective action – through the work of alliances and coalitions. Hence, it will drive the formation and consolidation of the locally appropriate, feasible and legitimate institutions that are most likely to advance development outcomes. The Developmental Leadership Program defines politics as the pervasive, unavoidable and necessary activities of conflict, negotiation and compromise involved in group decision-making about how resources are to be used, produced and distributed. Thinking politically means understanding that both political and technical dimensions are central to developmental outcomes. It also means: Understanding that ‘agency’ matters. That is, that people have the potential to change things, but always withhin the context of given institutional arrangements, which contain both constraints and opportunities. Leaders, organisations and followers think, strategise and attempt to resolve problems in different ways in the same contexts. Understanding leadership as a political process that mobilises people and resources in support of a goal: leaders seldom work on their own. Realising that overcoming collective action problems is a major challenge of development. Collective action problems occur when people with diverse (often competing) interests struggle to agree on an organisational arrangement from which they would all benefit. Understanding that coalitions (formal or informal) are a crucial political mechanism for the resolution of collective action problems. Paying attention to the detailed inner politics of regimes, sectors or issues (‘micro-politics’). This includes understanding who the players are, where they come from, their organisational affiliations, ideologies and interests and the political dynamics involved. (Many political analysis tools are inadequate for this level of detail.) Recognising that processes are as important as projects in development, and vary from context to context. Working politically in development means supporting, brokering, facilitating and aiding the emergence and practices of (public or private) developmental or reform leaderships, organisations, networks and coalitions at any level, and across all sectors. It means helping them to respond to, and work with, initiatives and requests from local individuals and groups. Working politically can also involve: Investing in the effectiveness of developmental coalitions by enhancing the political capacity of organisations in negotiation, advocacy, communication and the generation of constructive policy options. Rethinking higher educational support programmes so that they supplement a skills focus with strategies that help to build networks, and encourage the understanding of collective action problems and of the importance of providing public goods. Acquiring a deep and detailed knowledge of, and long-term exposure to, the country or issue concerned. Respectful and sensitive understanding of local political dynamics and cultural norms. Employing more social scientists and a well-trained, politically savvy workforce, both local and international, with the capacity to ‘read’ the politics. In particular, coalitions can help drive the endogenous politics of developmental reforms by: 1) achieving a specific policy goal; 2) opening up debate on a previously taboo issue; 3) deepening and strengthening the coalition’s internal organisation and relationships for future purposes; and 4) increasing the capacity of constituent organisations. It is also important to understand that: Developmental leaderships and coalitions often emerge in response to a critical juncture – a threat, challenge or danger – or a new opportunity. What matters is whether leaders have the knowledge, education, vision, prior experience and networks to seize such opportunities. The character and conditionality of funding by donors or supporters can make or break a coalition. Are tight conditions applied? Are funding arrangements transparent?

Leading Effectively in a VUCA Environment: A is for Ambiguity - Kail, Col Eric G. (Harvard Business Review, 2011)
This is the last in a series on the four aspects of VUCA, a framework used by the U.S. military to describe the environment in terms of volatility, uncertainty, complexity, and ambiguity. Diversity and global reach introduce ambiguity to the environment; therefore opportunities and challenges must be appreciated from multiple aspects, not just our own […]
Keywords: Leadership; Leading teams

Alps - Accountability, Learning and Planning System - 2011 Update - ActionAid (ActionAid International, 2011)
Alps is ActionAid’s over arching accountability framework, containing within it our programme planning system. Alps is distinctive in that it is strongly driven by principles, and sets out necessary personal attitudes and behaviours alongside organisational processes for planning, strategy formulation, learning, monitoring reviews/evaluations and audit. Alps defines our standards, not only about what we do but also how we do it. Alps is part of ActionAid’s human rights-based work.

’Adaptive Authoritarianism’ in Contemporary China: Identifying Zones of Legitimacy Building - Ahlers, Anna Lisa; Schubert, Gunter (Reviving Legitimacy: Lessons for and from China, 2011)
Anna L. Ahlers and Gunter Schubert, ’Adaptive Authoritarianism’ in Contemporary China: Identifying Zones of Legitimacy Building, in: Deng Zhenglai and Guo Sujian (eds), Reviving Legitimacy: Lessons for and from China, Lanham: Lexington Books (2011),

Navigating the landscape of conflict: Applications of dynamical systems theory to protracted social conflict - Coleman, Peter T.; Vallacher, Robin R.; Nowak, Andrzej; Bartoli, Andrea (The Non-linearity of Peace processes. Theory and Practice of Systemic Conflict Transformation, 2011)

Strategies for learning from failure - Edmondson, Amy C. (Harvard Business Review, 2011)

Foreign policy and complex adaptive systems: Exploring new paradigms for analysis and action - Frej, William; Ramalingam, Ben (Santa Fe Institute, 2011)

Taking responsibility for complexity: how implementation can achieve results in the face of complex problems - Jones, Harry (ODI, 2011)
OCLC: 837825712

Collective Impact - Kania, John; Kramer, Mark (Stanford Social Innovation Review, 2011)
Large-scale social change requires broad cross-sector coordination, not the isolated intervention of individual organizations.

Analysis of the factors affecting the sustainability of ICT4D initiatives - Marais, Mario (IDIA2011 Conference Proceedings, 2011)

Local Empowerment Through Rapid Results - Matta, Nadim; Morgan, Peter (Stanford Social Innovation Review, 2011)
Why local ownership and commitment are the exception in most development efforts—and what development professionals can do about this problem.

On understanding software agility: A social complexity point of view - Pelrine, Joseph (E:CO, 2011)
Over the last decade, the field of so-called Agile software development has grown to be a major force in the socio-economic arena of delivering quality software on time, on budget, and on spec. The acceleration in changing needs brought on by the rise in popularity of the Internet has helped push Agile practices far beyond their original boundaries, and possibly into domains where their application is not the optimal solution to the problems at hand. The question of where Agile software development practices and techniques make sense, and where are they out of place, is a valid one. It can be addressed by looking at software development as a complex endeavour, and using tools and techniques from the Cynefin method and other models of social complexity.
Keywords: IMPORTANT

Design thinking: understand - improve - apply - Plattner, Hasso; Meinel, Christoph; Leifer, Larry (Springer, 2011)
"In this book, the researchers take a system's view that begins with a demand for deep, evidence-based understanding of design thinking phenomena. They continue with an exploration of tools which can help improve the adaptive expertise needed for design thinking. The final part of the book concerns design thinking in information technology and its relevance for business process modeling and agile software development, i.e. real world creation and deployment of products, services, and enterprise systems"–Cover
Keywords: Creative ability in business; Creative thinking; Designer; Industrial management; Innovation; Organizational change; Product development; System design; Technological innovations

Learning to ADAPT: monitoring and evaluation approaches in climate change adaptation and disaster risk reduction – challenges, gaps and ways forward - Silva Villanueva, Paula (IDS, 2011)
This working paper is a methodological contribution to the emerging debate on monitoring and evaluation (M&E) in the context of climate change adaptationand disaster risk reduction. Effectively managing disaster risk is critical for adapting to the impacts of climate change, however disasters risk reduction M&E practice may be limited in capturing progress towards adaptation. The unique nature of adaptation to climate change calls for experience-based learning M&E processes for discovering the key insights into adaptive capacity and its links to adaptation processes, and to risk and vulnerability reduction at large. The ADAPT guiding principles and indicators set the foundations towards this end.

Leading Effectively in a VUCA Environment: C is for Complexity - Kail, Col Eric G. (Harvard Business Review, 2010)
This is the third in a series on the four aspects of VUCA, a framework used by the U.S. military to describe the environment in terms of volatility, uncertainty, complexity, and ambiguity. Our complex environment demands a perspective that goes beyond viewing threats and opportunities as collective; we must see them as interactive. Leading through […]
Keywords: Leadership; Leadership development

Leading in a VUCA Environment: U is for Uncertainty - Kail, Col Eric G. (Harvard Business Review, 2010)
This post is part of an HBR Spotlight examining leadership lessons from the military. It’s the second in a series on the four aspects of VUCA, a framework used by the U.S. military to describe the environment in terms of volatility, uncertainty, complexity, and ambiguity. The frenetic pace of our environment, brought on by volatility, […]
Keywords: Leadership

Leading in a VUCA Environment: V Is for Volatility - Kail, Col Eric G. (Harvard Business Review, 2010)
This post is part of an HBR Spotlight examining leadership lessons from the military This is the first in a series on the four aspects of VUCA, a framework used by the U.S. military to describe the environment in terms of volatility, uncertainty, complexity, and ambiguity. Do challenges and opportunities that once took days or […]
Keywords: Leadership

Passive and active adaptive management: Approaches and an example - Williams, Byron (Journal of Environmental Management, 2010)
Adaptive management is a framework for resource conservation that promotes iterative learning-based decision making. Yet there remains considerable confusion about what adaptive management entails, and how to actually make resource decisions adaptively. A key but somewhat ambiguous distinction in adaptive management is between active and passive forms of adaptive decision making. The objective of this paper is to illustrate some approaches to active and passive adaptive management with a simple example involving the drawdown of water impoundments on a wildlife refuge. The approaches are illustrated for the drawdown example, and contrasted in terms of objectives, costs, and potential learning rates. Some key challenges to the actual practice of AM are discussed, and tradeoffs between implementation costs and long-term benefits are highlighted.

Naturalizing sensemaking - Snowden, Dave (Informed by Knowledge: Expert Performance in Complex Situations, 2010)
The focus of this book is on how experts adapt to complexity, synthesize and interpret information in context, and transform or "fuse" disparate items of information into coherent knowledge. The chapters examine these processes across experts (e.g. global leaders, individuals in extreme environments, managers, police officers, pilots, commanders, doctors, inventors), across contexts (e.g. space and space analogs, corporate organizations, command and control, crisis and crowd management, air traffic control, the operating room, product development), and for both individual and team performance. Successful information integration is a key factor in the success of diverse endeavors, including team attempts to climb Mt. Everest, crowd control in the Middle East, and remote drilling operations. This volume is divided into four sections, each with a specific focus on an area of expert performance, resulting in a text that covers a wide range of useful information. These sections present well-researched discussions, such as: the management of complex situations in various fields and decision contexts; technological and training approaches to facilitate knowledge management by individual experts and expert teams; new or neglected perspectives in expert decision making; and the importance of ‘modeling’ expert performance through techniques and frameworks such as Cognitive Task Analysis, computational architectures based on the notion of causal belief mapping such as ‘Convince Me,’ or the data/frame model of sensemaking. The volume provides essential reading for researchers and practitioners of Naturalistic Decision Making and those who study Expertise; Organizational and Cognitive Psychologists; and researchers and students in Business and Engineering.

The unofficial SCRUM checklist - Kniberg, Henrik (CRISP, 2010)

Tips for Conducting a Gender Analysis at the Activity or Project Level - Cozzarelli, Cathy (USAID, 2010)
I. What is gender analysis? II. Relevant sections of the ADS III. Process – What should you do to collect the information you need to conduct a gender analysis at the activity or project level? IV. What questions should you ask in the context of doing your gender analysis? - Access - Knowledge, Beliefs, and Perceptions - Practices and Participation - Time and Space - Legal Rights and Status - Power and Decision-making IV. What should you do after you ask these questions?

Embracing the Chaotic: Cynefin and Humanitarian Response - Morealtitude (WanderLust, 2010)
Note: Many thanks to Dave Snowden for his willingness to comment on this article prior to release Because I’m always a little behind the eight-ball, a friend of mine* recently introduced me to the …

Paradigms, Poverty and Adaptive Pluralism - Chambers, Robert (IDS, 2010)
This paper explores participatory methodologies (PMs) associated with a paradigm of people, contrasted with a dominant paradigm associated with things.

A Practical Guide to Distributed Scrum - Woodward, Elizabeth; Surdek, Steffan; Ganis, Matthew (IBM Press, 2010)
Succeed with Scrum in Even the Largest, Most Complex Distributed Development Projects Forewords by Ken Schwaber, Scott Ambler, Roman Pichler, and Matthew Wang This is the first comprehensive, practical guide for Scrum practitioners working in large-scale distributed environments. Written by three of IBM’s leading Scrum practitioners–in close collaboration with the IBM QSE Scrum Community of more than 1000 members worldwide–this book offers specific, actionable guidance for everyone who wants to succeed with Scrum in the enterprise. Readers will follow a journey through the lifecycle of a distributed Scrum project, from envisioning products and setting up teams to preparing for Sprint planning and running retrospectives. Each chapter presents a baseline drawn from “conventional” Scrum, then discusses additional issues faced by distributed teams, and presents specific best-practice solutions, alternatives, and tips the authors have identified through hard, empirical experience. Using real-world examples, the book demonstrates how to apply key Scrum practices, such as look-ahead planning in geographically distributed environments. Readers will also gain valuable new insights into the agile management of complex problem and technical domains. Coverage includes• Developing user stories and working with Product Owners as a distributed team• Recognizing and fixing the flaws Scrum may reveal in existing processes• Engaging in more efficient Release and Sprint planning• Conducting intense, brief daily Scrum meetings in distributed environments• Managing cultural and language differences• Resolving dependencies, performing frequent integration, and maintaining transparency in geographically distributed environments• Successfully running remote software reviews and demos• Brainstorming what worked and what didn’t, to improve future Sprints This book will be an indispensable resource for every team leader, member, product owner, or manager working with Scrum or other agile methods in any distributed software development organization.

Adaptive Management in the Courts - Fischman, Robert L.; Ruhl, J.B. (Minnesota Law Review, 2010)
Adaptive management has become the tonic of natural resources policy. With its core idea of “learning while doing,” adaptive management has infused the natural resources policy world to the point of ubiquity, surfacing in everything from mundane agency permits to grand presidential proclamations. Indeed, it is no exaggeration to suggest that these days adaptive management is natural resources policy. But is it working? Does appending “adaptive” in front of “management” somehow make natural resources policy, which has always been about balancing competing claims to nature’s bounty, something more and better? Many legal and policy scholars have asked that question, with mixed reviews. Their evaluations, however, have rested on theory, program-specific surveys, and isolated case studies. This article provides the first comprehensive review of adaptive management from the perspective that likely matters most to the natural resource agencies practicing adaptive management - how is it faring in the courts? Part I of the Article examines the theory, policy, and practice of adaptive management, focusing on the experience of the federal resource management agencies. The end product in practice is something we call “a m-lite,” a watered down version of the theory that resembles ad hoc contingency planning more than it does planned “learning while doing.” This gap between theory and practice leads to profound disparities between how agencies justify decisions and how adaptive management in practice arrives at the courthouse doorsteps. In Part II we review how these disparities have played out in courts considering claims that agency practice of adaptive management has not lived up to its theoretical promise or to the legal demands of substantive and procedural environmental law. We extract three key themes from the body of case law in this respect. Part III extends from the existing case law to draw lessons for agencies and Congress about the future practice of adaptive management. Our ultimate message to agencies is that a m-lite can be an effective decision method - and one that survives judicial scrutiny - but agencies must be more disciplined about its design and implementation. This includes resisting the temptation to employ adaptive management to dodge burdensome procedural requirements, substantive management criteria, and contentious stakeholder participation. If faithfully followed and enforced, this model, despite its flaws, could serve as an important component of natural resources policy to confront problems of the future as daunting as climate change.

Unpacking the concept of political will to confront corruption - Brinkerhoff, Derek W. (U4 Anti-Corruption Resource Centre, 2010)
Quite often, "lack of political will" is identified as the culprit for poorly performing anti-corruption programmes. Yet despite the frequency with which it is used to explain unsatisfactory reform outcomes, political will remains under-defined and poorly understood. Further, assessments are often conducted retrospectively, looking back at failed programmes. By applying a model of political will that specifies a set of action-based components that are observable and measurable, and amenable to external reinforcement and support, more clarity regarding the degree of political will can be achieved.

Design Thinking for Social Innovation - Brown, Tim; Wyatt, Jocelyn (Stanford Social Innovation Review, 2010)
Designers have traditionally focused on enhancing the look and functionality of products. Recently, they have begun using design techniques to tackle more complex problems, such as finding ways to provide low-cost healthcare throughout the world. Businesses were the first to embrace this new approach—called design thinking—and nonprofits are beginning to adopt it too.

Bootcamp Bootleg Design Thinking Toolkit - d.school (Institute of Design, Stanford University, 2010)
Keywords: IMPORTANT

Coping with Complexity - Gerard Seijts; Niels Billou; Mary Crossan (Ivey Business Journal, 2010)

The Innovative Power of Positive Deviance - Goldstein, Jeffrey; Hazy, James; Lichtenstein, Benyamin B. (Complexity and the Nexus of Leadership, 2010)

Accountability and Learning: Exploding the Myth of Incompatibility between Accountability and Learning - Guijt, Irene (NGO Management - The Earthscan Compendium, 2010)
When accountability is understood as reporting on pre-deined deliverables, it is often considered to be irreconcilable with learning. This conventional wisdom inhibits an appreciation of their connection. In this chapter, Irene Guijt exposes the laws and traps in reasoning that keep accountability and learning apart. She provides practitioners with principles and basic good ideas that open up prospects for accountability and learning to complement each other.
Publication Title: NGO Management

Obliquity: Why Our Goals Are Best Achieved Indirectly - Kay, John (Penguin Books, 2010)
"John Kay tells a fast-paced detective story as he searches for the surprising secret to success...Brilliant." -Tim Harford, author of The Logic of Life In this revolutionary book, economist John Kay proves a notion that feels at once paradoxical and deeply commonsensical: the best way to achieve any complex or broadly defined goal, from happiness to preventing forest fires, is the indirect way. We can learn how to achieve our objectives only through a gradual process of risk taking and discovery-what Kay calls obliquity. The author traces this seemingly counterintuitive path to success as it manifests itself in nearly every aspect of life, including business, politics, sports, and more.

Grounded Theory Method in HCI and CSCW - Muller, Michael J; Kogan, Sandra (IBM Center for Social Software, 2010)

The open book of social innovation - Murray, Robin; Caulier-Grice, Julie; Mulgan, Geoff (Young Foundation & NESTA, 2010)

The Clash of the Counter-bureaucracy and Development - Natsios, Andrew (The Center for Global Development, 2010)
In this essay, Andrew Natsios gives a first-hand account of what he finds most hinders USAID—layers of bureaucracy that misguide and derail development work.

Quality standards for development evaluation - OECD; Development Assistance Committee (OECD, 2010)
Based on a broad international consultative process, the DAC Quality Standards for Development Evaluation are a reference guide to good practice in development evaluation. With a view to improving the quality of evaluation processes and products, and facilitating collaboration, this reference guide lays out standards for each phase of a typical evaluation process: from defining purpose, to planning, designing, implementing, reporting, and learning from and using evaluation results.
OCLC: 631212078

The Power of Positive Deviance - Pascale, Richard; Sternin, Jerry; Sternin, Monique (Harvard Business Press, 2010)

Applying Systems Thinking via Systemigrams™ for Defining the Body of Knowledge and Curriculum to Advance Systems Engineering (BKCASE) Project - Squires, Alice; Pyster, Art; Sauser, Brian; Olwell, David; Enck, Stephanie; Gelosh, Don; Anthony, Jim (INCOSE International Symposium, 2010)
Systems thinking is commonly accepted as the backbone of a successful systems engineering approach. As such, the Body of Knowledge and Curriculum to Advance Systems Engineering (BKCASE) team chose to leverage a systems thinking based tool, called Systemitool, to describe our project to the vast audience that would potentially become involved directly or indirectly in the success of the project. This paper describes the process and steps used by the authors and the BKCASE team to develop the project's systemic diagram, or Systemigram™, and the story behind the project, the products, and the vision of the BKCASE project. The goal of the paper is to provide guidance so that readers can leverage the lessons learned from this effort to successfully develop their own project definitions and stories.

Innovation, Sustainability, Development: A New Manifesto - STEPS Centre (STEPS Centre, 2010)
Our Manifesto project publication is available in print, on CD or to view online. Innovation, Sustainability, Development: A New Manifesto recommends new ways of linking science and innovation to development for a more sustainable, equitable and resilient future. The multimedia version, with added audio, video and background documents, is available on CD and online.

Change by Design: How Design Thinking Transforms Organizations and Inspires Innovation - Brown, Tim (HarperBusiness, 2009)
The myth of innovation is that brilliant ideas leap fully formed from the minds of geniuses. The reality is that most innovations come from a process of rigorous examination through which great ideas are identified and developed before being realized as new offerings and capabilities. This book introduces the idea of design thinking‚ the collaborative process by which the designer′s sensibilities and methods are employed to match people′s needs not only with what is technically feasible and a viable business strategy. In short‚ design thinking converts need into demand. It′s a human−centered approach to problem solving that helps people and organizations become more innovative and more creative. Design thinking is not just applicable to so−called creative industries or people who work in the design field. It′s a methodology that has been used by organizations such as Kaiser Permanente to increase the quality of patient care by re−examining the ways that their nurses manage shift change‚ or Kraft to rethink supply chain management. This is not a book by designers for designers; this is a book for creative leaders seeking to infuse design thinking into every level of an organization‚ product‚ or service to drive new alternatives for business and society.
Keywords: IMPORTANT

Appropriate ICT as a Tool to Increase Effectiveness in ICT4D: Theoretical considerations and illustrating cases - Reijswoud, Victor van (The Electronic Journal of Information Systems in Developing Countries, 2009)
The need to bridge the digital divide is no longer a point of discussion and therefore focus has shifted to the design and implementation of programs that have the potential to close the information and knowledge gap between the developing and developed nations. Unfortunately, the majority of these programs are small and mimic what has been successful in the developed world. It has become increasingly clear that these successes do not necessarily translate well in the context of developing nations. This paper develops the hypothesis that Information and Communication Technology (ICT) projects in developing countries will become successful only when they are adapted to local conditions. The general concept of Appropriate Technology (AT) will be explored for the field of ICT. AT has already been embraced by fields like architecture, building technology and agriculture, but has not yet been rooted in ICT. The paper proposes a preliminary theory of Appropriate ICT along the lines of existing theories in AT and System development. The theory identifies Appropriate Technology principles at three levels: hardware, software and ICT change management. By means of real life mini cases in the ICT for Development context in Africa, the guiding principles for Appropriate ICT are illustrated. The paper will conclude with an agenda for further research in the three identified levels. The research agenda targets academia, governments, NGO's and industry.
Keywords: IMPORTANT

Agile Project Management: Creating Innovative Products - Highsmith, Jim (Addison Wesley, 2009)
Best practices for managing projects in agile environments―now updated with new techniques for larger projectsToday, the pace of project management moves faster. Project management needs to become more flexible and far more responsive to customers. Using Agile Project Management (APM), project managers can achieve all these goals without compromising value, quality, or business discipline. In Agile Project Management, Second Edition, renowned agile pioneer Jim Highsmith thoroughly updates his classic guide to APM, extending and refining it to support even the largest projects and organizations. Writing for project leaders, managers, and executives at all levels, Highsmith integrates the best project management, product management, and software development practices into an overall framework designed to support unprecedented speed and mobility. The many topics added in this new edition include incorporating agile values, scaling agile projects, release planning, portfolio governance, and enhancing organizational agility. Project and business leaders will especially appreciate Highsmith’s new coverage of promoting agility through performance measurements based on value, quality, and constraints. This edition’s coverage includes: Understanding the agile revolution’s impact on product development Recognizing when agile methods will work in project management, and when they won’t Setting realistic business objectives for Agile Project Management Promoting agile values and principles across the organizationUtilizing a proven Agile Enterprise Framework that encompasses governance, project and iteration management, and technical practicesOptimizing all five stages of the agile project: Envision, Speculate, Explore, Adapt, and CloseOrganizational and product-related processes for scaling agile to the largest projects and teamsAgile project governance solutions for executives and management The “Agile Triangle”: measuring performance in ways that encourage agility instead of discouraging itThe changing role of the agile project leader

Political Economy Analysis - How to note - DFID (DFID, 2009)
Political economy analysis is a powerful tool for improving the effectiveness of aid. Bridging the traditional concerns of politics and economics, it focuses on how power and resources are distributed and contested in different contexts, and the implications for development outcomes. It gets beneath the formal structures to reveal the underlying interests, incentives and institutions that enable or frustrate change. Such insights are important if we are to advance challenging agendas around governance, economic growth and service delivery, which experience has shown do not lend themselves to technical solutions alone. Political economy analysis is not a magic bullet for the resolution of intractable development problems. However, it can support more effective and politically feasible development strategies, as well as inform more realistic expectations of what can be achieved, and the risks involved. It can also contribute to better results by identifying where the main opportunities and barriers for policy reform exist and how donors can use their programming and influencing tools to promote positive change. This understanding is particularly relevant in fragile and conflict-affected environments where the challenge of building peaceful states and societies is fundamentally political. There are an increasing number of political economy tools available to development agencies for a range of analytical and operational purposes. This note brings together this material with a view to explaining the relevance and uses of political economy analysis. It is intended to be used by a wide range of DFID programme managers and advisers, as well as staff in other HMG departments and partner organisations. The main questions it addresses are: 􀂃 what is political economy analysis? 􀂃 how and why does political economy analysis add value to DFID work? 􀂃 what approaches and tools are available? 􀂃 how should the analysis be prepared, undertaken and applied to DFID’s work? 􀂃 how should we work with other development partners and across HMG on analysis? Key messages include: • Political economy analysis is central to the formulation of sound country plans and sector programmes, and can play a key role in risk mitigation and ensuring that donors avoid harmful practices. • Political economy analysis can help to improve development effectiveness by identifying how and where donors should focus efforts to promote positive change. • There are a growing number of operationally relevant tools which can be used to inform development strategies at the country or sector level, or in relation to particular development problems. • Several DFID country offices have used political economy analysis to improve the quality and impact of aid. This experience provides valuable lessons that should be considered when commissioning and undertaking political economy analysis. • Where possible, analysis should be conducted on an ongoing basis with key partners in HMG and the wider development community to encourage shared understanding and joint action.

Design in the Organization: Parts and Wholes - Junginger, Sabine (Research Design Journal, 2009)
Inroduces the stages of adoption of Design in organizations, with a visual tool.

Impact assessment of ICT-for-development projects a compendium of approaches - Heeks, Richard; Molla, Alemayehu (University of Manchester. Institute for development policy and management (IDPM), 2009)
OCLC: 686761171

From Political Won't to Political Will: Building Support for Participatory Governance - Malena, Carmen (Kumarian Press, 2009)
* Geographically diverse examples of participatory governance in action* Practical case studies show how citizens can participate more fully in the political process Despite a recent wave of democratization around the world, traditional systems of representative democracy seem to be in crisis. Citizens in both the North and the South lack opportunities, rights and access to information and have expressed growing disillusionment with their governments. Ordinary citizens (especially women, poor people and other marginalized groups) are largely excluded from the political processes that directly affect their lives. There is now growing consensus that good governance is participatory governance (PG), but public officials are often reluctant to adopt such an approach. From Political Won’t to Political Will addresses the particular challenge of encouraging these officials to involve citizens in the political process. The book presents contributions by participants from CIVICUS’ 2008 conference on building political will for PG. Representing the perspectives of both civil society and government actors, they propose a number of strategies and lessons such as demonstrating the benefits of PG to governments, complementing formal democratic institutions, building trust, supporting PG champions and using strategic political timing. Their practical and highly original findings will interest anyone eager to see the empowerment of people around the world.
Google-Books-ID: xILlSXw3D5oC

Glossary of Key Terms in Evaluation and Results Based Management - OECD (OECD, 2009)

Innovations in international humanitarian action - Ramalingam, Ben; Scriven, Kim; Foley, Conor (8th review of humanitarian action, 2009)

How to Make Sense of Weak Signals - Schoemaker, Paul J. H.; Day, George S. (MIT Sloan Management Review, 2009)
Keywords: IMPORTANT

Thinking in Systems: A Primer - Meadows, Donella H. (Chelsea Green Publishing, 2008)
In the years following her role as the lead author of the international bestseller, Limits to Growth—the first book to show the consequences of unchecked growth on a finite planet— Donella Meadows remained a pioneer of environmental and social analysis until her untimely death in 2001.Thinking in Systems, is a concise and crucial book offering insight for problem solving on scales ranging from the personal to the global. Edited by the Sustainability Institute’s Diana Wright, this essential primer brings systems thinking out of the realm of computers and equations and into the tangible world, showing readers how to develop the systems-thinking skills that thought leaders across the globe consider critical for 21st-century life.Some of the biggest problems facing the world—war, hunger, poverty, and environmental degradation—are essentially system failures. They cannot be solved by fixing one piece in isolation from the others, because even seemingly minor details have enormous power to undermine the best efforts of too-narrow thinking.While readers will learn the conceptual tools and methods of systems thinking, the heart of the book is grander than methodology. Donella Meadows was known as much for nurturing positive outcomes as she was for delving into the science behind global dilemmas. She reminds readers to pay attention to what is important, not just what is quantifiable, to stay humble, and to stay a learner.In a world growing ever more complicated, crowded, and interdependent, Thinking in Systems helps readers avoid confusion and helplessness, the first step toward finding proactive and effective solutions.

The New Development Economics: We Shall Experiment, but How Shall We Learn? - Rodrik, Dani (SSRN, 2008)
Development economics is split between macro-development economists - who focus on economic growth, international trade, and fiscal/macro policies - and micro-development economists - who study microfinance, education, health, and other social programs. Recently there has been substantial convergence in the policy mindset exhibited by micro evaluation enthusiasts, on the one hand, and growth diagnosticians, on the other. At the same time, the randomized evaluation revolution has led to an accentuation of the methodological divergence between the two camps. Overcoming the split requires changes on both sides. Macrodevelopment economists need to recognize the distinct advantages of the experimental approach and adopt the policy mindset of the randomized evaluation enthusiasts. Micro-development economists, for their part, have to recognize that the utility of randomized evaluations is restricted by the narrow and limited scope of their application. As the Chinese example illustrates, extending the experimental mindset to the domain of economy-wide reforms is not just possible, it has already been practiced with resounding success in the most important development experience of our generation.
Keywords: Economics; Finance; Health Care; International Development; International Economics; International Trade; Macroeconomics; Microeconomics; Social Policy; Welfare

Systems Thinking. Applied. A primer - Edson, Robert (ASysT Institute, 2008)

Exploring the science of complexity: Ideas and implications for development and humanitarian efforts - Ramalingam, Ben; Jones, Harry; Reba, Toussaint; Young, John (ODI, 2008)
This paper draws on the science of complexity to outline alternative approaches to analysing and understanding problems faced in humanitarian and development work.

Historical roots of Agile Methods: Where did “Agile Thinking” come from? - Abbas, Noura; Gravell, Andrew M.; Wills, Gary B. (Agile Processes in Software Engineering and Extreme Programming, 2008)
The appearance of Agile methods has been the most noticeable change to software process thinking in the last fifteen years [16], but in fact many of the “Agile ideas” have been around since 70’s or even before. Many studies and reviews have been conducted about Agile methods which ascribe their emergence as a reaction against traditional methods. In this paper, we argue that although Agile methods are new as a whole, they have strong roots in the history of software engineering. In addition to the iterative and incremental approaches that have been in use since 1957 [21], people who criticised the traditional methods suggested alternative approaches which were actually Agile ideas such as the response to change, customer involvement, and working software over documentation. The authors of this paper believe that education about the history of Agile thinking will help to develop better understanding as well as promoting the use of Agile methods. We therefore present and discuss the reasons behind the development and introduction of Agile methods, as a reaction to traditional methods, as a result of people’s experience, and in particular focusing on reusing ideas from history.
Keywords: Agile methods; Software Development

Why to be Wary of "Design for Developing Countries" - Donaldson, Krista (Ambidextrous, 2008)

Success and Failure in eGovernment Projects - Heeks, Richard (Institute for Development Policy and Management, 2008)

The Art of Agile Development - Shore, James; Warden, Shane (O'Reilly Media, 2007)
The Art of Agile Development contains practical guidance for anyone considering or applying agile development for building valuable software. Plenty of books describe what agile development is or why it helps software projects succeed, but very few combine information for developers, managers, testers, and customers into a single package that they can apply directly. This book provides no-nonsense advice on agile planning, development, delivery, and management taken from the authors' many years of experience with Extreme Programming (XP). You get a gestalt view of the agile development process, including comprehensive guidance for non-technical readers and hands-on technical practices for developers and testers. The Art of Agile Development gives you clear answers to questions such as: How can we adopt agile development? Do we really need to pair program? What metrics should we report? What if I can't get my customer to participate? How much documentation should we write? When do we design and architect? As a non-developer, how should I work with my agile team? Where is my product roadmap? How does QA fit in? The book teaches you how to adopt XP practices, describes each practice in detail, then discusses principles that will allow you to modify XP and create your own agile method. In particular, this book tackles the difficult aspects of agile development: the need for cooperation and trust among team members. Whether you're currently part of an agile team, working with an agile team, or interested in agile development, this book provides the practical tips you need to start practicing agile development. As your experience grows, the book will grow with you, providing exercises and information that will teach you first to understand the rules of agile development, break them, and ultimately abandon rules altogether as you master the art of agile development."Jim Shore and Shane Warden expertly explain the practices and benefits of Extreme Programming. They offer advice from their real-world experiences in leading teams. They answer questions about the practices and show contraindications - ways that a practice may be mis-applied. They offer alternatives you can try if there are impediments to applying a practice, such as the lack of an on-site customer.–Ken Pugh, Author of Jolt Award Winner, Prefactoring "I will leave a copy of this book with every team I visit."–Brian Marick, Exampler Consulting
Keywords: IMPORTANT

A Leader’s Framework for Decision Making - Snowden, Dave; Boone, Mary E. (Harvard Business Review, 2007)

The Knowledge-Creating Company - Nonaka, Ikujiro (Harvard Business Review, 2007)
Editor’s Note: This 1991 article helped popularize the notion of “tacit” knowledge—the valuable and highly subjective insights and intuitions that are difficult to capture and share because people carry them in their heads. Years later, the piece can still startle a reader with its views of organizations and of the types of knowledge that inform […]
Keywords: Creativity; Innovation; Product development; Research & development

Responding to change: Learning to adapt in development cooperation - Engel, Paul; Keijzer, Niels; Ørnemark, Charlotte (ECDPM, 2007)

Good Enough Governance Revisited - Grindle, Merilee S. (Development Policy Review, 2007)
The concept of good enough governance provides a platform for questioning the long menu of institutional changes and capacity-building initiatives currently deemed important (or essential) for development. Nevertheless, it falls short of being a tool to explore what, specifically, needs to be done in any real world context. Thus, as argued by the author in 2004, given the limited resources of money, time, knowledge, and human and organisational capacities, practitioners are correct in searching for the best ways to move towards better governance in a particular country context. This article suggests that the feasibility of particular interventions can be assessed by analysing the context for change and the implications of the content of the intervention being considered.

Adaptive Management for International Development Programs - Loveridge, Donna (2007)
Capacity development, that is “the process whereby people, organisations and society as a whole unleash, strengthen, create, adapt and maintain capacity over time” (OECD 2005) has been a key aim of international aid programs. However, capacity development efforts have not met with resounding success despite approximately 25%, or USD15 billion a year, being spent by donors in recent years on technical assistance1 which has predominantly been aimed at developing capacity. A 1998 review by the World Bank (World Bank 1998) found that the success rate for capacity development efforts was between 30 – 40%. The Commission for Africa (2005) noted in 2005 that achievements were below expectations. The OECD (2007) sees capacity development as being one of the areas which are least responsive to development assistance and therefore one of the greatest challenges. This paper proposes that development practitioners and donors could benefit from taking an evaluative inquiry-type of approach to the design, implementation and monitoring and evaluation of capacity development programs. An alternative approach, “adaptive management”, is proposed. Adaptive management moves away from a rational linear A + B = C approach to capacity development towards constructing and testing theories of change2 for knowledge generation, adaptation and program improvement.

Using Emergence to Take Social Innovation to Scale - Wheatley, Margaret; Frieze, Deborah (The Shambhala Institute, 2007)
In spite of current ads and slogans, the world doesn’t change one person at a time. It changes as networks of relationships form among people who discover they share a common cause and vision of what’s possible. This is good news for those of us intent on changing the world and creating a positive future. Rather than worry about critical mass, our work is to foster critical connections. We don’t need to convince large numbers of people to change; instead, we need to connect with kindred spirits. Through these relationships, we will develop the new knowledge, practices, courage, and commitment that lead to broad-based change. But networks aren’t the whole story. As networks grow and transform into active, working communities of practice, we discover how Life truly changes, which is through emergence. When separate, local efforts connect with each other as networks, then strengthen as communities of practice, suddenly and surprisingly a new system emerges at a greater level of scale. This system of influence possesses qualities and capacities that were unknown in the individuals. It isn’t that they were hidden; they simply don’t exist until the system emerges. They are properties of the system, not the individual, but once there, individuals possess them. And the system that emerges always possesses greater power and influence than is possible through planned, incremental change. Emergence is how Life creates radical change and takes things to scale. Emergence has a life-cycle. It begins with networks, shifts to intentional communities of practice and evolves into powerful systems capable of global influence. Since its inception in 1992, The Berkana Institute has striven to learn how living systems work, how they emerge from networks to communities to systems of influence. In our global work—primarily with economically poor communities in many different nations—we have experimented actively with emergence in many different contexts. We have demonstrated what’s possible when we connect people across difference and distance. By applying the lessons of living systems and working intentionally with emergence and its life-cycle, we have become confident that local social innovations can be taken to scale and provide solutions to many of the world’s most intractable issues.

Reframing Complexity: A Four-Dimensional Approach to Organizational Diagnosis, Development and Change - Gallos, Joan V. (Organization Development: A Jossey-Bass Reader, 2006)
This is the third book in the Jossey–Bass Reader series, Organization Development: A Jossey–Bass Reader. This collection will introduce the key thinkers and contributors in organization development including Ed Lawler, Peter Senge, Chris Argyris, Richard Hackman, Jay Galbraith, Cooperrider, Rosabeth Moss Kanter, Bolman & Deal, Kouzes & Posner, and Ed Schein, among others. "Without reservations I recommend this volume to those students of organizational behavior who want an encyclopedia of OD to gain a perspective on the past, present, and future...." Jonathan D. Springer of the American Psychological Association.

Resilience Thinking: Sustaining Ecosystems and People in a Changing World - Walker, Brian; Salt, David; Reid, Walter V. (Island Press, 2006)
Increasingly, cracks are appearing in the capacity of communities, ecosystems, and landscapes to provide the goods and services that sustain our planet's well-being. The response from most quarters has been for "more of the same" that created the situation in the first place: more control, more intensification, and greater efficiency. "Resilience thinking" offers a different way of understanding the world and a new approach to managing resources. It embraces human and natural systems as complex entities continually adapting through cycles of change and seeks to understand the qualities of a system that must be maintained or enhanced in order to achieve sustainability. It explains why greater efficiency by itself cannot solve resource problems and offers a constructive alternative that opens up options rather than closing them down. In "Resilience Thinking", scientist Brian Walker and science writer David Salt present an accessible introduction to the emerging paradigm of resilience. The book arose out of appeals from colleagues in science and industry for a plainly written account of what resilience is all about and how a resilience approach differs from current practices. Rather than complicated theory, the book offers a conceptual overview along with five case studies of resilience thinking in the real world. It is an engaging and important work for anyone interested in managing risk in a complex world.

Herramientas de Conocimiento y Aprendizaje: Una Guía para Organizaciones Humanitarias y de Desarrollo - Ramalingam, Ben (ODI, 2006)
This toolkit presents entry points and references to the wide range of tools and methods that have been used to facilitate improved knowledge and learning in the development and humanitarian sectors.
Keywords: spanish

Tools for Knowledge and Learning: A Guide for Development and Humanitarian Organisations - Ramalingam, Ben (ODI, 2006)
This toolkit presents entry points and references to the wide range of tools and methods that have been used to facilitate improved knowledge and learning in the development and humanitarian sectors.

Agile Software Development: Adaptive Systems Principles and Best Practices - Meso, Peter; Jain, Radhika (Information Systems Management, 2006)
Today's environments of increasing business change require software development methodologies that are more adaptable. This article examines how complex adaptive systems (CAS) theory can be used to increase our understanding of how agile software development practices can be used to develop this capability. A mapping of agile practices to CAS principles and three dimensions (product, process, and people) results in several recommendations for “best practices” in systems development.
Keywords: IMPORTANT

Alps - Accountability, Learning and Planning System - ActionAid (ActionAid International, 2006)
Alps is ActionAid’s over arching accountability framework, containing within it our programme planning system. Alps is distinctive in that it is strongly driven by principles, and sets out necessary personal attitudes and behaviours alongside organisational processes for planning, strategy formulation, learning, monitoring reviews/evaluations and audit. Alps defines our standards, not only about what we do but also how we do it. Alps is part of ActionAid’s human rights-based work.

Planners versus Searchers in Foreign Aid - Easterly, William (Asian Development Review, 2006)
Only for the recipients of foreign aid is something akin to central planning seen as a way to achieve prosperity. The end of poverty is achieved with free markets and democracy—where decentralized “searchers” look for ways to meet individual needs—not Poverty Reduction Strategy Papers (PRSPs) to achieve Millennium Development Goals (MDGs). The PRSPs and MDGs create lots of bureaucracy but hold no one specific agency in foreign aid accountable for any one specific task. Planners in foreign aid use the old failed models of the past—the “Financing Gap”, the “poverty trap”, the government-to-government aid model; and the “expenditures = outcomes” mentality. Searchers in foreign aid would imitate the feedback and accountability of markets and democracy to provide goods and services to individuals until homegrown markets and democracy end poverty in the society as a whole. An example of the more promising “searchers” approach in foreign aid is 2006 Nobel Peace Laureate Mohammad Yunus and Grameen Bank.

Information and Communications Technology for Development (ICT4D)-A design challenge? - Tongia, Rahul; Subrahmanian, Eswaran (2006 International Conference on Information and Communication Technologies and Development, 2006)
Keywords: IMPORTANT

The Samaritan's Dilemma: The Political Economy of Development Aid - Gibson, Clark C.; Andersson, Krister; Ostrom, Elinor; Shivakumar, Sujai (Oxford University Press, 2005)
What's wrong with foreign aid? Many policymakers, aid practitioners, and scholars have called into question its ability to increase economic growth, alleviate poverty, or promote social development. At the macro level, only tenuous links between development aid and improved living conditions have been found. At the micro level, only a few programs outlast donor support and even fewer appear to achieve lasting improvements. The authors of this book argue that much of aid's failure is related to the institutions that structure its delivery. These institutions govern the complex relationships between the main actors in the aid delivery system and often generate a series of perverse incentives that promote inefficient and unsustainable outcomes. In their analysis, the authors apply the theoretical insights of the new institutional economics to several settings. First, they investigate the institutions of Sida, the Swedish aid agency, to analyze how that aid agency's institutions can produce incentives inimical to desired outcomes, contrary to the desires of its own staff. Second, the authors use cases from India, a country with low aid dependence, and Zambia, a country with high aid dependence, to explore how institutions on the ground in recipient countries also mediate the effectiveness of aid. Throughout the book, the authors offer suggestions about how to improve aid's effectiveness. These suggestions include how to structure evaluations in order to improve outcomes, how to employ agency staff to gain from their on-the-ground experience, and how to engage stakeholders as "owners" in the design, resource mobilization, learning, and evaluation processes of development assistance programs.

Rapid Results!: How 100-Day Projects Build the Capacity for Large-Scale Change - Schaffer, Robert H.; Ashkenas, Ron (Jossey-Bass, 2005)
Rapid Results! shows how to make large-scale changes succeed by using 100-day results-producing projects to develop this vital implementation capability. Written by Robert H. Schaffer, Ronald N. Ashkenas, and their associates—leaders in the field of change management—Rapid Results! describes an approach that has been field-tested by real organizations of every size and description to improve performance and speed the pace of change. Rapid results projects produce results quickly, introduce new work patterns, and enable participants to learn a variety of lessons about managing change. Step by step, the book describes how the use of rapid-cycle, or 100-day, projects will multiply your organization’s power to succeed at large-scale change. Schaffer and Ashkenas specifically outline the concept behind 100-day projects and show you how to Set up the architecture to implement rapid results projects Improve operational performance and also attain hard results in the soft areas of management Build rapid results into major organizational change such as reorganization, acquisition integration, and international development Use rapid results to drive leadership development and culture change

Management challenges to implementing agile processes in traditional development organizations - Boehm, B.; Turner, R. (IEEE Software, 2005)
Discussions with traditional developers and managers concerning agile software development practices nearly always contain two somewhat contradictory ideas. They find that on small, stand-alone projects, agile practices are less burdensome and more in tune with the software industry's increasing needs for rapid development and coping with continuous change. Managers face several barriers, real and perceived, when they try to bring agile approaches into traditional organizations. They categorized the barriers either as problems only in terms of scope or scale, or as significant general issues needing resolution. From these two categories, we've identified three areas - development process conflicts, business process conflicts, and people conflicts - that we believe are the critical challenges to software managers of large organizations in bringing agile approaches to bear in their projects.
Keywords: Aerospace engineering; Aerospace materials; Agile methods; Agile software development; Automatic testing; Business processes; Computer industry; DP industry; Programming; Project management; Refining; Software engineering; Software management; Software systems; development process conflicts; process integration; software development management; software industry; systems engineering; traditional development organizations

Learning in the Thick of It - Darling, Marilyn; Parry, Charles; Moore, Joseph (Harvard Business Review, 2005)
After-action reviews identify past mistakes but rarely enhance future performance. Companies wanting to fully exploit this tool should look to its master: the U.S. Army’s standing enemy brigade, where soldiers learn and improve even in the midst of battle.
Section: Meeting management
Keywords: Aerospace sector; Corporate governance; Decision making and problem solving; Defense industry; Defense sector; Fabrication and manufacturing; Meeting management; Military; North America; Organizational culture; Presentation skills; Project management; Psychology; Telecom

Your Company’s Secret Change Agents - Pascale, Richard T.; Sternin, Jerry (Harvard Business Review, 2005)
Somewhere in your organization, groups of people are already doing things differently and better. To create lasting change, find these areas of positive deviance and fan their flames.

Accountability Myopia: Losing Sight of Organizational Learning - Ebrahim, Alnoor (Nonprofit and Voluntary Sector Quarterly, 2005)
This article challenges a normative assumption about accountability in organizations: that more accountability is necessarily better. More specifically, it examines two forms of “myopia” that characterize conceptions of accountability among service-oriented nonprofit organizations: (a) accountability as a set of unconnected binary relationships rather than as a system of relations and (b) accountability as short-term and rule-following behavior rather than as a means to longer-term social change. The article explores the effects of these myopias on a central mechanism of accountability in organizations—evaluation—and proposes a broader view of accountability that includes organizational learning. Future directions for research and practice are elaborated.
Keywords: IMPORTANT

Organisational Learning in NGOs: Creating the motive, means and opportunity - Britton, Bruce (Intrac, 2005)
OCLC: 474871294

Donors' Learning Difficulties: Results, Relationships and Responsibilities - Eyben, Rosalind (IDS Bulletin, 2005)

The power of positive deviance - Marsh, David R; Schroeder, Dirk G; Dearden, Kirk A; Sternin, Jerry; Sternin, Monique (BMJ : British Medical Journal, 2004)
Identifying individuals with better outcome than their peers (positive deviance) and enabling communities to adopt the behaviours that explain the improved outcome are powerful methods of producing change

A Treatise on Efficacy: Between Western and Chinese Thinking - Jullien, Francois (University of Hawaii Press, 2004)
In this highly insightful analysis of Western and Chinese concepts of efficacy, Francois Jullien subtly delves into the metaphysical preconceptions of the two civilizations to account for diverging patterns of action in warfare, politics, and diplomacy. He shows how Western and Chinese stategies work in several domains (the battle-field, for example) and analyzes two resulting acts of war. The Chinese strategist manipulates his own troops and the enemy to win a battle without waging war and to bring about victory effortlessly. Efficacity in China is thus conceived of in terms of transformation (as opposed to action) and manipulation, making it closer to what is understood as efficacy in the West. Jullien's brilliant interpretations of an array of recondite texts are key to understanding our own conceptions of action, time, and reality in this foray into the world of Chinese thought. In its clear and penetrating characterization of two contrasting views of reality from a heretofore unexplored perspective, Treatise on Efficacy will be of central importance in the intellectual debate between East and West.

Complexity, Organizations and Change - McMillan, Elizabeth (Routledge, 2004)
Complexity science has seriously challenged long-held views in the scientific community about how the world works. These ideas, particularly about the living world, also have radical and profound implications for organizations and society as a whole. Available in paperback for the first time, this insightful book describes and considers ideas from complexity science and examines their use in organizations, especially in bringing about major organizational change. Author McMillan explores how organizations, their design, the way they operate and, importantly, the people who co-create them, are thought of.Explaining the history and development of complexity science in an accessible way for the non-scientific reader, this outstanding book describes key concepts and their use in theory and practice. Illustrated with real-life examples from organizations in the UK, Europe and the USA, the book includes an in-depth case study of an organization which used complexity principles as part of a strategic change intervention. From this, useful models for introducing a complexity-based change process are derived.Complexity, Organizations and Change will appeal to academics, researchers and advanced students who are interested in complexity science and what it means for strategy, organization and management theory and organizational change.

The Toyota Way: 14 Management Principles from the World's Greatest Manufacturer - Liker, Jeffrey K. (McGraw-Hill, 2004)
How to speed up business processes, improve quality, and cut costs in any industryIn factories around the world, Toyota consistently makes the highest-quality cars with the fewest defects of any competing manufacturer, while using fewer man-hours, less on-hand inventory, and half the floor space of its competitors. The Toyota Way is the first book for a general audience that explains the management principles and business philosophy behind Toyota's worldwide reputation for quality and reliability.Complete with profiles of organizations that have successfully adopted Toyota's principles, this book shows managers in every industry how to improve business processes by:Eliminating wasted time and resources Building quality into workplace systems Finding low-cost but reliable alternatives to expensive new technology Producing in small quantities Turning every employee into a quality control inspector

System Failure: Why Governments Must Learn to Think Differently - Chapman, Jake (Demos, 2004)
The current model of public policy-making is no longer right for a government that has set itself the challenge of delivery. Improvements are driven by central policy initiatives which assume a direct relationship between action and outcome - but this is a false assumption. Public services are complex adaptive systems which are subject to the law of unintended consequences, so intervention can make problems worse. That is why the carrot-and-stick approach to reform which links increased funding to tougher performance targets will not succeed in the long run. Renowned systems thinker Jake Chapman describes how government's energetic attempts to force change from the centre are becoming counter-productive. The alternative is government based on continuous learning. This is increasingly important as the impact of communication technology and other accelerating social trends offers a moving target for public service reformers. Systems thinking offers a better model for change in complex organisations such as the health service or the railway network. Case studies provided by the NHS confederation show the unintended and often bizarre consequences of introducing new policies without considering their impact on the whole system. Since the original publication of Systems Failure in 2002, many of its core ideas have been taken on by government. In this second edition, Chapman reflects on the experience of putting systems thinking into practice in public services, and explains why the changes he suggests are more difficult - and more urgent - than expected.

ALPS in action: a review of the shift in ActionAid towards a new Accountability, Learning and Planning System | Participatory Methods - Guijt, Irene (2004)

Iterative and incremental developments: A brief history - Larman, Craig; Basili, Victor R. (Computer, 2003)
Although many view iterative and incremental development as a modern practice, its application dates as far back as the mid-1950s. Prominent software-engineering thought leaders from each succeeding decade supported IID practices, and many large projects used them successfully. These practices may have differed in their details, but all had a common theme-to avoid a single-pass sequential, document-driven, gated-step approach.
Keywords: Agile methods; Application software; Feedback; Government; History; Iterative and incremental developments; Iterative methods; Personnel; Programming; Radio access networks; Terminology; Testing; iterative enhancement; software engineering; software system

The high cost of accurate knowledge - Sutcliffe, Kathleen M.; Weber, Klaus (Harvard Business Review, 2003)
Many business thinkers believe it's the role of senior managers to scan the external environment to monitor contingencies and constraints, and to use that precise knowledge to modify the company's strategy and design. As these thinkers see it, managers need accurate and abundant information to carry out that role. According to that logic, it makes sense to invest heavily in systems for collecting and organizing competitive information. Another school of pundits contends that, since today's complex information often isn't precise anyway, it's not worth going overboard with such investments. In other words, it's not the accuracy and abundance of information that should matter most to top executives–rather, it's how that information is interpreted. After all, the role of senior managers isn't just to make decisions; it's to set direction and motivate others in the face of ambiguities and conflicting demands. Top executives must interpret information and communicate those interpretations–they must manage meaning more than they must manage information. So which of these competing views is the right one? Research conducted by academics Sutcliffe and Weber found that how accurate senior executives are about their competitive environments is indeed less important for strategy and corresponding organizational changes than the way in which they interpret information about their environments. Investments in shaping those interpretations, therefore, may create a more durable competitive advantage than investments in obtaining and organizing more information. And what kinds of interpretations are most closely linked with high performance? Their research suggests that high performers respond positively to opportunities, yet they aren't overconfident in their abilities to take advantage of those opportunities.
Keywords: Administrative Personnel; Data Collection; Decision Making; Organizational; Economic Competition; Information Management; Investments; Marketing; Organizational Innovation; United States

Most egovernment-for-development projects fail: how can risks be reduced? - Heeks, Richard (Institute for Development Policy and Management, 2003)
Research on the Information Society, the Digital Divide and Information and Communication Technologies for development

The new dynamics of strategy: Sense-making in a complex and complicated world - Kurtz, C.F.; Snowden, Dave (IBM Systems Journal, 2003)
Keywords: IMPORTANT

Development and the Learning Organization - Roper, Laura; Pettit, Jethro; Eade, Deborah (Oxfam Publications, 2003)

Should development agencies have official views? - Ellerman, David (Development in Practice, 2002)

Development and the Learning Organisation: An introduction - Roper, Laura; Pettit, Jethro (Development in Practice, 2002)

The struggle for organisational change: how the ActionAid Accountability, Learning and Planning System emerged - Scott-Villiers, Patta (Policy & Practice, 2002)
Change is driven not only by good ideas, but also by disagreement and frustration. This article takes the reader through a selective organisational history of the British NGO ActionAid from 1998 to 2001, looking at events and changes that had a bearing on the

Information Systems and Developing Countries: Failure, Success, and Local Improvisations - Heeks, Richard (The Information Society, 2002)
This article presents evidence that–alongside the successes– many information systems in developing countries can be categorized as failing either totally or partially. It then develops a new model that seeks to explain the high rates of failure. The model draws on contingency theory in order to advance the notion of design-actuality gaps: the match or mismatch between IS designs and local user actuality. This helps identify two high-risk archetypes that affect IS in developing countries: country context gaps and hard-soft gaps. The model is also of value in explaining the constraints that exist to local IS improvisations in developing countries. Overall, the article shows how model and theory help understand IS cases in developing countries, and equally, how those cases provide valuable data to help develop IS models and theories.
Keywords: Developing Country; Evaluation; Failure; Information System; implementation

Failure, Success and Improvisation of Information Systems Projects in Developing Countries - Heeks, Richard (Institute for Development Policy and Management, 2002)
Research on the Information Society, the Digital Divide and Information and Communication Technologies for development

A trainer's guide for participatory learning and action - Pretty, Jules; Guijt, Irene (2002)

The Blind Man and the Elephant: Analysing the Local State in China - Saich, Tony (On the Roots of Growth and Crisis: Capitalism, State and Society in East Asia, 2002)

Supporting Pioneering Leaders as Communities of Practice - How to Rapidly Develop New Leaders in Great Numbers - Wheatley, Margaret J (The Berkana Institute, 2002)
Do you ever stand back and try to see the big picture, the view from 50,000 feet of what's going on in organizations, communities, the world? From up there, how would you describe these times? Is it a time of increasing economic and political instability, of growing divisiveness and fear, of failing systems and dying dreams? Is it a time of new possibilities, of great examples of hope, of positive human evolution, of transformation? Are we succeeding in solving major problems, are we creating more? Is it any of these things, is it all of these things? It's important to think about how we answer this question, because that answer affects our choice of actions. If we think that, generally, things are working, that at present we're going through a difficult but temporary downturn, then we don't question current systems or their operating assumptions. Instead, we work hard to revive and improve them. We support initiatives and programs focused on process improvements, developing present systems to work more effectively and more efficiently. If we believe that the old system cannot be repaired, if we expect to see only more system failures, then the work is not to fix. Instead, support needs to be given to radically different processes and methods, new systems based on new assumptions. The work becomes not process improvement but process revolution.

Evaluation Feedback for Effective Learning and Accountability - OECD (OECD, 2001)
Evaluation is a key tool in improving the quality and effectiveness of development co-operation. The Development Assistance Committee (DAC) Working Party in Aid Evaluation is the only international forum where bilateral and multilateral evaluation experts meet regularly. Its Members meet to improve evaluation practice and to learn lessons from development co-operation activities and experiences. A series "Evaluation and Aid Effectiveness" was launched to share selected pieces of work with a broader public. This publication is composed of two parts: The Workshop Report, based on the fore-mentioned meeting, highlights the various issues raised, topics of discussion and different feedback systems, and outlines the areas identified by participants as most relevant for improving evaluation feedback. The Background Synthesis Report, intended as a starting point for discussion at the workshop, outlines the main concerns and challenges facing evaluation feedback and the means to address these. The report is based on an analysis of questionnaire results, and a review of previous initiatives in this area. The print version of the above report is available free of charge from the Development Co-operation Directorate; please send an email to dac.contact@oecd.org to get a copy.
Google-Books-ID: kA39FghYYUgC

The Soul in the Computer: The Story of a Corporate Revolutionary - Waugh, Barbara (Inner Ocean Publishing, 2001)
When Barbara Waugh joined the Hewlett-Packard Corporation in the mid-80's, this 60's radical encountered a company with a benign but topdown leadership. As she progressed from recruiting manager to world change manager, she used a set of radical tools to transform its corporate culture and to help realize the true potential of The HP Way.

Notes to Accompany ALPS - ActionAid (ActionAid International, 2001)

Manifesto for Agile Software Development - Agile Alliance (Agile Alliance, 2001)

Outcome Mapping: Building Learning and Reflection into Development Programs - Earl, Sarah; Carden, Fred; Smutylo, Terry; Patten, Michael Quinn (IDRC Books, 2001)
"Outcome Mapping provides not only a guide to essential evaluation map-making, but also a guide to learning and increased effectiveness, and affirmation that being attentive along the journey is as important as, and critical to, arriving at a destination." - Michael Quinn PattonMore and more, development organizations are under pressure to demonstrate that their programs result in significant and lasting changes in the well-being of their intended beneficiaries. However, such "impacts" are often the product of a confluence of events for which no single agency or group of agencies can realistically claim full credit. As a result, assessing development impacts is problematic, yet many organizations continue to struggle to measure results far beyond the reach of their programs. "Outcome Mapping" recognizes that development is essentially about people relating to each other and their environment. The originality of this approach lies in its shift away from assessing the products of a program to focus on changes in behaviour, relationships, actions, and activities in the people, groups, and organizations it works with directly. In doing so, "Outcome Mapping" debunks many of the myths about measuring impact. It will help a program be specific about the actors it targets, the changes it expects to see, and the strategies it employs and, as a result, be more effective in terms of the results it achieves. This publication explains the various steps in the outcome mapping approach and provides detailed information on workshop design and facilitation. It includes numerous worksheets and examples.

Positive Deviant - Dorsey, David (Fast Company, 2000)
Jerry Sternin’s job was to help save starving children in Vietnam. Faced with an impossible time frame, he adopted a radical approach to making change. His idea: Real change begins from the inside.

Spiral Development: Experience, Principles, and Refinements - Boehm, B. W. (Carnegie Mellon University, 2000)

Adaptive Software Development: A Collaborative Approach to Managing Complex Systems - Highsmith, Jim (Dorset House Publishing, 2000)
In today's turbulent e-business world, software project teams that survive and thrive won't be those that continue their traditions of optimization, efficiency, and control, but those that exhibit adaptability, speed, and collaboration. Adaptive Software Development is targeted at software teams where competition creates extreme pressure on the delivery process. Four goals of the book are * to support an adaptive culture in which change and uncertainty are assumed to be the natural state * to introduce frameworks to guide the iterative process of managing change * to institute collaboration, the interaction of people on interpersonal, cultural, and structural levels * to add rigor and discipline to the RAD approach, making it scalable to the uncertainty and complexity of real-world undertakings. This innovative text, grounded in the science of complex adaptive systems theory, offers a practical, realistic approach to managing the high-speed, high-change projects characteristic of our highly uncertain economy.

Accountability Learning and Planning System - ActionAid (ActionAid International, 2000)

Learning in Development Co-operation - Carlsson, Jerker; Wohlgemuth, Lennart (Almqvist & Wiksell International, 2000)
Google-Books-ID: guMkAQAAIAAJ

Evaluating the ‘logical framework approach’ towards learning-oriented development evaluation - Gasper, Des (Public Administration and Development, 2000)
The logical framework approach has spread enormously, including increasingly to stages of review and evaluation. Yet it has had little systematic evaluation itself. Survey of available materials indicates several recurrent failings, some less easily countered than others. In particular: focus on achievement of intended effects by intended routes makes logframes a very limiting tool in evaluation; an assumption of consensual project objectives often becomes problematic in public and inter-organizational projects; and automatic choice of an audit form of accountability as the priority in evaluations can be at the expense of evaluation as learning.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/1099-162X%28200002%2920%3A1%3C17%3A%3AAID-PAD89%3E3.0.CO%3B2-5

Strategic Management and Organisational Dynamics: The Challenge of Complexity - Stacey, Ralph D. (Pitman, 2000)
In the third edition of this successful text, Ralph Stacey continues to question the view that organisations operate and succeed in relatively stable environments. He argues that in order to succeed in uncertainty and continual change, organisations need to create new perspectives and learn from the chaos within which they operate. This edition continues to focus on this radically different approach to strategic management. The central tenets of this approach have to do with unpredictability and the limitations of control, and therefore it argues against the rational models of planning and control covered in other strategy textbooks. This is done by emphasising the importance of narrative, conversation and learning from one's own experience as the central means by which we can gain understanding and knowledge of strategy in organisations. - Sharper distinction between systemic and process thinking with new chapters on the philosophical origins of systems and process thinking, second order and critical system thinking. - new material on theory of complex responsive processes, particularly to do with control, leadership and ethics. - Includes 7 management narratives, ie, personal ac
Google-Books-ID: z7haAAAAYAAJ
Keywords: Organizational Behavior; Strategic Planning

Theory of Constraints - Goldratt, Eliyahu M. (North River Pr, 1999)
Theory of Constraints walks you through the crucial stages of a continuous program: the five steps of focusing; the process of change; how to prove effect-cause-effect; and how to invent simple solutions to complex problems. Equally important, the author reveals the devastating impact that an organization's psychology can have on the process of improvements. Theory of Constraints is a crucial document for understanding what it takes to achieve manufacturing breakthroughs.

Appraising Adaptive Management - Lee, Kai (Conservation Ecology, 1999)
Lee, K. N. 1999. Appraising adaptive management. Conservation Ecology 3(2): 3. https://doi.org/10.5751/ES-00131-030203

Foundations of the After Action Review Process - Morrison, John E; Meliza, Larry L (Army Research Institute, 1999)
The U.S. Army has adopted the After Action Review AAR as its primary method of providing feedback after unit collective training exercises. The AAR is an interactive discussion in which unit members decide what happened, why it happened, and how to improve or sustain collective performance in future exercises. other services and organizations outside the military are also beginning to employ the AAR as a feedback tool. This report describes the twenty-five year history of AAR research and development and the major behavioral research areas contributing to AAR development and refinement. In addition, this report defines goals for future AAR research.
Section: Technical Reports

Harnessing Complexity: Organizational Implications of a Scientific Frontier - Axelrod, Robert M.; Cohen, Michael D. (Free Press, 1999)
Recent advances in the study of complexity have given scientists profound new insights into how natural innovation occurs and how its power can be exploited. Now two pioneers in the field, Robert Axelrod and Michael D. Cohen, provide leaders in business and government with a guide to complexity that will help them make effective decisions in a world of rapid change. Building on evolutionary biology, computer science, and social design, Axelrod and Cohen have constructed a unique framework for improving the way people work together. Their approach to management is based on the concept of the Complex Adaptive System, which can describe everything from rain forests to the human gene pool, and from automated software agents to multinational companies. The authors' framework reveals three qualities that all kinds of managers must cultivate in their organization: "Variation" What is the best way to manage the development of software? Should the problem be broken up into small pieces for programmers working independently, thus enhancing variation, or should there be a centralized hierarchy of programmers ruled by a chain of command? The authors show how the decentralized creation of variation combined with the centralized maintenance of standards was the key to the success of the Linux "open source software" project, which brought together thousands of volunteers in cyberspace to produce an operating system that can outperform Microsoft's. "Interaction" Why did northern Italy prosper while southern Italy remained poor? Recognizing the internal interactions of a Complex Adaptive System – be it a national region, a company, or a nonprofit group – reveals vitalnetworks of trust. Axelrod and Cohen explain that in successful adaptive systems, rich networks of horizontal linkages foster cooperation and provide an advantage over other less cooperatively networked groups. In the case of Italy, voluntary associations created networks of trust in the Middle Ages that became northern Italy's critical advantage over the south. "Selection" Is a Pulitzer Prize better than a National Book Award? How can foundations and corporations design competitions that have a positive effect on the evolution of excellence? The authors' framework makes clear that the worst selection processes are mired in orthodox standards that have not adapted to a new environment. The best selection processes, on the other hand, are created and run by leaders who understand how the standards they use can transform their organization and its environment. This simple, paradigm-shifting analysis of how people work together will transform the way we think about getting things done in a group. "Harnessing Complexity" is the essential guide to creating wealth, power, and knowledge in the 21st century.
Google-Books-ID: zR8HRAAACAAJ
Keywords: Organizational Behavior

Adaptive Management - Bormann, B.T.; Martin, J.R.; Wagner, F.H.; Wood, G.W.; Alegria, J. (Ecological stewardship: a common reference for ecosystem management, 1999)
Wagner
Google-Books-ID: a5vuAAAAMAAJ
Keywords: Conservation of natural resources; Ecology; Ecosystem management; Ecosystem management - United States; Environmental Science; Environmental management; Wildlife

Introduction to Systems Thinking - Kim, Daniel H (Pegasus Communications, 1999)

PLA Notes 32: Participation, Literacy and Empowerment - PLA (IIED, 1998)

Development as Process: Concepts and Methods for Working with Complexity - Mosse, David; Farrington, John; Rew, Alan (Routledge, 1998)
Process" approaches to economic and social development appear to be more flexible and offer greater prospects of success than traditional "project" methods. Development as Process addresses the questions raised by the different natures of the two approaches. The authors examine development projects through experience in water resources development in India and in organizational learning by a Bangladeshi NGO. Inter-agency contexts are examined in the setting of an aquaculture project in Bangladesh and in the setting of agriculture and natural resources development in Rajisthan, India. Finally, the role of process monitoring is explained in the context of policy reform, with illustrations from forestry in India and land reform in Russia.
Google-Books-ID: baVE8SzJkNMC
Keywords: Demography; Economic Development; Sociology

Finding out fast: investigative skills for policy and development - Thomas, Alan; Chataway, Joanna; Wuyts, Marc (Sage, 1998)

Complexity Rising: From Human Beings to Human Civilization, a Complexity Proﬁle - Bar-Yam, Yaneer (New England Complex Systems Institute, 1997)
It is generally recognized that life is becoming more complex. This article analyzes the human social environment using the "complexity proﬁle," a mathematical tool for characterizing the collective behavior of a system. The analysis is used to justify the qualitative observation that complexity of existence has increased and is increasing. The increase in complexity is directly related to sweeping changes in the structure and dynamics of human civilization—the increasing interdependence of the global economic and social system, and the instabilities of dictatorships, communism and corporate hierarchies. Our complex social environment is consistent with identifying global human civilization as an organism capable of complex behavior that protects its components (us) and which should be capable of responding eﬀectively to complex environmental demands.

Changing the way we change - Pascale, R.; Millemann, M.; Gioja, L. (Harvard Business Review, 1997)
More and more companies struggle with growing competition by introducing improvements into every aspect of performance. But the treadmill keeps moving faster, the companies keep working harder, and results improve slowly or not at all. The problem here is not the improvement programs. The problem is that the whole burden of change typically rests on so few people. Companies achieve real agility only when every function and process–when every person–is able and eager to rise to every challenge. This type and degree of fundamental change, commonly called revitalization or transformation, is what many companies seek but rarely achieve because they have never before identified the factors that produce sustained transformational change. The authors identify three interventions that will restore companies to vital agility and then keep them in good health: incorporating employees fully into the principal business challenges facing the company, leading the organization in a different way in order to sharpen and maintain incorporation and constructive stress, and instilling mental disciplines that will make people behave differently and then help them sustain their new behavior. The authors discovered these basic sources of revitalization by tracking the change efforts of Sears, Roebuck & Company, Royal Dutch Shell, and the United States Army. The organizations used these interventions to alter the way their people experienced their own power and identity, as well as the way they dealt with conflict and learning. As at Sears, Shell, and the U.S. Army, any major shift in those four elements will create a landmark shift in any organization's operating state or culture.
Keywords: Commerce; Conflict (Psychology); Decision Making; Organizational; Economic Competition; Leadership; Military Personnel; Organizational Culture; Organizational Innovation; Personnel Management; Power; Psychology; United States

Messy, Exciting, and Anxiety-Ridden: Adaptive Software Development - Highsmith, Jim (American Programmer, 1997)

Whose Reality Counts? Putting the First Last - Chambers, Robert (ITDG Publishing, 1997)
In this sequel to "Rural Development: Putting the last first" Robert Chambers argues that central issues in development have been overlooked, and that many past errors have flowed from domination by those with power.Development professionals now need new approaches and methods forinteracting, learning and knowing. Through analyzing experience - of past mistakes and myths, and of the continuing methodological revolution of PRA (participatory rural appraisal) - the author points towards solutions.In many countries, urban and rural people alike have shown an astonishing ability to express and analyze their local, complex and diverse realities which are often at odds with the top-down realities imposed by professionals. The author argues that personal, professional and institutional change is essential if the realities of the poor are to receive greater recognition. Self-critical awareness and changes in concepts, values, methods and behaviour must be developed to explore the new high ground of participation and empowerment."Whose Reality Counts?" presents a radical challenge to all concernedwith development, whether practitioners, researchers or policy-makers, in all organizations and disciplines, and at all levels from fieldworkers to the heads of agencies. With its thrust of putting the first last it presents a new, exciting and above all practical agenda for future development which cannot be ignored.

Learning to Plan–and Planning to Learn - Michael, Donald N. (Miles River Press, 1997)
Don Michael says that, yes, the world can meet future social and organizational challenges - but only if we learn to plan in order– to live uncertainty– to learn from mistakes, actually embrace error– to do goal setting that is future-responsive– to lower barriers by spanning boundaries– to improve personal interaction– to overcome resistance to learning and change.This book treats planning as the way for persons, organizations, and societies to learn their way into the future. It reveals the complex and unavoidable social psychological resistances to learning that must be overcome by competent citizenry in order to plan for the future. A viable ecology, Third World development, new-city building, democratic government in a turbulent society – all depend on the anticipation of future conditions and on planning to meet these conditions.
Google-Books-ID: nJ2ePwAACAAJ
Keywords: Social science

NGO Accountability: A Conceptual Framework - Najam, Adil (Development Policy Review, 1996)

Adaptive management: Promises and pitfalls - McLain, Rebecca J.; Lee, Robert G. (Environmental Management, 1996)
Proponents of the scientific adaptive management approach argue that it increases knowledge acquisition rates, enhances information flow among policy actors, and provides opportunities for creating shared understandings. However, evidence from efforts to implement the approach in New Brunswick, British Columbia, Canada, and the Columbia River Basin indicates that these promises have not been met. The data show that scientific adaptive management relies excessively on the use of linear systems models, discounts nonscientific forms of knowledge, and pays inadequate attention to policy processes that promote the development of shared understandings among diverse stakeholders. To be effective, new adaptive management efforts will need to incorporate knowledge from multiple sources, make use of multiple systems models, and support new forms of cooperation among stakeholders.

Calvin and Hobbes on Learning - Wattersho, Bill (1995)

What Barriers? What Bridges? - Holling, C.S. (Barriers and Bridges to the Renewal of Ecosystems and Institutions, 1995)
This volume uses a series of case studies to test an emerging theory of complex adaptive systems that forms the basis for explaining the interrelated dynamics of ecosystems, institutions and society. It deals equally with institutional organization and ecosystem structure.

Growth of human factors in application development - Cockburn, Alistair (Humans and Technology Technical Report, 1995)

Learning to Learn: Improving International Governance - Haas, Peter M.; Haas, Ernst B. (Global Governance, 1995)

The Knowledge-creating Company: How Japanese Companies Create the Dynamics of Innovation - Nonaka, Ikujirō; Nonaka, Ikujir o; Ikujiro, Nonaka; Nonaka, Professor of Knowledge Ikujiro; Takeuchi, Hirotaka; Takeuchi, Both Professors of Management at the Institute of Business Research Hirotaka (Oxford University Press, 1995)
How have Japanese companies become world leaders in the automotive and electronics industries, among others? What is the secret of their success? Two leading Japanese business experts, Ikujiro Nonaka and Hirotaka Takeuchi, are the first to tie the success of Japanese companies to their ability to create new knowledge and use it to produce successful products and technologies. In The Knowledge-Creating Company, Nonaka and Takeuchi provide an inside look at how Japanese companies go about creating this new knowledge organizationally.The authors point out that there are two types of knowledge: explicit knowledge, contained in manuals and procedures, and tacit knowledge, learned only by experience, and communicated only indirectly, through metaphor and analogy. U.S. managers focus on explicit knowledge. The Japanese, on the other hand, focus on tacit knowledge. And this, the authors argue, is the key to their success–the Japanese have learned how to transform tacit into explicit knowledge. To explain how this is done–and illuminate Japanese business practices as they do so–the authors range from Greek philosophy to Zen Buddhism, from classical economists to modern management gurus, illustrating the theory of organizational knowledge creation with case studies drawn from such firms as Honda, Canon, Matsushita, NEC, Nissan, 3M, GE, and even the U.S. Marines. For instance, using Matsushita's development of the Home Bakery (the world's first fully automated bread-baking machine for home use), they show how tacit knowledge can be converted to explicit knowledge: when the designers couldn't perfect the dough kneading mechanism, a software programmer apprenticed herself with the master baker at Osaka International Hotel, gained a tacit understanding of kneading, and then conveyed this information to the engineers. In addition, the authors show that, to create knowledge, the best management style is neither top-down nor bottom-up, but rather what they call "middle-up-down," in which the middle managers form a bridge between the ideals of top management and the chaotic realities of the frontline.As we make the turn into the 21st century, a new society is emerging. Peter Drucker calls it the "knowledge society," one that is drastically different from the "industrial society," and one in which acquiring and applying knowledge will become key competitive factors. Nonaka and Takeuchi go a step further, arguing that creating knowledge will become the key to sustaining a competitive advantage in the future. Because the competitive environment and customer preferences changes constantly, knowledge perishes quickly. With The Knowledge-Creating Company, managers have at their fingertips years of insight from Japanese firms that reveal how to create knowledge continuously, and how to exploit it to make successful new products, services, and systems.
Keywords: Entrepreneurship; Knowledge Capital; Leadership

SCRUM Development Process - Sutherland, Jeffrey (Business object design and implementation: OOPSLA '95 workshop proceedings, 1995)
OCLC: 845294232
Keywords: Computer security Congresses; Softwareentwicklung

Complexity: Life at the Edge of Chaos - Lewin, Roger (University of Chicago Press, 1994)
"Put together one of the world's best science writers with one of the universe's most fascinating subjects and you are bound to produce a wonderful book. . . . The subject of complexity is vital and controversial. This book is important and beautifully done."—Stephen Jay Gould"[Complexity] is that curious mix of complication and organization that we find throughout the natural and human worlds: the workings of a cell, the structure of the brain, the behavior of the stock market, the shifts of political power. . . . It is time science . . . thinks about meaning as well as counting information. . . . This is the core of the complexity manifesto. Read it, think about it . . . but don't ignore it."—Ian Stewart, NatureThis second edition has been brought up to date with an essay entitled "On the Edge in the Business World" and an interview with John Holland, author of Emergence: From Chaos to Order.

Complexity: The Emerging Science at the Edge of Order and Chaos - Waldrop, Mitchell M. (Touchstone Press, 1993)
In a rented convent in Santa Fe, a revolution has been brewing. The activists are not anarchists, but rather Nobel Laureates in physics and economics such as Murray Gell-Mann and Kenneth Arrow, and pony-tailed graduate students, mathematicians, and computer scientists down from Los Alamos. They've formed an iconoclastic think tank called the Santa Fe Institute, and their radical idea is to create a new science called complexity. These mavericks from academe share a deep impatience with the kind of linear, reductionist thinking that has dominated science since the time of Newton. Instead, they are gathering novel ideas about interconnectedness, coevolution, chaos, structure, and order - and they're forging them into an entirely new, unified way of thinking about nature, human social behavior, life, and the universe itself. They want to know how a primordial soup of simple molecules managed to turn itself into the first living cell - and what the origin of life some four billion years ago can tell us about the process of technological innovation today. They want to know why ancient ecosystems often remained stable for millions of years, only to vanish in a geological instant - and what such events have to do with the sudden collapse of Soviet communism in the late 1980s. They want to know why the economy can behave in unpredictable ways that economists can't explain - and how the random process of Darwinian natural selection managed to produce such wonderfully intricate structures as the eye and the kidney. Above all, they want to know how the universe manages to bring forth complex structures such as galaxies, stars, planets, bacteria, plants, animals, and brains. There are commonthreads in all of these queries, and these Santa Fe scientists seek to understand them. Complexity is their story: the messy, funny, human story of how science really happens. Here is the tale of Brian Arthur, the Belfast-born economist who stubbornly pushed his theories of economic ch

Building a Learning Organization - Garvin, David A. (Harvard Business Review, 1993)
Beyond high philosophy and grand themes lie the gritty details of practice.

A leaders's guide to after-action reviews - U.S. Army (Department of the Army, 1993)
An after-action review (AAR) is a professional discussion of an event, focused on performance standards, that enables soldiers to discover for themselves what happened, why it happened, and how to sustain strengths and improve on weaknesses. It is a tool leaders and units can use to get maximum benefit from every mission or task. It provides- • Candid insights into specific soldier, leader, and unit strengths and weaknesses from various perspectives. • Feedback and insight critical to battle-focused training. • Details often lacking in evaluation reports alone. Evaluation is the basis for the commander's unit-training assessment. No commander, no matter how skilled, will see as much as the individual soldiers and leaders who actually conduct the training. Leaders can better correct deficiencies and sustain strengths by carefully evaluating and comparing soldier, leader, and unit performance against the standard. The AAR is the keystone of the evaluation process. Feedback compares the actual output of a process with the intended outcome. By focusing on the task's standards and by describing specific observations, leaders and soldiers identify strengths and weaknesses and together decide how to improve their performances. This shared learning improves task proficiency and promotes unit bonding and esprit. Squad and platoon leaders will use the information to develop input for unittraining plans. The AAR is a valid and valuable technique regardless of branch, echelon, or training task. Of course, AARs are not cure-alls for unit-training problems. Leaders must still make on-the-spot corrections and take responsibility for training their soldiers and units. However, AARs are a key part of the training process. The goal is to improve soldier, leader, and unit performance. The result is a more cohesive and proficient fighting force. Because soldiers and leaders participating in an AAR actively discover what happened and why, they learn and remember more than they would from a critique alone. A critique only gives one viewpoint and frequently provides little opportunity for discussion of events by participants. Soldier observations and comments may not be encouraged. The climate of the critique, focusing only on what is wrong, prevents candid discussion of training events and stifles learning and team building.

Compass and Gyroscope: Integrating Science and Politics in the Environment - Lee, Kai N. (Island Press, 1993)
In this original and far-reaching synthesis, Kai N. Lee explains that together science and politics can lead the waytoward the sustainable management of the world’s resources. Rigorous science can act as our compass, pointingus toward greater and more useful knowledge (adaptive management), and practical politics can serve as our gyroscope, keeping usbalanced between competing interest groups. Unlike some approaches to sustainable development, Compass and Gyroscope is refreshingly grounded in the realworld. Lee explains that sustainability cannot occur overnight, we have neither an adequate base of knowledgenor a reliable means of properly implementing and executing management plans. "Sustainable development is not a goal, not a condition likely to be attained on earth as we know it. Rather it is more like freedom or justice,a direction in which we strive..." Using the Columbia River Basin in the Pacific Northwest as a case study, Lee examines the successes andfailures of past and present management. He describes what has been learned, and explains how that experiencecan be applied to environmental management generally. Throughout, the author delves deeply into the theoretical framework behind the real-world experience, exploring how theories of science, politics, and cognitive psychology can be integrated into environmental management.

The Goal: A Process of Ongoing Improvement - Goldratt, Eliyahu M.; Cox, Jeff (North River Press, 1992)
Over 2 million copies sold! Used by thousands of companies and hundreds of business schools! Required reading for anyone interested in the Theory of Constraints. This book, which introduces the Theory of Constraints, is changing how America does business. The Goal is a gripping, fast-paced business novel about overcoming the barriers to making money. You will learn the fundamentals of identifying and solving the problems created by constraints. From the moment you finish the book you will be able to start successfully addressing chronic productivity and quality problems.

Approprite Technologies for Rural Development in India - Blankenbey, Floris P. (Concept Publishing Co, 1991)

America’s Most Successful Export to Japan: Continuous Improvement Programs - Dean M., Schroeder; Robinson, Alan G. (MIT Sloan Management Review, 1991)
CONTINUOUS IMPROVEMENT Programs (CIPs) unleash employee experience and I creativity to improve both products and processes. They are often cited as the most important difference between the Japanese and Western management styles and as a major factor in Japan’s economic success.2Yet the CIP was conceived, developed, and brought to maturation in the United States. After World War II, the U.S. government helped to export it to Japan, where it was well received and promptly flourished. Despite the long history and well-documented benefits of such systems, few U.S. companies have invested effort in CIPs equivalent to that of their Japanese competitors. Japanese companies have put almost forty years into the development and refinement of CIPs, or kaizen programs as they are known in Japan, and have brought the art and science of managing them to new levels of sophistication. The aim of these programs is precisely to design and implement a system whose natural equilibrium is constant improvement and change. How can a company that does not have such a program compete with one that does? In this paper we give the historical background of CIPs, which we believe is essential for a useful understanding of these programs. We document their export across the Pacific immediately following World War II and illustrate their power as a competitive weapon when fully and properly deployed. We then identify and discuss requirements for successful implementation and suggest reasons why many U.S. firms find them difficult to start and maintain. We conclude by arguing that what is commonly perceived to be the “best practice” of CIP management is itself open to improvement. Throughout the article, we identify promising directions for companies to pursue so that all minds in the company, not just those of a few at the top, are actively solving problems, reducing costs, and eliminating waste.

When Knowledge is Power: Three Models of Change in International Organizations - Haas, Ernst B. (University of California Press, 1991)
Do governments seeking to collaborate in such international organizations as the United Nations and the World Bank ever learn to improve the performance of those organizations? Can international organizations be improved by a deliberate institutional design that reflects lessons learned in peacekeeping, the protection of human rights, and environmentally sound economic development? In this incisive work, Ernst Haas examines these and other issues to delineate the conditions under which organizations change their methods for defining problems. Haas contends that international organizations change most effectively when they are able to redefine the causes underlying the problems to be addressed. He shows that such self-reflection is possible when the expert-generated knowledge about the problems can be made to mesh with the interests of hegemonic coalitions of member governments. But usually efforts to change organizations begin as adaptive practices that owe little to a systematic questioning of past behavior. Often organizations adapt and survive without fully satisfying most of their members, as has been the case with the United Nations since 1970. When Knowledge Is Power is a wide-ranging work that will elicit interest from political scientists, organization theorists, bureaucrats, and students of management and international administration.

The machine that changed the World: the story of Lean Production - Womack, James P.; Jones, Daniel T.; Roos, Daniel (Simon & Schuster, 1990)

Learning and not learning from experience in rural project planning - Hulme, David (Public Administration and Development, 1989)
The theme of learning from experience as a means of improving the effectiveness of rural development projects and programmers has been common in recent years. Considerable effort has been put into refining, monitoring and evaluation systems to enhance organizational learning processes. However, an emphasis on normative approaches to evaluation and learning from experience has led to the neglect of research into the actual processes by which rural development agencies utilize experience. The case study presented here points to the shortcomings of such approaches and illustrates the partisan manner in which individuals and organizations treat the lessons of experience. Actively ‘not learning from experience’ is as much a part of organizational processes as learning from experience. This paper examines the implications of this finding and reviews alternative approaches to improving experiential learning in rural development activities. It is found that such a perspective does not generate the innocuous technical prescriptions characteristic of conventional approaches, but a number of useful directions for further research can be identified.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/pad.4230090102

The process approach to projects - ODA (Overseas Development Administration, 1989)

Toyota production system: beyond large-scale production - Ōno, Taiichi; Bodek, Norman (Productivity Press, 1988)
OCLC: 255047797
Keywords: Lean Production; Production management; Toyota-Jidōsha-Kōgyō-KK

A spiral model of software development and enhancement - Boehm, B. W. (Computer, 1988)

Strengthening Farmers’ Capacity for Technology Development - Haverkort, Bertus; Hiemstra, Wim; Reijntjes, Coen; Essers, Sander (ILEIA Newsletter, 1988)
First Reference to Participatory Technology Development

Design thinking - Rowe, Peter G. (The MIT Press, 1987)

The New New Product Development Game - Takeuchi, Hirotaka; Nonaka, Ikujiro (Harvard Business Review, 1986)
In today’s fast-paced, fiercely competitive world of commercial new product development, speed and flexibility are essential. Companies are increasingly realizing that the old, sequential approach to developing new products simply won’t get the job done. Instead, companies in Japan and the United States are using a holistic method—as in rugby, the ball gets passed within […]

Appropriate Technology Sourcebook - Darrow, Ken; Saxenian, Mike (Village Earth, 1986)
Keywords: IMPORTANT

Adaptive Management of Renewable Resources - Walters, C. J. (Macmillan Publishers Ltd, 1986)
The author challenges the traditional approach to dealing with uncertainty in the management of such renewable resources as fish and wildlife. He argues that scientific understanding will come from the experience of management as an ongoing, adaptive, and experimental process, rather than through basic research or the development of ecological theory. The opening chapters review approaches to formulating management objectives as well as models for understanding how policy choices affect the attainment of these objectives. Subsequent chapters present various statistical methods for understanding the dynamics of uncertainty in managed fish and wildlife populations and for seeking optimum harvest policies in the face of uncertainty. The book concludes with a look at prospects for adaptive management of complex systems, emphasizing such human factors involved in decision making as risk aversion and conflicting objectives as well as biophysical factors. Throughout the text dynamic models and Bayesian statistical theory are used as tools for understanding the behavior of managed systems. These tools are illustrated with simple graphs and plots of data from representative cases. This text/reference will serve researchers, graduate students, and resource managers who formulate harvest policies and study the dynamics of harvest populations, as well as analysts (modelers, statisticians, and stock assessment experts) who are concerned with the practice of policy design.

Evolutionary Delivery Versus the "Waterfall Model" - Gilb, Tom (SIGSOFT Softw. Eng. Notes, 1985)
The conventional wisdom of planning software engineering projects, using the widely cited "waterfall model" is not the only useful software development process model. In fact, the "waterfall model" may be unrealistic, and dangerous to the primary objectives of any software project.The alternative model, which I choose to call "evolutionary delivery" is not widely taught or practiced yet. But there is already more than a decade of practical experience in using it. In various forms. It is quite clear from these experiences that evolutionary delivery is a powerful general tool for both software development and associated systems development.Almost all experienced software developers do make use of some of the ideas in evolutionary development at one time or another. But, this is often unplanned, informal and it is an incomplete exploitation of this powerful method. This paper will try to expose the theoretical and practical aspects of the method in a fuller perspective. We need to learn the theory fully, so that we can apply and learn it completely.

Adaptive environmental assessment and management: a new approach to environmental impact assessment - Jones, Michael L.; Greig, Lorne A. (New directions in environmental impact assessment in Canada, 1985)

Review of Development Projects as Policy Experiments: An Adaptive Approach to Development Administration - Uphoff, Norman (Economic Geography, 1985)
Publisher: [Clark University, Wiley]

Knowledge-based Communication Processes in Software Engineering - Fischer, Gerhard; Schneider, Matthias (Proceedings of the 7th International Conference on Software Engineering, 1984)
A large number of problems to be solved with the help of computer systems are ill-structured. Their solution requires incremental design processes, because complete and stable specifications are net available. For tasks of this sort, life cycle models are inadequate. Our design methodology is based on a rapid prototyping approach which supports the coevolution of specification and implementation. Communication between customers, designers and implementors and communication between the humans and the knowledge base in which the emerging product is embedded are of crucial importance. Our work is centered around knowledge-based systems which enhance and support the communication needs in connection with software systems. Program documentation systems are used as an example to illustrate the relevance of knowledge-based human-computer communication in software engineering.
Keywords: Rapid prototyping; experimental programming environments; human-computer communication; incremental design; knowledge-based systems; program documentation; user interfaces

Experiential Learning: Experience as the Source of Learning and Development - Kolb, David A. (Prentice Hall, 1983)
Drawing from the intellectual origins of experiential learning in the works of John Dewey, Kurt Lewin, and Jean Piaget, this comprehensive and systematic book describes the process of experiential learning. The author proposes a model of the underlying structures of the learning process based on research in psychology, philosophy, and physiology, and bases its typology of individual learning styles and corresponding structures of knowledge in different academic disciplines and careers on this structural model. He also applies experiential learning to higher education and lifelong learning, particularly with regard to adult education.

Development Projects as Policy Experiments: An Adaptive Approach to Development Administration - Rondinelli, Dennis A. (Methuen, 1983)
International assistance programmes for developing countries are in urgent need of revision. Continuous testing and verification is required if development activity is to cope effectively with the uncertainty and complexity of the development process. This examines the alternatives and offers an approach which focuses on strategic planning, administrative procedures that facilitate innovation, responsiveness and experimentation, and on decision-making processes that join learning with action. A useful text for academics and practitioners in development studies, geography and sociology.

Community Organization and Rural Development: A Learning Process Approach - Korten, David C. (Public Administration Review, 1980)

Organizational Learning: A Theory of Action Perspective - Argyris, Chris; Schon, Donald A. (Addison Wesley, 1978)

Adaptive environmental assessment and management - Holling, C. S. (Wiley, 1978)
Keywords: Ecology; Economic development; Environmental impact analysis; Environmental protection

Inside Foreign Aid - Tendler, Judith (The Johns Hopkins University Press, 1975)
A classic, important study in the anthropology of development, grounded in the author's own work within USAID, and analysis of the organizational and institutional pressures that constrain and shape development agency employees' cognition and action.
Keywords: IMPORTANT

The Logical Categories of Learning and Communication - Bateson, Gregory (Steps to an Ecology of Mind, 1973)

Small is beautiful: economics as if people mattered - Schumacher, Ernst Friedrich (Blond & Briggs, 1973)

Managing the development of large software systems - Royce, Winston (Proceedings of IEEE WesCon, 1970)

The principle of the hiding hand - Hirschman, Albert O. (National Observer, 1967)

Requisite Variety and Its Implications for the Control of Complex Systems - Ashby, W. Ross (Cybernetica, 1958)

Science and Civilisation in China. Vol. 1 Introductory Orientations - Needham, Joseph (Cambridge University Press, 1956)
Dr Joseph Needham's account of the Chinese achievement in science and technology will stand as one of the great works of our time. It has been acclaimed by specialists in both East and West and also by readers with wider and more general interests. The text, based on research of a high critical quality, is supported by many hundreds of illustrations and is imbued with a warm appreciation of China. Volume I is an introductory volume, in which Dr Needham prepares his readers for the study of a whole human culture. He begins by examining the structure of the Chinese language; he reviews the geography of China and the long history of its people, and discusses the scientific contacts which have occurred throughout the centuries, between Europe and East Asia.

Field Theory in Social Science: Selected Theoretical Papers - Lewin, Kurt (Harper & Brothers, 1951)

Science and Complexity - Weaver, Warren (American Scientist, 1948)
Publisher: Sigma Xi, The Scientific Research Society

Two Loops – Excerpted from - Stilger, Bob